Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2019)
AIM: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. METHODS: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self-reported pain was at least six on a scale from 0-10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. RESULTS: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9-14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0-4.3) and tramadol 3.0 (IQR 1.0-5.0) vs paracetamol 3.0 (IQR 0.8-5.0). The median pain reductions were all 5.0 points. CONCLUSION: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.

Adolescent with painful vesicular otitis and vertigo. - Conversano, Ester; Cozzi, Giorgio; Poropat, Federico; Di Mascio, Alberto; Salis, Simona; Grasso, Domenico Leonardo; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2019)

Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

Evidence-based mixture containing Lactobacillus strains and lactoferrin to prevent recurrent bacterial vaginosis: a double blind, placebo controlled, randomised clinical trial. - Russo, R; Karadja, E; De Seta, F (Benef Microbes, 2019)
Bacterial vaginosis (BV) is the most common cause of vaginal discomfort in women. It is characterised by abnormal vaginal microbiota with a depletion of lactobacilli and predominance of anaerobic microorganisms, mainly Gardnerella vaginalis and Atopobium vaginae. Although antibiotics represent an effective therapeutic option in the short-term, recurrent infections still remain a serious problem. Nowadays, evidence exists about the efficacy of probiotics for the management of BV. The aim of the current double blind, randomised clinical trial was to assess the efficacy of a probiotic mixture, including Lactobacillus acidophilus GLA-14 and Lactobacillus rhamnosus HN001, in combination with bovine lactoferrin, as adjuvant therapy to metronidazole in women with recurrent BV. In particular, normalisation of Nugent score, remission of symptoms and recurrences during a six-months follow-up were assessed. 48 adult women received metronidazole (500 mg twice daily) for 7 days and randomly assigned to take simultaneously either probiotics plus lactoferrin or placebo (2 capsules/day for 5 days followed by 1 capsule/day for 10 consecutive days; induction phase). The verum or placebo administration (1 capsule/day for 10 consecutive days) was repeated each month (maintenance phase) during the six months of follow-up starting the first day of menstrual cycle since the menstrual blood increases the vaginal pH and contributes to increase the risk of recurrences. The results showed that symptoms (vaginal discharge and itching), Nugent score and recurrence rate were significantly improved by probiotics mixture in association with lactoferrin. This alternative approach may represent a safe and effective remedy for the restoration of healthy vaginal microbiota in preventing recurrent BV.

Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

When Long-Lasting Food Selectivity Leads to an Unusual Genetic Diagnosis: A Case Report. - Da Lozzo, Prisca; Magnolato, Andrea; Del Rizzo, Irene; Sirchia, Fabio; Bruno, Irene; Barbi, Egidio (J Adolesc Health, 2019)
Hereditary fructose intolerance is an autosomal recessive disorder of fructose metabolism caused by catalytic deficiency of aldolase B enzyme [1]. The disease is typically expressed when fructose- and sucrose-containing foods are first introduced in the diet; acute manifestations include nausea, vomiting, abdominal distress, and symptomatic hypoglycemia [1,2]. Chronic fructose ingestion eventually leads to poor feeding, growth retardation and gradual liver and/or renal failure [3,4]. Some patients may remain undiagnosed until adulthood because of a self-protective avoidance of sweet tasting food that prevents the development of acute toxicity from fructose containing food; however, these subjects may suffer intermittent symptoms throughout life, leading to potentially serious misdiagnosis [4]. We report the case of a patient with unrecognized hereditary fructose intolerance in which chronic gastrointestinal complaints, low body weight, and unexplained food avoidance were addressed as manifestations of an eating disorder during adolescence.

Antibody response to polyomavirus primary infection: high seroprevalence of Merkel cell polyomavirus and lymphoid tissue involvement. - Cason, Carolina; Monasta, Lorenzo; Zanotta, Nunzia; Campisciano, Giuseppina; Maestri, Iva; Tommasino, Massimo; Pawlita, Michael; Villani, Sonia; Comar, Manola; Delbue, Serena (J Neurovirol, 2018)
Human polyomaviruses (HPyVs) asymptomatically infect the human population establishing latency in the host, and their seroprevalence can reach 90% in healthy adults. Few studies have focused on the pediatric population, and there are no reports regarding the seroprevalence of all the newly isolated HPyVs among Italian children. Therefore, we investigated the frequency of serum antibodies against 12 PyVs in 182 immunocompetent children from Northeast Italy, by means of a multiplex antibody detection system. Additionally, secondary lymphoid tissues were collected to analyze the presence of HPyV DNA sequences using a specific real-time PCRs or PCRs. Almost 100% of subjects were seropositive for at least one PyV. Seropositivity ranged from 3% for antibodies against simian virus 40 (SV40) in children from 0 to 3 years, to 91% for antibodies against WU polyomavirus (WUPyV) and HPyV10 in children from 8 to 17 years. The mean number of PyV for which children were seropositive increased with the increasing of age: 4 standard deviations (SD) 1.8 in the 0-3-year group, 5 (SD 1.9) in the 4-7-year group, and 6 (SD 2.2) in the 8-17-year group. JC polyomavirus (JCPyV) DNA was detected in 1% of the adenoids, WUPyV in 12% of the tonsils, and 28% of the adenoids, and Merkel cell polyomavirus (MCPyV) was present in 6 and 2% of the tonsils and adenoids, respectively. Our study gives new insights on the serological evidence of exposure to PyVs during childhood, and on their possible respiratory route of transmission.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Are aortic coarctation and rheumatoid arthritis different models of aortic stiffness? Data from an echocardiographic study. - Faganello, Giorgio; Cioffi, Giovanni; Rossini, Maurizio; Ognibeni, Federica; Giollo, Alessandro; Fisicaro, Maurizio; Russo, Giulia; Di Nora, Concetta; Doimo, Sara; Tarantini, Luigi; Mazzone, Carmine; Cherubini, Antonella; et al. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Patients who underwent a successful repair of the aortic coarctation (CoA) show high risk for cardiovascular (CV) events. Mechanical and structural abnormalities in the ascending aorta (Ao) might have a role in the prognosis of CoA patients. We analyzed the elastic properties of Ao measured as aortic stiffness index (AoSI) in CoA patients in the long-term period and we compared AoSI with a cohort of 38 patients with rheumatoid arthritis (RA) and 38 non-RA matched controls. METHODS: Data from 19 CoA patients were analyzed 28 ± 13 years after surgery. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation. RESULTS: CoA patients showed more than two-fold higher AoSI compared to RA and controls (9.8 ± 12.6 vs 4.8 ± 2.5% and 3.1 ± 2.0%, respectively; all p < 0.05 and in 5 of 19 patients with CoA (26%) AoSI was exceptionally high. The 5 patients with abnormally high AoSI were older with higher BP, LV mass and prevalence of LV diastolic dysfunction. Multiple linear regression analysis revealed that AoSI was independently related to the presence of LV hypertrophy and higher LV relative wall thickness. CONCLUSIONS: CoA patients have higher AoSI levels than RA patients and non-RA matched controls. AoSI levels are abnormally high in a small sub-group of CoA patients who show a very high-risk clinical profile for adverse CV events.
Keywords: Aorta; Aortic Coarctation; Arthritis, Rheumatoid; Humans; Prognosis; Vascular Stiffness

Bariatric surgery drives major rearrangements of the intestinal microbiota including the biofilm composition. - Campisciano, Giuseppina; Cason, Carolina; Palmisano, Silvia; Giuricin, Michela; Rizzardi, Alessia; Croce, Lory Saveria; De Manzini, Nicolo; Comar, Manola (Front Biosci (Elite Ed), 2018)
The intestinal microbiota disequilibrium has been associated with obesity, while the role of the gut mucosal biofilms in this pathology is still unknown. We analysed the changes in the intestinal microbiota of obese patients after bariatric surgery with the aim of disclosing the rearrangement of the biofilm configuration. Although the bariatric surgery drives major rearrangements of the gut microbiota, obese patients maintain the enterotype before and after surgery, as shown by normal weight patients, with an increase of and . The enterotype guarantees the strong ability to form a biofilm which allows a more efficient digestion of polysaccharides than planktonic communities and leads to the production of acetate which is a key player to inhibit enteropathogens. Additionally, the laparoscopic gastric bypass induces an increase of , a facultative anaerobic bacterium involved in intestinal and inflammatory disorders. Bariatric surgery influences the microbial composition of gut biofilm. Further studies are needed to elucidate the impact of this variation on recovery after surgery and on weight loss.
Keywords: Biofilms; Case-Control Studies; Gastric Bypass; Gastrointestinal Microbiome; Humans; Intestinal Mucosa; Obesity; Prospective Studies

Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells. - Bellazzo, Arianna; Di Minin, Giulio; Valentino, Elena; Sicari, Daria; Torre, Denis; Marchionni, Luigi; Serpi, Federica; Stadler, Michael B; Taverna, Daniela; Zuccolotto, Gaia; Montagner, Isabella Monia; Rosato, Antonio; et al. (Cell Death Differ, 2018)
The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP. By efficiently downregulating DAB2IP, this miRNA enhances cancer cell motility and invasiveness, facilitating activation of NF-kB signaling and promoting expression of pro-inflammatory and pro-angiogenic factors. In addition, we found that miR-149-3p secreted by prostate cancer cells induces DAB2IP downregulation in recipient vascular endothelial cells, stimulating their proliferation and motility, thus potentially remodeling the tumor microenvironment. Finally, we found that inhibition of endogenous miR-149-3p restores DAB2IP activity and efficiently reduces tumor growth and dissemination of malignant cells. These observations suggest that miR-149-3p can promote cancer progression via coordinated inhibition of DAB2IP in tumor cells and in stromal cells.

Characterization of multi-locus imprinting disturbances and underlying genetic defects in patients with chromosome 11p15.5 related imprinting disorders. - Fontana, L; Bedeschi, M F; Maitz, S; Cereda, A; Faré, C; Motta, S; Seresini, A; D'Ursi, P; Orro, A; Pecile, V; Calvello, M; Selicorni, A; et al. (Epigenetics, 2018)
The identification of multilocus imprinting disturbances (MLID) appears fundamental to uncover molecular pathways underlying imprinting disorders (IDs) and to complete clinical diagnosis of patients. However, MLID genetic associated mechanisms remain largely unknown. To characterize MLID in Beckwith-Wiedemann (BWS) and Silver-Russell (SRS) syndromes, we profiled by MassARRAY the methylation of 12 imprinted differentially methylated regions (iDMRs) in 21 BWS and 7 SRS patients with chromosome 11p15.5 epimutations. MLID was identified in 50% of BWS and 29% of SRS patients as a maternal hypomethylation syndrome. By next-generation sequencing, we searched for putative MLID-causative mutations in genes involved in methylation establishment/maintenance and found two novel missense mutations possibly causative of MLID: one in NLRP2, affecting ADP binding and protein activity, and one in ZFP42, likely leading to loss of DNA binding specificity. Both variants were paternally inherited. In silico protein modelling allowed to define the functional effect of these mutations. We found that MLID is very frequent in BWS/SRS. In addition, since MLID-BWS patients in our cohort show a peculiar pattern of BWS-associated clinical signs, MLID test could be important for a comprehensive clinical assessment. Finally, we highlighted the possible involvement of ZFP42 variants in MLID development and confirmed NLRP2 as causative locus in BWS-MLID.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Beckwith-Wiedemann Syndrome; Child; Child, Preschool; Chromosomes, Human, Pair 15; DNA Methylation; Female; Genomic Imprinting; Humans; Infant; Kruppel-Like Transcription Factors; Male; Mutation, Missense; Silver-Russell Syndrome; Young Adult

A Child with Diminished Linear Growth and Waddling Gait. - Tamaro, Gianluca; Pederiva, Federica; Dibello, Daniela; Gregori, Massimo; Carbone, Marco; Pantaleoni, Francesca; Dentici, Maria Lisa; Niceta, Marcello; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abnormalities, Multiple; Child; Dwarfism; Female; Gait; Humans; Osteochondrodysplasias; Radiography

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Endocrine and psychological aspects of sexual dysfunction in Klinefelter patients. - Ferlin, A; Selice, R; Angelini, S; Di Grazia, M; Caretta, N; Cavalieri, F; Di Mambro, A; Foresta, C (Andrology, 2018)
Klinefelter syndrome is a frequent cause of hypogonadism, but despite hundreds of publications on different aspects of Klinefelter syndrome, only a few studies dealt with sexual dysfunction. In particular, testosterone is critical for various aspects of sexual response, but its role on sexuality in Klinefelter syndrome patients is debatable and no studies have evaluated the efficacy of testosterone treatment on sexual dysfunction in these subjects. Furthermore, the impact of psychological and relational aspects on sexual function of Klinefelter syndrome subjects is poorly defined. In this study, we aimed to determine the presence and type of sexual dysfunctions in Klinefelter syndrome subjects; to correlate them with testosterone levels and psychosexological and relational domains; and to evaluate the effects of testosterone therapy. We studied 62 non-mosaic naïve Klinefelter syndrome patients and 60 age-matched controls by means of medical history, psychosexological history, 15-item International Index of Erectile Function questionnaire, endocrine assessment, and dynamic penile color Doppler ultrasound. Twenty-five hypogonadal Klinefelter syndrome patients were studied after 6 months of testosterone replacement therapy. Klinefelter syndrome subjects have reduced 15-item International Index of Erectile Function scores regarding sexual desire, intercourse satisfaction, and overall satisfaction with respect to controls, and these aspects were significantly associated with testosterone levels. Klinefelter syndrome subjects had also higher prevalence of erectile dysfunction, but no relation with testosterone levels was evident. A high prevalence of a range of psychological disturbances was present in Klinefelter syndrome subjects with erectile dysfunction with respect to those without erectile dysfunction. No statistical difference in the prevalence of premature and delayed ejaculation was observed between Klinefelter syndrome and control subjects. Testosterone replacement therapy improved sexual desire, intercourse satisfaction, and overall satisfaction scores, but had no effect on erectile function. Penile color Doppler ultrasound was normal in all subjects. This study shows that sexual dysfunction in Klinefelter syndrome is multifactorial and related only in part to hypogonadism and largely to psychological disturbances. Evaluation and therapy of sexual dysfunction should include a combined andrological and psychosexological approach.

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population. - Bevilacqua, Lorenzo; Navarra, Chiara O; Pirastu, Nicola; Lenarda, Roberto Di; Gasparini, Paolo; Robino, Antonietta (J Periodontal Res, 2018)
BACKGROUND AND OBJECTIVE: Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. METHODS: Diagnosis of chronic periodontitis was made following the criteria of the American Academy of Periodontology. Patients with chronic periodontitis were grouped into different categories: slight, severe, localized and generalized. A control group composed by people without signs of periodontitis or gingivitis was defined. DNA was genotyped using 370k Illumina chips. Linear mixed model regression was used to test the association between each single nucleotide polymorphism (SNP) (independent variable) and the periodontitis status (dependent variable), controlling for confounders sex, age and smoking. The genomic kinship matrix was also used as random effect. RESULTS: Four SNPs on the gene EFCAB4B resulted significantly associated to localized periodontitis (P < 5 × 10 ), with the best hit on the rs242016 SNP (P = 1.5 × 10 ). CONCLUSION: We have identified a novel significant association between the EFCAB4B gene and localized periodontitis. These results open a new perspective in the understanding of genetic factors contributing to this common disorder.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium-Binding Proteins; Chronic Periodontitis; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Young Adult

Gut microbiota characterisation in obese patients before and after bariatric surgery. - Campisciano, G; Palmisano, S; Cason, C; Giuricin, M; Silvestri, M; Guerra, M; Macor, D; De Manzini, N; Crocé, L S; Comar, M (Benef Microbes, 2018)
Intestinal microbiota analysis of obese patients after bariatric surgery showed that Proteobacteria decreased after laparoscopic sleeve gastrectomy (SG), while it increased after laparoscopic gastric bypass (LGB). Comparing to normal weight (NW) patients, obese patients that were selected for SG showed an almost equal amount of Firmicutes and Bacteroidetes and the ratio was not affected by the surgery. Obese patients before LGB showed a predominance of Bacteroidetes, whose amount regained a relative abundance similar to NW patients after surgery. Obese patients before LGB showed the predominance of Bacteroides, which decreased after surgery in favour of Prevotella, a bacterium associated with a healthy diet. The bacteria detected at the highest percentages belonged to biofilm forming species. In conclusion, in this study, we found that the characterization of the gut microbial communities and the modality of mucosal colonisation have a central role as markers for the clinical management of obesity and promote the maintenance of good health and the weight loss.
Keywords: Adult; Bariatric Surgery; Gastrointestinal Microbiome; Humans; Laparoscopy; Microbiota; Middle Aged; Obesity; Young Adult

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

How to predict response to anti-tumour necrosis factor agents in inflammatory bowel disease. - Naviglio, Samuele; Giuffrida, Paolo; Stocco, Gabriele; Lenti, Marco Vincenzo; Ventura, Alessandro; Corazza, Gino Roberto; Di Sabatino, Antonio (Expert Rev Gastroenterol Hepatol, 2018)
INTRODUCTION: Anti-tumor necrosis factor (TNF) agents have changed the therapeutic approach to inflammatory bowel disease (IBD). However, a considerable proportion of patients either do not primarily respond or lose response to treatment. Despite the long-standing experience in the use of these drugs, still there is the need of identifying the possible predictors of efficacy. Areas covered: We critically review the current knowledge on predictors of response to anti-TNF therapy - both those available in clinical practice and those still under investigation. Multiple factors are involved in treatment success, including disease phenotype and severity, adherence to medications, and pharmacogenomic, pharmacokinetic, and immunologic factors. Literature search was conducted in PubMed using keywords 'inflammatory bowel disease,' 'Crohn's disease,' and 'ulcerative colitis,' matched with 'antitumor necrosis factor,' 'biologic therapy,' 'clinical response,' 'predictors,' and 'efficacy,' Relevant articles were selected for review. Expert commentary: While the role of several factors in clinical practice is clearly established, other investigational markers have been proposed, mostly in small studies, yet for many of them little external validation exists. Therapeutic drug monitoring is emerging as a pivotal strategy to guide decisions in clinical practice. In the near future, novel markers could improve our ability to direct treatment and personalize therapy.
Keywords: Antibodies, Monoclonal; Biological Therapy; Gastrointestinal Agents; Humans; Inflammatory Bowel Diseases; Patient Selection; Prognosis; Treatment Outcome; Tumor Necrosis Factor-alpha

Hypomorphic FANCA mutations correlate with mild mitochondrial and clinical phenotype in Fanconi anemia. - Bottega, Roberta; Nicchia, Elena; Cappelli, Enrico; Ravera, Silvia; De Rocco, Daniela; Faleschini, Michela; Corsolini, Fabio; Pierri, Filomena; Calvillo, Michaela; Russo, Giovanna; Casazza, Gabriella; Ramenghi, Ugo; et al. (Haematologica, 2018)
Fanconi anemia is a rare disease characterized by congenital malformations, aplastic anemia, and predisposition to cancer. Despite the consolidated role of the Fanconi anemia proteins in DNA repair, their involvement in mitochondrial function is emerging. The purpose of this work was to assess whether the mitochondrial phenotype, independent of genomic integrity, could correlate with patient phenotype. We evaluated mitochondrial and clinical features of 11 affected individuals homozygous or compound heterozygous for p.His913Pro and p.Arg951Gln/Trp, the two residues of FANCA that are more frequently affected in our cohort of patients. Although p.His913Pro and p.Arg951Gln proteins are stably expressed in cytoplasm, they are unable to migrate in the nucleus, preventing cells from repairing DNA. In these cells, the electron transfer between respiring complex I-III is reduced and the ATP/AMP ratio is impaired with defective ATP production and AMP accumulation. These activities are intermediate between those observed in wild-type and FANCA-/- cells, suggesting that the variants at residues His913 and Arg951 are hypomorphic mutations. Consistent with these findings, the clinical phenotype of most of the patients carrying these mutations is mild. These data further support the recent finding that the Fanconi anemia proteins play a role in mitochondria, and open up possibilities for genotype/phenotype studies based on novel mitochondrial criteria.

Imaging and therapy of ovarian cancer: clinical application of nanoparticles and future perspectives. - Di Lorenzo, Giovanni; Ricci, Giuseppe; Severini, Giovanni Maria; Romano, Federico; Biffi, Stefania (Theranostics, 2018)
Despite significant advances in cancer diagnostics and treatment, ovarian cancers (OC) continue to kill more than 150,000 women every year worldwide. Due to the relatively asymptomatic nature and the advanced stage of the disease at the time of diagnosis, OC is the most lethal gynecologic malignancy. The current treatment for advanced OC relies on the synergistic effect of combining surgical cytoreduction and chemotherapy; however, beside the fact that chemotherapy resistance is a major challenge in OC management, new imaging strategies are needed to target microscopic lesions and improve both cytoreductive surgery and patient outcomes. In this context, nanostructured probes are emerging as a new class of medical tool that can simultaneously provide imaging contrast, target tumor cells, and carry a wide range of medicines resulting in better diagnosis and therapeutic precision. Herein we summarize several exemplary efforts in nanomedicine for addressing unmet clinical needs.

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

In vivo microbiome and associated immune markers: New insights into the pathogenesis of vaginal dysbiosis. - Campisciano, Giuseppina; Zanotta, Nunzia; Licastro, Danilo; De Seta, Francesco; Comar, Manola (Sci Rep, 2018)
The microbiota fulfils a key role in the training and function of the immune system, which contributes to the symbiosis between the host and complex microbial communities. In this study, we characterized the interplay between vaginal bacteria and local immune mediators during dysbiosis in selected women of reproductive age who were grouped according to Nugent's criteria. The abundance of Gardnerella vaginalis and Bifidobacterium breve was increased in the intermediate dysbiotic status, while the presence of a plethora of non-resident bacteria characterized the group with overt vaginosis. In response to these increases, the anti-inflammatory IL1ra and pro-inflammatory IL2 increased, while the embryo trophic factors FGFβ and GMCSF decreased compared to the healthy milieu. A specific pattern, including IL1α, IL1β, IL8, MIG, MIP1α and RANTES, distinguished the intermediate group from the vaginosis group, while IL5 and IL13, which are secreted by Th2 cells, were significantly associated with the perturbation of the commensals Lactobacilli, Gardnerella and Ureaplasma. Summarizing, we postulate that although the dysbiotic condition triggers a pro-inflammatory process, the presence of a steady state level of Th2 may influence clinical manifestations. These results raise clinically relevant questions regarding the use of vaginal immunological markers as efficacious tools to monitor microbial alterations.
Keywords: Adult; Biomarkers; Cytokines; Dysbiosis; Female; Humans; Microbiota; Th2 Cells; Vagina

Infant Analgesia With a Combination of Breast Milk, Glucose, or Maternal Holding. - Bembich, Stefano; Cont, Gabriele; Causin, Enrica; Paviotti, Giulia; Marzari, Patrizia; Demarini, Sergio (Pediatrics, 2018)
OBJECTIVES: We studied neonatal cortical brain response to 4 types of nonpharmacological analgesia (oral glucose, expressed breast milk, maternal holding plus oral glucose, breastfeeding). We aimed to assess the differential effect of oral solutions (glucose, breast milk) given alone or combined with the maternal-infant relationship (holding, breastfeeding). METHODS: Eighty healthy term newborns undergoing a heel stick were randomly assigned to 4 parallel groups of 20 infants each: group 1, infants received a glucose solution on a changing table; group 2, infants received expressed breast milk on a changing table; group 3, infants received a glucose solution in their mothers' arms; and group 4, infants were breastfed by their mothers. Cortical activation in parietal, temporal, and frontal cortices was assessed by multichannel near-infrared spectroscopy. Pain expression was also evaluated. RESULTS: Oral glucose alone or combined with maternal holding was associated with no cortical activation during heel stick. Expressed breast milk was associated with localized bilateral activation of somatosensory and motor cortices ( < .01). Breastfeeding was associated with extensive bilateral activation of somatomotor, somatosensory, and right parietal cortices ( < .01). Pain expression was lower with the maternal-infant relationship ( = .007). CONCLUSIONS: Oral glucose, either alone or combined with maternal holding, appears to block or weaken cortical pain processing. Breast milk alone is associated with localized cortical activation. Breastfeeding is associated with extensive activation and may act by extending cortical processing. Maternal relationship, both combined with oral glucose and in breastfeeding, shows the greatest analgesic effect, although the neural patterns involved are distributed differently.

Interstitial Fluid in Gynecologic Tumors and Its Possible Application in the Clinical Practice. - Ura, Blendi; Di Lorenzo, Giovanni; Romano, Federico; Monasta, Lorenzo; Mirenda, Giuseppe; Scrimin, Federica; Ricci, Giuseppe (Int J Mol Sci, 2018)
Gynecologic cancers are an important cause of worldwide mortality. The interstitium consists of solid and fluid phases, situated between the blood vessels and cells. The interstitial fluid (IF), or fluid phase, is an extracellular fluid bathing and surrounding the tissue cells. The TIF (tumor interstitial fluid) is a dynamic fluid rich in lipids, proteins and enzyme-derived substances. The molecules found in the IF may be associated with pathological changes in tissues leading to cancer growth and metastatization. Proteomic techniques have allowed an extensive study of the composition of the TIF as a source of biomarkers for gynecologic cancers. In our review, we analyze the composition of the TIF, its formation process, the sampling methods, the consequences of its accumulation and the proteomic analyses performed, that make TIF valuable for monitoring different types of cancers.
Keywords: Biomarkers, Tumor; Biophysical Phenomena; Extracellular Fluid; Female; Genital Neoplasms, Female; Humans; Practice Patterns, Physicians'; Tumor Microenvironment

Intranasal dexmedetomidine, as midazolam-sparing drug, for MRI in preterm neonates. - Bua, Jenny; Massaro, Marta; Cossovel, Francesca; Monasta, Lorenzo; Brovedani, Pierpaolo; Cozzi, Giorgio; Barbi, Egidio; Demarini, Sergio; Travan, Laura (Paediatr Anaesth, 2018)

Iron-related toxicity of single-walled carbon nanotubes and crocidolite fibres in human mesothelial cells investigated by Synchrotron XRF microscopy. - Cammisuli, Francesca; Giordani, Silvia; Gianoncelli, Alessandra; Rizzardi, Clara; Radillo, Lucia; Zweyer, Marina; Da Ros, Tatiana; Salomè, Murielle; Melato, Mauro; Pascolo, Lorella (Sci Rep, 2018)
Carbon nanotubes (CNTs) are promising products in industry and medicine, but there are several human health concerns since their fibrous structure resembles asbestos. The presence of transition metals, mainly iron, in the fibres seems also implicated in the pathogenetic mechanisms. To unravel the role of iron at mesothelial level, we compared the chemical changes induced in MeT-5A cells by the exposure to asbestos (crocidolite) or CNTs at different content of iron impurities (raw-SWCNTs, purified- and highly purified-SWCNTs). We applied synchrotron-based X-Ray Fluorescence (XRF) microscopy and soft X-ray imaging (absorption and phase contrast images) to monitor chemical and morphological changes of the exposed cells. In parallel, we performed a ferritin assay. X-ray microscopy imaging and XRF well localize the crocidolite fibres interacting with cells, as well as the damage-related morphological changes. Differently, CNTs presence could be only partially evinced by low energy XRF through carbon distribution and sometimes iron co-localisation. Compared to controls, the cells treated with raw-SWCNTs and crocidolite fibres showed a severe alteration of iron distribution and content, with concomitant stimulation of ferritin production. Interestingly, highly purified nanotubes did not altered iron metabolism. The data provide new insights for possible CNTs effects at mesothelial/pleural level in humans.
Keywords: Asbestos, Crocidolite; Cell Line; Epithelial Cells; Humans; Iron; Microscopy, Fluorescence; Nanotubes, Carbon

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

MKRN3 levels in girls with central precocious puberty and correlation with sexual hormone levels: a pilot study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Capristo, Carlo; Tornese, Gianluca; Marzuillo, Pierluigi; Luongo, Caterina; Rosaria Umano, Giuseppina; Festa, Adalgisa; Coppola, Ruggero; Miraglia Del Giudice, Emanuele; Perrone, Laura (Endocrine, 2018)
PURPOSE: Recently, mutations of makorin RING-finger protein 3 (MKRN3) have been described in familial central precocious puberty. Serum levels of this protein decline before the pubertal onset in healthy girls and boys. The aim of the study is to investigate MKRN3 circulating levels in patients with central precocious puberty. METHODS: We performed an observational cross-sectional study. We enrolled 17 patients with central precocious puberty aged 7 years (range: 2-8 years) and breast development onset <8 years; 17 prepubertal control age-matched patients aged 6.3 years (2-8.2); and 10 pubertal stage-matched control patients aged 11.4 years (9-14). Serum values of MKRN3, gonadotropins, (17)estradiol and Anti-Müllerian Hormone were evaluated and the MKRN3 genotyped in central precocious puberty patients. RESULTS: No MKRN3 mutation was found among central precocious puberty patients. MKRN3 levels were lower in patients with central precocious puberty compared to prepubertal age-matched ones (p: 0.0004) and comparable to those matched for pubertal stage. MKRN3 levels were inversely correlated to Body Mass Index Standard Deviations (r:-0.35; p:0.02), Luteinizing Hormone (r:-0.35; p:0.03), FSH (r:-0.37; p:0.02), and (17)estradiol (r: -0.36; p:0.02). CONCLUSIONS: We showed that girls with central precocious puberty had lower peripheral levels of MKRN3 compared to age-matched pairs and that they negatively correlated to gonadotropins, estrogen, and BMI. Our findings support the MKRN3 involvement in central precocious puberty also in absence of deleterious mutations, although our sample size is small. In addition our data suggest the role of MKRN3 in the complex mechanism controlling puberty onset and its interaction with other factors affecting puberty such as nutrition.
Keywords: Adolescent; Adolescent Nutritional Physiological Phenomena; Anti-Mullerian Hormone; Case-Control Studies; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Cross-Sectional Studies; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Pilot Projects; Puberty, Precocious; Ribonucleoproteins; Sexual Maturation

MKRN3 Levels in Girls with Central Precocious Puberty during GnRHa Treatment: A Longitudinal Study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Tornese, Gianluca; Luongo, Caterina; Festa, Adalgisa; Marzuillo, Pierluigi; Miraglia Del Giudice, Emanuele (Horm Res Paediatr, 2018)
BACKGROUND: Recently, mutations of makorin RING finger protein 3 (MKRN3) have been identified in familial central precocious puberty (CPP). Serum levels of this protein decline before the pubertal onset in healthy girls and boys and are lower in patients with CPP compared to prepubertal matched pairs. The aim of our study was to investigate longitudinal changes in circulating MKRN3 levels in patients with CPP before and during GnRH analogs (GnRHa) treatment. METHODS: We performed a longitudinal prospective study. We enrolled 15 patients with CPP aged 7.2 years (range: 2-8) with age at breast development onset < 8 years and 12 control girls matched for the time from puberty onset (mean age 11.8 ± 1.2 years). Serum values of MKRN3, gonadotropins, and 17β-estradiol were evaluated before and during treatment with GnRHa (at 6 and 12 months). The MKRN3 gene was genotyped in CPP patients. In the girls from the control group, only basal levels were analyzed. RESULTS: No MKRN3 mutations were found among CPP patients. MKRN3 levels declined significantly from baseline to 6 months of GnRHa treatment (p = 0.0007) and from 6 to 12 months of treatment (p = 0.003); MKRN3 levels at 6 months were significantly lower than in the control girls (p < 0.0001). CONCLUSIONS: We showed that girls with CPP had a decline in peripheral levels of MKRN3 during GnRHa treatment. Our data suggest a suppression of MKRN3 by continuous pharmacological administration of GnRHa.
Keywords: Brain Diseases; Case-Control Studies; Child; Child, Preschool; Female; Follicle Stimulating Hormone; Genotype; Gonadotropin-Releasing Hormone; Humans; Longitudinal Studies; Luteinizing Hormone; Male; Puberty, Precocious; Ribonucleoproteins

Multicenter randomized, double-blind controlled trial to evaluate the efficacy of laser therapy for the treatment of severe oral mucositis induced by chemotherapy in children: laMPO RCT. - Gobbo, Margherita; Verzegnassi, Federico; Ronfani, Luca; Zanon, Davide; Melchionda, Fraia; Bagattoni, Simone; Majorana, Alessandra; Bardellini, Elena; Mura, Rosamaria; Piras, Alessandra; Petris, Maria Grazia; Mariuzzi, Maria Livia; et al. (Pediatr Blood Cancer, 2018)
OBJECTIVES: To demonstrate the efficacy of laser photobiomodulation (PBM) compared to that of placebo on severe oral mucositis (OM) in pediatric oncology patients. The primary objective was the reduction of OM grade (World Health Organization [WHO] scale) 7 days after starting PBM. Secondary objectives were reduction of pain, analgesic consumption, and incidence of side effects. METHODS: One hundred and one children with WHO grade > 2 chemotherapy-induced OM were enrolled in eight Italian hospitals. Patients were randomized to either PBM or sham treatment for four consecutive days (days +1 to +4). On days +4, +7, and +11, OM grade, pain (following a 0-10 numeric pain rating scale, NRS) and need for analgesics were evaluated by an operator blinded to treatment. RESULTS: Fifty-one patients were allocated to the PBM group, and 50 were allocated to the sham group. In total, 93.7% of PBM patients and 72% of sham patients had OM grade < 3 WHO on day +7 (P = 0.01). A significant reduction of pain was registered on day +7 in the PBM versus sham group (NRS 1 [0-3] vs. 2.5 [1-5], P < 0.006). Reduced use of analgesics was reported in the PBM group, although it was not statistically significant. No significant adverse events attributable to treatment were recorded. CONCLUSIONS: PBM is a safe, feasible, and effective treatment for children affected by chemotherapy-induced OM, as it accelerates mucosal recovery and reduces pain.

A new form of inherited thrombocytopenia due to monoallelic loss of function mutation in the thrombopoietin gene. - Noris, Patrizia; Marconi, Caterina; De Rocco, Daniela; Melazzini, Federica; Pippucci, Tommaso; Loffredo, Giuseppe; Giangregorio, Tania; Pecci, Alessandro; Seri, Marco; Savoia, Anna (Br J Haematol, 2018)

Non-invasive biomarkers of fetal brain development reflecting prenatal stress: An integrative multi-scale multi-species perspective on data collection and analysis. - Frasch, Martin G; Lobmaier, Silvia M; Stampalija, Tamara; Desplats, Paula; Pallarés, María Eugenia; Pastor, Verónica; Brocco, Marcela A; Wu, Hau-Tieng; Schulkin, Jay; Herry, Christophe L; Seely, Andrew J E; Metz, Gerlinde A S; et al. (Neurosci Biobehav Rev, 2018)
Prenatal stress (PS) impacts early postnatal behavioural and cognitive development. This process of 'fetal programming' is mediated by the effects of the prenatal experience on the developing hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). We derive a multi-scale multi-species approach to devising preclinical and clinical studies to identify early non-invasively available pre- and postnatal biomarkers of PS. The multiple scales include brain epigenome, metabolome, microbiome and the ANS activity gauged via an array of advanced non-invasively obtainable properties of fetal heart rate fluctuations. The proposed framework has the potential to reveal mechanistic links between maternal stress during pregnancy and changes across these physiological scales. Such biomarkers may hence be useful as early and non-invasive predictors of neurodevelopmental trajectories influenced by the PS as well as follow-up indicators of success of therapeutic interventions to correct such altered neurodevelopmental trajectories. PS studies must be conducted on multiple scales derived from concerted observations in multiple animal models and human cohorts performed in an interactive and iterative manner and deploying machine learning for data synthesis, identification and validation of the best non-invasive detection and follow-up biomarkers, a prerequisite for designing effective therapeutic interventions.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Off-label drugs use in pediatric palliative care. - De Zen, Lucia; Marchetti, Federico; Barbi, Egidio; Benini, Franca (Ital J Pediatr, 2018)
BACKGROUND: Paediatric palliative care (PPC) aim to ensure the control of symptoms and the best possible quality of life for patients whose underlying disease, characterized by an unstoppable evolution and negative prognosis, no longer responds to specific treatments. The scientific evidence in this context are very deficient and, in order to obtain welfare objectives consistent with the situation, in the overwhelming majority of cases the prescription of drugs is off-label for indication of use and/or for age and/or for way of administration and/or formulation. The Agenzia Italiana del Farmaco - AIFA and the Italian Society of Palliative Care (Società Italiana di Cure Palliative - SICP), under a dedicated working group, wrote a document that collects the scientific evidence available to support the off-label use of medicines more frequently used in PPC. The goal is to certify the consolidated off-label use of these drugs and propose their use under the Law 648/96, in the absence of data from its pivotal clinical trials. Aim of the commentary is to report the conditions for this important work and to present the 10 drugs, usually used off-label in PPC and in pain therapy, now included in Law 648/96. CONCLUSION: This work is deemed essential to resolve, at least in part, the lack of availability of medicines researched and approved.

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Pharmacogenetics of treatments for inflammatory bowel disease. - Lucafò, Marianna; Franca, Raffaella; Selvestrel, Davide; Curci, Debora; Pugnetti, Letizia; Decorti, Giuliana; Stocco, Gabriele (Expert Opin Drug Metab Toxicol, 2018)
INTRODUCTION: Inflammatory bowel disease is a chronic inflammation of the gut whose pathogenesis is still unclear. Although no curative therapy is currently available, a number of drugs are used in induction and maintenance therapy; however, for most of these drugs, a high inter-individual variability in response is observed. Among the factors of this variability, genetics plays an important role. Areas covered: This review summarizes the results of pharmacogenetic studies, considering the most important drugs used and in particular aminosalycilates, glucocorticoids, thiopurines, monoclonal antibodies and thalidomide. Most studies used a candidate gene approach, even if significant breakthroughs have been obtained recently from applying genome-wide studies. When available, also investigations considering epigenetics and pharmacogenetic dosing guidelines have been included. Expert opinion: Only for thiopurines, genetic markers identified as predictors of efficacy or adverse events have allowed the development of dosing guidelines. For the other drugs, encouraging results are available and great expectations rely on the study of epigenetics and integration with pharmacokinetic information, especially useful for biologics. However, to improve therapy of IBD patients with these drugs, for implementation in the clinics of pharmacogenetics, informatic clinical decision support systems and training about pharmacogenetics of health providers are needed.
Keywords: Dose-Response Relationship, Drug; Epigenesis, Genetic; Gastrointestinal Agents; Genetic Markers; Genetic Predisposition to Disease; Humans; Inflammatory Bowel Diseases; Pharmacogenetics

Photobiomodulation at Multiple Wavelengths Differentially Modulates Oxidative Stress and . - Rupel, Katia; Zupin, Luisa; Colliva, Andrea; Kamada, Anselmo; Poropat, Augusto; Ottaviani, Giulia; Gobbo, Margherita; Fanfoni, Lidia; Gratton, Rossella; Santoro, Massimo; Di Lenarda, Roberto; Biasotto, Matteo; et al. (Oxid Med Cell Longev, 2018)
Photobiomodulation (PBM) is emerging as an effective strategy for the management of multiple inflammatory conditions, including oral mucositis (OM) in cancer patients who receive chemotherapy or radiotherapy. Still, the poor understanding of the mechanisms by which the light interacts with biological tissues and the heterogeneity of light sources and protocols employed worldwide significantly limits its applicability. Reactive oxygen species (ROS) are massively generated during the early phases of OM and play a major role in the pathogenesis of inflammation in general. Here, we report the results of a clinical and experimental study, aimed at evaluating the effect of laser light at different wavelengths on oxidative stress in oncologic patients suffering from OM and in two cell types abundantly present within the inflamed oral mucosa, neutrophil polymorphonuclear (PMN) granulocytes, and keratinocytes. In addition to standard ROS detection methods, we exploited a roGFP2-Orp1 genetically encoded sensor, allowing specific, quantitative, and dynamic imaging of redox events in living cells in response to oxidative stress and PBM. We found that the various wavelengths differentially modulate ROS production. In particular, the 660 nm laser light increases ROS production when applied either before or after an oxidative stimulus. In contrast, the 970 nm laser light exerted a moderate antioxidant activity both in the saliva of OM patients and in both cell types. The most marked reduction in the levels of ROS was detected in cells exposed either to the 800 nm laser light or to the combination of the three wavelengths. Overall, our study demonstrates that PBM exerts different effects on the redox state of both PMNs and keratinocytes depending on the used wavelength and prompts the validation of a multiwavelength protocol in the clinical settings.
Keywords: Adult; Aged; Aged, 80 and over; Female; Humans; Keratinocytes; Lasers, Semiconductor; Low-Level Light Therapy; Male; Middle Aged; Neutrophils; Oxidation-Reduction; Oxidative Stress; Stomatitis

Potential use of MCR-ALS for the identification of coeliac-related biochemical changes in hyperspectral Raman maps from pediatric intestinal biopsies. - Fornasaro, Stefano; Vicario, Annalisa; De Leo, Luigina; Bonifacio, Alois; Not, Tarcisio; Sergo, Valter (Integr Biol (Camb), 2018)
Raman hyperspectral imaging is an emerging practice in biological and biomedical research for label free analysis of tissues and cells. Using this method, both spatial distribution and spectral information of analyzed samples can be obtained. The current study reports the first Raman microspectroscopic characterisation of colon tissues from patients with Coeliac Disease (CD). The aim was to assess if Raman imaging coupled with hyperspectral multivariate image analysis is capable of detecting the alterations in the biochemical composition of intestinal tissues associated with CD. The analytical approach was based on a multi-step methodology: duodenal biopsies from healthy and coeliac patients were measured and processed with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS). Based on the distribution maps and the pure spectra of the image constituents obtained from MCR-ALS, interesting biochemical differences between healthy and coeliac patients has been derived. Noticeably, a reduced distribution of complex lipids in the pericryptic space, and a different distribution and abundance of proteins rich in beta-sheet structures was found in CD patients. The output of the MCR-ALS analysis was then used as a starting point for two clustering algorithms (k-means clustering and hierarchical clustering methods). Both methods converged with similar results providing precise segmentation over multiple Raman images of studied tissues.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future. - Cattaneo, Adriano; Amani, Adidja; Charpak, Nathalie; De Leon-Mendoza, Socorro; Moxon, Sarah; Nimbalkar, Somashekhar; Tamburlini, Giorgio; Villegas, Julieta; Bergh, Anne-Marie (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Globally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and high-income settings. Nevertheless, KMC is not as widely used as it should be. The International Network on KMC runs biennial workshops and congresses to help improve the coverage and quality of KMC worldwide. This paper reports the results of the two-day workshop held in November 2016, where 92 participants from 33 countries shared experiences in a series of round tables, group work sessions and plenaries. FINDINGS: Barriers to and enablers of KMC are discussed with regard to parents, health workers and the health system. Key factors for effective implementation and uptake relate to appropriate training for health staff, adherence to protocols and the creation of a welcoming environment for families. Recommendations for planning for national programmes are made according to a six-stage change model. Resources and the cost of making progress are discussed in terms of investment, maintenance, and acceleration and scaling-up costs. KMC training requirements are presented according to three levels of care. To ensure quality KMC, key requisites are proposed for the different KMC components and for sensitive communication with caregivers. The group attending to the monitoring and evaluation of KMC at a national and subnational level highlight the lack of standard indicator definitions. Key priorities for investment include health services research, harmonisation of indicators, development of a costing tool, programming and scaling up, and the follow-up of preterm infants. CONCLUSION: It is hoped that this report will help to further scale-up and sustain KMC through a systematic approach that includes raising commitment, identifying key strategies to address the main barriers and using existing facilitators, ensuring training and quality, agreeing on indicators for monitoring and evaluation, and advancing implementation research.
Keywords: Education; Education, Nonprofessional; Female; Government Programs; Health Plan Implementation; Humans; Infant; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; International Cooperation; Kangaroo-Mother Care Method; Male

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Total body irradiation and iron chelation treatment are associated with pancreatic injury following pediatric hematopoietic stem cell transplantation. - Maximova, Natalia; Gregori, Massimo; Simeone, Roberto; Sonzogni, Aurelio; Zanon, Davide; Boz, Giulia; D'Antiga, Lorenzo (Oncotarget, 2018)
Whereas many studies have addressed the risk of organ dysfunction following hematopoietic stem cell transplantation (HSCT), little is known about pancreatic susceptibility in this setting. We aimed to investigate the effect of iron overload (IO) and total body irradiation (TBI) on pancreatic function of children undergoing HSCT. We retrospectively evaluated children admitted between 2012-2016 fulfilling the following criteria: normal pancreatic iron concentration (PIC), regular pancreatic function before HSCT, availability of abdominal magnetic resonance imaging with gradient-recalled-echo sequences and a full set of biochemical markers of IO and pancreatic function performed before HSCT and at discharge. We divided the patients according to the use of TBI or myeloablative chemotherapy (MCHT) in the conditioning regimen. All patients with severe IO or moderate IO with a high risk of engraftment delay or transplantation-related complications underwent chelation therapy with deferoxamine (DFO) from the first day of conditioning to discharge. 63 patients had a HSCT in the study period, 13 did not fulfill the inclusion criteria; 50 (25 in each group) are included in the analysis, and did not show differences at baseline evaluation. At follow up testing the TBI group showed a significantly higher PIC (107,8±100,3 μmol/g vs 28,4±37,9 in MCHT group, p<0,0001). In the TBI group the patients who had DFO treatment had higher PIC (223,2±48,8 μmol/g vs 55,7±10,5 without DFO treatment, p<0,0001), and all patients having PIC >100 μmol/g at follow up had DFO-based chelation therapy, versus 26% of those with lower PIC (p<0,0001). The number of patients presenting exocrine pancreatic dysfunctions one month after transplantation was significantly higher in the TBI group (48% vs 4%; p<0.0001). The mean pancreatic volume reduction was significantly greater in the TBI group (39,1% vs 0,9% in the MCHT group; p<0,05), and was significantly worse on those who received DFO therapy. Based on our data, we suggest that TBI is detrimental for pancreatic functions, and speculate that DFO may contribute to the rapid pancreatic IO observed in these patients.

A transcriptomics study of hereditary angioedema attacks. - Castellano, Giuseppe; Divella, Chiara; Sallustio, Fabio; Montinaro, Vincenzo; Curci, Claudia; Zanichelli, Andrea; Bonanni, Erika; Suffritti, Chiara; Caccia, Sonia; Bossi, Fleur; Gallone, Anna; Schena, Francesco Paolo; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Hereditary angioedema (HAE) caused by C1-inhibitor deficiency is a lifelong illness characterized by recurrent acute attacks of localized skin or mucosal edema. Activation of the kallikrein/bradykinin pathway at the endothelial cell level has a relevant pathogenetic role in acute HAE attacks. Moreover, other pathways are involved given the variable clinical expression of the disease in different patients. OBJECTIVE: We sought to explore the involvement of other putative genes in edema formation. METHODS: We performed a PBMC microarray gene expression analysis on RNA isolated from patients with HAE during an acute attack and compared them with the transcriptomic profile of the same patients in the remission phase. RESULTS: Gene expression analysis identified 23 genes significantly modulated during acute attacks that are involved primarily in the natural killer cell signaling and leukocyte extravasation signaling pathways. Gene set enrichment analysis showed a significant activation of relevant biological processes, such as response to external stimuli and protein processing (q < 0.05), suggesting involvement of PBMCs during acute HAE attacks. Upregulation of 2 genes, those encoding adrenomedullin and cellular receptor for urokinase plasminogen activator (uPAR), which occurs during an acute attack, was confirmed in PBMCs of 20 additional patients with HAE by using real-time PCR. Finally, in vitro studies demonstrated the involvement of uPAR in the generation of bradykinin and endothelial leakage. CONCLUSIONS: Our study demonstrates the increase in levels of adrenomedullin and uPAR in PBMCs during an acute HAE attack. Activation of these genes usually involved in regulation of vascular tone and in inflammatory response might have a pathogenic role by amplifying bradykinin production and edema formation in patients with HAE.

Ultrasound-guided genitofemoral nerve block for inguinal hernia repair in the male adult: a randomized controlled pilot study. - Frassanito, Luciano; Zanfini, Bruno A; Pitoni, Sara; Germini, Paolo; Del Vicario, Miryam; Draisci, Gaetano (Minerva Anestesiol, 2018)
BACKGROUND: Ultrasound-guided (USG) ilioinguinal/iliohypogastric nerve (II/IHN) block is a widely validated anesthetic technique for inguinal herniorrhaphy. As the spermatic cord, scrotum, and adjacent thigh receive sensory innervation from the genital branch of genitofemoral nerve (GFN), the addition of GFN block has been suggested to improve the quality of perioperative anesthesia and analgesia. The aim of this study is to compare GFN block plus II/IHN block with II/IHN block alone for intraoperative anesthesia and post-operative pain management. METHODS: We enrolled 80, ASA I-III, male adults scheduled for elective open herniorrhaphy. Patients were randomized to receive either USG II/IHN plus GFN block (Case Group) or USG II/IHN block alone (Control Group). The outcome measures were the assessment of postoperative VAS scores on coughing and the adequacy of anesthesia, measured with intraoperative requirement for extra local anesthetic (LA) infiltration and number of patients needing systemic sedation. RESULTS: The requirement of intraoperative additional doses of LA was significantly lower in the Case Group (median LA volume administered by the surgeon: 13.8±5.6 mL vs. 20.7±9.1 mL, P<0.05). Two patients in the Control Group needed systemic sedation. VAS scores at 15 minutes, 30 minutes, 1 hour, 2 hours, pre-discharge, and 24 hours were significantly lower in the Case Group (P<0.005). Four cases of femoral nerve block were reported, three in the Control Group, one in the Case Group (2.2% vs. 7.7%, P>0.05). CONCLUSIONS: The combination of GFN block and II/IHN block is associated with lower postoperative VAS scores and lower doses of intraoperative additional LA.

Vaginal microbiota dysmicrobism and role of biofilm-forming bacteria. - Campisciano, Giuseppina; Zanotta, Nunzia; Petix, Vincenzo; Corich, Lucia; De Seta, Francesco; Comar, Manola (Front Biosci (Elite Ed), 2018)
Bacterial vaginosis involves the presence of a polymicrobial biofilm on the vaginal epithelium, guaranteeing immune escape and spread of antibiotic resistance. To spot known biofilm-forming bacteria, we profiled the vaginal microbiome of sixty-four symptomatic women suffering from a different grade of vaginal disorders and sixty asymptomatic healthy women. Specific microbial profiles distinguished symptomatic from asymptomatic women and characterized the grade of dysmicrobism within the symptomatic group. Lactobacillus crispatus and iners predominated on the healthy vaginal mucosa, while Lactobacillus gasseri predominated in the intermediate dysmicrobism. Furthermore, the intermediate grade of dysmicrobism was characterized by other lactic acid-producers species than Lactobacilli, able to rescue the microbial imbalance, and Ureaplasma parvum-serovar 3. The vaginosis group exhibited the overgrowth of Prevotella bivia, which is known to enhance the biofilm formation by Gardnerella vaginalis, and the presence of Streptococcus anginosus, which is emerging as a new cooperating player of the vaginal biofilm. Identifying specific microorganisms promoting or preventing the biofilm formation could increase the accuracy for a better definition of the vaginal dysmicrobism concept and therapeutic intervention.
Keywords: Adult; Biofilms; Female; Humans; Microbiota; Vagina; Vaginosis, Bacterial

Vanishing Bile Ducts in the Long Term after Pediatric Hematopoietic Stem Cell Transplantation. - Maximova, Natalia; Sonzogni, Aurelio; Matarazzo, Lorenza; Ghirardi, Arianna; D'Antiga, Lorenzo (Biol Blood Marrow Transplant, 2018)
There are no structured studies on liver histology after hematopoietic stem cell transplantation (HSCT). We aimed to prospectively describe the clinicopathologic features of liver disease in the long term after HSCT in an observational, longitudinal study of liver histology in a consecutive cohort of children undergoing allogeneic HSCT. First liver biopsy was performed in presence of abnormal liver function tests and repeated per protocol thereafter. A previously reported semiquantitative score evaluating inflammation, cholestasis, and ductopenia (bile ducts-to-portal tracts ratio ≤ .5) was adopted. Graft-versus-host disease (GVHD) was diagnosed according to standard criteria. We evaluated 131 biopsies taken in 50 HSCTs performed in 47 children (mean age, 9.7 ± 5.2 years). Pre-HSCT chemotherapy was administered in 36 of 50 (72%). GVHD was diagnosed in 17 of 50 (34%). Over time the overall score decreased from a mean of 6 ± 2.7 to 3.25 ± .96 (P < .01), inflammation from 1.22 ± 1.19 to 1 ± 0 (not significant), and cholestasis from 3.9 ± 2.08 to 1.5 ± .58 (P < .01). Ductopenia, found in 113 of 131 biopsies (93%), worsened from .63 ± .35 to .16 ± .14 (P < .01). On multivariate analysis severe ductopenia (ratio ≤ .2) was associated with previous chemotherapy (P = .04), in particular with thiotepa, but not with history of GVHD. Vanishing bile duct syndrome after HSCT may be due to drug-induced liver disease. Longer follow-up will reveal whether these patients are prone to late liver-related morbidity and mortality.

What is the quality of the maternal near-miss case reviews in WHO European Region? Cross-sectional study in Armenia, Georgia, Latvia, Republic of Moldova and Uzbekistan. - Bacci, Alberta; Hodorogea, Stelian; Khachatryan, Henrik; Babojonova, Shohida; Irsa, Signe; Jansone, Maira; Dondiuc, Iurie; Matarazde, George; Lazdane, Gunta; Lazzerini, Marzia (BMJ Open, 2018)
OBJECTIVES: The maternal near-miss case review (NMCR) cycle is a type of clinical audit aiming at improving quality of maternal healthcare by discussing near-miss cases. In several countries this approach has been introduced and supported by WHO and partners since 2004, but information on the quality of its implementation is missing. This study aimed at evaluating the quality of the NMCR implementation in selected countries within WHO European Region. DESIGN: Cross-sectional study. SETTINGS: Twenty-three maternity units in Armenia, Georgia, Latvia, Moldova and Uzbekistan. ASSESSMENT TOOLS: A predefined checklist including 50 items, according to WHO methodology. Quality in the NMCR implementation was defined by summary scores ranging from 0 (totally inappropriate) to 3 (appropriate). RESULTS: Quality of the NMCR implementation was heterogeneous among different countries, and within the same country. Overall, the first part of the audit cycle (from case identification to case analysis) was fairly well performed (mean score 2.00, 95% CI 1.94 to 2.06), with the exception of the 'inclusion of users' views' (mean score 0.66, 95% CI 0.11 to 1.22), while the second part (developing recommendations, implementing them and ensuring quality) was poorly performed (mean score 0.66, 95% CI 0.11 to 1.22). Each country had at least one champion facility, where quality of the NMCR cycle was acceptable. Quality of the implementation was not associated with its duration. Gaps in implementation were of technical, organisational and attitudinal nature. CONCLUSIONS: Ensuring quality in the NMCR may be difficult but achievable. The high heterogeneity in results within the same country suggests that quality of the NMCR implementation depends, to a large extent, from hospital factors, including staff's commitment, managerial support and local coordination. Efforts should be put in preventing and mitigating common barriers that hamper successful NMCR implementation.
Keywords: Armenia; Checklist; Cross-Sectional Studies; Female; Georgia; Humans; Latvia; Maternal Mortality; Medical Audit; Moldova; Near Miss, Healthcare; Pregnancy; Pregnancy Complications; Quality Improvement; Uzbekistan

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

46,XY ovotesticular disorders of sex development: A therapeutic challenge. - Scarpa, Maria-Grazia; Grazia, Massimo Di; Tornese, Gianluca (Pediatr Rep, 2017)

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

Amniocentesis and chorionic villus sampling in HIV-infected pregnant women: a multicentre case series. - Floridia, M; Masuelli, G; Meloni, A; Cetin, I; Tamburrini, E; Cavaliere, A F; Dalzero, S; Sansone, M; Alberico, S; Guerra, B; Spinillo, A; Chiadò Fiorio Tin, M; et al. (BJOG, 2017)
OBJECTIVES: To assess in pregnant women with HIV the rates of amniocentesis and chorionic villus sampling (CVS), and the outcomes associated with such procedures. DESIGN: Observational study. Data from the Italian National Program on Surveillance on Antiretroviral Treatment in Pregnancy were used. SETTING: University and hospital clinics. POPULATION: Pregnant women with HIV. METHODS: Temporal trends were analysed by analysis of variance and by the Chi-square test for trend. Quantitative variables were compared by Student's t-test and categorical data by the Chi-square test, with odds ratios and 95% confidence intervals calculated. MAIN OUTCOME MEASURES: Rate of invasive testing, intrauterine death, HIV transmission. RESULTS: Between 2001 and 2015, among 2065 pregnancies in women with HIV, 113 (5.5%) had invasive tests performed. The procedures were conducted under antiretroviral treatment in 99 cases (87.6%), with a significant increase over time in the proportion of tests performed under highly active antiretroviral therapy (HAART) (100% in 2011-2015). Three intrauterine deaths were observed (2.6%), and 14 pregnancies were terminated because of fetal anomalies. Among 96 live newborns, eight had no information available on HIV status. Among the remaining 88 cases with either amniocentesis (n = 75), CVS (n = 12), or both (n = 1), two HIV transmissions occurred (2.3%). No HIV transmission occurred among the women who were on HAART at the time of invasive testing, and none after 2005. CONCLUSIONS: The findings reinforce the assumption that invasive prenatal testing does not increase the risk of HIV vertical transmission among pregnant women under suppressive antiretroviral treatment. TWEETABLE ABSTRACT: No HIV transmission occurred among women who underwent amniocentesis or CVS under effective anti-HIV regimens.
Keywords: Adult; Amniocentesis; Analysis of Variance; Anti-Retroviral Agents; Chi-Square Distribution; Chorionic Villi Sampling; Female; Fetal Death; HIV Infections; Humans; Infectious Disease Transmission, Vertical; Odds Ratio; Pregnancy; Pregnancy Complications, Infectious

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Avoiding Ethanol Presence in DNA Samples Enhances the Performance of Ultraviolet Resonance Raman Spectroscopy Analysis. - Cammisuli, Francesca; Pascolo, Lorella; Morgutti, Marcello; Gessini, Alessandro; Masciovecchio, Claudio; D'Amico, Francesco (Appl Spectrosc, 2017)
Ethanol is an essential chemical reagent in DNA preparation as its use increases the yield of extraction. All methodologies for DNA isolation involve the use of ethanol in order to prevent DNA dissolution in water and to optimize the binding of DNA to chromatographic membranes. In this note, we show how the presence of ethanol traces in DNA aqueous solution affects ultraviolet Raman spectra, leading to possible misinterpretations. We report a simple method to remove the ethanol Raman features from the spectra, based on heating the DNA sample at 80 ℃, followed by a slow cooling procedure.
Keywords: DNA; Ethanol; Female; Humans; Placenta; Pregnancy; Spectrophotometry, Ultraviolet; Spectrum Analysis, Raman

Bipolar Disorder With Psychotic Features and Ocular Toxoplasmosis: A Possible Pathogenetic Role of the Parasite? - Del Grande, Claudia; Contini, Carlo; Schiavi, Elisa; Rutigliano, Grazia; Maritati, Martina; Seraceni, Silva; Pinto, Barbara; Dell'Osso, Liliana; Bruschi, Fabrizio (J Nerv Ment Dis, 2017)
Recent evidence suggests the involvement of Toxoplasma gondii infection in the emergence of psychotic and affective disorders. In this report, we describe the case of a young Brazilian woman affected by recurrent ocular toxoplasmosis and presenting with a manic episode with psychotic features in the context of a diagnosis of Bipolar Disorder (BD), type I. We observed a relationship between ocular manifestations and the clinical course of bipolar illness, confirmed by molecular analyses (nested-PCR), as well as by the high level of T. gondii specific IgG. This case report is the first showing the presence of circulating parasite DNA at the time of occurrence of psychiatric symptoms, thus providing further support for a possible role of the parasite in the pathogenesis of some cases of BD.
Keywords: Adult; Bipolar Disorder; Brazil; Female; Humans; Toxoplasmosis, Ocular; Young Adult

Bolus feeding has no effect on cerebral hemodynamics, irrespective of gestational age. - Bembich, Stefano; Cont, Gabriele; Bua, Jenny; Orlando, Chiara; Di Benedetto, Donatella; Demarini, Sergio (J Matern Fetal Neonatal Med, 2017)
OBJECTIVE: By multichannel near-infrared spectroscopy, we studied if gestational age has any influence on preterm cerebral hemodynamics, during bolus feeding. METHODS: Oxy-haemoglobin (HbO), as cerebral blood flow estimate, and the ratio between HbO and total haemoglobin (HbO/HbTot), as cerebral oxygenation estimate, were assessed in 40 stable premature infants, during a 10 min bolus feeding. RESULTS: We found no effect of any of the gestational ages studied (25-34 weeks) either on cerebral blood flow or on oxygenation, during a bolus feeding procedure. CONCLUSIONS: Bolus feeding appears not to affect cerebral hemodynamics of uncritically preterm infants, irrespective of gestational age.
Keywords: Cerebrovascular Circulation; Enteral Nutrition; Female; Gestational Age; Heart Rate; Humans; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Male; Oxygen; Oxyhemoglobins; Spectroscopy, Near-Infrared

Cardiac output decreases and systemic vascular resistance increases in newborns placed in the left-lateral position. - Paviotti, G; Todero, S; Demarini, S (J Perinatol, 2017)
OBJECTIVE: The objective of the study was to study the effect of short-term left-lateral position on cardiovascular parameters in hemodynamically stable newborns. STUDY DESIGN: Cardiac output (CO), stroke volume (SV), systemic vascular resistance index (SVRI) and heart rate (HR) were measured by electric velocimetry in hemodynamically stable newborns without respiratory support in the supine, left-lateral and back-to-supine positions, each kept for 10 min. RESULTS: Thirty-two newborns were enrolled, birth weight 2134 (1818 to 2460) g, gestational age 34.5±2.4 weeks. CO and SV decreased significantly from supine to left-lateral position (CO supine: 193.4 (168.0 to 229.6) ml kgmin; CO left-lateral: 172.0 (154.9 to 201.6) ml kgmin, P<0.0001; SV supine: 3.0 (2.7 to 4.0) ml; SV left-lateral: 2.7 (2.4 to 3.2) ml, P<0.0004). Conversely, SVRI increased in left-lateral position: SVRI supine: 18865±9244 dyns cm m; SVRI left-lateral: 21203±10059 dyns cm m, P<0.0001). All variables returned to the initial value when infants were back in the supine position. HR and blood pressure did not change. CONCLUSION: In stable infants, CO and SV decrease and SVRI increases, in left-lateral position.
Keywords: Blood Pressure; Cardiac Output; Female; Gestational Age; Heart Rate; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Italy; Male; Posture; Stroke Volume; Vascular Resistance

CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

A complete duplication of X chromosome resulting in a tricentric isochromosome originated by centromere repositioning. - Villa, N; Conconi, D; Benussi, D Gambel; Tornese, G; Crosti, F; Sala, E; Dalprà, L; Pecile, V (Mol Cytogenet, 2017)
BACKGROUND: Neocentromeres are rare and considered chromosomal aberrations, because a non-centromeric region evolves in an active centromere by mutation. The literature reported several structural anomalies of X chromosome and they influence the female reproductive capacity or are associated to Turner syndrome in the presence of monosomy X cell line. CASE PRESENTATION: We report a case of chromosome X complex rearrangement found in a prenatal diagnosis. The fetal karyotype showed a mosaicism with a 45,X cell line and a 46 chromosomes second line with a big marker, instead of a sex chromosome. The marker morphology and fluorescence in situ hybridization (FISH) characterization allowed us to identify a tricentric X chromosome constituted by two complete X chromosome fused at the p arms telomere and an active neocentromere in the middle, at the union of the two Xp arms, where usually are the telomeric regions. FISH also showed the presence of a paracentric inversion of both Xp arms. Furthermore, fragility figures were found in 56% of metaphases from peripheral blood lymphocytes culture at birth: a shorter marker chromosome and an apparently acentric fragment frequently lost. CONCLUSIONS: At our knowledge, this is the first isochromosome of an entire non-acrocentric chromosome. The neocentromere is constituted by canonical sequences but localized in an unusual position and the original centromeres are inactivated. We speculated that marker chromosome was the result of a double rearrangement: firstly, a paracentric inversion which involved the Xp arm, shifting a part of the centromere at the p end and subsequently a duplication of the entire X chromosome, which gave rise to an isochromosome. It is possible to suppose that the first event could be a result of a non-allelic homologous recombination mediated by inverted low-copy repeats. As expected, our case shows a Turner phenotype with mild facial features and no major skeletal deformity, normal psychomotor development and a spontaneous development of puberty and menarche, although with irregular menses since the last follow-up.

A congenital purplish tumour. - Matarazzo, L; Delise, A; Zennaro, F; Bussani, R; Demarini, S; Berti, I; Ventura, A (Arch Dis Child Educ Pract Ed, 2017)
Keywords: Congenital Abnormalities; Humans; India; Infant; Infant, Newborn; Knee; Male; Neonatology; Neoplasms; Treatment Outcome

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

DEFB1 polymorphisms and salivary hBD-1 concentration in Oral Lichen Planus patients and healthy subjects. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Pozzato, Gabriele; Ottaviani, Giulia; Gobbo, Margherita; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2017)
OBJECTIVES: The aetiology of Oral Lichen Planus (OLP), a chronic inflammatory disease of oral mucosa, is not yet well understood. Since innate immunity may be hypothesized as involved in the susceptibility to OLP, we studied human beta defensin 1 (hBD-1) an antimicrobial peptide constitutively expressed in the saliva, looking at functional genetic variants possibly able to diminish hBD-1 production an consequently conferring major susceptibility to OLP. DESIGN: We analysed three DEFB1 polymorphisms at 5' UTR, -52G>A (rs1799946), -44C>G (rs1800972), -20G>A (rs11362) and two DEFB1 polymorphisms at 3'UTR, c*5G>A (rs1047031), c*87A>G (rs1800971), with the aim of correlating these genetic variants and hBD-1 salivary level in a group of OLP patients and in healthy subjects. We also evaluated hBD-1 salivary concentrations, using ELISA, in OLP and healthy controls. RESULTS: We compared hBD-1 concentrations in OLP and healthy subjects: hBD-1 concentration was significantly higher in OLP patients respect to control. When considering the correlation between DEFB1 polymorphisms genotypes and hBD-1 expression levels, significant results were obtained for SNPs -52G>A (p=0.03 both in OLP patients and healthy individuals) and -44C>G (p=0.02 in OLP patients). CONCLUSIONS: hBD-1 production was different between OLP and healthy subjects (not age-matched with OLP). DEFB1 gene polymorphisms, -52G>A and -44C>G, correlated with hBD-1 salivary concentrations.
Keywords: 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; beta-Defensins; Female; Genetic Predisposition to Disease; Genotype; Humans; Lichen Planus, Oral; Male; Middle Aged; Polymorphism, Single Nucleotide; Saliva; Sequence Analysis, DNA

Defects in mitochondrial energetic function compels Fanconi Anaemia cells to glycolytic metabolism. - Cappelli, Enrico; Cuccarolo, Paola; Stroppiana, Giorgia; Miano, Maurizio; Bottega, Roberta; Cossu, Vanessa; Degan, Paolo; Ravera, Silvia (Biochim Biophys Acta Mol Basis Dis, 2017)
Energetic metabolism plays an essential role in the differentiation of haematopoietic stem cells (HSC). In Fanconi Anaemia (FA), DNA damage is accumulated during HSC differentiation, an event that is likely associated with bone marrow failure (BMF). One of the sources of the DNA damage is altered mitochondrial metabolism and an associated increment of oxidative stress. Recently, altered mitochondrial morphology and a deficit in the energetic activity in FA cells have been reported. Considering that mitochondria are the principal site of aerobic ATP production, we investigated FA metabolism in order to understand what pathways are able to compensate for this energy deficiency. In this work, we report that the impairment in mitochondrial oxidative phosphorylation (OXPHOS) in FA cells is countered by an increase in glycolytic flux. By contrast, glutaminolysis appears lower with respect to controls. Therefore, it is possible to conclude that in FA cells glycolysis represents the main pathway for producing energy, balancing the NADH/NAD ratio by the conversion of pyruvate to lactate. Finally, we show that a forced switch from glycolytic to OXPHOS metabolism increases FA cell oxidative stress. This could be the cause of the impoverishment in bone marrow HSC during exit from the homeostatic quiescent state. This is the first work that systematically explores FA energy metabolism, highlighting its flaws, and discusses the possible relationships between these defects and BMF.
Keywords: Cell Line; Fanconi Anemia; Glycolysis; Humans; Mitochondria; Oxidative Phosphorylation; Oxidative Stress

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Dynamic quadripolar radiofrequency treatment of vaginal laxity/menopausal vulvo-vaginal atrophy: 12-month efficacy and safety. - Vicariotto, Franco; De Seta, Francesco; Faoro, Valentina; Raichi, Mauro (Minerva Ginecol, 2017)
BACKGROUND: Twelve-month extension of a previous spontaneous exploratory study investigating safety and efficacy of a new low-energy dynamic quadripolar radiofrequency (DQRF) device in: A) premenopausal women with symptoms of vaginal laxity, with special reference to dysuria, urinary incontinence and unsatisfactory sexual life (vaginal laxity arm of the study); B) postmenopausal women with vulvovaginal atrophy/genitourinary syndrome of menopause (VVA/GSM) and VVA/GSM-related symptoms (VVA/GSM arm of the study). DQRF treatment schedule in both study arms: 4 to 6 procedures of 15 to 20 min every 14 days (vaginal laxity, range 12-17 days; VVA/GSM, range 13-16). Operative temperatures in vaginal target tissues during procedure: vaginal laxity, 42 °C (range 40-43 °C); VVA/GSM, 40 °C (range 40-42 °C). METHODS: In the vaginal laxity arm of the study, 25 women with subjective sensation of vaginal introital laxity (very to slightly loose). Assessment of urinary incontinence, satisfaction with sexual relationship and contribution of pelvic organ prolapse: Vaginal Laxity Questionnaire (VLQ, Italian certified translation) and short form of the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12, Italian certified translation). Further evaluation of sexual gratification: Sexual Satisfaction Questionnaire (SSQ). In the VVA/GSM arm of the study, 32 women with objective evidence of VVA and vaginal dryness and/or dyspareunia as most bothersome symptoms. Assessment of VVA/GSM symptoms and overall satisfaction with sexual life: specifically designed 10-cm visual analogue scales. RESULTS: All 4 to 6 planned DQRF sessions were well tolerated in both the vaginal laxity and VVA/GSM arms of the study, with no troubling pain, thermal injury or other immediate adverse effects during all the procedures. All screened women completed the planned DQRF treatment sessions in both arms of the extension study. There was no participant attrition with only a few occasionally missing visits over the 12-month follow-up period. Improvements were rapid in self-perception of introital looseness and related symptoms like dysuria/urinary incontinence and unrewarding sexual relationship (vaginal laxity patients) and atrophy-related symptoms including painful and unsatisfactory sexual activity (VVA/GSM patients). Participating women consistently reported wide-spectrum strong clinical improvements by the end of the planned DQRF sessions. Clinical improvements remained steady for the whole follow-up period in postmenopausal women; a statistically non-significant tendency to slight deterioration in VLQ, PISQ-12 and SSQ mean scores was detected after 6 to 9 months of follow-up in the vaginal laxity arm of the study. CONCLUSIONS: Safety was excellent during all DQRF procedures and over the 12 months following the end of the treatment sessions. VLQ, PISQ-12 and SSQ scores (women with vaginal laxity), VAS self-evaluation of VVA/GSM symptoms and overall satisfaction with sexual life (women with VVA/GSM symptoms) improved rapidly, reaching almost normal levels by the last DQRF session and suggesting rapid, but also persistent, vaginal rejuvenation in both indications. A late tendency to some slight deterioration in women treated for vaginal laxity suggests such women might benefit from new DQRF treatments 6 to 9 months after the previous cycle.
Keywords: Adult; Atrophy; Dyspareunia; Electric Stimulation Therapy; Female; Follow-Up Studies; Humans; Italy; Middle Aged; Orgasm; Patient Satisfaction; Pelvic Organ Prolapse; Postmenopause; Premenopause; Sexual Behavior; Surveys and Questionnaires; Time Factors; Treatment Outcome; Urinary Incontinence; Vagina; Vaginal Diseases; Vulva

Early-life nutritional exposures and lifelong health: immediate and long-lasting impacts of probiotics, vitamin D, and breastfeeding. - Berti, Cristiana; Agostoni, Carlo; Davanzo, Riccardo; Hyppönen, Elina; Isolauri, Erika; Meltzer, Helle M; Steegers-Theunissen, Régine P M; Cetin, Irene (Nutr Rev, 2017)
Pregnancy and infancy comprise the most critical stages for conditioning an individual's health, with a number of implications for subsequent risks of morbidity, mortality, and reproductive health. Nutrition may influence both the overall pregnancy outcome and the growth trajectory and immune system of the fetus and infant, with short- and long-term effects on the health of the offspring. Within this context, leading experts at Expo Milano 2015 in Milan, Italy, discussed up-to-date knowledge while providing suggestions and challenges before, during, and after pregnancy. This narrative review summarizes the key issues raised by the experts concerning the interplay between the nutritional environment from conception to early infancy and the offspring's immediate and lifelong health, with a particular focus on epigenetic mechanisms, probiotics, vitamin D, and breastfeeding. Taken together, the findings strengthen the awareness that nutritional exposures occurring from preconception to the postnatal period may be strong determinants of the offspring's health and may provide supportive evidence for current nutritional recommendations and guidelines for pregnant women and infants. Critical topics to be addressed in future research and translated into recommendations of public health relevance are also highlighted.
Keywords: Breast Feeding; Diet; Female; Humans; Infant; Infant Nutritional Physiological Phenomena; Meta-Analysis as Topic; Nutritional Status; Pregnancy; Pregnancy Outcome; Probiotics; Vitamin D

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Epratuzumab and Blinatumomab as Therapeutic Antibodies for Treatment of Pediatric Acute Lymphoblastic Leukemia: Current Status and Future Perspectives. - Franca, Raffaella; Favretto, Diego; Granzotto, Marilena; Decorti, Giuliana; Rabusin, Marco; Stocco, Gabriele (Curr Med Chem, 2017)
BACKGROUND: More than 85% of children affected by acute lymphoblastic leukemia (ALL) are successfully treated; however relapse remains a remarkable clinical concern, with 50-60% of relapsing patients facing a fatal outcome. Management of relapsed patients includes standardized intensive risk-adapted regimens based on conventional drugs, and hematopoietic stem cells transplantation for patients with unfavourable features. Biological drugs, in particular the monoclonal antibody epratuzumab and the bi-functional recombinant single chain peptide blinatumomab, have been recently recognized as novel potential agents to be integrated in salvage ALL therapy to further improve rescue outcome. METHODS: A systematic search of peer-reviewed scientific literature and clinical trials in public databases has been carried out. Both clinical and pre-clinical studies have been included to summarize recent evidence on epratuzumab and blinatumomab for salvage ALL therapy. RESULTS: Sixty-two papers and 25 clinical trials were included. Although not all patients responded properly to these agents, their use in relapsed and refractory pediatric ALL seems promising. CONCLUSION: Phase 3 studies have recently begun and more consistent results about epratuzumab and blinatumomab safety and efficacy in comparison to conventional therapies are expected in the next years. Epratuzumab seems safe in the dosing scheme proposed in ALL, but its efficacy over the conventional chemotherapy is still questionable. Blinatumomab has shown promising results in high risk cases such as elder adult patients and conclusive studies on pediatric ALL are needed. Patient inter-individual variability to these agents has not been investigated in depth, but this issue needs to be addressed, in particular for blinatumomab.
Keywords: Antibodies, Bispecific; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antineoplastic Agents; Child; Clinical Trials as Topic; Half-Life; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Sialic Acid Binding Ig-like Lectin 2

Fetal and umbilical Doppler ultrasound in high-risk pregnancies. - Alfirevic, Zarko; Stampalija, Tamara; Dowswell, Therese (Cochrane Database Syst Rev, 2017)
BACKGROUND: Abnormal blood flow patterns in fetal circulation detected by Doppler ultrasound may indicate poor fetal prognosis. It is also possible that false positive Doppler ultrasound findings could lead to adverse outcomes from unnecessary interventions, including preterm delivery. OBJECTIVES: The objective of this review was to assess the effects of Doppler ultrasound used to assess fetal well-being in high-risk pregnancies on obstetric care and fetal outcomes. SEARCH METHODS: We updated the search of Cochrane Pregnancy and Childbirth's Trials Register on 31 March 2017 and checked reference lists of retrieved studies. SELECTION CRITERIA: Randomised and quasi-randomised controlled trials of Doppler ultrasound for the investigation of umbilical and fetal vessels waveforms in high-risk pregnancies compared with no Doppler ultrasound. Cluster-randomised trials were eligible for inclusion but none were identified. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed the studies for inclusion, assessed risk of bias and carried out data extraction. Data entry was checked. We assessed the quality of evidence using the GRADE approach. MAIN RESULTS: Nineteen trials involving 10,667 women were included. Risk of bias in trials was difficult to assess accurately due to incomplete reporting. None of the evidence relating to our main outcomes was graded as high quality. The quality of evidence was downgraded due to missing information on trial methods, imprecision in risk estimates and heterogeneity. Eighteen of these studies compared the use of Doppler ultrasound of the umbilical artery of the unborn baby with no Doppler or with cardiotocography (CTG). One more recent trial compared Doppler examination of other fetal blood vessels (ductus venosus) with computerised CTG.The use of Doppler ultrasound of the umbilical artery in high-risk pregnancy was associated with fewer perinatal deaths (risk ratio (RR) 0.71, 95% confidence interval (CI) 0.52 to 0.98, 16 studies, 10,225 babies, 1.2% versus 1.7 %, number needed to treat (NNT) = 203; 95% CI 103 to 4352, evidence graded moderate). The results for stillbirths were consistent with the overall rate of perinatal deaths, although there was no clear difference between groups for this outcome (RR 0.65, 95% CI 0.41 to 1.04; 15 studies, 9560 babies, evidence graded low). Where Doppler ultrasound was used, there were fewer inductions of labour (average RR 0.89, 95% CI 0.80 to 0.99, 10 studies, 5633 women, random-effects, evidence graded moderate) and fewer caesarean sections (RR 0.90, 95% CI 0.84 to 0.97, 14 studies, 7918 women, evidence graded moderate). There was no comparative long-term follow-up of babies exposed to Doppler ultrasound in pregnancy in women at increased risk of complications.No difference was found in operative vaginal births (RR 0.95, 95% CI 0.80 to 1.14, four studies, 2813 women), nor in Apgar scores less than seven at five minutes (RR 0.92, 95% CI 0.69 to 1.24, seven studies, 6321 babies, evidence graded low). Data for serious neonatal morbidity were not pooled due to high heterogeneity between the three studies that reported it (1098 babies) (evidence graded very low).The use of Doppler to evaluate early and late changes in ductus venosus in early fetal growth restriction was not associated with significant differences in any perinatal death after randomisation. However, there was an improvement in long-term neurological outcome in the cohort of babies in whom the trigger for delivery was either late changes in ductus venosus or abnormalities seen on computerised CTG. AUTHORS' CONCLUSIONS: Current evidence suggests that the use of Doppler ultrasound on the umbilical artery in high-risk pregnancies reduces the risk of perinatal deaths and may result in fewer obstetric interventions. The results should be interpreted with caution, as the evidence is not of high quality. Serial monitoring of Doppler changes in ductus venosus may be beneficial, but more studies of high quality with follow-up including neurological development are needed for evidence to be conclusive.
Keywords: Cardiotocography; Cesarean Section; Female; Fetal Monitoring; Humans; Labor, Induced; Perinatal Mortality; Pregnancy; Pregnancy, High-Risk; Randomized Controlled Trials as Topic; Stillbirth; Ultrasonography, Prenatal; Umbilical Arteries; Umbilical Cord

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

Genetic structure in the Sherpa and neighboring Nepalese populations. - Cole, Amy M; Cox, Sean; Jeong, Choongwon; Petousi, Nayia; Aryal, Dhana R; Droma, Yunden; Hanaoka, Masayuki; Ota, Masao; Kobayashi, Nobumitsu; Gasparini, Paolo; Montgomery, Hugh; Robbins, Peter; et al. (BMC Genomics, 2017)
BACKGROUND: We set out to describe the fine-scale population structure across the Eastern region of Nepal. To date there is relatively little known about the genetic structure of the Sherpa residing in Nepal and their genetic relationship with the Nepalese. We assembled dense genotype data from a total of 1245 individuals representing Nepal and a variety of different populations resident across the greater Himalayan region including Tibet, China, India, Pakistan, Kazakhstan, Uzbekistan, Tajikistan and Kirghizstan. We performed analysis of principal components, admixture and homozygosity. RESULTS: We identified clear substructure across populations resident in the Himalayan arc, with genetic structure broadly mirroring geographical features of the region. Ethnic subgroups within Nepal show distinct genetic structure, on both admixture and principal component analysis. We detected differential proportions of ancestry from northern Himalayan populations across Nepalese subgroups, with the Nepalese Rai, Magar and Tamang carrying the greatest proportions of Tibetan ancestry. CONCLUSIONS: We show that populations dwelling on the Himalayan plateau have had a clear impact on the Northern Indian gene pool. We illustrate how the Sherpa are a remarkably isolated population, with little gene flow from surrounding Nepalese populations.
Keywords: Asian Continental Ancestry Group; Chromosomes, Human, Y; DNA; DNA, Mitochondrial; Ethnic Groups; Gene Flow; Genotype; Humans; Leukocytes; Likelihood Functions; Nepal; Principal Component Analysis

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the esophageal atresia. - Chiarenza, Salvatore Fabio; Conighi, Maria Luisa; Conforti, Andrea; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Esophageal Atresia; Humans; Infant; Minimally Invasive Surgical Procedures; Video-Assisted Surgery

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the ureteropelvic-junction obstruction. - Chiarenza, Salvatore Fabio; Bleve, Cosimo; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; Bagolan, Pietro; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Humans; Infant; Kidney Pelvis; Minimally Invasive Surgical Procedures; Ureteral Obstruction; Video-Assisted Surgery

Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Clinical and Hypoxemic Childhood Pneumonia over Three Years in Central Malawi: An Observational Study. - McCollum, Eric D; Nambiar, Bejoy; Deula, Rashid; Zadutsa, Beatiwel; Bondo, Austin; King, Carina; Beard, James; Liyaya, Harry; Mankhambo, Limangeni; Lazzerini, Marzia; Makwenda, Charles; Masache, Gibson; et al. (PLoS One, 2017)
BACKGROUND: The pneumococcal conjugate vaccine's (PCV) impact on childhood pneumonia during programmatic conditions in Africa is poorly understood. Following PCV13 introduction in Malawi in November 2011, we evaluated the case burden and rates of childhood pneumonia. METHODS AND FINDINGS: Between January 1, 2012-June 30, 2014 we conducted active pneumonia surveillance in children <5 years at seven hospitals, 18 health centres, and with 38 community health workers in two districts, central Malawi. Eligible children had clinical pneumonia per Malawi guidelines, defined as fast breathing only, chest indrawing +/- fast breathing, or, ≥1 clinical danger sign. Since pulse oximetry was not in the Malawi guidelines, oxygenation <90% defined hypoxemic pneumonia, a distinct category from clinical pneumonia. We quantified the pneumonia case burden and rates in two ways. We compared the period immediately following vaccine introduction (early) to the period with >75% three-dose PCV13 coverage (post). We also used multivariable time-series regression, adjusting for autocorrelation and exploring seasonal variation and alternative model specifications in sensitivity analyses. The early versus post analysis showed an increase in cases and rates of total, fast breathing, and indrawing pneumonia and a decrease in danger sign and hypoxemic pneumonia, and pneumonia mortality. At 76% three-dose PCV13 coverage, versus 0%, the time-series model showed a non-significant increase in total cases (+47%, 95% CI: -13%, +149%, p = 0.154); fast breathing cases increased 135% (+39%, +297%, p = 0.001), however, hypoxemia fell 47% (-5%, -70%, p = 0.031) and hospital deaths decreased 36% (-1%, -58%, p = 0.047) in children <5 years. We observed a shift towards disease without danger signs, as the proportion of cases with danger signs decreased by 65% (-46%, -77%, p<0.0001). These results were generally robust to plausible alternative model specifications. CONCLUSIONS: Thirty months after PCV13 introduction in Malawi, the health system burden and rates of the severest forms of childhood pneumonia, including hypoxemia and death, have markedly decreased.
Keywords: Child; Child Mortality; Cost of Illness; Dose-Response Relationship, Immunologic; Geography; Humans; Hypoxia; Malawi; Pneumococcal Vaccines; Pneumonia, Pneumococcal; Time Factors; Vaccines, Conjugate

Impaired fasting glucose and impaired glucose tolerance in children and adolescents with overweight/obesity. - Di Bonito, P; Pacifico, L; Chiesa, C; Valerio, G; Miraglia Del Giudice, E; Maffeis, C; Morandi, A; Invitti, C; Licenziati, M R; Loche, S; Tornese, G; Franco, F; et al. (J Endocrinol Invest, 2017)
OBJECTIVE: To investigate in a large sample of overweight/obese (OW/OB) children and adolescents the prevalence of prediabetic phenotypes such as impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and to assess their association with cardiometabolic risk (CMR) factors including hepatic steatosis (HS). METHODS: Population data were obtained from the CARdiometabolic risk factors in children and adolescents in ITALY study. Between 2003 and 2013, 3088 youths (972 children and 2116 adolescents) received oral glucose tolerance test (OGTT) and were included in the study. In 798 individuals, abdominal ultrasound for identification of HS was available. RESULTS: The prevalence of IFG (3.2 vs. 3.3%) and IGT (4.6 vs. 5.0%) was similar between children and adolescents. Children with isolated IGT had a 2-11 fold increased risk of high LDL-C, non-HDL-C, Tg/HDL-C ratio, and low insulin sensitivity, when compared to those with normal glucose tolerance (NGT). No significant association of IFG with any CMR factor was found in children. Among adolescents, IGT subjects, and to a lesser extent those with IFG, showed a worse CMR profile compared to NGT subgroup. In the overall sample, IGT phenotype showed a twofold increased risk of HS compared to NGT subgroup. CONCLUSIONS: Our study shows an unexpected similar prevalence of IFG and IGT between children and adolescents with overweight/obesity. The IGT phenotype was associated with a worse CMR profile in both children and adolescents. Phenotyping prediabetes conditions by OGTT should be done as part of prediction and prevention of cardiometabolic diseases in OW/OB youth since early childhood.
Keywords: Adolescent; Blood Glucose; Case-Control Studies; Child; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin; Insulin Resistance; Italy; Male; Obesity; Overweight; Prediabetic State; Prevalence

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

Longitudinal Responses to Weighing and Bathing Procedures in Preterm Infants. - Bembich, Stefano; Fiani, Giulia; Strajn, Tamara; Sanesi, Cecilia; Demarini, Sergio; Sanson, Gianfranco (J Perinat Neonatal Nurs, 2017)
Knowledge of the effects of nursing-induced stress on short-term outcomes in preterm infants is limited. Effects of 2 standard nursing procedures-weighing and bathing-on autonomic and motor stability of preterm infants were studied during their hospitalization. Outcomes were evaluated during and after the procedures. Eleven preterm infants were observed between 32 and 35 weeks' postmenstrual age (PMA) (postnatal days range: 4-63). Neonatal responses were assessed according to the Synactive Theory of Development and nursing was performed taking into account Newborn Individualized Developmental Care and Assessment Program (NIDCAP) principles. Effects of the studied nursing procedures on infants' stability during and after their execution were evaluated by nonparametric statistics. During monitored procedures, stress responses in autonomic and motor systems were observed at all PMAs. However, after 32 weeks' PMA, preterm infants also showed an autonomic and motor stability recovery 5 minutes after procedure completion. Contrary to our hypothesis, preterm infants showed to be stressed by weighing and bathing procedures up to 35 weeks' PMA. However, if facilitated and supported after nursing conclusion by interventions such as swaddling and nesting, according to NIDCAP principles, they recovered autonomic and motor stability by 5 minutes after ending procedures.
Keywords: Baths; Body Weight; Female; Humans; Infant Behavior; Infant Care; Infant, Newborn; Infant, Premature; Male; Neonatal Nursing

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

MCM8 and MCM9 Nucleotide Variants in Women With Primary Ovarian Insufficiency. - Desai, Swapna; Wood-Trageser, Michelle; Matic, Jelena; Chipkin, Jaqueline; Jiang, Huaiyang; Bachelot, Anne; Dulon, Jerome; Sala, Cinzia; Barbieri, Caterina; Cocca, Massimiliano; Toniolo, Daniela; Touraine, Philippe; et al. (J Clin Endocrinol Metab, 2017)
Objective: To assess the frequency of variants, including biallelic pathogenic variants, in minichromosome maintenance 8 (MCM8) and minichromosome maintenance 9 (MCM9), other genes related to MCM8-MCM9, and DNA damage repair (DDR) pathway in participants with primary ovarian insufficiency (POI). Design: MCM8, MCM9, and genes encoding DDR proteins that have been implicated in reproductive aging were sequenced among POI participants. Setting: Academic research institution. Participants: All were diagnosed with POI prior to age 40 years and presented with elevated follicle-stimulating hormone levels. Interventions: None. Main Outcome Measures: We identified nucleotide variants in MCM8, MCM9, and genes thought to be involved in the DNA damage response pathway and/or implicated in reproductive aging. Results: MCM8 was sequenced in 155 POI participants, whereas MCM9 was sequenced in 151 participants. Three of 155 (2%) participants carried possibly damaging heterozygous variants in MCM8, whereas 7 of 151 (5%) individuals carried possibly damaging heterozygous variants in MCM9. One participant carried a novel homozygous variant, c.1651C>T, p.Gln551*, in MCM9, which is predicted to introduce a premature stop codon in exon 9. Biallelic damaging heterozygous variants in both MCM8 and MCM9 were identified in 1 participant. Of a total of 10 participants carrying damaging heterozygous variants in either MCM8 or MCM9, 2 individuals carried heterozygous damaging variants in genes associated with either MCM8 or MCM9 or the DDR pathway. Conclusions: We identified a significant number of potentially damaging and novel variants in MCM8 and MCM9 among participants with POI and examined multiallelic association with variants in DDR and MCM8-MCM9 interactome genes.
Keywords: Adult; Aging; DNA Damage; DNA Repair; Female; Humans; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency; Sequence Analysis, DNA

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

"Milky" bowel and malrotation. - Poillucci, Gabriele; Degrassi, Ferruccio; Guida, Edoardo; Pederiva, Federica (Surgery, 2017)
Keywords: Appendectomy; Chylous Ascites; Digestive System Abnormalities; Follow-Up Studies; Humans; Infant, Newborn; Intestinal Volvulus; Laparotomy; Male; Rare Diseases; Severity of Illness Index; Tomography, X-Ray Computed; Treatment Outcome; Ultrasonography, Doppler

MRI in Postreduction Evaluation of Developmental Dysplasia of the Hip: Our Experience. - Dibello, Daniela; Odoni, Luca; Pederiva, Federica; Di Carlo, Valentina (J Pediatr Orthop, 2017)
BACKGROUND: Developmental dysplasia of the hip (DDH) is one of the most common congenital defects in the newborn. When its severe form is not corrected, it is associated with long-term morbidity. Closed reduction with casting is the standard primary treatment and reduction is confirmed by magnetic resonance imaging (MRI). We reported our experience on the reliability of MRI in postreduction assessment of DDH. METHODS: All children who underwent closed reduction for Graf type IV DDH at our institution between September 2010 and June 2016 were retrospectively reviewed. Since 2010 we assessed postreduction position of the femoral head by performing a MRI. RESULTS: Twenty-five (5 male, 20 female) patients presented with 29 (15 left sided, 6 right sided, 4 bilateral) Graf type IV DDH and underwent closed reduction at a mean age of 3.4 months. In all patients MRI studies performed within 24 hours were diagnostic, showing a concentric reduction of the femoral head within the acetabulum in 24/25 patients. In the patient with persistent hip instability, a subsequent open reduction was performed. In all the cases, there was no need of any contention or sedation during MRI. CONCLUSIONS: On the basis of our experience, MRI is an excellent, safe and, reliable modality to confirm maintenance of adequate femoral head position and to evaluate soft tissue interposition. We agree that MRI is the gold standard to early depict dislocation after closed reduction of DDH.

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

MYH9 gene mutations associated with bleeding. - Savoia, Anna; De Rocco, Daniela; Pecci, Alessandro (Platelets, 2017)
Keywords: Asymptomatic Diseases; Blood Platelets; Cell Size; Chromosomes, Human, Pair 22; Exons; Gene Expression; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Hemorrhage; Humans; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Platelet Count; Protein Domains; Severity of Illness Index; Thrombocytopenia

Natalizumab treatment of multiple sclerosis: new insights. - Delbue, Serena; Comar, Manola; Ferrante, Pasquale (Immunotherapy, 2017)
Natalizumab is a monoclonal antibody directed against the α4 chain of the very late activating antigen 4 and α4β7 integrins, present on the leukocytes surface, used as monotherapy for the treatment of relapsing-remitting multiple sclerosis. It substantially reduces relapse rate and the accumulation of disability, but its use is associated with a very adverse event, that is the development of progressive multifocal leukoencephalopathy, a fatal demyelinating disease of the CNS, due to the lytic replication of the human polyomavirus JC. The main focus of the review is to describe the newest insights on natalizumab, its current use in the clinical practice, the natalizumab-treated patients' management and the risk stratification related to the progressive multifocal leukoencephalopathy development.
Keywords: Animals; Drug-Related Side Effects and Adverse Reactions; Humans; Immunotherapy; Integrin alpha Chains; Integrin alpha4; Integrin beta Chains; JC Virus; Leukoencephalopathy, Progressive Multifocal; Multiple Sclerosis, Relapsing-Remitting; Natalizumab; Risk; Virus Activation; Virus Replication

Neuroimaging Changes in Menkes Disease, Part 1. - Manara, R; D'Agata, L; Rocco, M C; Cusmai, R; Freri, E; Pinelli, L; Darra, F; Procopio, E; Mardari, R; Zanus, C; Di Rosa, G; Soddu, C; et al. (AJNR Am J Neuroradiol, 2017)
Menkes disease is a rare multisystem X-linked disorder of copper metabolism. Despite an early, severe, and progressive neurologic involvement, our knowledge of brain involvement remains unsatisfactory. The first part of this retrospective and review MR imaging study aims to define the frequency rate, timing, imaging features, and evolution of intracranial vascular and white matter changes. According to our analysis, striking but also poorly evolutive vascular abnormalities characterize the very early phases of disease. After the first months, myelination delay becomes evident, often in association with protean focal white matter lesions, some of which reveal an age-specific brain vulnerability. In later phases of the disease, concomitant progressive neurodegeneration might hinder the myelination progression. The currently enriched knowledge of neuroradiologic finding evolution provides valuable clues for early diagnosis, identifies possible MR imaging biomarkers of new treatment efficacy, and improves our comprehension of possible mechanisms of brain injury in Menkes disease.
Keywords: Brain; Disease Progression; Female; Humans; Magnetic Resonance Imaging; Male; Menkes Kinky Hair Syndrome; Neuroimaging; Retrospective Studies; White Matter

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

A Novel Panel of Serum Biomarkers for MPM Diagnosis. - Bonotti, A; Foddis, R; Landi, S; Melaiu, O; De Santi, C; Giusti, L; Donadio, E; Ciregia, F; Mazzoni, M R; Lucacchini, A; Bovenzi, M; Comar, M; et al. (Dis Markers, 2017)
Exposure to asbestos is the main cause of malignant pleural mesothelioma (MPM), a highly aggressive cancer of the pleura. Since the only tools for early detection are based on radiological tests, some authors focused on serum markers (i.e., mesothelin). The aim of this study was the evaluation of new serum biomarkers to be used individually or in combination, in order to improve the outcome of patients whose disease would be diagnosed at an earlier stage. Serum and plasma were available from 43 subjects previously exposed to asbestos and 27 MPM patients, all being epithelioid type. All the new markers found differentially expressed in MPM and healthy subjects, by proteomic and genomic approaches, have been validated in the serum by the use of specific ELISA. The combined approach, using tools of genomics and proteomics, is found to be highly innovative for this type of disease and led to the identification of new serum markers in the diagnosis of MPM. These results, if confirmed in a larger series, may have a strong impact in this area, because early detection of this cancer in people at high risk could significantly improve the course of the disease and the clinical approach to an individualized therapy.
Keywords: Aged; Biomarkers, Tumor; Blood Proteins; Case-Control Studies; Female; Humans; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Proteome

Pediatric gastrointestinal bleeding: Perspectives from the Italian Society of Pediatric Gastroenterology. - Romano, Claudio; Oliva, Salvatore; Martellossi, Stefano; Miele, Erasmo; Arrigo, Serena; Graziani, Maria Giovanna; Cardile, Sabrina; Gaiani, Federica; de'Angelis, Gian Luigi; Torroni, Filippo (World J Gastroenterol, 2017)
There are many causes of gastrointestinal bleeding (GIB) in children, and this condition is not rare, having a reported incidence of 6.4%. Causes vary with age, but show considerable overlap; moreover, while many of the causes in the pediatric population are similar to those in adults, some lesions are unique to children. The diagnostic approach for pediatric GIB includes definition of the etiology, localization of the bleeding site and determination of the severity of bleeding; timely and accurate diagnosis is necessary to reduce morbidity and mortality. To assist medical care providers in the evaluation and management of children with GIB, the "Gastro-Ped Bleed Team" of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP) carried out a systematic search on MEDLINE PubMed (http://www.ncbi.nlm.nih.gov/pubmed/) to identify all articles published in English from January 1990 to 2016; the following key words were used to conduct the electronic search: "upper GIB" and "pediatric" [all fields]; "lower GIB" and "pediatric" [all fields]; "obscure GIB" and "pediatric" [all fields]; "GIB" and "endoscopy" [all fields]; "GIB" and "therapy" [all fields]. The identified publications included articles describing randomized controlled trials, reviews, case reports, cohort studies, case-control studies and observational studies. References from the pertinent articles were also reviewed. This paper expresses a position statement of SIGENP that can have an immediate impact on clinical practice and for which sufficient evidence is not available in literature. The experts participating in this effort were selected according to their expertise and professional qualifications.
Keywords: Adolescent; Child; Child, Preschool; Diagnostic Imaging; Endoscopy; Gastroenterology; Gastrointestinal Diseases; Gastrointestinal Hemorrhage; Hemodynamics; Humans; Infant; Infant, Newborn; Italy; Pediatrics; Recurrence; Societies, Medical

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature. - Travan, Laura; Naviglio, Samuele; De Cunto, Angela; Pellegrin, Andrea; Pecile, Vanna; Spinelli, Alessandro Mauro; Cappellani, Stefania; Faletra, Flavio (Am J Med Genet A, 2017)
The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were reviewed and compared to our patient, highlighting the common features of a possible 19q13.32 microdeletion syndrome.

Predictors of Relapse after Discontinuing Systemic Treatment in Childhood Autoimmune Chronic Uveitis. - Simonini, Gabriele; Bracaglia, Claudia; Cattalini, Marco; Taddio, Andrea; Brambilla, Alice; de Libero, Cinzia; Pires Marafon, Denise; Caputo, Roberto; Cimaz, Rolando (J Rheumatol, 2017)
OBJECTIVE: To identify clinical predictors of relapse in childhood autoimmune chronic uveitis after stopping systemic treatment. METHODS: A retrospective, multicenter, cohort study. RESULTS: Ninety-four children in remission, receiving no treatments and with at least a 6-month followup, were enrolled. A higher probability of maintaining remission after discontinuing treatment was shown in idiopathic compared with juvenile idiopathic arthritis uveitis (Mantel-Cox chi-square = 23.21) if inactivity had been obtained within 6 months from starting systemic treatment (Mantel-Cox chi-square = 24.17) and by antitumor necrosis factor-α treatment (Mantel-Cox chi-square = 6.43). CONCLUSION: Type of disease, time, and type of systemic therapy to achieve inactivity predict different duration of uveitis remission after treatment withdrawal.
Keywords: Adolescent; Antirheumatic Agents; Autoimmune Diseases; Child; Child, Preschool; Female; Humans; Male; Predictive Value of Tests; Recurrence; Retrospective Studies; Treatment Outcome; Uveitis; Withholding Treatment

Pregnant with HIV before age 25: data from a large national study in Italy, 2001-2016. - Floridia, M; Masuelli, G; Tamburrini, E; Cetin, I; Liuzzi, G; Martinelli, P; Guaraldi, G; Spinillo, A; Vimercati, A; Maso, G; Pinnetti, C; Frisina, V; et al. (Epidemiol Infect, 2017)
Young pregnant women with HIV may be at significant risk of unplanned pregnancy, lower treatment coverage, and other adverse pregnancy outcomes. In a large cohort of pregnant women with HIV in Italy, among 2979 pregnancies followed in 2001-2016, 9·0% were in women <25 years, with a significant increase over time (2001-2005: 7·0%; 2006-2010: 9·1%; 2011-2016: 12·2%, P < 0·001). Younger women had a lower rate of planned pregnancy (23·2% vs. 37·7%, odds ratio (OR) 0·50, 95% confidence interval (CI) 0·36-0·69), were more frequently diagnosed with HIV in pregnancy (46·5% vs. 20·9%, OR 3·29, 95% CI 2·54-4·25), and, if already diagnosed with HIV before pregnancy, were less frequently on antiretroviral treatment at conception (<25 years: 56·3%; ⩾25 years: 69·0%, OR 0·58, 95% CI 0·41-0·81). During pregnancy, treatment coverage was almost universal in both age groups (98·5% vs. 99·3%), with no differences in rate of HIV viral suppression at third trimester and adverse pregnancy outcomes. The data show that young women represent a growing proportion of pregnant women with HIV, and are significantly more likely to have unplanned pregnancy, undiagnosed HIV infection, and lower treatment coverage at conception. During pregnancy, antiretroviral treatment, HIV suppression, and pregnancy outcomes are similar compared with older women. Earlier intervention strategies may provide additional benefits in the quality of care for women with HIV.
Keywords: Adolescent; Cohort Studies; Female; HIV Infections; Humans; Italy; Odds Ratio; Pregnancy; Young Adult

Preoperative Serum Human Epididymis Protein 4 Levels in Early Stage Endometrial Cancer: A Prospective Study. - Fanfani, Francesco; Restaino, Stefano; Cicogna, Stefania; Petrillo, Marco; Montico, Marcella; Perrone, Emanuele; Radillo, Oriano; De Leo, Rossella; Ceccarello, Matteo; Scambia, Giovanni; Ricci, Giuseppe (Int J Gynecol Cancer, 2017)
OBJECTIVE: The aim of the study was to evaluate the prognostic value of human epididymis protein 4 (HE4) and cancer antigen 125 markers with pathological prognostic factor to complete the preoperative clinical panel and help the treatment planning. METHODS: This prospective multicenter study was conducted in 2 gynecologic oncology centers between 2012 and 2014 (Institute for Maternal and Child Health IRCCS Burlo Garofolo in Trieste and Catholic University of the Sacred Heart in Rome, Italy). We enrolled 153 patients diagnosed with clinical early (International Federation of Gynecology and Obstetrics stages I-II) type I endometrial cancer. RESULTS: Human epididymis protein 4 levels seemed to be strictly related to age (P < 0.001) and menopausal status (P < 0.002). Compared with myometrial invasion (MI), the HE4 values were significantly higher in case of invasion of greater than 50% of the thickness: MI of greater than 50%, median of 94.85 pmol/L (38.3-820.8 pmol/L), versus MI of less than 50%, median of 65.65 pmol/L (25.1-360.2 pmol/L), (P < 0.001). The HE4 levels increase significantly with increasing tumor size: diameter of larger than 2 cm, median of 86.9 pmol/L (35.8-820.8 pmol/L), versus diameter of smaller than 2 cm, median of 52.2 pmol/L (33.3-146.8 pmol/L), (P < 0.001). In our population, HE4 did not correlate with the histological grade, endometrial cancer type I versus type II (P = 0.86), the lymphovascular infiltration (P = 0.12), and the cervical invasion (P = 0.6). We established a new variable, considering 3 high-risk tumor features: MI of greater than 50% and/or histological G3 and/or type II. Human epididymis protein 4 levels significantly increase in high-risk tumors (high risk HE4, 93.6 pmol/L vs low-medium risk, 65.5 pmol/L; P < 0.001). CONCLUSIONS: A preoperative HE4 evaluation could help stratify patients with deep invasion and/or metastatic disease and is correlated with other relevant prognostic factors to be considered to tailor an adequate surgical strategy.
Keywords: Adult; Aged; Aged, 80 and over; Biomarkers, Tumor; Endometrial Neoplasms; Female; Humans; Middle Aged; Neoplasm Staging; Preoperative Care; Prognosis; Prospective Studies; Proteins

Puzzling Results from Germline Mutations Analysis in a Group of Asbestos-Exposed Patients in a High-risk Area of Northeast Italy. - Rizzardi, Clara; Athanasakis, Emmanouil; Cammisuli, Francesca; Monego, Simeone Dal; DE Spelorzi, Yeraldin Chiquinquira Castillo; Costantinides, Fulvio; Giudici, Fabiola; Pinamonti, Maurizio; Canzonieri, Vincenzo; Melato, Mauro; Pascolo, Lorella (Anticancer Res, 2017)
BACKGROUND: Germline mutations of the oncosuppressor gene breast cancer 1-associated protein 1 (BAP1) were recently related to an autosomal-dominant tumor predisposition syndrome (BAP1-TPDS), characterized by uveal melanoma, malignant mesothelioma (MM), cutaneous melanoma, and other malignancies. The demonstration that BAP1 mutations are strongly associated with MM has provided a real breakthrough in the study of genetic predisposition in MM, that may explain why only a fraction of asbestos-exposed individuals go on to develop MM. MATERIALS AND METHODS: To evaluate the possible role of BAP1 mutations in the epidemiology of sporadic MM, and their relationship with asbestos exposure, we determined the prevalence of germline BAP1 mutations by the Sanger method in a group of 29 asbestos-exposed patients, 21 of which were diagnosed with MM. They were residents of Trieste, a ship-building town in Northeast Italy with a very high incidence of mesothelioma. RESULTS: We identified non-obviously pathogenetic germline sequence variants of BAP1 in 3/29 patients and in 2/21 MM cases (10%). CONCLUSION: Non obviously pathogenic germline sequence variants of BAP1 were found. Nevertheless, limitations of predictive web tools allowed us to comment on some interesting peculiarities of our findings.
Keywords: Aged; Aged, 80 and over; Asbestos; Environmental Exposure; Female; Germ-Line Mutation; Humans; Italy; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Risk; Tumor Suppressor Proteins; Ubiquitin Thiolesterase

Qualitative questionnaire on the psychosocial wellbeing of mothers of children with BEEC. - Di Grazia, Massimo; Pellizzoni, Sandra; Tonegatti, Luca Giacomo; Rigamonti, Waifro (J Pediatr Urol, 2017)
INTRODUCTION: The bladder exstrophy-epispadias complex (BEEC) represents a spectrum of malformations that affect the anatomical and functional structure of the urogenital system. The parents of patients affected by this condition are subject to particularly stressful situations, such as worrying about their child's health, long hospital stays, concerns about the health and constant need for personal care for their children, that can profoundly compromise the quality of family life. OBJECTIVE: The objective of this explorative qualitative study is to evaluate the social situation and the psychological strategies implemented by the mothers of children between 6 and 10 years of age who are affected by BEEC. STUDY DESIGN: Fourteen mothers of children aged 6-10 years and affected by BEEC (9 boys and 5 girls) were interviewed. Data on the mothers' experiences were collected through semi-structured interviews (Table). RESULTS: The qualitative analysis of the interviews showed that participants described experiences that were characterised by emotions such as fear and anger. Each mother had implemented a different and, sometimes, dysfunctional strategy in order to cope with the complex situation of the son/daughter. The aspects that most clearly emerged from mothers' descriptions were (1) the traumatic situation at the birth of the baby, (2) the sense of embarrassment concerning the pathological condition as the child was growing and the consequent sense of isolation of the mother, and (3) the fluctuation of feelings towards the multidisciplinary staff, which was sometimes seen as an important source of help and some other times as too destabilising and not helpful at all. DISCUSSION: The study provided some insight into the psychological and social conditions experienced by mothers of children with BEEC, which could serve as a basis for developing multidisciplinary teams with greater awareness about families living with this condition and better timing in addressing their needs. CONCLUSIONS: Mothers of children with BEEC show emotional and social difficulties. This is a crucial aspect to consider when planning a multidisciplinary approach to the treatment/therapy, especially considering that children examined in this study are approaching adolescence.
Keywords: Adaptation, Psychological; Adolescent; Bladder Exstrophy; Child; Epispadias; Female; Humans; Long-Term Care; Male; Mother-Child Relations; Mothers; Qualitative Research; Quality of Life; Stress, Psychological; Surveys and Questionnaires; Treatment Outcome

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rate, correlates and outcomes of repeat pregnancy in HIV-infected women. - Floridia, M; Tamburrini, E; Masuelli, G; Martinelli, P; Spinillo, A; Liuzzi, G; Vimercati, A; Alberico, S; Maccabruni, A; Pinnetti, C; Frisina, V; Dalzero, S; et al. (HIV Med, 2017)
OBJECTIVES: The aim of the study was to assess the rate, determinants, and outcomes of repeat pregnancies in women with HIV infection. METHODS: Data from a national study of pregnant women with HIV infection were used. Main outcomes were preterm delivery, low birth weight, CD4 cell count and HIV plasma viral load. RESULTS: The rate of repeat pregnancy among 3007 women was 16.2%. Women with a repeat pregnancy were on average younger than those with a single pregnancy (median age 30 vs. 33 years, respectively), more recently diagnosed with HIV infection (median time since diagnosis 25 vs. 51 months, respectively), and more frequently of foreign origin [odds ratio (OR) 1.36; 95% confidence interval (CI) 1.10-1.68], diagnosed with HIV infection in the current pregnancy (OR: 1.69; 95% CI: 1.35-2.11), and at their first pregnancy (OR: 1.33; 95% CI: 1.06-1.66). In women with sequential pregnancies, compared with the first pregnancy, several outcomes showed a significant improvement in the second pregnancy, with a higher rate of antiretroviral treatment at conception (39.0 vs. 65.4%, respectively), better median maternal weight at the start of pregnancy (60 vs. 61 kg, respectively), a higher rate of end-of-pregnancy undetectable HIV RNA (60.7 vs. 71.6%, respectively), a higher median birth weight (2815 vs. 2885 g, respectively), lower rates of preterm delivery (23.0 vs. 17.7%, respectively) and of low birth weight (23.4 vs. 15.4%, respectively), and a higher median CD4 cell count (+47 cells/μL), with almost no clinical progression to Centers for Disease Control and Prevention stage C (CDC-C) HIV disease (0.3%). The second pregnancy was significantly more likely to end in voluntary termination than the first pregnancy (11.4 vs. 6.1%, respectively). CONCLUSIONS: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Emigrants and Immigrants; Female; HIV Infections; HIV-1; Humans; Infant, Low Birth Weight; Pregnancy; Premature Birth; Viral Load

Retrospective study on the incidence and outcome of proven and probable invasive fungal infections in high-risk pediatric onco-hematological patients. - Cesaro, Simone; Tridello, Gloria; Castagnola, Elio; Calore, Elisabetta; Carraro, Francesca; Mariotti, Ilaria; Colombini, Antonella; Perruccio, Katia; Decembrino, Nunzia; Russo, Giovanna; Maximova, Natalia; Baretta, Valentina; et al. (Eur J Haematol, 2017)
BACKGROUND: Invasive fungal infection (IFI) is a cause of morbidity, mortality and increased health costs in children undergoing chemotherapy or hematopoietic stem cell transplant (HSCT). METHODS: Multicenter, retrospective study to assess the incidence, outcome of proven and probable IFI (PP-IFI) in children treated for acute leukemia, non-Hodgkin lymphoma or who underwent HSCT from 2006 to 2012. RESULTS: Over the 7-year period, 127 PP-IFI were diagnosed in 123 patients, median age of 9.7 years. The 1-year cumulative incidence was 2.5% (CI 1.8-3.7) after frontline chemotherapy, 9.4% (CI 5.8-15.0) after relapse, and 5.3% (CI 3.9-7.1) after HSCT. Severe neutropenia was present in 98 (77%) patients. Culture-proven agents were Candida spp., mostly non-albicans, 28, mold 23, whereas three proven IFI were identified by histopathology. Favorable response to treatment within 3 months from diagnosis was observed in 77 (89%). The overall ninety-day probability of survival was 68% (CI 59-76). CONCLUSIONS: About two-thirds of pediatric patients with PP-IFI survived, regardless of whether the infection occurred after frontline chemotherapy, reinduction chemotherapy for disease relapse, or after HSCT. Further prospective studies are needed to define the impact of antifungal prophylaxis and early combination therapy on short-term overall survival.
Keywords: Adolescent; Antifungal Agents; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Drug Therapy, Combination; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Incidence; Male; Mycoses; Patient Outcome Assessment; Retrospective Studies; Survival Analysis; Treatment Outcome

Review on the role of the human Polyomavirus JC in the development of tumors. - Delbue, Serena; Comar, Manola; Ferrante, Pasquale (Infect Agent Cancer, 2017)
Almost one fifth of human cancers worldwide are associated with infectious agents, either bacteria or viruses, and this makes the possible association between infections and tumors a relevant research issue. We focused our attention on the human Polyomavirus JC (JCPyV), that is a small, naked DNA virus, belonging to the family. It is the recognized etiological agent of the Progressive Multifocal Leukoencephalopathy (PML), a fatal demyelinating disease, occurring in immunosuppressed individuals. JCPyV is able to induce cell transformation in vitro when infecting non-permissive cells, that do not support viral replication and JCPyV inoculation into small animal models and non human primates drives to tumor formation. The molecular mechanisms involved in JCPyV oncogenesis have been extensively studied: the main oncogenic viral protein is the large tumor antigen (T-Ag), that is able to bind, among other cellular factors, both Retinoblastoma protein (pRb) and p53 and to dysregulate the cell cycle, but also the early proteins small tumor antigen (t-Ag) and Agnoprotein appear to cooperate in the process of cell transformation. Consequently, it is not surprising that JCPyV genomic sequences and protein expression have been detected in Central Nervous System (CNS) tumors and colon cancer and an association between this virus and several brain and non CNS-tumors has been proposed. However, the significances of these findings are under debate because there is still insufficient evidence of a casual association between JCPyV and solid cancer development. In this paper we summarized and critically analyzed the published literature, in order to describe the current knowledge on the possible role of JCPyV in the development of human tumors.

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Shifts of subgingival bacterial population after nonsurgical and pharmacological therapy of localized aggressive periodontitis, followed for 1 year by Ion Torrent PGM platform. - Campisciano, Giuseppina; Toschetti, Annamaria; Comar, Manola; Taranto, Rosanna Di; Berton, Federico; Stacchi, Claudio (Eur J Dent, 2017)
The possibility of targeting the hypervariable region V3 of the 16S rRNA gene using Ion Torrent Personal Genome Machine (PGM) could provide a complete analysis of subgingival plaque samples, potentially able to identify microbiological species missed by culture-based methods. A 16-year-old female smoker patient, affected by localized aggressive periodontitis, underwent a full-mouth disinfection protocol and was inserted in a 3-month recall program. Microbiological samples were collected at baseline and at 30, 100, 365 days follow-up and analyzed by Ion Torrent PGM. , , , and were the most represented pathogens at baseline. Nonsurgical treatment and systemic antibiotics drastically lowered the anaerobic species, and their presence remained limited after 100 days, while a consistent recolonization by anaerobic bacteria was detected at 365 days. The patient showed a general improvement of periodontal conditions. Differently from polymerase chain reaction and other microarray techniques, Ion Torrent performs a quantitative analysis of the microbiota, irrespective of the searched species. An accurate definition of the shifts of the bacterial community might help periodontal researchers for a better understanding of the impact of different treatment approaches or in intercepting nonresponsive conditions.

Subclinical alteration of the cervical-vaginal microbiome in women with idiopathic infertility. - Campisciano, Giuseppina; Florian, Fiorella; D'Eustacchio, Angela; Stanković, David; Ricci, Giuseppe; De Seta, Francesco; Comar, Manola (J Cell Physiol, 2017)
Biomarkers have a wide application in research and clinic, they help to choose the correct treatment for diseases. Recent studies, addressing the vaginal microbiome using next generation sequencing (NGS), reported the involvement of bacterial species in infertility. We compared the vaginal microbiome of idiopathic infertile women with that of healthy, including bacterial vaginosis affected women and non-idiopathic infertile women, to identify bacterial species suitable as biomarkers. Information on microorganisms was obtained from the V3-16S rDNA sequencing of cervical-vaginal fluids of 96 women using the Ion Torrent platform. Data were processed with QIIME and classified against the Vaginal 16S rDNA Reference Database. The analysis revealed a significant beta-diversity variation (p < 0.001) between the four groups included in the study. L. iners, L. crispatus, and L. gasseri distinguished idiopathic infertile women from the other groups. In these women, a microbial profile similar to that observed in bacterial vaginosis women has been detected. Our results suggest that the quantitative assessment and identification of specific microorganisms of the cervical-vaginal microflora could increase the accuracy of available tools for the diagnosis of infertility and improve the adoption of therapeutic protocols.
Keywords: Adult; Biodiversity; Cervix Uteri; Cohort Studies; Demography; Female; Humans; Infertility, Female; Microbiota; Species Specificity; Vagina; Vaginosis, Bacterial

Surgery for distal hypospadias: what about the catheter? - Scarpa, Maria-Grazia; Perin, Giordano; Di Grazia, Massimo; Codrich, Daniela; Pederiva, Federica; Guida, Edoardo; Lembo, Maria Antonietta; Giannotta, Antonio; Schleef, Jurgen (Pediatr Med Chir, 2017)
No agreed recommendations exist for timing of urethral stent removal, after distal hypospadias surgery. We compared our preliminary case series with outcomes from literature: 18/44 patients were treated with catheter and 26/44 without it. The surgical outcome was comparable in the two groups. After hypospadias surgery, the main advantage of the immediate postoperative catheter removal was the shorter hospital stay without negatively affecting the care and home management.
Keywords: Child; Child, Preschool; Device Removal; Humans; Hypospadias; Infant; Length of Stay; Male; Retrospective Studies; Stents; Treatment Outcome; Urinary Catheterization

SV40 Infection of Mesenchymal Stromal Cells From Wharton's Jelly Drives the Production of Inflammatory and Tumoral Mediators. - Cason, Carolina; Campisciano, Giuseppina; Zanotta, Nunzia; Valencic, Erica; Delbue, Serena; Bella, Ramona; Comar, Manola (J Cell Physiol, 2017)
The Mesenchymal Stromal Cells from umbilical cord Wharton's jelly (WJSCs) are a source of cells with high potentiality for the treatment of human immunological disorders. Footprints of the oncogenic viruses Simian Virus 40 (SV40) and JC Virus (JCPyV) have been recently detected in human WJSCs specimens. The aim of this study is to evaluate if WJSCs can be efficiently infected by these Polyomaviruses and if they can potentially exert tumoral activity. Cell culture experiments indicated that WJSCs could sustain both SV40 and JCPyV infections. A transient and lytic replication was observed for JCPyV, while SV40 persistently infected WJSCs over a long period of time, releasing a viral progeny at low titer without evident cytopathic effect (CPE). Considering the association between SV40 and human tumors and the reported ability of the oncogenic viruses to drive the host innate immune response to cell transformation, the expression profile of a large panel of immune mediators was evaluated in supernatants by the Bioplex platform. RANTES, IL-3, MIG, and IL-12p40, involved in chronic inflammation, cells differentiation, and transformation, were constantly measured at high concentration comparing to control. These findings represent a new aspect of SV40 biological activity in the humans, highlighting its interaction with specific host cellular pathways. In view of these results, it seems to be increasingly urgent to consider Polyomaviruses in the management of WJSCs for their safely use as promising therapeutic source. J. Cell. Physiol. 232: 3060-3066, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: Cell Line, Transformed; Cell Separation; Cell Transformation, Viral; Chemokine CCL5; Chemokine CXCL9; Cytopathogenic Effect, Viral; DNA, Viral; Host-Pathogen Interactions; Humans; Inflammation Mediators; Interleukin-12 Subunit p40; Interleukin-3; JC Virus; Mesenchymal Stem Cells; Real-Time Polymerase Chain Reaction; Simian virus 40; Time Factors; Up-Regulation; Viral Load; Virus Replication; Wharton Jelly

Theophylline increases diaphragmatic contractility in mechanically ventilated newborns. - De Cunto, Angela; Paviotti, Giulia; Bua, Jenny; Demarini, Sergio (J Crit Care, 2017)
Keywords: Diaphragm; Humans; Infant, Newborn; Muscle Contraction; Theophylline

Towards measles elimination in Italy: Virological surveillance and genotypes trend (2013-2015). - Magurano, Fabio; Baggieri, Melissa; Filia, Antonietta; Del Manso, Martina; Lazzarotto, Tiziana; Amendola, Antonella; D'Agaro, Pierlanfranco; Chironna, Maria; Ansaldi, Filippo; Iannazzo, Stefania; Bucci, Paola; Marchi, Antonella; et al. (Virus Res, 2017)
In accordance with the goal of the World Health Organization Regional Office for Europe, the Italian National Measles and Rubella Elimination Plan aimed to interrupt indigenous measles transmission in Italy by the end of 2015. However, from 2013 to 2015, Italy experienced high measles burden with 4902 measles cases (49.3% laboratory-confirmed) reported to the enhanced measles surveillance system (cumulative incidence in the triennium reference period: 2.4/100,000 population). The measles elimination goal was not reached. Laboratory surveillance of measles circulating genotypes is performed by the Measles and Rubella National Reference Laboratory (NRL) at the Italian National Institute of Health (Istituto Superiore di Sanità - ISS), in Rome. Samples received from 1 January 2013-31 December 2015 were analysed. Those positive for measles genome by molecular tests were sequenced and phylogenetically analysed. Phylogenetic analysis performed by NRL identified that genotypes D4 and D8 were endemic and co-circulated in 2011-2013: study results show that genotype D4 disappeared during 2013. Sporadic cases were associated to genotype B3 during 2011-2013, which became endemic in Italy during 2014 and co-circulated with D8 until 2015. Sporadic cases were found belonging to genotypes D9 and H1 all over the period in exam. Similar trend has been observed in European WHO Region.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Disease Outbreaks; Female; Genotype; Humans; Infant; Italy; Male; Measles; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny; RNA, Viral; Sentinel Surveillance; Young Adult

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Zika virus induces inflammasome activation in the glial cell line U87-MG. - Tricarico, Paola Maura; Caracciolo, Ilaria; Crovella, Sergio; D'Agaro, Pierlanfranco (Biochem Biophys Res Commun, 2017)
In the last years, neurological complications related to Zika virus (ZIKV) infection have emerged as an important threat to public health worldwide. ZIKV infection has been associated to neurological disorders such as congenital microcephaly in newborns and Guillain-Barré syndrome, myelopathy and encephalitis in adults. ZIKV is characterized by neurotropism and neurovirulence. Several studies have identified microglial nodules, gliosis, neuronal and glial cells degeneration and necrosis in the brain of ZIKV infected infants, suggesting that ZIKV could play a role in these neurological disorders through neuroinflammation and microglial activation. Little information is available about neuroinflammation and ZIKV-related neurological disorders. Therefore, we investigated if ZIKV is able to infect a glial cell line (U87-MG) and how the glial cell line responds to this infection in terms of inflammation (IL-1β, NLRP-3 and CASP-1), oxidative stress (SOD2 and HemeOX) and cell death. We observed a significant increase of ZIKV load in both cells and supernatants after 72 h, compared to 48 h of infection. We found that ZIKV infection induces an increase of IL-1β, NLRP-3 and CASP-1 genes expression. Significant increase of IL-1β and unchanged pro-IL-1β protein levels have also been detected. Moreover, we observed SOD2 and HemeOX increased gene expression mainly after 72 h post ZIKV infection. Subsequently, we found a decrease of U87-MG cell viability, after both 48 h and 72 h of ZIKV infection. Our results show that U87-MG cells are susceptible to ZIKV infection. ZIKV is able to successfully replicate in infected cells causing oxidative stress, NLRP3 inflammasome activation and subsequent release of mature IL-1β; this process culminates in cell death. Thus, considering the central role of neuroinflammation in neurological disorders, it is important to comprehend every aspect of this mechanism in order to better understand the pathogenesis of ZIKV infection and to identify possible strategies to fight the virus by rescuing cell death.
Keywords: Apoptosis; Cell Line; Cytokines; Humans; Immunity, Innate; Inflammasomes; Inflammation Mediators; Neuroglia; Oxidative Stress; Virus Replication; Zika Virus

Achieving effective hearing aid fitting within one month after identification of childhood permanent hearing impairment. - Bastanza, G; Gallus, R; De Carlini, M; Picciotti, P M; Muzzi, E; Ciciriello, E; Orzan, E; Conti, G (Acta Otorhinolaryngol Ital, 2016)
Diagnosis of child permanent hearing impairment (PHI) can be made with extreme timeliness compared to the past thanks to improvements in PHI identification through newborn hearing screening programmes. It now becomes essential to provide an effective amplification as quickly as possible in order to restore auditory function and favour speech and language development. The early fitting of hearing aids and possible later cochlear implantation indeed prompts the development of central auditory pathways, connections with secondary sensory brain areas, as well as with motor and articulatory cortex. The aim of this paper is to report the results of a strategic analysis that involves identification of strengths, weaknesses, opportunities and threats regarding the process of achieving early amplification in all cases of significant childhood PHI. The analysis is focused on the Italian situation and is part of the Italian Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children".

Action of methotrexate and tofacitinib on directly stimulated and bystander-activated lymphocytes. - Piscianz, Elisa; Candilera, Vanessa; Valencic, Erica; Loganes, Claudia; Paron, Greta; De Iudicibus, Sara; Decorti, Giuliana; Tommasini, Alberto (Mol Med Rep, 2016)
Chronic inflammation associated with autoimmune activation is characteristic of rheumatic diseases from childhood to adulthood. In recent decades, significant improvements in the treatment of these types of disease have been achieved using disease modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) and, more recently, using biologic inhibitors. The recent introduction of kinase inhibitors (for example, tofacitinib; Tofa) further increases the available ARDs. However, there are patients that do not respond to any treatment strategies, for whom combination therapies are proposed. The data regarding the combined action of different drugs is lacking and the knowledge of the mechanisms of ARDs and their actions upon pathogenic lymphocytes, which are hypothesized to sustain disease, is poor. An in vitro model of inflammation was developed in the current study, in which stimulated and unstimulated lymphocytes were cultured together, but tracked separately, to investigate the action of MTX and Tofa on the two populations. By analysing lymphocyte proliferation and activation, and cytokine secretion in the culture supernatants, it was established that, due to the presence of activated cells, unstimulated cells underwent a bystander activation that was modulated by the ARDs. Additionally, varying administration schedules were demonstrated to affect lymphocytes differently in vitro, either directly or via bystander activation. Furthermore, MTX and Tofa exerted different effects; while MTX showed an antiproliferative effect, Tofa marginally effected activation, although only a slight antiproliferative action, which could be potentiated by sequential treatment with MTX. Thus, it was hypothesized that these differences may be exploited in sequential therapeutic strategies, to maximize the anti‑rheumatic effect. These findings are notable and must be accounted for, as bystander‑activated cells in vivo could contribute to the spread of autoimmune activation and disease progression.

Acute myelitis as presenting symptom of HIV-HTLV-1 co-infection. - Cucca, A; Stragapede, L; Antonutti, L; Catalan, M; Caracciolo, I; Valentinotti, Romina; Granato, A; D'Agaro, P; Manganotti, P (J Neurovirol, 2016)
A 21-year-old woman presented with acute-onset spastic paraparesis. The MRI spinal scan revealed a contrast-enhanced T2 hyperintensity between C5-T2. The most common neurotropic pathogens were excluded by first level tests. Under suspicion of an acute immune-mediated myelitis, a corticosteroid therapy was administered. However, a seropositivity for both human immunodeficiency virus (HIV) type 1 and human T-lymphotropic virus (HTLV) subsequently emerged. An antiretroviral therapy was started while steroids discontinued. Patient's clinical conditions remained unchanged. HIV-HTLV-1 co-infection should be included in the differential diagnosis of any acute myelitis, even in patients with a preserved immune status and no risk factors.

An Animal Model for the Juvenile Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis. - Marin, Veronica; Rosso, Natalia; Dal Ben, Matteo; Raseni, Alan; Boschelle, Manuela; Degrassi, Cristina; Nemeckova, Ivana; Nachtigal, Petr; Avellini, Claudio; Tiribelli, Claudio; Gazzin, Silvia (PLoS One, 2016)
Non Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH) are the hepatic manifestations of the metabolic syndrome; worrisome is the booming increase in pediatric age. To recreate the full spectrum of juvenile liver pathology and investigate the gender impact, male and female C57Bl/6 mice were fed with high fat diet plus fructose in the drinking water (HFHC) immediately after weaning (equal to 3-years old human), and disease progression followed for 16 weeks, until adults (equal to 30-years old human). 100% of subjects of both genders on HFHC diet developed steatosis in 4weeks, and some degree of fibrosis in 8weeks, with the 86% of males and 15% of females presenting a stage 2 fibrosis at 16weeks. Despite a similar final liver damage both groups, a sex difference in the pathology progression was observed. Alterations in glucose homeostasis, dyslipidemia, hepatomegaly and obese phenotype were evident from the very beginning in males with an increased hepatic inflammatory activity. Conversely, such alterations were present in females only at the end of the HFHC diet (with the exception of insulin resistance and the hepatic inflammatory state). Interestingly, only females showed an altered hepatic redox state. This juvenile model appears a good platform to unravel the underlying gender dependent mechanisms in the progression from NAFLD to NASH, and to characterize novel therapeutic approaches.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

Association between p21 Ser31Arg polymorphism and the development of cervical lesion in women infected with high risk HPV. - Lima, Géssica; Santos, Erinaldo; Angelo, Hildson; Oliveira, Micheline; Heráclio, Sandra; Leite, Fernanda; de Melo, Celso; Crovella, Sergio; Maia, Maria; Souza, Paulo (Tumour Biol, 2016)
Infection by high-risk human papillomavirus (HR-HPV) and single nucleotide polymorphism (SNP) in genes involved in cell cycle control, as p21 and p27, are important factors in the development of different types of human cancers. This study aims at investigating whether both the p21 Ser31Arg and p27 V109G polymorphisms are associated with susceptibility to the development of cervical lesions in women HR-HPV positive. We analyzed 132 women HPV positive and with cervical lesions or CC and 154 healthy control (HPV negative and without cervical lesions). p21 Ser31Arg and p27 V109G polymorphisms were analyzed using the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method and sequencing. The p21 31Arg allele was associated with susceptibility for the development of cervical lesions (P* = 0.0009), while p27 V109G polymorphism showed no significant differences for this association (P* = 0.89). However, the combined effect of the polymorphisms showed that the presence of the CC genotype (SNP p21 Ser31Arg) conferred protection for the development of cervical lesions (OR = 0.39). p21 Ser31Arg and p27 V109G polymorphisms were not associated with the grade of cervical lesions (CINI, CINII, and CINIII) or CC (P* > 0.05). The HR-HPV more frequent in this study were of 16 (57.6 %) and 18 (37.1 %) types; however, no association was observed when both polymorphisms and risk factors analyzed were compared (P* > 0.05). Our findings suggest a possible association between p21 Ser31tabArg polymorphism and susceptibility to the development of cervical lesions in women from Pernambuco. Brazil.

Body mass index curves for Italian preterm infants are comparable with American curves for infants born before 34 weeks of gestational age. - Paviotti, Giulia; Monasta, Lorenzo; Ronfani, Luca; Montico, Marcella; Copertino, Marco; De Cunto, Angela; Demarini, Sergio (Acta Paediatr, 2016)
AIM: Body mass index (BMI)-for-age curves have been developed in the USA, but not compared with other populations. This study created gender-specific intrauterine BMI-for-age curves for Italian preterm infants and compared them with the USA version. METHODS: Data on 92 262 newborn infants, born at 26-42 weeks of gestational age in the north-eastern Italian region of Friuli Venezia Giulia between 2005 and 2013, were analysed to create gender-specific BMI-for-age curves. Gender-specific and age-specific BMI Z scores for Italian infants were calculated using the parameters of the USA growth curves and the World Health Organization charts. RESULTS: Gender-specific BMI-for-age at birth curves were developed for premature Italian infants from 26 gestational weeks. The comparison with the USA charts showed no significant difference in BMI percentiles in Italian infants born at ≤33 gestational weeks, but infants born at ≥34 gestational weeks had a significantly higher BMI than the USA population, by 0.2 standard deviations. CONCLUSION: We developed the first European BMI-for-age at birth curves for premature infants. According to our findings, the Italian curves were comparable to the USA curves for the subgroup of infants born at ≤33 gestational weeks, but not ≥34 gestational weeks.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

Carbamazepine-induced thrombocytopenic purpura in a child: Insights from a genomic analysis. - Abate, Maria Valentina; Stocco, Gabriele; Devescovi, Raffaella; Carrozzi, Marco; Pierobon, Chiara; Valencic, Erica; Lucafò, Marianna; Di Silvestre, Alessia; d'Adamo, Pio; Tommasini, Alberto; Decorti, Giuliana; Ventura, Alessandro (Blood Cells Mol Dis, 2016)

CCR2 and CCR5 genes polymorphisms in women with cervical lesions from Pernambuco, Northeast Region of Brazil: a case-control study. - Santos, Erinaldo Ubirajara Damasceno Dos; Lima, Géssica Dayane Cordeiro de; Oliveira, Micheline de Lucena; Heráclio, Sandra de Andrade; Silva, Hildson Dornelas Angelo da; Crovella, Sergio; Maia, Maria de Mascena Diniz; Souza, Paulo Roberto Eleutério de (Mem Inst Oswaldo Cruz, 2016)
Polymorphisms in chemokine receptors play an important role in the progression of cervical intraepithelial neoplasia (CIN) to cervical cancer (CC). Our study examined the association of CCR2-64I (rs1799864) andCCR5-Δ32 (rs333) polymorphisms with susceptibility to develop cervical lesion (CIN and CC) in a Brazilian population. The genotyping of 139 women with cervical lesions and 151 women without cervical lesions for the CCR2-64I and CCR5-Δ32 polymorphisms were performed using polymerase chain reaction-restriction fragment length polymorphism. The individuals carrying heterozygous or homozygous genotypes (GA+AA) for CCR2-64I polymorphisms seem to be at lower risk for cervical lesion [odds ratio (OR) = 0.37, p = 0.0008)]. The same was observed for the A allele (OR = 0.39, p = 0.0002), while no association was detected (p > 0.05) with CCR5-Δ32 polymorphism. Regarding the human papillomavirus (HPV) type, patients carrying the CCR2-64Ipolymorphism were protected against infection by HPV type 16 (OR = 0.35, p = 0.0184). In summary, our study showed a protective effect ofCCR2-64I rs1799864 polymorphism against the development of cervical lesions (CIN and CC) and in the susceptibility of HPV 16 infection.

Chemokines SNPs in HIV-1+ Patients and Healthy Controls from Northeast Brazil: Association with Protection against HIV-1 Infection. - Celerino da Silva, Ronaldo; Victor Campos Coelho, Antonio; Cláudio Arraes, Luiz; André Cavalcanti Brandão, Lucas; Lima Guimarães, Rafael; Crovella, Sergio (Curr HIV Res, 2016)
BACKGROUND: HIV-1 virus is known to infect the host mainly through CD4+ T-lymphocyte cells, by interactions among the viral envelope proteins, CD4 receptor and HIV-1 coreceptors, such as chemokines receptors. Variations in the genes encoding HIV-1 coreceptors and their natural ligands have been shown to modify HIV-1 infection susceptibility and disease progression. METHODS AND RESULTS: We analysed the distribution of SNPs in chemokines (CCL3, CCL4, CCL5, CXCL12) and chemokine receptor (CXCR6) genes, in 268 HIV-1 infected patients (HIV-1+) and 221 healthy controls from Northeast Brazil, and their possible connection with susceptibility to HIV-1 infection. The genotyping were performed through allele specific fluorogenic probes using real time PCR. We observed that the T alleles and AT genotype of rs1719153 CCL4 SNP were more frequent in healthy controls (19.8% and 35.0%, respectively) than in HIV-1+ patients (T allele: 14.1%; OR=0.67; 95%CI=0.47-0.95; p-value=0.020; and AT genotype: 24.4%; OR=0.61; 95%CI=0.40- 0.93; p-value=0.021) after correcting for age and sex. The rs1719134 (CCL3) and rs1719153 (CCL4) SNPs presented linkage disequilibrium (D'=0.83). The AT haplotype frequency was increased in healthy controls (17.3%) in relation to HIV-1+ patients (11.0%; OR=0.62; 95%CI=0.42-0.93; p-value=0.020). CONCLUSION: Since our results revealed an increased frequency of alleles and genotypes of CCL3/CCL4 SNPs and haplotype (CCL3-CCL4) among healthy controls, we suggest that these variations might have a potential protective role against HIV-1 infection.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.

The cortical response to a noxious procedure changes over time in preterm infants. - Bembich, Stefano; Marrazzo, Francesca; Barini, Alice; Ravalico, Paola; Cont, Gabriele; Demarini, Sergio (Pain, 2016)
The aim of the study was to investigate whether cortical response to a repeated noxious procedure may change over time in preterm infants. Possible reasons for change are: (1) advancing maturation of central nervous system; and (2) increasing experience with noxious procedures during hospital stay. Sixteen preterm infants were recruited, with a postmenstrual age (PMA) ranging between 29 and 36 weeks. Newborns were assessed during a heel-prick procedure, once a week for at least 3 consecutive times. Multichannel near-infrared spectroscopy was used to detect cortical activation, by measuring increase in cortical oxy-haemoglobin (HbO2). Parietal, temporal, and posterior frontal areas were monitored bilaterally. By regression analysis, we studied the effect of (1) increasing PMA and (2) increasing number of heel pricks, on the magnitude of cortical activation. We observed a bilateral nociceptive event-related activation of the posterior frontal cortex, mainly contralateral to the side pricked. Additionally, we found a significant positive effect of PMA, as HbO2 progressively increased in the posterior frontal cortex (P < 0.001), bilaterally, over time. Conversely, the degree of cortical activation decreased as the number of noxious events increased (P < 0.002). We conclude the following: (1) Preterm newborns showed a significant activation of the posterior frontal cortex in association with noxious stimuli; (2) Cortical activation was progressively greater with increasing PMA; (3) There was an inverse relationship between cortical activation and the number of heel pricks. We speculate that such findings may be due to both endogenous cortical maturation and experience-dependent neuroplasticity of the developing brain (eg, synaptogenesis, synaptic pruning).

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

DEFB1 gene polymorphisms and tuberculosis in a Northeastern Brazilian population. - Celerino da Silva, Ronaldo; da Cruz, Heidi Lacerda Alves; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Montenegro, Lilian Maria Lapa; Schindler, Haiana Charifker; Segat, Ludovica; Crovella, Sergio (Braz J Microbiol, 2016)
β-Defensin-1, an antimicrobial peptide encoded by the DEFB1 gene, is known to play an important role in lung mucosal immunity. In our association study we analyzed three DEFB1 functional polymorphisms -52G>A (rs1799946), -44C>G (rs1800972) and -20G>A (rs11362) in 92 tuberculosis patients and 286 healthy controls, both from Northeast Brazil: no association was found between the studied DEFB1 polymorphisms and the disease. However we cannot exclude that this lack of association could be due to the low number of subjects analyzed, as suggested by the low statistical power achieved for the three analyzed SNPs (values between 0.16 and 0.50).

Differential expression of GAS5 in rapamycin-induced reversion of glucocorticoid resistance. - Lucafò, Marianna; Bravin, Vanessa; Tommasini, Alberto; Martelossi, Stefano; Rabach, Ingrid; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Clin Exp Pharmacol Physiol, 2016)
This study evaluates the association between the long noncoding RNA GAS5 levels and the anti-proliferative effect of the glucocorticoid (GC) methylprednisolone (MP) alone and in combination with rapamycin in peripheral blood mononuclear cells (PBMCs) obtained from healthy donors. The effect of MP, rapamycin, and MP plus rapamycin was determined in 17 healthy donors by labelling metabolically active cells with [methyl-3H] thymidine and the expression levels of GAS5 gene were evaluated by real-time RT-PCR TaqMan analysis. We confirmed a role for GAS5 in modulating GC response: poor responders presented higher levels of GAS5 in comparison with good responders. Interestingly, when PBMCs were treated with the combination of rapamycin plus MP, the high levels of GAS5 observed for each drug in the MP poor responders group decreased in comparison with rapamycin (P value = 0.0134) or MP alone (P value = 0.0193). GAS5 is involved in GC resistance and co-treatment of rapamycin with GCs restores GC effectiveness in poor responders through the downregulation of the long noncoding RNA. GAS5 could be considered a biomarker to personalize therapy and a novel therapeutic target useful for the development of new pharmacological approaches to restore GC sensitivity.

Dyslipidemia, Diet, and Physical Exercise in Children on Treatment with Anti-Retroviral Medication in El Salvador: A Cross-Sectional Study. - Sonego, Michela; Sagrado, Maria José; Escobar, Gustavo; Lazzerini, Marzia; Rivas, Estefanie; Martín-Cañavate, Rocio; de López, Elsy Pérez; Ayala, Sandra; Castaneda, Luis; Aparicio, Pilar; Custodio, Estefanía (Pediatr Infect Dis J, 2016)
BACKGROUND: Dyslipidemias are common in HIV-infected children, especially if treated with protease-inhibitors, but there are few data on how to treat dyslipidemias in this population. We estimated the dislypidemia prevalence and its association with treatment, diet, and physical exercise in children on anti-retroviral treatment at the El Salvador reference center for pediatric HIV care (CENID). METHODS: Information was gathered regarding socio-demographic characteristics, treatment, diet, and physical activity of 173 children aged 5-18 years and receiving anti-retroviral therapy.Triglycerides, total cholesterol, low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), viral load, and CD4 T-lymphocytes were measured. Abnormal concentrations were defined as triglycerides ≥130 mg/dl in 10- to 18-year-olds and ≥100 mg/dl in <10 year-olds; total cholesterol ≥200 mg/dl; LDL-C ≥130 mg/dl; and HDL-C ≤35 mg/dl.We adjusted four different multivariate models to assess the independent association of each type of dyslipidemia with protease-inhibitors, diet, and physical exercise. RESULTS: Of the 173 children, 83 (48%) had hypertriglyceridemia and 25 (14.5%) hypercholesterolemia. High LDL-C concentrations were observed in 17 children (9.8%) and low HDL-C in 38 (22%). Treatment with protease-inhibitors was significantly associated with hypertriglyceridemia (Prevalence Ratio (PR) 2.8; 95%CI 2.0-3.8) and hypercholesterolemia (PR 9.0; 95%CI 3.6-22.2).Higher adherence to a "high fat/sugar diet" was associated with hypercholesterolemia (PR 1.6; 95%CI 1.1-2.3) and high LDL-C (PR 1.7; 95%CI 1.0-2.9).Compared with those exercising <3 times/week, children exercising ≥7 times were less likely to have low HDL-C (PR=0.4; 95%CI 0.2-0.7). CONCLUSIONS: These results suggest that a healthy diet and exercise habits can contribute to controlling some aspects of the lipid profile in this population.

Early diagnosis and Early Start Denver Model intervention in autism spectrum disorders delivered in an Italian Public Health System service. - Devescovi, Raffaella; Monasta, Lorenzo; Mancini, Alice; Bin, Maura; Vellante, Valerio; Carrozzi, Marco; Colombi, Costanza (Neuropsychiatr Dis Treat, 2016)
BACKGROUND: Early diagnosis combined with an early intervention program, such as the Early Start Denver Model (ESDM), can positively influence the early natural history of autism spectrum disorders. This study evaluated the effectiveness of an early ESDM-inspired intervention, in a small group of toddlers, delivered at low intensity by the Italian Public Health System. METHODS: Twenty-one toddlers at risk for autism spectrum disorders, aged 20-36 months, received 3 hours/wk of one-to-one ESDM-inspired intervention by trained therapists, combined with parents' and teachers' active engagement in ecological implementation of treatment. The mean duration of treatment was 15 months. Cognitive and communication skills, as well as severity of autism symptoms, were assessed by using standardized measures at pre-intervention (Time 0 [T0]; mean age =27 months) and post-intervention (Time 1 [T1]; mean age =42 months). RESULTS: Children made statistically significant improvements in the language and cognitive domains, as demonstrated by a series of nonparametric Wilcoxon tests for paired data. Regarding severity of autism symptoms, younger age at diagnosis was positively associated with greater improvement at post-assessment. CONCLUSION: Our results are consistent with the literature that underlines the importance of early diagnosis and early intervention, since prompt diagnosis can reduce the severity of autism symptoms and improve cognitive and language skills in younger children. Particularly in toddlers, it seems that an intervention model based on the ESDM principles, involving the active engagement of parents and nursery school teachers, may be effective even when the individual treatment is delivered at low intensity. Furthermore, our study supports the adaptation and the positive impact of the ESDM entirely sustained by the Italian Public Health System.

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

Efficacy of ketamine in refractory convulsive status epilepticus in children: a protocol for a sequential design, multicentre, randomised, controlled, open-label, non-profit trial (KETASER01). - Rosati, Anna; Ilvento, Lucrezia; L'Erario, Manuela; De Masi, Salvatore; Biggeri, Annibale; Fabbro, Giancarlo; Bianchi, Roberto; Stoppa, Francesca; Fusco, Lucia; Pulitanò, Silvia; Battaglia, Domenica; Pettenazzo, Andrea; et al. (BMJ Open, 2016)
INTRODUCTION: Status epilepticus (SE) is a life-threatening neurological emergency. SE lasting longer than 120 min and not responding to first-line and second-line antiepileptic drugs is defined as 'refractory' (RCSE) and requires intensive care unit treatment. There is currently neither evidence nor consensus to guide either the optimal choice of therapy or treatment goals for RCSE, which is generally treated with coma induction using conventional anaesthetics (high dose midazolam, thiopental and/or propofol). Increasing evidence indicates that ketamine (KE), a strong N-methyl-d-aspartate glutamate receptor antagonist, may be effective in treating RCSE. We hypothesised that intravenous KE is more efficacious and safer than conventional anaesthetics in treating RCSE. METHODS AND ANALYSIS: A multicentre, randomised, controlled, open-label, non-profit, sequentially designed study will be conducted to assess the efficacy of KE compared with conventional anaesthetics in the treatment of RCSE in children. 10 Italian centres/hospitals are involved in enrolling 57 patients aged 1 month to 18 years with RCSE. Primary outcome is the resolution of SE up to 24 hours after withdrawal of therapy and is updated for each patient treated according to the sequential method. ETHICS AND DISSEMINATION: The study received ethical approval from the Tuscan Paediatric Ethics Committee (12/2015). The results of this study will be published in peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NCT02431663; Pre-results.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Epigenetic Signals on Plant Adaptation: A Biotic Stress Perspective. - Neto, José Ribamar Costa Ferreira; da Silva, Manassés Daniel; Pandolfi, Valesca; Crovella, Sergio; Benko-Iseppon, Ana Maria; Kido, Éderson Akio (Curr Protein Pept Sci, 2016)
For sessile organisms such as plants, regulatory mechanisms of gene expression are vital, since they remain exposed to climatic and biological threats. Thus, they have to face hazards with instantaneous reorganization of their internal environment. For this purpose, besides the use of transcription factors, the participation of chromatin as an active factor in the regulation of transcription is crucial. Chemical changes in chromatin structure affect the accessibility of the transcriptional machinery and acting in signaling, engaging/inhibiting factors that participate in the transcription processes. Mechanisms in which gene expression undergoes changes without the occurrence of DNA gene mutations in the monomers that make up DNA, are understood as epigenetic phenomena. These include (1) post-translational modifications of histones, which results in stimulation or repression of gene activity and (2) cytosine methylation in the promoter region of individual genes, both preventing access of transcriptional activators as well as signaling the recruitment of repressors. There is evidence that such modifications can pass on to subsequent generations of daughter cells and even generations of individuals. However, reports indicate that they persist only in the presence of a stressor factor (or an inductor of the above-mentioned modifications). In its absence, these modifications weaken or lose heritability, being eliminated in the next few generations. In this review, it is argued how epigenetic signals influence gene regulation, the mechanisms involved and their participation in processes of resistance to biotic stresses, controlling processes of the plant immune system.

Evaluation of energy metabolism and calcium homeostasis in cells affected by Shwachman-Diamond syndrome. - Ravera, Silvia; Dufour, Carlo; Cesaro, Simone; Bottega, Roberta; Faleschini, Michela; Cuccarolo, Paola; Corsolini, Fabio; Usai, Cesare; Columbaro, Marta; Cipolli, Marco; Savoia, Anna; Degan, Paolo; et al. (Sci Rep, 2016)
Isomorphic mutation of the SBDS gene causes Shwachman-Diamond syndrome (SDS). SDS is a rare genetic bone marrow failure and cancer predisposition syndrome. SDS cells have ribosome biogenesis and their protein synthesis altered, which are two high-energy consuming cellular processes. The reported changes in reactive oxygen species production, endoplasmic reticulum stress response and reduced mitochondrial functionality suggest an energy production defect in SDS cells. In our work, we have demonstrated that SDS cells display a Complex IV activity impairment, which causes an oxidative phosphorylation metabolism defect, with a consequent decrease in ATP production. These data were confirmed by an increased glycolytic rate, which compensated for the energetic stress. Moreover, the signalling pathways involved in glycolysis activation also appeared more activated; i.e. we reported AMP-activated protein kinase hyper-phosphorylation. Notably, we also observed an increase in a mammalian target of rapamycin phosphorylation and high intracellular calcium concentration levels ([Ca(2+)]i), which probably represent new biochemical equilibrium modulation in SDS cells. Finally, the SDS cell response to leucine (Leu) was investigated, suggesting its possible use as a therapeutic adjuvant to be tested in clinical trials.

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Fecal Calprotectin: Diagnostic Accuracy of the Immunochromatographic CalFast Assay in a Pediatric Population. - Radillo, Oriano; Pascolo, Lorella; Martelossi, Stefano; Dal Bo, Sara; Ventura, Alessandro (J Clin Lab Anal, 2016)
BACKGROUND: Fecal calprotectin is a noninvasive marker for bowel diseases and it is high valuable to follow disease activity in Crohn's disease (CD) and ulcerative colitis (UC). In this study, we evaluated the diagnostic performance of the recently introduced immunochromatographic assay CalFast in comparison to the well-known ELISA tests for calprotectin assay to obtain a rapid diagnosis of bowel inflammation in pediatric patients. METHODS: CalFast was tested in parallel to the classic ELISA tests CalPrest and PhiCal (gold standards for the calprotectin determination) on 148 fecal samples from pediatric subjects including 104 healthy subjects, 29 with CD, and 15 with UC. RESULTS: In this study, the sensitivity and specificity of CalFast, CalPrest, and PhiCal were 86.4%, 88.6%, and 93.2% and 86.6%, 74%, and 64.4%, respectively. The area under the curve, obtained from receiver operating characteristic analysis, indicated the lack of significant difference among all the kits used. CONCLUSION: The immunochromatographic assay demonstrated good diagnostic predictive values, comparable to those of the ELISA methods, and may represent a valid alternative in order to save operators' time. The test, in fact, has a short turnaround time and does not need a specific ELISA instrumentation.

Frequency of the CCR5-delta32 allele in Brazilian populations: A systematic literature review and meta-analysis. - Silva-Carvalho, Wlisses Henrique Veloso; De Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Crovella, Sergio; Guimarães, Rafael Lima (Infect Genet Evol, 2016)
The CCR5 is a chemokine receptor widely expressed by several immune cells that are engaged in inflammatory responses. Some populations have individuals exhibiting a 32bp deletion in the CCR5 gene (CCR5-delta32) that produces a truncated non-functional protein not expressed on the cell surface. This polymorphism, known to be associated with susceptibility to infectious and inflammatory diseases, such as osteomyelitis, pre-eclampsia, systemic lupus erythematous, juvenile idiopathic arthritis, rheumatoid arthritis and HIV/AIDS, is more commonly found in European populations with average frequency of 10%. However, it is also possible to observe a significant frequency in other world populations, such as the Brazilian one. We performed a systematic review and meta-analysis of CCR5-delta32 genetic association studies in Brazilian populations throughout the country to estimate the frequency of this polymorphism. We also compared CCR5-delta32 frequencies across Brazilian regions. The systematic literature reviewed studies involving delta32 allele in Brazilian populations published from 1995 to 2015. Among the reviewed literature, 25 studies including 30 Brazilian populations distributed between the North, Northeast, South and Southeast regions were included in our meta-analysis. We observed an overall allelic frequency of 4% (95%-CI, 0.03-0.05), that was considered moderate and, notably, higher than some European populations, such as Cyprus (2.8%), Italy (3%) and Greece (2.4%). Regarding the regional frequency comparisons between North-Northeast (N-NE) and South-Southeast (S-SE) regions, we observed an allelic frequency of 3% (95%-CI, 0.02-0.04) and 4% (95%-CI, 0.03-0.05), respectively. The populations from S-SE regions had a slightly higher CCR5-delta32 frequency than N-NE regions (OR=1.41, p=0.002). Although there are several studies about the CCR5-delta32 polymorphism and its effect on the immune response of some infectious diseases, this report is the first meta-analysis study that provides a descriptive study of the distribution of CCR5-delta32 allele in Brazilian population.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

In vitro sensitivity to methyl-prednisolone is associated with clinical response in pediatric idiopathic nephrotic syndrome. - Cuzzoni, E; De Iudicibus, S; Stocco, G; Favretto, D; Pelin, M; Messina, G; Ghio, L; Monti, E; Pasini, A; Montini, G; Decorti, G (Clin Pharmacol Ther, 2016)
The aim of this study was to evaluate the in vitro steroid sensitivity as a predictor of clinical response to glucocorticoids in childhood idiopathic nephrotic syndrome (INS). Seventy-four patients (median age 4.33, interquartile range [IQR] 2.82-7.23; 63.5% male) were enrolled in a prospective multicenter study: in vitro steroid inhibition of patients' peripheral blood mononuclear cell proliferation was evaluated by [methyl-(3) H] thymidine incorporation assay at disease onset (T0) and after 4 weeks (T4) of treatment. Steroid dependence was associated with increased in vitro sensitivity at T4 assessed both as drug concentration inducing 50% of inhibition (IC50 ; odds ratio [OR] = 0.48, 95% confidence interval [CI] = 0.24-0.85; P = 0.0094) and maximum inhibition at the highest drug concentration (Imax ; OR = 1.13, 95% CI = 1.02-1.31; P = 0.017). IC50 > 4.4 nM and Imax < 92% at T4 were good predictors for optimal clinical response. These results suggest that this test may be useful for predicting the response to glucocorticoid therapy in pediatric INS.

Innate and adaptive immunity in self-reported nonceliac gluten sensitivity versus celiac disease. - Di Sabatino, Antonio; Giuffrida, Paolo; Fornasa, Giulia; Salvatore, Chiara; Vanoli, Alessandro; Naviglio, Samuele; De Leo, Luigina; Pasini, Alessandra; De Amici, Mara; Alvisi, Costanza; Not, Tarcisio; Rescigno, Maria; et al. (Dig Liver Dis, 2016)
BACKGROUND: Immune mechanisms have been implicated in nonceliac gluten sensitivity (NCGS), a condition characterized by intestinal and/or extraintestinal symptoms caused by the ingestion of gluten in non-celiac/non-wheat allergic individuals. AIMS: We investigated innate and adaptive immunity in self-reported NCGS versus celiac disease (CD). METHODS: In the supernatants of ex vivo-cultured duodenal biopsies from 14 self-reported NCGS patients, 9 untreated and 10 treated CD patients, and 12 controls we detected innate cytokines - interleukin (IL)-15, tumor necrosis factor-α, IL-1β, IL-6, IL-12p70, IL-23, IL-27, IL-32α, thymic stromal lymphopoietin (TSLP), IFN-α-, adaptive cytokines - interferon (IFN)-γ, IL-17A, IL-4, IL-5, IL-10, IL-13-, chemokines - IL-8, CCL1, CCL2, CCL3, CCL4, CCL5, CXCL1, CXCL10-, granulocyte colony stimulating factor (G-CSF) and granulocyte-macrophage colony stimulating factor (GM-CSF). RESULTS: Mucosal innate and adaptive cytokines, chemokines and growth factors did not differ between self-reported NCGS, treated CD and controls. On the contrary, IL-6, IL-15, IL-27, IFN-α, IFN-γ, IL-17A, IL-23, G-CSF, GM-CSF, IL-8, CCL1 and CCL4 were significantly higher in untreated CD than in self-reported NCGS, treated CD and controls, while TSLP was significantly lower in untreated CD than in self-reported NCGS, treated CD and controls. CONCLUSION: In our hands, patients with self-reported NCGS showed no abnormalities of the mucosal immune response.

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

The Klinefelter syndrome is associated with high recurrence of copy number variations on the X chromosome with a potential role in the clinical phenotype. - Rocca, M S; Pecile, V; Cleva, L; Speltra, E; Selice, R; Di Mambro, A; Foresta, C; Ferlin, A (Andrology, 2016)
The Klinefelter syndrome (KS) is the most frequent sex chromosomal disorder in males, characterized by at least one supernumerary X chromosome (most frequent karyotype 47,XXY). This syndrome presents with a broad range of phenotypes. The common characteristics include small testes and infertility, but KS subjects are at increased risk of hypogonadism, cognitive dysfunction, obesity, diabetes, metabolic syndrome, osteoporosis, and autoimmune disorders, which are present in variable proportion. Although part of the clinical variability might be linked to a different degree of testicular function observed in KS patients, genetic mechanisms of the supernumerary X chromosome might contribute. Gene-dosage effects and parental origin of the supernumerary X chromosome have been suggested to this regard. No study has been performed analyzing the genetic constitution of the X chromosome in terms of copy number variations (CNVs) and their possible involvement in phenotype of KS. To this aim, we performed a SNP arrays analysis on 94 KS and 85 controls. We found that KS subjects have more frequently than controls X-linked CNVs (39/94, [41.5%] with respect to 12/42, [28.6%] of females, and 8/43, [18.6%] of males, p < 0.01). The number of X-linked CNVs in KS patients was 4.58 ± 1.92 CNVs/subject, significantly higher with respect to that found in control females (1.50 ± 1.29 CNVs/subject) and males (1.14 ± 0.37 CNVs/subject). Importantly, 94.4% X-linked CNVs in KS subjects were duplications, higher with respect to control males (50.0%, p < 0.001) and females (83.3%, p = 0.1). Half of the X-linked CNVs fell within regions encompassing genes and most of them (90%) included genes escaping X-inactivation in the regions of X-Y homology, particularly in the pseudoautosomal region 1 (PAR1) and Xq21.31. This study described for the first time the genetic properties of the X chromosome in KS and suggests that X-linked CNVs (especially duplications) might contribute to the clinical phenotype.

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Molecular diagnosis of thrombocytopenia-absent radius syndrome using next-generation sequencing. - Nicchia, E; Giordano, P; Greco, C; De Rocco, D; Savoia, A (Int J Lab Hematol, 2016)
INTRODUCTION: Thrombocytopenia-absent radius (TAR) syndrome is a rare autosomal recessive disease. Patients are compound heterozygotes for a loss-of-function allele, which in most cases is a large genomic deletion on chromosome 1q21.1 containing the RBM8A gene, and a noncoding variant located in the 5'UTR (rs139428292) or intronic (rs201779890) regions of RBM8A. As the molecular genetic testing in TAR requires multiple techniques for detection of copy-number variations (CNV) and nucleotide substitutions, we tested whether a next-generation sequencing (NGS) approach could identify both alterations. METHODS: Two unrelated families were analyzed with Ion PGM sequencing using a target panel of genes responsible for different forms of inherited thrombocytopenia. A statistical quantitative evaluation of amplicon coverage was performed to detect CNV, in particular those on the RBM8A gene. RESULTS: All the probands were apparently homozygous for the rare allele inherited by the father at the rs139428292 locus, suggesting the presence of a deletion on the maternal chromosome. The statistical analysis confirmed the hemizygous condition of RBM8A. CONCLUSION: We concluded that NGS approaches could be used as a cost-effective method for molecular investigation of TAR as they could simultaneously detect CNV and point mutations.

A multi-method approach to the molecular diagnosis of overt and borderline 11p15.5 defects underlying Silver-Russell and Beckwith-Wiedemann syndromes. - Russo, Silvia; Calzari, Luciano; Mussa, Alessandro; Mainini, Ester; Cassina, Matteo; Di Candia, Stefania; Clementi, Maurizio; Guzzetti, Sara; Tabano, Silvia; Miozzo, Monica; Sirchia, Silvia; Finelli, Palma; et al. (Clin Epigenetics, 2016)
BACKGROUND: Multiple (epi)genetic defects affecting the expression of the imprinted genes within the 11p15.5 chromosomal region underlie Silver-Russell (SRS) and Beckwith-Wiedemann (BWS) syndromes. The molecular diagnosis of these opposite growth disorders requires a multi-approach flowchart to disclose known primary and secondary (epi)genetic alterations; however, up to 20 and 30 % of clinically diagnosed BWS and SRS cases remain without molecular diagnosis. The complex structure of the 11p15 region with variable CpG methylation and low-rate mosaicism may account for missed diagnoses. Here, we demonstrate the relevance of complementary techniques for the assessment of different CpGs and the importance of testing multiple tissues to increase the SRS and BWS detection rate. RESULTS: Molecular testing of 147 and 450 clinically diagnosed SRS and BWS cases provided diagnosis in 34 SRS and 185 BWS patients, with 9 SRS and 21 BWS cases remaining undiagnosed and herein referred to as "borderline." A flowchart including complementary techniques and, when applicable, the analysis of buccal swabs, allowed confirmation of the molecular diagnosis in all borderline cases. Comparison of methylation levels by methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in borderline and control cases defined an interval of H19/IGF2:IG-DMR loss of methylation that was distinct between "easy to diagnose" and "borderline" cases, which were characterized by values ≤mean -3 standard deviations (SDs) compared to controls. Values ≥mean +1 SD at H19/IGF2: IG-DMR were assigned to borderline hypermethylated BWS cases and those ≤mean -2 SD at KCNQ1OT1: TSS-DMR to hypomethylated BWS cases; these were supported by quantitative pyrosequencing or Southern blot analysis. Six BWS cases suspected to carry mosaic paternal uniparental disomy of chromosome 11 were confirmed by SNP array, which detected mosaicism till 10 %. Regarding the clinical presentation, borderline SRS were representative of the syndromic phenotype, with exception of one patient, whereas BWS cases showed low frequency of the most common features except hemihyperplasia. CONCLUSIONS: A conclusive molecular diagnosis was reached in borderline methylation cases, increasing the detection rate by 6 % for SRS and 5 % for BWS cases. The introduction of complementary techniques and additional tissue analyses into routine diagnostic work-up should facilitate the identification of cases undiagnosed because of mosaicism, a distinctive feature of epigenetic disorders.
Keywords: Beckwith-Wiedemann Syndrome; Blotting, Southern; Child; Child, Preschool; Chromosomes, Human, Pair 11; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Humans; Infant; Male; Mosaicism; Multiplex Polymerase Chain Reaction; Oligonucleotide Array Sequence Analysis; Silver-Russell Syndrome

Plant Elite Squad: First Defense Line and Resistance Genes - Identification, Diversity and Functional Roles. - Wanderley-Nogueira, Ana Carolina; Bezerra-Neto, João Pacífico; Kido, Éderson Akio; de Araújo, Flávia Tadeu; Amorim, Lidiane Lindinalva Barbosa; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Plants exhibit sensitive mechanisms to respond to environmental stresses, presenting some specific and non-specific reactions when attacked by pathogens, including organisms from different classes and complexity, as viroids, viruses, bacteria, fungi and nematodes. A crucial step to define the fate of the plant facing an invading pathogen is the activation of a compatible Resistance (R) gene, the focus of the present review. Different aspects regarding R-genes and their products are discussed, including pathogen recognition mechanisms, signaling and effects on induced and constitutive defense processes, splicing and post transcriptional mechanisms involved. There are still countless challenges to the complete understanding of the mechanisms involving R-genes in plants, in particular those related to the interactions with other genes of the pathogen and of the host itself, their regulation, acting mechanisms at transcriptional and post-transcriptional levels, as well as the influence of other types of stress over their regulation. A magnification of knowledge is expected when considering the novel information from the omics and systems biology.

Plants Defense-related Cyclic Peptides: Diversity, Structure and Applications. - Maria, Ana Carolina Wanderley-Nogueira; Bezerra-Neto, João Pacífico; Kido, Éderson Akio; de Araújo, Flávia Tadeu; Amorim, Lidiane Lindinalva Barbosa; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Plant growth is prone to several unfavorable factors that may compromise or impair development and survival, including abiotic or biotic stressors. Aiming at defending themselves, plants have developed several strategies to survive and adapt to such adversities. Cyclotides are a family of plant-derived proteins that exhibit a diverse range of biological activities including antimicrobial and insecticidal activities that actively participate in plant defense processes. Three main categories of peptides have been described: (i) Cyclotides (ii) Sunflower Trypsin Inhibitor (SFTI) and (iii) peptides MCoTI-I and II, from Momordica cochinchinensis. They comprise proteins of approximately 30 amino acids, containing a head-to-tail cyclized backbone, with three disulfide bonds configured in a cystine knot topology, therefore bearing greater peptide stability. Given their features and multifunctionality, cyclotides stand out as promising sources for the discovery of new antimicrobial agents. The present review describes cyclotide occurrence, abundance and action in plants, also their diversity and evolution. Considerations regarding their use in the context of biomedical and agronomical sciences uses are also presented.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Protective Role of BST2 Polymorphisms in Mother-to-Child Transmission of HIV-1 and Adult AIDS Progression. - Kamada, Anselmo J; Bianco, Anna M; Zupin, Luisa; Girardelli, Martina; Matte, Maria C C; Medeiros, Rúbia Marília de; Almeida, Sabrina Esteves de Matos; Rocha, Marineide M; Segat, Ludovica; Chies, José A B; Kuhn, Louise; Crovella, Sergio (J Acquir Immune Defic Syndr, 2016)
Bone marrow stromal cell antigen-2 (BST-2)/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (rs919266, rs9192677, and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 single nucleotide polymorphism analyses were performed in 2 cohorts with acquired immunodeficiency syndrome (AIDS) progression: an adult Brazilian cohort (37 rapid, 30 chronic and 21 long-term non-progressors) and an Italian pediatric cohort (21 rapid and 67 slow progressors). The rs9576A allele was nominally associated with protection during breastfeeding (P = 0.019) and individuals carrying rs919266 GA showed slower progression to AIDS (P = 0.033). Despite the influence of rs919266 and rs9576 on BST2 expression being still undetermined, a preventive role by BST2 polymorphisms was found during HIV-1 infection.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

A Spotted Bone. - Perin, Silvia; Rabach, Ingrid; Pascolo, Paola; Dibello, Daniela; Ventura, Alessandro (J Pediatr, 2016)

Thiopurine Biotransformation and Pharmacological Effects: Contribution of Oxidative Stress. - Pelin, Marco; De Iudicibus, Sara; Londero, Margherita; Spizzo, Riccardo; Dei Rossi, Sveva; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Curr Drug Metab, 2016)
BACKGROUND: Thiopurine antimetabolites are important agents for the treatment of severe diseases, such as acute lymphoblastic leukemia and inflammatory bowel disease. Their pharmacological actions depend on biotransformation into active thioguanine-nucleotides; intracellular metabolism is mediated by enzymes of the salvage pathway of nucleotide synthesis and relies on polymorphic enzymes involved in thiopurines' catabolism such as thiopurine-S-methyl transferase. Given the enzymes involved in thiopurines' metabolism, it is reasonable to hypothesize that these drugs are able to induce significant oxidative stress conditions, possibly altering their pharmacological activity. METHODS: A systemic search of peer-reviewed scientific literature in bibliographic databases has been carried out. Both clinical and preclinical studies as well as mechanistic studies have been included to shed light on the role of oxidative stress in thiopurines' pharmacological effects. RESULTS: Sixty-nine papers were included in our review, allowing us to review the contribution of oxidative stress in the pharmacological action of thiopurines. Thiopurines are catabolized in the liver by xanthine oxidase, with potential production of reactive oxidative species and azathioprine is converted into mercaptopurine by a reaction with reduced glutathione, that, in some tissues, may be facilitated by glutathione- S-transferase (GST). A clear role of GSTM1 in modulating azathioprine cytotoxicity, with a close dependency on superoxide anion production, has been recently demonstrated. Interestingly, recent genome-wide association studies have shown that, for both azathioprine in inflammatory bowel disease and mercaptopurine in acute lymphoblastic leukemia, treatment effects on patients' white blood cells are related to variants of a gene, NUDT15, involved in biotransformation of oxidated nucleotides. CONCLUSIONS: Basing on previous evidences published in literature, oxidative stress may contribute to thiopurine effects in significant ways that, however, are still not completely elucidated.

Time for the 70°C water precautionary option in the home dilution of powdered infant formula. - Silano, Marco; Paganin, Paola; Davanzo, Riccardo (Ital J Pediatr, 2016)
Powdered infant formulas (PIF) are usually not sterile and may frequently be contaminated by several bacteria strains. Among them, Cronobacter species, previously known as Enterobacter sakazakii, is one of the most harmful, since it might be the causative agent of sepsis and meningitis in newborns and preterm infants during the first weeks of life. The mortality rate of these infections is up to 80 %. Therefore, some precautions are required in the home handling and dilution of PIF. Whereas there is wide consensus about the need that a PIF should be used immediately after being diluted or, if not, stored at < "5 °C", still recently the optimal temperature of the water used to dilute PIF is controversial among scientific societies and health agencies. The current knowledge is reviewed in this paper and provides sufficient evidence to cautiously advise the use of hot water at a temperature of "70 °C" in the dilution of PIF in order to prevent the Cronobacter sp. contamination and growth.

Tracking of the origin of recurrent mutations of the BRCA1 and BRCA2 genes in the North-East of Italy and improved mutation analysis strategy. - Cini, Giulia; Mezzavilla, Massimo; Della Puppa, Lara; Cupelli, Elisa; Fornasin, Alessio; D'Elia, Angela Valentina; Dolcetti, Riccardo; Damante, Giuseppe; Bertok, Sara; Miolo, Gianmaria; Maestro, Roberta; de Paoli, Paolo; et al. (BMC Med Genet, 2016)
BACKGROUND: About 20 % of hereditary breast cancers are caused by mutations in BRCA1 and BRCA2 genes. Since BRCA1 and BRCA2 mutations may be spread throughout the gene, genetic testing is usually performed by direct sequencing of entire coding regions. In some populations, especially if relatively isolated, a few number of recurrent mutations is reported, sometimes caused by founder effect. METHODS: BRCA1 and BRCA2 screening for mutations was carried out on 1114 breast and/or ovarian cancer patients complying with the eligibility criteria for BRCA testing. Haplotype analysis was performed on the probands carrying recurrent mutations and their relatives, using two sets of microsatellite markers covering the BRCA1 (D17S588, D17S806, D17S902, D17S1325, D17S855, D17S1328, D17S800, and D17S250) and BRCA2 (D13S220, D13S267, D13S171, D13S1701, D13S1698, D13S260, D13S290, D13S1246) loci. The DMLE + 2.2 software was used to estimate the age of BRCA1 c.676delT and BRCA2 c.7806-2A > G. A multiplex PCR and two different primer extension assays were optimized and used for genotyping the recurrent mutations of the two genes. RESULTS: In the time frame of almost 20 years of genetic testing, we have found that five BRCA1 and three BRCA2 mutations are recurrent in a substantial subset of carriers from North-East Italy and neighboring Istria, where they represent more than 50 % of all mutations. Microsatellite analyses identified a common haplotype of different length for each mutation. Age estimation of BRCA1 c.676delT and BRCA2 c.7806-2A > G mutations revealed that they arose in the Friuli Venezia Giulia area about 86 and 94 generations ago, respectively. Suggestion of an association between BRCA2 c.7806-2A > G and risk of breast cancer in males has emerged. Finally, we developed a simple and efficient pre-screening test, performing an in-house primer extension SNaPshot® assay for the rapid identification of the eight recurrent mutations. CONCLUSIONS: Proofs of common ancestry has been obtained for the eight recurrent mutations. The observed genotype-phenotype correlation and the proposed rapid mutation detection strategy could improve the clinical management of breast and ovarian patients in North-East of Italy and neighboring geographic areas.
Keywords: Adult; Aged; Alleles; BRCA1 Protein; BRCA2 Protein; Breast Neoplasms; Case-Control Studies; DNA Mutational Analysis; Female; Founder Effect; Genetic Testing; Genome-Wide Association Study; Genotyping Techniques; Haplotypes; Humans; Italy; Male; Microsatellite Repeats; Middle Aged; Mutation; Ovarian Neoplasms; Young Adult

Transcription factors involved in plant resistance to pathogens. - Amorim, Lidiane L B; da Fonseca-Dos-Santos, Romulo; Guida-Santos, Mauro; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Phytopathogenic microorganisms have a significant influence on survival and productivity of several crop plants. Transcription factors (TFs) are important players in the response to biotic stresses, as insect attack and pathogen infection. In face of such adversities many TF families have been previously reported as differentially expressed in plants as a reaction to bacterial, fungal and viral infection. This review highlights recent progresses in understanding the structure, function, signal regulation and interaction of transcription factors with other proteins in response to pathogens. Hence, we focus on three families of transcription factors: ERF, bZIP and WRKY, due to their abundance, importance and the availability of functionally well-characterized members in response to pathogen attack. Their roles and the possibilities related to the use of this knowledge for engineering pathogen resistance in crop plants are also discussed.

TRIM5 gene polymorphisms in HIV-1-infected patients and healthy controls from Northeastern Brazil. - Celerino da Silva, Ronaldo; Coelho, Antônio Victor Campos; Arraes, Luiz Claudio; Brandão, Lucas André Cavalcanti; Crovella, Sergio; Guimarães, Rafael Lima (Immunol Res, 2016)
Humans show heterogeneity in vulnerability to HIV-1 infection, partially under control of genes involved in host immunity and virus replication. TRIM5α protein has restriction activity against replication of many retroviruses. Human TRIM5 gene single nucleotide polymorphisms have been reported as involved in susceptibility to HIV-1 infection. We recruited 213 HIV-1-positive patients and 234 healthy uninfected controls from Northeast Brazil; two non-synonymous variants at exon 2, rs3740996 (H43Y) and rs10838525 (R136Q), and one regulatory polymorphism (rs16934386) at 5'UTR region of TRIM5 were analyzed. The R136Q variation presented significant differences between HIV-1-positive patients and healthy controls. The 136Q allele and the 136QQ genotype were more frequent in healthy controls (32.7 and 10.2 %, respectively) than in HIV-1-positive patients (136Q allele: 24.4 %; OR 0.66; CI 95 % 0.49-0.90; p value = 0.008/136QQ genotype: 4.2 %; OR 0.33; CI 95 % 0.13-0.79, p = 0.008) also after adjusting for age and sex. We also stratified our findings according to the presence of CCR5Δ32 variation, but the results remained the same. We observed that rs10838525 (R136Q) and rs3740996 (H43Y) were in linkage disequilibrium (D' = 0.71), forming four possible haplotypes. The H43-136Q haplotype was significantly more frequent in healthy controls (28.2 %) than in HIV-positive patients (21.4 %; OR 0.69; CI 95 % 0.50-0.96; p = 0.022). An increased frequency of allele (136Q) and genotype (136QQ) of the non-synonymous rs10838525 (R136Q) variant and the haplotype (43H-136Q) was observed among healthy controls individuals. Being aware of the limitation of this study (unavailability of exposed but uninfected individuals), we hypothesize a potential role for TRIM5 variations in the protection against HIV-1 infection.

When a lymphatic malformation determines a bowel volvulus: Are clinical status and images always reliable? - Guida, Edoardo; Di Grazia, Massimo; Cattaruzzi, Elisabetta; Bussani, Rossana; Rigamonti, Waifro; Lembo, Maria Antonietta (Int J Surg Case Rep, 2016)
INTRODUCTION: An acute abdomen in the form of small-bowel volvulus could be a presentation of a lymphatic malformation in childhood. CASE PRESENTATION: A 5year old male was admitted to our Institute for an acute abdomen. Clinical aspects and radiological images were not specific for a certain diagnosis. Laparotomy revealed a big soft mass, with a milky content, completely involving about 50cm of ileus with a partial volvulus of the intestinal loop. A complete mass excision and also a bowel involved resection were performed. After a histological examination, a lymphatic malformation was diagnosed. DISCUSSION: The diagnosis of a mesenteric lymphatic malformation could be intraoperative and a complete resection should be the treatment of choice. Sometimes it could be necessary to perform an involved bowel tract resection in the case of volvolus with ischemia. CONCLUSIONS: Paediatricians and surgeons should bare in mind that an intrabdominal lymphatic malformation may present as a nonspecific an acute abdomen caused by a bowel volvolus and diagnosis may not be so simple preoperatively.

5-Aminoimidazole-4-carboxamide ribonucleotide-transformylase and inosine-triphosphate-pyrophosphatase genes variants predict remission rate during methotrexate therapy in patients with juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Moressa, Valentina; Zandonà, Luigi; Favretto, Diego; Malusà, Noelia; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Rheumatol Int, 2015)
For children with juvenile idiopathic arthritis (JIA) who fail to respond to methotrexate, the delay in identifying the optimal treatment at an early stage of disease can lead to long-term joint damage. Recent studies indicate that relevant variants to predict methotrexate response in JIA are those in 5-aminoimidazole-4-carboxamide ribonucleotide-transformylase (ATIC), inosine-triphosphate-pyrophosphatase (ITPA) and solute-liquid-carrier-19A1 genes. The purpose of the study was, therefore, to explore the role of these candidate genetic factors on methotrexate response in an Italian cohort of children with JIA. Clinical response to methotrexate was evaluated as clinical remission stable for a 6-month period, as ACRPed score and as change in Juvenile Arthritis Disease score. The most relevant SNPs for each gene considered were assayed on patients' DNA. ITPA activity was measured in patients' erythrocytes. Sixty-nine patients with JIA were analyzed: 52.2 % responded to therapy (ACRPed70 score), while 37.7 % reached clinical remission stable for 6 months. ATIC rs2372536 GG genotype was associated with improved clinical remission (adjusted p value = 0.0090). For ITPA, rs1127354 A variant was associated with reduced clinical remission: (adjusted p value = 0.028); this association was present even for patients with wild-type ITPA and low ITPA activity. These preliminary results indicate that genotyping of ATIC rs2372536 and ITPA rs1127354 variants or measuring ITPA activity could be useful to predict methotrexate response in children with JIA after validation by further prospective studies on a larger patient cohort.

Acute pseudotumoral hemicerebellitis in a child: a rare and distinct entity? - Alberini, Elena; Vellante, Valerio; Zennaro, Floriana; Calligaris, Lorenzo; Barbi, Egidio; Carrozzi, Marco; Devescovi, Raffaella (J Child Neurol, 2015)
A pseudotumoral presentation of acute hemicerebellitis is rare in pediatric age. The authors report a new single case study of a 7-year-old child with pseudotumoral unilateral cerebellitis mimicking an intracranial tumor, which clinically presented itself with signs of intracranial hypertension and mild contralateral hemiparesis, completely recovered after anti-inflammatory therapy. Brain magnetic resonance imaging (MRI) was essential for the differential diagnosis between inflammatory and neoplastic processes. The literature highlighting specific clues about pseudotumoral hemicerebellitis as a distinct clinical and radiological entity is reviewed.
Keywords: Brain; Cerebellar Diseases; Child; Diagnosis, Differential; Encephalitis; Humans; Magnetic Resonance Imaging; Male

Advising Mothers on the Use of Medications during Breastfeeding: A Need for a Positive Attitude. - Davanzo, Riccardo; Bua, Jenny; De Cunto, Angela; Farina, Maria Luisa; De Ponti, Fabrizio; Clavenna, Antonio; Mandrella, Stefania; Sagone, Antonella; Clementi, Maurizio (J Hum Lact, 2015)
The use of medications by the nursing mother is a common reason for interrupting breastfeeding. Few drugs have been demonstrated to be absolutely contraindicated during breastfeeding. Excessive caution may lead health professionals to unnecessarily advise to interrupt breastfeeding, without assessing the latest evidence or considering the risk-benefit ratio of taking a medication versus terminating breastfeeding. To foster an appropriate approach toward the use of medications in breastfeeding women, the Italian Society of Perinatal Medicine created the following policy statement.

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

Association Study between Cervical Lesions and Single or Multiple Vaccine-Target and Non-Vaccine Target Human Papillomavirus (HPV) Types in Women from Northeastern Brazil. - Chagas, Bárbara Simas; Comar, Manola; Gurgel, Ana Pavla Almeida Diniz; Paiva, Sérgio; Seraceni, Silva; de Freitas, Antonio Carlos; Crovella, Sergio (PLoS One, 2015)
We performed an association between high-grade squamous intraepithelial lesions (HSIL), low-grade squamous intraepithelial lesions (LSIL) and single or multiple vaccine-target as well as non-vaccine target Human papillomavirus (HPV) types. Using bead-based HPV genotyping, 594 gynecological samples were genotyped. An association between squamous intraepithelial lesion (SIL) and presence of HPV16, 18, 31, 58 and 56 types were calculated. The risk was estimated by using odds ratio (OR) and 95% of confidence intervals (CI). A total of 370 (62.3%) women were HPV positive. Among these, 157 (42.7%) presented a single HPV infection, and 212 (57.3%) were infected by more than one HPV type. HPV31 was the most prevalent genotype, regardless single and multiple HPV infections. Single infection with HPV31 was associated with LSIL (OR=2.32; 95%CI: 1.01 to 5.32; p=0.04); HPV31 was also associated with LSIL (OR=3.28; 95%CI: 1.74 to 6.19; p= 0.0002) and HSIL (OR=3.82; 95%CI: 2.10 to 6.97; p<0.001) in multiple HPV infections. Risk to harbor cervical lesions was observed in multiple HPV infections with regard to the HPV56 (OR=5.39; 95%CI: 2.44 to 11.90; p<0.001for LSIL; OR=5.37; 95%CI: 2.71 to 10.69; p<0.001) and HPV58 (OR=3.29; 95%CI: 1.34 to 8.09; p=0.0091 for LSIL; OR=3.55; 95%CI: 1.56 to 8.11; p=0.0026) genotypes. In addition, women coinfected with HPV16/31/56 types had 6 and 5-fold increased risk of HSIL (OR=6.46; 95%CI: 1.89 to 22.09; p=0.002) and LSIL (OR=5.22; 95%CI: 1.10 to 24.70; p=0.03), respectively. Multiple HPV infections without HPV16/18 has 2-fold increased risk of HSIL (OR=2.57; 95%CI: 1.41 to 4.70; p=0.002) and LSIL OR=2.03; 95%CI: 1.08 to 3.79; p=0.02). The results of this study suggest that single and multiple vaccine target as well as non-vaccine target HPV types are associated with LSIL and HSIL. These finding should be taken into consideration in the design of HPV vaccination strategies.

Brain-derived neurotrophic factor serum levels in genetically isolated populations: gender-specific association with anxiety disorder subtypes but not with anxiety levels or Val66Met polymorphism. - Carlino, Davide; Francavilla, Ruggiero; Baj, Gabriele; Kulak, Karolina; d'Adamo, Pio; Ulivi, Sheila; Cappellani, Stefania; Gasparini, Paolo; Tongiorgi, Enrico (PeerJ, 2015)
Anxiety disorders (ADs) are disabling chronic disorders with exaggerated behavioral response to threats. This study was aimed at testing the hypothesis that ADs may be associated with reduced neurotrophic activity, particularly of Brain-derived neurotrophic factor (BDNF), and determining possible effects of genetics on serum BDNF concentrations. In 672 adult subjects from six isolated villages in North-Eastern Italy with high inbreeding, we determined serum BDNF levels and identified subjects with different ADs subtypes such as Social and Specific Phobias (PHSOC, PHSP), Generalized Anxiety Disorder (GAD), and Panic Disorder (PAD). Analysis of the population as a whole or individual village showed no significant correlation between serum BDNF levels and Val66Met polymorphism and no association with anxiety levels. Stratification of subjects highlighted a significant decrease in serum BDNF in females with GAD and males with PHSP. This study indicates low heritability and absence of any impact of the Val66Met polymorphism on circulating concentrations of BDNF. Our results show that BDNF is not a general biomarker of anxiety but serum BDNF levels correlate in a gender-specific manner with ADs subtypes.

A case of Rubinstein-Taybi syndrome associated with growth hormone deficiency in childhood. - Tornese, Gianluca; Marzuillo, Pierluigi; Pellegrin, Maria Chiara; Germani, Claudio; Faleschini, Elena; Zennaro, Floriana; Grandone, Anna; Miraglia Del Giudice, Emanuele; Perrone, Laura; Ventura, Alessandro (Clin Endocrinol (Oxf), 2015)

Central venous access devices in pediatric malignancies: a position paper of Italian Association of Pediatric Hematology and Oncology. - Crocoli, Alessandro; Tornesello, Assunta; Pittiruti, Mauro; Barone, Angelica; Muggeo, Paola; Inserra, Alessandro; Molinari, Angelo Claudio; Grillenzoni, Valeria; Durante, Viviana; Cicalese, Maria Pia; Zanazzo, Giulio Andrea; Cesaro, Simone (J Vasc Access, 2015)
INTRODUCTION: Treatment of pediatric malignancies is becoming progressively more complex, implying the adoption of multimodal therapies. A reliable, long-lasting venous access represents one of the critical requirements for the success of those treatments. Recent technical innovations-such as minimally invasive procedures for placement, new devices and novel materials-have rapidly spread for clinical use in adult patients, but are still not consistently used in the pediatric population. METHODS: The Supportive Therapy Working Group of Italian Association of Hematology and Oncology (AIEOP) reviewed medical literature focusing on new aspects of central venous access devices (VADs) in pediatric patients affected by oncohematological diseases. RESULTS: Appropriate recommendations for clinical use in these patients have been discussed and formulated. CONCLUSIONS: The importance of the correct choice, management and use of VADs in pediatric oncohematological patients is a necessary prerequisite for an adequate standard of care, also considering the increased chances of cure and the longer life expectancy of those patients with modern therapies.

Cerebral oxygenation with different nasal continuous positive airway pressure levels in preterm infants. - Bembich, Stefano; Travan, Laura; Cont, Gabriele; Bua, Jenny; Strajn, Tamara; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2015)
OBJECTIVES: This study evaluates the effect of varying nasal continuous positive airway pressure (NCPAP) level on cerebral blood flow (CBF) and oxygenation in preterm infants. METHODS: Oxy-haemoglobin (HbO2) and total haemoglobin (HbTot), as CBF estimates, and the ratio between HbO2 and HbTot (HbO2/HbTot), as cerebral oxygenation estimate, were assessed by near-infrared spectroscopy in 26 stable preterm newborns at a postmenstrual age between 26 and 33 weeks. Baseline HbO2, HbTot and HbO2/HbTot values were initially collected with NCPAP at 5 cm H2O and then compared with values obtained with NCPAP levels at both 3 and 8 cm H2O. RESULTS: Compared with 5 cm H2O, cerebral HbO2, HbTot and HbO2/HbTot remained unchanged both after increasing (to 8 cm H2O) and decreasing (to 3 cm H2O) the NCPAP level. This result was observed both in regional areas (24 sites) and in the overall monitored area (frontal and parietal cortex). Compared with 8 cm H2O, peripheral oxygen saturation significantly decreased at 3 cm H2O (p=0.021). Heart rate did not change. CONCLUSIONS: No differences in CBF and cerebral oxygenation were observed with NCPAP levels in the range 3-8 cm H2O despite a decrease in peripheral oxygenation with 3 cm H2O.
Keywords: Cerebrovascular Circulation; Continuous Positive Airway Pressure; Female; Hemoglobins; Humans; Infant, Newborn; Infant, Premature; Intensive Care, Neonatal; Male; Nasal Cavity; Oxygen; Oxygen Consumption; Oxyhemoglobins; Spectroscopy, Near-Infrared

Clinical aspects of Fanconi anemia individuals with the same mutation of FANCF identified by next generation sequencing. - Nicchia, Elena; Benedicenti, Francesco; Rocco, Daniela De; Greco, Chiara; Bottega, Roberta; Inzana, Francesca; Faleschini, Michela; Bonin, Serena; Cappelli, Enrico; Mogni, Massimo; Stanzial, Franco; Svahn, Johanna; et al. (Birth Defects Res A Clin Mol Teratol, 2015)
BACKGROUND: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations, aplastic anemia and increased risk of developing malignancies. FA is genetically heterogeneous as it is caused by at least 17 different genes. Among these, FANCA, FANCC, and FANCG account for approximately 85% of the patients whereas the remaining genes are mutated in only a small percentage of cases. For this reason, the molecular diagnostic process is complex and not always extended to all the FA genes, preventing the characterization of individuals belonging to rare groups. METHODS: The FA genes were analyzed using a next generation sequencing approach in two unrelated families. RESULTS: The analysis identified the same, c.484_485del, homozygous mutation of FANCF in both families. A careful examination of three electively aborted fetuses in one family and one affected girl in the other indicated an association of the FANCF loss-of-function mutation with a severe phenotype characterized by multiple malformations. CONCLUSION: The systematic use of next generation sequencing will allow the recognition of individuals from rare complementation groups, a better definition of their clinical phenotypes, and consequently, an appropriate genetic counseling. Birth Defects Research (Part A) 103:1003-1010, 2015. © 2015 Wiley Periodicals, Inc.

The combination of N-acetyl cysteine, alpha-lipoic acid, and bromelain shows high anti-inflammatory properties in novel in vivo and in vitro models of endometriosis. - Agostinis, C; Zorzet, S; De Leo, R; Zauli, G; De Seta, F; Bulla, R (Mediators Inflamm, 2015)
To evaluate the efficacy of an association of N-acetyl cystein, alpha-lipoic acid, and bromelain (NAC/LA/Br) in the treatment of endometriosis we set up a new in vivo murine model. We explored the anti-inflammatory and proapoptotic effect of this combination on human endometriotic endothelial cells (EECs) and on endothelial cells isolated from normal uterus (UtMECs). We implanted fragments of human endometriotic cysts intraperitoneally into SCID mice to evaluate the efficacy of NAC/LA/Br treatment. UtMECs and EECs, untreated or treated with NAC/LA/Br, were activated with the proinflammatory stimulus TNF-α and their response in terms of VCAM1 expression was evaluated. The proapoptotic effect of higher doses of NAC/LA/Br on UtMECs and EECs was measured with a fluorogenic substrate for activated caspases 3 and 7. The preincubation of EECs with NAC/LA/Br prior to cell stimulation with TNF-α prevents the upregulation of the expression of the inflammatory "marker" VCAM1. Furthermore NAC/LA/Br were able to induce EEC, but not UtMEC, apoptosis. Finally, the novel mouse model allowed us to demonstrate that mice treated with NAC/LA/Br presented a lower number of cysts, smaller in size, compared to untreated mice. Our findings suggest that these dietary supplements may have potential therapeutic uses in the treatment of chronic inflammatory diseases like endometriosis.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Comprehensive analysis of polymorphisms in the HLA-G 5' upstream regulatory and 3' untranslated regions in Brazilian patients with systemic lupus erythematosus. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Tavares Dantas, A; de Ataíde Mariz, H; Ferreira da Rocha Junior, L; Branco PintoDuarte, A L; Coelho, A V C; de Moura, R R; Polesello, V; Crovella, S; et al. (Tissue Antigens, 2015)
This study aims to comprehensively analyze human leucocyte antigen (HLA)-G polymorphisms association with susceptibility to systemic lupus erythematosus (SLE) development and clinical manifestations. The HLA-G 5' upstream regulatory region (URR), 3' untranslated region (UTR) and a cytosine deletion at exon 3 (ΔC, HLA-G*0105N allele) were analyzed in 114 SLE patients and 128 healthy controls from North East Brazil. The +3003T>C (rs1707) C allele and the HG010101c extended HLA-G allele were significantly more frequent in SLE patients than healthy controls (+3003C allele frequency: 12% in SLE patients vs 6% in controls; odds ratio (OR), 2.10, 95% confidence interval (CI), 1.06-4.28, P = 0.026; HG010101c frequency: 11.8% in SLE patients and 6.3% in controls; OR, 2.14, 95% CI, 1.01-4.51, P = 0.046) and were associated with susceptibility for disease development. Other polymorphisms were associated with different clinical manifestations. Although HLA-G role in SLE disease is far from being elucidated yet, our association study results along with a systematic review and meta-analysis suggest that HLA-G might be able to slightly modulate the complex SLE phenotype (pooled OR, 1.14, 95% CI, 1.02-1.27, P = 0.021).

Connexin 26 variant carriers have a better gastrointestinal health: is this the heterozygote advantage? - Vuckovic, Dragana; Dallapiccola, Bruno; Franzè, Annamaria; Mauri, Lucia; Perrone, Maria Dolores; Gasparini, Paolo (Eur J Hum Genet, 2015)

Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic analysis of Italian patients with congenital tufting enteropathy. - d'Apolito, Maria; Pisanelli, Daniela; Faletra, Flavio; Giardino, Ida; Gigante, Maddalena; Pettoello-Mantovani, Massimo; Goulet, Olivier; Gasparini, Paolo; Campanozzi, Angelo (World J Pediatr, 2015)
BACKGROUND: Congenital tufting enteropathy (CTE), an inherited autosomal recessive rare disease, is a severe diarrhea of infancy which is clinically characterized by absence of inflammation and presence of intestinal villous atrophy. Mutations in the EpCAM gene were identified to cause CTE. Recent cases of syndromic tufting enteropathy harboring the SPINT2 (19q13.2) mutation were described. METHODS: Four CTE Italian patients were clinically and immunohistochemically characterized. Direct DNA sequencing of EpCAM and SPINT2 genes was performed. RESULTS: All patients were of Italian origin. Three different mutations were detected (p.Asp219Metfs*15, Tyr186Phefs*6 and p.Ile146Asn) in the EpCAM gene; one of them is novel (p.Ile146Asn). Two patients (P1 and P2) showed compound heterozygosity revealing two mutations in separate alleles. A third patient (P3) was heterozygous for only one novel EpCAM missense mutation (p.Ile146Asn). In a syndromic patient (P4), no deleterious EpCAM mutation was found. Additional SPINT2 mutational analysis was performed. P4 showed a homozygous SPINT2 mutation (p.Y163C). No SPINT2 mutation was found in P3. CLDN7 was also evaluated as a candidate gene by mutational screening in P3 but no mutation was identified. CONCLUSIONS: This study presented a molecular characterization of CTE Italian patients, and identified three mutations in the EpCAM gene and one in the SPINT2 gene. One of EpCAM mutations was novel, therefore increasing the mutational spectrum of allelic variants of the EpCAM gene. Molecular analysis of the SPINT2 gene also allowed us to identify a SPINT2 substitution mutation (c.488A>G) recently found to be associated with syndromic CTE subjects.

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

Glucocorticoid pharmacogenetics in pediatric idiopathic nephrotic syndrome. - Cuzzoni, Eva; De Iudicibus, Sara; Franca, Raffaella; Stocco, Gabriele; Lucafò, Marianna; Pelin, Marco; Favretto, Diego; Pasini, Andrea; Montini, Giovanni; Decorti, Giuliana (Pharmacogenomics, 2015)
Idiopathic nephrotic syndrome represents the most common type of primary glomerular disease in children: glucocorticoids (GCs) are the first-line therapy, even if considerable interindividual differences in thepir efficacy and side effects have been reported. Immunosuppressive and anti-inflammatory effects of these drugs are mainly due to the GC-mediated transcription regulation of pro- and anti-inflammatory genes. This mechanism of action is the result of a complex multistep pathway that involves the glucocorticoid receptor and several other proteins, encoded by polymorphic genes. Aim of this review is to highlight the current knowledge on genetic variants that could affect GC response, particularly focusing on children with idiopathic nephrotic syndrome.

An IBCLC in the Maternity Ward of a Mother and Child Hospital: A Pre- and Post-Intervention Study. - Chiurco, Antonella; Montico, Marcella; Brovedani, Pierpaolo; Monasta, Lorenzo; Davanzo, Riccardo (Int J Environ Res Public Health, 2015)
Published evidence on the impact of the integration of International Board Certified Lactation Consultants (IBCLCs) for breastfeeding promotion is growing, but still relatively limited. Our study aims at evaluating the effects of adding an IBCLC for breastfeeding support in a mother and child hospital environment. We conducted a prospective study in the maternity ward of our maternal and child health Institute, recruiting 402 mothers of healthy term newborns soon after birth. The 18-month intervention of the IBCLC (Phase II) was preceded (Phase I) by data collection on breastfeeding rates and factors related to breastfeeding, both at hospital discharge and two weeks later. Data collection was replicated just before the end of the intervention (Phase III). In Phase III, a significantly higher percentage of mothers: (a) received help to breastfeed, and also received correct information on breastfeeding and community support, (b) started breastfeeding within two hours from delivery, (c) reported a good experience with the hospital staff. Moreover, the frequency of sore and/or cracked nipples was significantly lower in Phase III. However, no difference was found in exclusive breastfeeding rates at hospital discharge or at two weeks after birth.

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Immunologic evidence of a strong association between non-Hodgkin lymphoma and simian virus 40. - Tognon, Mauro; Luppi, Mario; Corallini, Alfredo; Taronna, Angelo; Barozzi, Patrizia; Rotondo, John Charles; Comar, Manola; Casali, Maria Vittoria; Bovenzi, Massimo; D'Agostino, Antonio; Vinante, Fabrizio; Rigo, Antonella; et al. (Cancer, 2015)
BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed to detect specific antibodies against SV40. Serum samples were taken from 2 distinct cohorts of NHL-affected patients (NHL1 [n = 89] and NHL2 [n = 61]) along with controls represented by oncologic patients affected by breast cancer (BC; n = 78) and undifferentiated nasopharyngeal carcinoma (UNPC; n = 64) and 3 different cohorts of healthy subjects (HSs; HS1 [n = 130], HS2 [n = 83], and HS3 [n = 87]). RESULTS: Immunologic data indicated that in serum samples from NHL patients, antibodies against SV40 mimotopes were detectable with a prevalence of 40% in NHL1 patients and with a prevalence of 43% in NHL2 patients. In HSs of the same median age as NHL patients, the prevalence was 16% for the HS1 group (57 years) and 14% for the HS2 group (65 years). The difference was statistically significant (P < .0001 and P < .001). Interestingly, the difference between NHL1/NHL2 patients and BC patients (40%/43% vs 15%, P < .001) and between NHL1/NHL2 patients and UNPC patients (40%/43% vs 25%, P < .05) was significant. CONCLUSIONS: Our data indicate a strong association between NHL and SV40 and thus a need for innovative therapeutic approaches for this hematologic malignancy.
Keywords: Adult; Aged; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lymphoma, Non-Hodgkin; Male; Middle Aged; Polyomavirus Infections; Seroepidemiologic Studies; Simian virus 40; Tumor Virus Infections

Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2015)
OBJECTIVES: Human β-defensin 1 (hBD-1) is an antimicrobial peptide involved in epithelial defence of various tissues, also present in the saliva. Individual genetic variations within the DEFB1 gene, encoding for hBD-1, could influence gene expression and protein production. DESIGN: Three DEFB1 polymorphisms at 5' untranslated region (UTR), -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362), and two polymorphisms at DEFB1 3' UTR, c*5G > A (rs1047031) and c*87A > G (rs1800971), were analysed by direct sequencing and correlated with hDB-1 salivary concentration (tested with enzyme-linked immunosorbent assay (ELISA)) in 40 healthy subjects. RESULTS: Significant associations were found between individuals presenting different DEFB1 polymorphisms at positions -52 and -44 of the gene and hBD-1 salivary concentrations: -52 G/G carriers had higher levels of protein than G/A and A/A; -44C/G subjects showed a higher protein concentration than homozygous wild-type C/C. For the -20G > A, c*5G > A and c*87A > G polymorphisms, no statistically significant differences were found. Combined haplotype analysis confirmed the results obtained considering the single-nucleotide polymorphisms (SNPs) singularly. CONCLUSION: Polymorphisms in the DEFB1 gene influence hBD-1 production and, therefore, could modify the innate immune system responses and, consequently, the oral health.

Impact of Surgery for Neonatal Gastrointestinal Diseases on Weight and Fat Mass. - De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (J Pediatr, 2015)
OBJECTIVE: To compare growth, fat mass (FM), and fat-free mass in surgical infants vs matched controls at similar postconceptional age (PCA). STUDY DESIGN: Anthropometric and body composition measurements by air-displacement plethysmography (PeaPod-Infant Body Composition System; LMI, Concord, California) were performed at the same PCA in 21 infants who received gastrointestinal surgery and in 21 controls matched for gestational age, birth weight, and sex. RESULTS: Despite similar anthropometry at birth, postsurgical infants were shorter (50.4 [4.7] cm vs 53.2 [4.1] cm, P = .001), lighter (3516 [743] g vs 3946 [874] g, P < .001), and had lower FM content (%FM 14.8 [4.7]% vs 20.2 [5.8]%, P < .0001) than their peers at similar PCA (43 [4] weeks). All surgical infants but 1 (20/21) received parenteral nutrition (PN). Mean PN duration was 40 (30) days. Five infants in the control group received PN because of prematurity for 15 (9-30) days. Nine infants in the surgical group and 1 in the control group had PN-associated cholestasis. CONCLUSIONS: Neonates having surgery for gastrointestinal diseases were shorter, had lower weight, and lower FM content than their peers, despite receiving more PN. Body composition evaluation and monitoring may help optimize growth in these newborns.

Impaired immune response to Candida albicans in cells from Fanconi anemia patients. - Parodi, Alessia; Kalli, Francesca; Svahn, Johanna; Stroppiana, Giorgia; De Rocco, Daniela; Terranova, Paola; Dufour, Carlo; Fenoglio, Daniela; Cappelli, Enrico (Cytokine, 2015)
Fanconi anemia (FA) is a genetic disorder characterized by bone marrow failure and cancer predisposition. Several studies show alterations of the immunological status of FA patients including defects in peripheral blood lymphocyte subsets, serum immunoglobulin levels, and inflammatory cytokines. However scanty information is available on the response of FA cells to specific infectious antigens. In this work we examined the response of FA cells to different immunological stimuli and found a defective response of IL-1β, TNF-α and IL-17 to Candida albicans stimulation thus pointing to a potentially impaired response to fungal infections of FA patients.
Keywords: Adolescent; Candida albicans; CD8-Positive T-Lymphocytes; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Cytokines; Fanconi Anemia; Humans; Immunity; Infant; Young Adult

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Insights from Cardiac Mechanics after Three Decades from Successfully Repaired Aortic Coarctation. - Faganello, Giorgio; Fisicaro, Maurizio; Russo, Giulia; Iorio, Anita; Mazzone, Carmine; Grande, Eliana; Humar, Franco; Cherubini, Antonella; Pandullo, Claudio; Barbati, Giulia; Tarantini, Luigi; Benettoni, Alessandra; et al. (Congenit Heart Dis, 2015)
BACKGROUND AND AIMS: Patients who underwent a successful repair of the aortic coarctation show chronic hyperdynamic state and normal left ventricular (LV) geometry; however, there are few data regarding the LV systolic function in the long term. Accordingly, we assessed LV systolic mechanics and factors associated with LV systolic dysfunction (LVSD) in patients with repaired CoA. METHODS: Clinical and echocardiographic data from 19 repaired CoA were analyzed 28 ± 13 years after surgery. Stress-corrected midwall shortening (sc-MS) and mitral annular peak systolic velocity (S') were analyzed as indexes of LV circumferential and longitudinal systolic function, respectively. Echocardiographic data of CoA patients were compared with 19 patients matched for age and hypertension and 38 healthy controls. Sc-MS was considered impaired if <89%, S' if <8.5 cm/s (10th percentiles of healthy controls, respectively). RESULTS: There were no statistical differences between study groups in LV volumes, mass and geometry. LV ejection fraction and Sc-MS were similar in all groups, however, CoA group had a significantly lower peak S' in comparison with matched and healthy controls (7.1 ± 1.3, 10.3 ± 1.9, and 11.1 ± 1.5, respectively; all P < 0.001). Prevalence of longitudinal LVSD defined as low S' was 84% in CoA, 13% in matched, and 5% in healthy control group (all P<0.05). Multivariate logistic regression analysis revealed that low peak S' was independently related to higher E/E' ratio and the presence of CoA. CONCLUSIONS: Patients who underwent a successful repair of CoA commonly show asymptomatic longitudinal LVSD associated with worse LV diastolic function in the long-term follow-up.

Interleukin-18, interleukin-12B and interferon-γ gene polymorphisms in Brazilian patients with rheumatoid arthritis: a pilot study. - Angelo, H D; Gomes Silva, I I F; Oliveira, R D R; Louzada-Júnior, P; Donadi, E A; Crovella, S; Maia, M M D; de Souza, P R E; Sandrin-Garcia, P (Tissue Antigens, 2015)
Polymorphisms in interleukin (IL)-18, IL-12 and interferon (IFN)-γ genes are associated with different levels of cytokines expression and have been associated with rheumatoid arthritis (RA). IL-18 +105 A/C, IL-12B +1188 A/C and IFN-γ +874 T/A polymorphisms were analyzed by restriction fragment length polymorphism-polymerase chain reaction (PCR) and amplification refractory mutation system PCR from 90 RA patients and 186 healthy individuals. There were significant differences to IL-18 +105 A/C polymorphism between the RA and control groups (odds ratio = 3.77; P < 0.0001). Individual carriers of the variant allele C had a 3.77-fold increased risk of for RA (P = 0.0032). No association was observed for IL-12B and IFN-γ polymorphisms. Our finds suggest a possible role for IL-18 polymorphism in the RA susceptibility in studied population.

Intrapartum fetal heart rate monitoring interpretation in labour: a critical appraisal. - Maso, G; Piccoli, M; De Seta, F; Parolin, S; Banco, R; Camacho Mattos, L; Bogatti, P; Alberico, S (Minerva Ginecol, 2015)
Electronic fetal monitoring (EFM) has been introduced in the obstetrics practice as a test to identify the first signs of fetal deterioration, allowing a prompt intervention to reduce neonatal morbidity and mortality. However, results from clinical trials fail to demonstrate a clear benefit with the use of EFM. No decrease in the incidence of cerebral palsy due to intrapartum asphyxia has been achieved and a significant increase in the rate of operative deliveries and in medico-legal litigations has been observed instead. Despite the lack of evidence supporting its safety and effectiveness, this method is routinely used in the clinical practice and periodical updated guidelines to standardize the method of interpretation and proper actions are proposed. However, limitations still exist and the unavoidable consequences are the increasing rate of caesarean delivery, partly due to a defensive attitude in medical choices, and medico-legal litigations for presumed inappropriate evaluation in case of perinatal adverse event. While Obstetrics Societies are trying to "fight" the rise in caesarean section rates, intrapartum EFM tracings are taken in the court proceedings as one of the main evidences in case of adverse event. The aim of this review is to discuss the limitations of guidelines dealing with intrapartum EFM and the pathophysiological basis to assess the suspicious tracings which represent the most observed and critical issue of EFM interpretation.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Leptin/adiponectin ratio predicts poststroke neurological outcome. - Carbone, Federico; Burger, Fabienne; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; Bertolotto, Maria; Dallegri, Franco; Mach, François; Fainardi, Enrico; et al. (Eur J Clin Invest, 2015)
BACKGROUND AND AIMS: Different adipokines have been associated with atherosclerotic plaque rupture and cardiovascular events, such as acute ischaemic stroke (AIS). However, the potential role of these molecules in postischaemic brain injury remains largely unknown. METHODS AND METHODS: We performed a substudy analysis on nonobese patients with first atherothrombotic stroke (n = 35) from a recently published prospective cohort. Primary endpoint was to investigate the predictive value of serum leptin/adiponectin ratio on neurological recovery at 90 days after AIS. The secondary endpoint was the predictive value of serum adipokine levels of clinical and radiological outcomes at a shorter follow-up (at days 1 and 7 after AIS). The radiological evaluation included ischaemic lesion volume and haemorrhagic transformation (HT). The clinical examination was based on National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). RESULTS: At day 1 after AIS, serum leptin and leptin/adiponectin ratio were increased and inversely correlated with both radiological and clinical parameters at all follow-up time points. Once identified the best cut-off points by receiver operating characteristic (ROC) analysis, risk analysis showed that higher circulating leptin improved neurological recovery at day 90. In addition, leptin/adiponectin ratio maintained statistical significance after adjustment for age, gender and thrombolysis, also predicting the occurrence of HT in the first 7 days after AIS (adjusted OR 0·15 [95% CI 0·03-0·83); P = 0·030]). CONCLUSIONS: Higher leptin/adiponectin ratio at day 1 predicted better neurological outcomes in patients with atherothrombotic AIS and might be potentially useful as a prognostic biomarker of the disease.

Long noncoding RNA GAS5: a novel marker involved in glucocorticoid response. - Lucafo, M; De Iudicibus, S; Di Silvestre, A; Pelin, M; Candussio, L; Martelossi, S; Tommasini, A; Piscianz, E; Ventura, A; Decorti, G (Curr Mol Med, 2015)
Glucocorticoids (GCs) exert their effects through regulation of gene expression after activation in the cytoplasm of the glucocorticoid receptor (GR) encoded by NR3C1 gene. A negative feedback mechanism resulting in GR autoregulation has been demonstrated through the binding of the activated receptor to intragenic sequences called GRE-like elements, contained in GR gene. The long noncoding RNA growth arrest-specific transcript 5 (GAS5) interacts with the activated GR suppressing its transcriptional activity. The aim of this study was to evaluate the possible role of GAS5 and NR3C1 gene expression in the antiproliferative effect of methylprednisolone in peripheral blood mononuclear cells and to correlate the expression with individual sensitivity to GCs. Subjects being poor responders to GCs presented higher levels of GAS5 and NR3C1 in comparison with good responders. We suggest that abnormal levels of GAS5 may alter GC effectiveness, probably interfering with the mechanism of GR autoregulation.
Keywords: Adult; Cell Proliferation; Female; Gene Expression Regulation; Glucocorticoids; Humans; Leukocytes, Mononuclear; Male; Methylprednisolone; Middle Aged; Receptors, Glucocorticoid; RNA, Long Noncoding; Transcription, Genetic

Making patient centered care a reality: a survey of patient educational programs in Italian Cancer Research and Care Institutes. - Cipolat Mis, C; Truccolo, I; Ravaioli, V; Cocchi, S; Gangeri, L; Mosconi, P; Drace, C; Pomicino, L; Paradiso, A; De Paoli, P (BMC Health Serv Res, 2015)
BACKGROUND: Educational intervention represents an essential element of care for cancer patients; while several single institutions develop their own patient education (PE) programs on cancer, little information is available on the effective existence of PE programs at the level of research and care institutes. In Italy such institutes--Istituti di Ricovero e Cura a Carattere Scientifico--are appointed by the Ministry of Health, and 11 (Cancer Research & Care Istitute-CRCI) of the 48 are specific for cancer on the basis of specific requirements regarding cancer care, research and education. Therefore, they represent an ideal and homogeneous model through which to investigate PE policies and activities throughout the country. The objective of this study was to assess PE activities in Italian CRCI. METHODS: We carried out a survey on PE strategies and services through a questionnaire. Four key points were investigated: a) PE as a cancer care priority, b) activities that are routinely part of PE, c) real involvement of the patients, and d) involvement of healthcare workers in PE activities. RESULTS: Most CRCI (85%) completed the survey. All reported having ongoing PE activities, and 4 of the 11 considered PE an institutional activity. More than 90% of CRCI organize classes and prepare PE handouts, while other PE activities (e.g., Cancer Information Services, mutual support groups) are less frequently part of institutional PE programs. Patients are frequently involved in the organization and preparation of educational activities on the basis of their own needs. Various PE activities are carried out for caregivers in 8 (73%) out of 11 institutes. Finally, health care workers have an active role in the organization of PE programs, although nurses take part in these activities in only half of CRCI and pharmacists are seldom included. CONCLUSIONS: The information arising from our research constitutes a necessary framework to identify areas of development and to design new strategies and standards to disseminate the culture of PE. This may ultimately help and stimulate the establishment of institutional integrated PE programs, including policies and interventions that can benefit a significant proportion of cancer patients.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

Maternal holding vs oral glucose administration as nonpharmacologic analgesia in newborns: a functional neuroimaging study. - Bembich, Stefano; Cont, Gabriele; Baldassi, Giulio; Bua, Jenny; Demarini, Sergio (JAMA Pediatr, 2015)
Keywords: Administration, Oral; Analgesia; Blood Specimen Collection; Female; Functional Neuroimaging; Glucose; Humans; Infant, Newborn; Mother-Child Relations; Pain; Pain Management; Spectroscopy, Near-Infrared

Mature and immature teratoma: A report from the second Italian pediatric study. - Terenziani, Monica; D'Angelo, Paolo; Inserra, Alessandro; Boldrini, Renata; Bisogno, Gianni; Babbo, Gian Luca; Conte, Massimo; Dall' Igna, Patrizia; De Pasquale, Maria Debora; Indolfi, Paolo; Piva, Luigi; Riccipetitoni, Giovanna; et al. (Pediatr Blood Cancer, 2015)
BACKGROUND: Teratomas demonstrate a benign clinical behavior, however they may recur with malignant components or as teratoma, and in a small group of patients prognosis could be fatal. After the first Italian study, we collected cases of teratoma, alongside the protocol for malignant germ cell tumors. PROCEDURE: Patients with teratoma were collected from 2004 to 2014. Teratomas were classified according to the WHO classifications, as mature and immature. Patients with pathological aFP and/or bHCG, and those with a malignant germ cell component were not included. RESULTS: The study enrolled 219 patients (150 mature, 69 immature teratomas) with a median age at diagnosis of 42 months. The primary sites involved were: 118 gonadal and 101 extragonadal teratomas. Two females with ovarian teratoma had a positive family history. Complete and incomplete surgeries were performed in 85% and 9% of cases. Seventeen events occurred: six females had a second metachronous tumor (5 contralateral ovarian teratoma, 1 adrenal neuroblastoma) and 11 teratomas relapsed/progressed (3 mature, 8 immature teratomas). Two patients died, one of progressive immature teratoma and one of surgical complications. At a median follow up of 68 months, the event-free, relapse-free, and overall survival rates were 90.6%, 94.3%, 98.6%, respectively. CONCLUSIONS: Teratomas show a good prognosis, especially the mature ones: surgery and follow-up remain the standard approach. Incomplete surgery in immature teratoma is the group at greatest risk of relapse. Bilateral ovarian tumors are a possibility, and the rare family predisposition to ovarian mature teratoma warrants further analyses.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasm Grading; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Second Primary; Neuroblastoma; Ovarian Neoplasms; Prognosis; Prospective Studies; Survival Rate; Teratoma; Testicular Neoplasms; Young Adult

The mediating role of interpersonal conflict at work in the relationship between negative affectivity and biomarkers of stress. - Girardi, Damiano; Falco, Alessandra; De Carlo, Alessandro; Benevene, Paula; Comar, Manola; Tongiorgi, Enrico; Bartolucci, Giovanni Battista (J Behav Med, 2015)
This study examined the association between interpersonal conflict at work (ICW) and serum levels of three possible biomarkers of stress, namely the pro-inflammatory cytokines Interleukin 1 beta (IL-1β), Interleukin 12 (IL-12), and Interleukin 17 (IL-17). Additionally, this study investigated the role of negative affectivity (NA) in the relationship between ICW and the pro-inflammatory cytokines. Data from 121 employees in an Italian healthcare organization were analyzed using structural equation modeling. Results showed that ICW was positively associated with IL-1β, IL-12, and IL-17, after controlling for the effect of gender. Moreover, ICW completely mediated the relationship between NA and the pro-inflammatory cytokines IL-1β, IL-12, and IL-17. This mediating effect was significant after controlling for the effect of gender. Overall, this study suggests that work-related stress may be associated with biomarkers of inflammation, and that negative affectivity may influence the stress process affecting the exposure to psychosocial stressors.

Meta-analysis and time series modeling allow a systematic review of primary HIV-1 drug-resistant prevalence in Latin America and Caribbean. - Coelho, Antônio Victor Campos; De Moura, Ronald Rodrigues; da Silva, Ronaldo Celerino; Kamada, Anselmo Jiro; Guimarães, Rafael Lima; Brandão, Lucas André Cavalcanti; Coelho, Hemílio Fernandes Campos; Crovella, Sergio (Curr HIV Res, 2015)
Here we review the prevalence of HIV-1 primary drug resistance in Latin America and Caribbean using meta-analysis as well as time-series modeling. We also discuss whether there could be a drawback to HIV/AIDS programs due to drug resistance in Latin America and Caribbean in the next years. We observed that, although some studies report low or moderate primary drug resistance prevalence in Caribbean countries, this evidence needs to be updated. In other countries, such as Brazil and Argentina, the prevalence of drug resistance appears to be rising. Mutations conferring resistance against reverse transcriptase inhibitors were the most frequent in the analyzed populations (70% of all mutational events). HIV-1 subtype B was the most prevalent in Latin America and the Caribbean, although subtype C and B/F recombinants have significant contributions in Argentina and Brazil. Thus, we suggest that primary drug resistance in Latin America and the Caribbean could have been underestimated. Clinical monitoring should be improved to offer better therapy, reducing the risk for HIV-1 resistance emergence and spread, principally in vulnerable populations, such as men who have sex with men transmission group, sex workers and intravenous drug users.

Meta-analysis of Brazilian genetic admixture and comparison with other Latin America countries. - Moura, Ronald Rodrigues de; Coelho, Antônio Victor Campos; Balbino, Valdir de Queiroz; Crovella, Sergio; Brandão, Lucas André Cavalcanti (Am J Hum Biol, 2015)
OBJECTIVES: This study aims at performing a systematic review and meta-analysis with the studies of genetic admixture inference of Brazilian population and to compare these results with the genetic admixture levels in other Latin American countries. METHODS: We searched for articles regarding the estimation of Brazilian genetic admixture published between 1980 and 2014 that used autosomal markers. Then, conducted meta-analyses at the whole-country and regional level. Finally, we compared the results of Brazil with other estimates from other South, Central and North American countries. RESULTS: We analyzed data from 25 studies in 38 different Brazilian populations. European (EUR) ancestry is the major contributor to the genetic background of Brazilians, followed by African (AFR), and Amerindian (AMR) ancestries. The pooled ancestry contributions were 0.62 EUR, 0.21 AFR, and 0.17AMR. The Southern region had a greater EUR contribution (0.77) than other regions. Individuals from the Northeast (NE) region had the highest AFR contribution (0.27) whereas individuals from the North regions had more AMR contribution (0.32). In the Latin America context, Brazil has the 5th high EUR contribution, the 12th for the AFR component and the 10th for the AMR ancestry. CONCLUSIONS: Admixture proportions vary greatly among Brazilian populations and also through Latin America. More studies in the Center-West, North and NE regions are needed to capture a more complete picture of the genomic ancestry of Brazil.

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

A nationwide survey of PMM2-CDG in Italy: high frequency of a mild neurological variant associated with the L32R mutation. - Barone, Rita; Carrozzi, M; Parini, R; Battini, R; Martinelli, D; Elia, M; Spada, M; Lilliu, F; Ciana, G; Burlina, A; Leuzzi, V; Leoni, M; et al. (J Neurol, 2015)
PMM2-CDG (PMM2 gene mutations) is the most common congenital disorder of N-glycosylation. We conducted a nationwide survey to characterize the frequency, clinical features, glycosylation and genetic correlates in Italian patients with PMM2-CDG. Clinical information was obtained through a questionnaire filled in by the referral physicians including demographics, neurological and systemic features, neuroimaging data and genotype. Glycosylation analyses of serum transferrin were complemented by MALDI-Mass Spectrometry (MALDI-MS). Between 1996 and 2012, data on 37 Italian patients with PMM2-CDG were collected. All the patients with a severe phenotype were unable to walk unaided, 84 % had severe intellectual disability and 81 % microcephaly. Conversely, among 17 mildly affected patients 82 % had independent ambulation, 64 % had borderline to mild intellectual disability and 35 % microcephaly. Epilepsy and stroke-like events did not occur among patients with the mild phenotype. The rate and extent of systemic involvement were more pronounced in severely affected patients. The L32R misfolding mutation of the PMM2 gene occurred in 70 % of the patients with the mild phenotype and was associated with a less severe underglycosylation of serum Tf at MALDI-MS analyses. Despite their different disease severity, all patients had progressive (olivo)ponto-cerebellar atrophy that was the hallmark clinical feature for the diagnosis. A mild neurological phenotype of PMM2-CDG marked by preserved ambulatory ability and autonomy and associated with L32R mutation is particularly frequent in Italy. PMM2-CDG should be considered in patients with even mild developmental disability and/or unexplained progressive cerebellar atrophy.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

New lenses to look at preeclampsia. - Zullino, Sara; Di Martino, Daniela; Stampalija, Tamara; Ferrazzi, Enrico (Gynecol Endocrinol, 2015)

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

Is "option B+" also being adopted in pregnant women in high-income countries? Temporal trends from a national study in Italy. - Floridia, Marco; Guaraldi, Giovanni; Ravizza, Marina; Tibaldi, Cecilia; Pinnetti, Carmela; Maccabruni, Anna; Molinari, Atim; Liuzzi, Giuseppina; Alberico, Salvatore; Meloni, Alessandra; Rizzi, Laura; Dalzero, Serena; et al. (Clin Infect Dis, 2015)
Keywords: Anti-Retroviral Agents; Antiretroviral Therapy, Highly Active; Developed Countries; Female; HIV Infections; Humans; Infant, Newborn; Italy; Patient Acceptance of Health Care; Pregnancy; Pregnancy Complications, Infectious

Pain activates a defined area of the somatosensory and motor cortex in newborn infants. - Bembich, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Travan, Laura; Grassi, Veronica; Demarini, Sergio (Acta Paediatr, 2015)

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

Persistent viremia and urine shedding of tick-borne encephalitis virus in an infected immunosuppressed patient from a new epidemic cluster in North-Eastern Italy. - Caracciolo, Ilaria; Bassetti, Matteo; Paladini, Giorgio; Luzzati, Roberto; Santon, Daniela; Merelli, Maria; Sabbata, Giovanni De; Carletti, Tea; Marcello, Alessandro; D'Agaro, Pierlanfranco (J Clin Virol, 2015)
A persistent tick-borne encephalitis virus infection in an immune-suppressed patient is presented. Such an unusual clinical case offers the unique chance of detecting persistent viremia associated to the erythrocyte fraction and shedding of the virus in the urine for more than six weeks. The infection occurred in a new area of the Friuli Venezia-Giulia region (North Eastern Italy) where two additional cases are also being reported.

Phenotypic and genetic characterization of a family carrying two Xq21.1-21.3 interstitial deletions associated with syndromic hearing loss. - Iossa, Sandra; Costa, Valerio; Corvino, Virginia; Auletta, Gennaro; Barruffo, Luigi; Cappellani, Stefania; Ceglia, Carlo; Cennamo, Giovanni; d'Adamo, Adamo Pio; D'Amico, Alessandra; Di Paolo, Nilde; Forte, Raimondo; et al. (Mol Cytogenet, 2015)
BACKGROUND: Sensorineural hearing impairment is a common pathological manifestation in patients affected by X-linked intellectual disability. A few cases of interstitial deletions at Xq21 with several different phenotypic characteristics have been described, but to date, a complete molecular characterization of the deletions harboring disease-causing genes is still missing. Thus, the aim of this study is to realize a detailed clinical and molecular analysis of a family affected by syndromic X-linked hearing loss with intellectual disability. RESULTS: Clinical analyses revealed a very complex phenotype that included inner ear malformations, vestibular problems, choroideremia and hypotonia with a peculiar pattern of phenotypic variability. Genomic analysis revealed, for the first time, the presence of two close interstitial deletions in the Xq21.1-21.3, harboring 11 protein coding, 9 non-coding genes and 19 pseudogenes. Among these, 3 protein coding genes have already been associated with X-linked hearing loss, intellectual disability and choroideremia. CONCLUSIONS: In this study we highlighted the presence of peculiar genotypic and phenotypic details in a family affected by syndromic X-linked hearing loss with intellectual disability. We identified two, previously unreported, Xq21.1-21.3 interstitial deletions. The two rearrangements, containing several genes, segregate with the clinical features, suggesting their role in the pathogenicity. However, not all the observed phenotypic features can be clearly associated with the known genes thus, further study is necessary to determine regions involved.

Polymorphisms in sweet taste genes (TAS1R2 and GLUT2), sweet liking, and dental caries prevalence in an adult Italian population. - Robino, Antonietta; Bevilacqua, Lorenzo; Pirastu, Nicola; Situlin, Roberta; Di Lenarda, Roberto; Gasparini, Paolo; Navarra, Chiara Ottavia (Genes Nutr, 2015)
The aim of the study was to assess the relationship between sweet taste genes and dental caries prevalence in a large sample of adults. In addition, the association between sweet liking and sugar intake with dental caries was investigated. Caries was measured by the decayed, missing, filled teeth (DMFT) index in 647 Caucasian subjects (285 males and 362 females, aged 18-65 years), coming from six villages in northeastern Italy. Sweet liking was assessed using a 9-point scale, and the mean of the liking given by each individual to specific sweet food and beverages was used to create a sweet liking score. Simple sugar consumption was estimated by a dietary history interview, considering both added sugars and sugar present naturally in foods. Our study confirmed that polymorphisms in TAS1R2 and GLUT2 genes are related to DMFT index. In particular, GG homozygous individuals for rs3935570 in TAS1R2 gene (p value = 0.0117) and GG homozygous individuals for rs1499821 in GLUT2 gene (p value = 0.0273) showed higher DMFT levels compared to both heterozygous and homozygous for the alternative allele. Furthermore, while the relationship sugar intake-DMFT did not achieve statistical significance (p value = 0.075), a significant association was identified between sweet liking and DMFT (p value = 0.004), independent of other variables. Our study showed that sweet taste genetic factors contribute to caries prevalence and highlighted the role of sweet liking as a predictor of caries risk. Therefore, these results may open new perspectives for individual risk identification and implementation of target preventive strategies, such as identifying high-risk patients before caries development.

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

Position Statement on Breastfeeding from the Italian Pediatric Societies. - Davanzo, Riccardo; Romagnoli, Costantino; Corsello, Giovanni (Ital J Pediatr, 2015)
The 2015 Position Statement on Breastfeeding of The Italian Pediatric Societies (SIP, SIN, SICupp, SIGENP) recognizes breastfeeding as an healthy behaviour with many short and long term benefits for both mother and infant.While protecting, promoting and supporting breastfeeding, neonatologists and pediatricians need specific knowledge, skills and a positive attitude toward breastfeeding. In Maternity Hospitals and in Neonatal Units, appropriate organizative interventions should be applied in order to facilitate the beginning of breastfeeding and the use of mother's/human milk.The Italian Pediatric Societies indicate the desiderable goal of around 6 months exclusive breastfeeding if the infant grows properly according to WHO Growth Charts. In principle, complementary feeding should not be anticipated before 6 months as a nutritional strategy pretending to prevent allergy and/or celiac disease. Eventually, long term breastfeeding should be supported meeting mother's desire.

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

PSIP1/LEDGF: a new gene likely involved in sensorineural progressive hearing loss. - Girotto, Giorgia; Scheffer, Deborah I; Morgan, Anna; Vozzi, Diego; Rubinato, Elisa; Di Stazio, Mariateresa; Muzzi, Enrico; Pensiero, Stefano; Giersch, Anne B; Corey, David P; Gasparini, Paolo (Sci Rep, 2015)
Hereditary Hearing Loss (HHL) is an extremely heterogeneous disorder. Approximately 30 out of 80 known HHL genes are associated with autosomal dominant forms. Here, we identified PSIP1/LEDGF (isoform p75) as a novel strong candidate gene involved in dominant HHL. Using exome sequencing we found a frameshift deletion (c.1554_1555del leading to p.E518Dfs*2) in an Italian pedigree affected by sensorineural mild-to-moderate HHL but also showing a variable eye phenotype (i.e. uveitis, optic neuropathy). This deletion led to a premature stop codon (p.T519X) with truncation of the last 12 amino acids. PSIP1 was recently described as a transcriptional co-activator regulated by miR-135b in vestibular hair cells of the mouse inner ear as well as a possible protector against photoreceptor degeneration. Here, we demonstrate that it is ubiquitously expressed in the mouse inner ear. The PSIP1 mutation is associated with a peculiar audiometric slope toward the high frequencies. These findings indicate that PSIP1 likely plays an important role in HHL.

R705H mutation of MYH9 is associated with MYH9-related disease and not only with non-syndromic deafness DFNA17. - Verver, E; Pecci, A; De Rocco, D; Ryhänen, S; Barozzi, S; Kunst, H; Topsakal, V; Savoia, A (Clin Genet, 2015)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disease caused by mutation of MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (NMMHC-IIA). MYH9-RD patients have macrothrombocytopenia and granulocyte inclusions (pathognomonic sign of the disease) containing wild-type and mutant NMMHC-IIA. During life they might develop sensorineural hearing loss, cataract, glomerulonephritis, and elevation of liver enzymes. One of the MYH9 mutations, p.R705H, was previously reported to be associated with DFNA17, an autosomal dominant non-syndromic sensorineural hearing loss without any other features associated. We identified the same mutation in two unrelated families, whose four affected individuals had not only hearing impairment but also thrombocytopenia, giant platelets, leukocyte inclusions, as well as mild to moderate elevation of some liver enzymes. Our data suggest that DFNA17 should not be a separate genetic entity but part of the wide phenotypic spectrum of MYH9-RD characterized by congenital hematological manifestations and variable penetrance and expressivity of the extra-hematological features.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

RelB activation in anti-inflammatory decidual endothelial cells: a master plan to avoid pregnancy failure? - Masat, Elisa; Gasparini, Chiara; Agostinis, Chiara; Bossi, Fleur; Radillo, Oriano; De Seta, Francesco; Tamassia, Nicola; Cassatella, Marco A; Bulla, Roberta (Sci Rep, 2015)
It is known that excessive inflammation at fetal-maternal interface is a key contributor in a compromised pregnancy. Female genital tract is constantly in contact with microorganisms and several strategies must be adopted to avoid pregnancy failure. Decidual endothelial cells (DECs) lining decidual microvascular vessels are the first cells that interact with pro-inflammatory stimuli released into the environment by microorganisms derived from gestational tissues or systemic circulation. Here, we show that DECs are hypo-responsive to LPS stimulation in terms of IL-6, CXCL8 and CCL2 production. Our results demonstrate that DECs express low levels of TLR4 and are characterized by a strong constitutive activation of the non-canonical NF-κB pathway and a low responsiveness of the canonical pathway to LPS. In conclusion, DECs show a unique hypo-responsive phenotype to the pro-inflammatory stimulus LPS in order to control the inflammatory response at feto-maternal interface.

Risk-adjusted operative delivery rates and maternal-neonatal outcomes as measures of quality assessment in obstetric care: a multicenter prospective study. - Maso, Gianpaolo; Monasta, Lorenzo; Piccoli, Monica; Ronfani, Luca; Montico, Marcella; De Seta, Francesco; Parolin, Sara; Businelli, Caterina; Travan, Laura; Alberico, Salvatore (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Although the evaluation of caesarean delivery rates has been suggested as one of the most important indicators of quality in obstetrics, it has been criticized because of its controversial ability to capture maternal and neonatal outcomes. In an "ideal" process of labor and delivery auditing, both caesarean (CD) and assisted vaginal delivery (AVD) rates should be considered because both of them may be associated with an increased risk of complications. The aim of our study was to evaluate maternal and neonatal outcomes according to the outlier status for case-mix adjusted CD and AVD rates in the same obstetric population. METHODS: Standardized data on 15,189 deliveries from 11 centers were prospectively collected. Multiple logistic regression was used to estimate the risk-adjusted probability of a woman in each center having an AVD or a CD. Centers were classified as "above", "below", or "within" the expected rates by considering the observed-to-expected rates and the 95% confidence interval around the ratio. Adjusted maternal and neonatal outcomes were compared among the three groupings. RESULTS: Centers classified as "above" or "below" the expected CD rates had, in both cases, higher adjusted incidence of composite maternal (2.97%, 4.69%, 3.90% for "within", "above" and "below", respectively; p = 0.000) and neonatal complications (3.85%, 9.66%, 6.29% for "within", "above" and "below", respectively; p = 0.000) than centers "within" CD expected rates. Centers with AVD rates above and below the expected showed poorer and better composite maternal (3.96%, 4.61%, 2.97% for "within", "above" and "below", respectively; p = 0.000) and neonatal (6.52%, 9.77%, 3.52% for "within", "above" and "below", respectively; p = 0.000) outcomes respectively than centers with "within" AVD rates. CONCLUSIONS: Both risk-adjusted CD and AVD delivery rates should be considered to assess the level of obstetric care. In this context, both higher and lower-than-expected rates of CD and "above" AVD rates are significantly associated with increased risk of complications, whereas the "below" status for AVD showed a "protective" effect on maternal and neonatal outcomes.

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Role of Pharmacogenetics in Hematopoietic Stem Cell Transplantation Outcome in Children. - Franca, Raffaella; Stocco, Gabriele; Favretto, Diego; Giurici, Nagua; Decorti, Giuliana; Rabusin, Marco (Int J Mol Sci, 2015)
Hematopoietic stem cell transplantation (HSCT) is an established therapeutic procedure for several congenital and acquired disorders, both malignant and nonmalignant. Despite the great improvements in HSCT clinical practices over the last few decades, complications, such as graft vs. host disease (GVHD) and sinusoidal obstructive syndrome (SOS), are still largely unpredictable and remain the major causes of morbidity and mortality. Both donor and patient genetic background might influence the success of bone marrow transplantation and could at least partially explain the inter-individual variability in HSCT outcome. This review summarizes some of the recent studies on candidate gene polymorphisms in HSCT, with particular reference to pediatric cohorts. The interest is especially focused on pharmacogenetic variants affecting myeloablative and immunosuppressive drugs, although genetic traits involved in SOS susceptibility and transplant-related mortality are also reviewed.

A Sensitive Electrochemiluminescence Immunosensor for Celiac Disease Diagnosis Based on Nanoelectrode Ensembles. - Habtamu, Henok B; Sentic, Milica; Silvestrini, Morena; De Leo, Luigina; Not, Tarcisio; Arbault, Stephane; Manojlovic, Dragan; Sojic, Neso; Ugo, Paolo (Anal Chem, 2015)

Serum anti-tissue transglutaminase antibodies detected during febrile illness may not be produced by the intestinal mucosa. - De Leo, Luigina; Quaglia, Sara; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Maschio, Massimo; Not, Tarcisio (J Pediatr, 2015)
Anti-transglutaminase antibodies are the diagnostic marker of celiac disease, and are considered to be synthesized only by intestinal B-lymphocytes. During an infectious disease, these antibodies are transiently detected in serum. We show that these infection-triggered antibodies may not originate in the intestinal mucosa and are not an indication of celiac disease.
Keywords: Autoantibodies; Celiac Disease; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; GTP-Binding Proteins; Humans; Intestinal Mucosa; Male; Transglutaminases

Target sequencing approach intended to discover new mutations in non-syndromic intellectual disability. - Morgan, Anna; Gandin, Ilaria; Belcaro, Chiara; Palumbo, Pietro; Palumbo, Orazio; Biamino, Elisa; Dal Col, Valentina; Laurini, Erik; Pricl, Sabrina; Bosco, Paolo; Carella, Massimo; Ferrero, Giovanni Battista; et al. (Mutat Res, 2015)
The technological improvements over the last years made considerable progresses in the knowledge of the etiology of intellectual Disability (ID). However, at present very little is known about the genetic heterogeneity underlying the non-syndromic form of ID (NS-ID). To investigate the genetic basis of NS-ID we analyzed 43 trios and 22 isolated NS-ID patients using a targeted sequencing (TS) approach. 71 NS-ID genes have been selected and sequenced in all subjects. We found putative pathogenic mutations in 7 out of 65 patients. The pathogenic role of mutations was evaluated through sequence comparison and structural analysis was performed to predict the effect of alterations in a 3D computational model through molecular dynamics simulations. Additionally, a deep patient clinical re-evaluation has been performed after the molecular results. This approach allowed us to find novel pathogenic mutations with a detection rate close to 11% in our cohort of patients. This result supports the hypothesis that many NS-ID related genes still remain to be discovered and that NS-ID is a more complex phenotype compared to syndromic form, likely caused by a complex and broad interaction between genes alterations and environment factors.

Tumor necrosis factor (TNF) alpha and interleukin (IL) 18 genes polymorphisms are correlated with susceptibility to HPV infection in patients with and without cervical intraepithelial lesion. - Tavares, Mayara C Mansur; de Lima Júnior, Sérgio F; Coelho, Antonio V C; Marques, Trícia Ruschelle N M; de Araújo, Diêgo Henrique T; Heráclio, Sandra de A; Amorim, Melânia M Ramos; de Souza, Paulo Roberto E; Crovella, Sergio (Ann Hum Biol, 2015)
BACKGROUND: The Human Papillomavirus (HPV) predisposes 500 000 women to cervical cancer. Host genetic background may facilitate virus persistence in the uterine cervix. Polymorphisms in regulatory and coding regions of cytokine genes have been associated with susceptibility to some human diseases. AIM: This study aims at investigating whether TNFA -308 G/A and IL18 -137 G/C and -607 C/A polymorphisms are associated with susceptibility to HPV infection/progression to high-grade squamous intraepithelial lesion (HSIL). SUBJECTS AND METHODS: One hundred and twenty-two HPV infected and 132 HPV negative women (the latter used as healthy controls) were analysed. TNFA -308 G/A and IL18 (-137G/C and -607 C/A) polymorphisms were analysed using specific sequence polymorphism PCR (SSP-PCR). Univariate statistical analysis and a logistic regression were performed. RESULTS: The TNFA -308A allele was associated with susceptibility to HPV infection (p = 0.0008), while the IL18 -607A allele conferred protection against HPV infection (p = 0.0043). TNFA -308 G/A and IL18 (-137G/C and -607 C/A) polymorphisms were not associated with development of cervical lesions (p > 0.05). An association was also observed between smoking and susceptibility to the development of HSIL. CONCLUSION: The findings suggest an association between two TNFA SNPs and susceptibility to HPV infection in women from Northeast Brazil. The results need to be functionally validated and replicated in other populations with different ethnic backgrounds.

On the use of Chinese population as a proxy of Amerindian ancestors in genetic admixture studies with Latin American populations. - de Moura, Ronald R; de Queiroz Balbino, Valdir; Crovella, Sergio; Brandão, Lucas A C (Eur J Hum Genet, 2015)

Usher syndrome: an effective sequencing approach to establish a genetic and clinical diagnosis. - Lenarduzzi, S; Vozzi, D; Morgan, A; Rubinato, E; D'Eustacchio, A; Osland, T M; Rossi, C; Graziano, C; Castorina, P; Ambrosetti, U; Morgutti, M; Girotto, G (Hear Res, 2015)
Usher syndrome is an autosomal recessive disorder characterized by retinitis pigmentosa, sensorineural hearing loss and, in some cases, vestibular dysfunction. The disorder is clinically and genetically heterogeneous and, to date, mutations in 11 genes have been described. This finding makes difficult to get a precise molecular diagnosis and offer patients accurate genetic counselling. To overcome this problem and to increase our knowledge of the molecular basis of Usher syndrome, we designed a targeted resequencing custom panel. In a first validation step a series of 16 Italian patients with known molecular diagnosis were analysed and 31 out of 32 alleles were detected (97% of accuracy). After this step, 31 patients without a molecular diagnosis were enrolled in the study. Three out of them with an uncertain Usher diagnosis were excluded. One causative allele was detected in 24 out 28 patients (86%) while the presence of both causative alleles characterized 19 patients out 28 (68%). Sixteen novel and 27 known alleles were found in the following genes: USH2A (50%), MYO7A (7%), CDH23 (11%), PCDH15 (7%) and USH1G (2%). Overall, on the 44 patients the protocol was able to characterize 74 alleles out of 88 (84%). These results suggest that our panel is an effective approach for the genetic diagnosis of Usher syndrome leading to: 1) an accurate molecular diagnosis, 2) better genetic counselling, 3) more precise molecular epidemiology data fundamental for future interventional plans.
Keywords: Adult; Alleles; Cadherins; Extracellular Matrix Proteins; Female; Genetic Counseling; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; Myosins; Nerve Tissue Proteins; Usher Syndromes

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

When Feeding Difficulties Are due to Genetics: The Case of Familial Partial 9q Duplication. - Travan, Laura; Rocca, Maria Santa; Buonomo, Francesca; Cleva, Lisa; Pecile, Vanna; De Cunto, Angela (J Investig Med High Impact Case Rep, 2015)
Chromosomal abnormalities may cause growth failure before or since birth. 9q duplication is reported as a cause of intrauterine growth restriction, mild dysmporphism, and intellectual disabilities. We report a case of a maternally inherited 9q21.31q21.33 duplication causing prenatal and postnatal growth restriction with feeding refusal and mild facial dysmorphisms, prenatally diagnosed by single-nucleotide polymorphism array analysis. Hypothesis of the possible pathogenic mechanisms are discussed.

Acquired long QT syndrome: a focus for the general pediatrician. - Marzuillo, Pierluigi; Benettoni, Alessandra; Germani, Claudio; Ferrara, Giovanna; D'Agata, Biancamaria; Barbi, Egidio (Pediatr Emerg Care, 2014)
Acquired long QT syndrome (LQTS) is a disorder of cardiac repolarization most often due to specific drugs, hypokalemia, or hypomagnesemia that may precipitate torsade de pointes and cause sudden cardiac death. Common presentations of the LQTS are palpitations, presyncope, syncope, cardiac arrest, and seizures. An abnormal 12-lead electrocardiogram obtained while the patient is at rest is the key to diagnosis. The occurrence of drug-induced LQTS is unpredictable in any given individual, but a common observation is that most patients have at least 1 identifiable risk factor in addition to drug exposure. The cornerstone of the management of acquired LQTS includes the identification and discontinuation of any precipitating drug and the correction of metabolic abnormalities, such as hypokalemia or hypomagnesemia. Most of the episodes of torsade de pointes are short-lived and terminate spontaneously. We propose a management protocol that could be useful for the daily practice in the emergency pediatric department to reduce the risk of acquired QT prolongation.
Keywords: Adolescent; Death, Sudden, Cardiac; Electrocardiography; Female; General Practitioners; Humans; Long QT Syndrome; Ondansetron; Risk Factors; Serotonin Antagonists

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

Association of CD209 and CD209L polymorphisms with tuberculosis infection in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; da Cruz, Heidi Lacerda Alves; Schindler, Haiana Charifker; Montenegro, Lilian Maria Lapa; Crovella, Sergio; Guimarães, Rafael Lima (Mol Biol Rep, 2014)
Tuberculosis (TB) caused by Mycobacterium tuberculosis, is major cause of morbidity and mortality worldwide. So far, many candidate genes have been investigated for their possible association with TB. Dendritic cell-specific intercellular adhesion molecule 3 (ICAM-3) grabbing non-integrin (DC-SIGN) and Liver/lymph node-specific intercellular adhesion molecule-grabbing non-integrin (L-SIGN), encoded by CD209 and CD209L genes respectively, are known for binding to M. tuberculosis on human dendritic cells and macrophages. We screened 4 single nucleotide polymorphisms (SNPs) in the promoter region of CD209, namely -939G>A (rs735240), -871A>G (rs735239), -336A>G (rs4804803) and -139G>A (rs2287886) and tandem repeat polymorphisms in exon 4 of CD209 and CD209L genes looking for association with TB in a Northeastern Brazilian population (295 subjects, 131 TB patients and 164 healthy controls). The -139G>A and -939G>A SNPs were associated with susceptibility to TB, and in particular with pulmonary and extra-pulmonary forms respectively. The -871A>G and -336A>G SNPs were associated, the first with protection to both pulmonary and extra-pulmonary TB, the latter only with the pulmonary form. An association between GGAG haplotype and protection to TB infection was also found. Also tandem repeat polymorphism in CD209L exon 4 was associated with TB infection. This study provides evidence of an association between CD209 and CD209L polymorphisms and TB development in a Brazilian population, suggesting that variations in these genes may influence the protection and susceptibility to infection caused by M. tuberculosis.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; Cell Adhesion Molecules; Dendritic Cells; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Lectins, C-Type; Male; Mycobacterium tuberculosis; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tuberculosis; Young Adult

An asymptomatic multiple magnet ingestion with transmesenteric entero-enteric fistula. - Pederiva, Federica; Daniela, Codrich; Scarpa, Maria-Grazia; Guida, Edoardo; Dragovic, Danica; Martelossi, Stefano (APSP J Case Rep, 2014)
Ingestion of foreign bodies is a common presenting complaint in the pediatric emergency department. We present a case of a child in whom disc battery ingestion was suspected initially. The immobility of the foreign body on few days of conservative management raised the suspicion of two magnets. At operation, two magnets were found in the bowel causing a transmesenteric entero-enteric fistula.

Autoimmune hematological diseases after allogeneic hematopoietic stem cell transplantation in children: an Italian multicenter experience. - Faraci, Maura; Zecca, Marco; Pillon, Marta; Rovelli, Attilio; Menconi, Maria Cristina; Ripaldi, Mimmo; Fagioli, Franca; Rabusin, Marco; Ziino, Ottavio; Lanino, Edoardo; Locatelli, Franco; Daikeler, Thomas; et al. (Biol Blood Marrow Transplant, 2014)
Autoimmune hematological diseases (AHDs) may occur after allogeneic hematopoietic stem cell transplantation (HSCT), but reports on these complications in large cohorts of pediatric patients are lacking. Between 1998 and 2011, 1574 consecutive children underwent allogeneic HSCT in 9 Italian centers. Thirty-three children (2.1%) developed AHDs: 15 autoimmune hemolytic anemia (45%), 10 immune thrombocytopenia (30%), 5 Evans' syndrome (15%), 2 pure red cell aplasia (6%), and 1 immune neutropenia (3%). The 10-year cumulative incidence of AHDs was 2.5% (95% confidence interval, 1.7 to 3.6). In a multivariate analysis, the use of alternative donor and nonmalignant disease was statistically associated with AHDs. Most patients with AHDs (64%) did not respond to steroids. Sustained complete remission was achieved in 87% of cases with the anti-CD20 monoclonal antibody (rituximab). Four patients (9%) (1 autoimmune hemolytic anemia, 1 Evans' syndrome, 2 immune thrombocytopenia) died at a median of 87 days after AHD diagnosis as a direct or indirect consequence of their disorder. Our data suggest that AHDs are a relatively rare complication occurring after HSCT that usually respond to treatment with rituximab.
Keywords: Child; Child, Preschool; Female; Hematologic Diseases; Hematopoietic Stem Cell Transplantation; Humans; Italy; Male; Remission Induction; Risk Factors; Transplantation Conditioning

Autosomal recessive Stickler syndrome due to a loss of function mutation in the COL9A3 gene. - Faletra, Flavio; d'Adamo, Adamo P; Bruno, Irene; Athanasakis, Emmanouil; Biskup, Saskia; Esposito, Laura; Gasparini, Paolo (Am J Med Genet A, 2014)
Stickler syndrome (STL) is a clinically variable and genetically heterogeneous syndrome characterized by ophthalmic, articular, orofacial, and auditory manifestations. STL has been described with both autosomal dominant and recessive inheritance. The dominant form is caused by mutations of COL2A1 (STL 1, OMIM 108300), COL11A1 (STL 2, OMIM 604841), and COL11A2 (STL 3, OMIM 184840) genes, while recessive forms have been associated with mutations of COL9A1 (OMIM 120210) and COL9A2 (OMIM 120260) genes. Type IX collagen is a heterotrimeric molecule formed by three genetically distinct chains: α1, α2, and α3 encoded by the COL9A1, COL9A2, and COL9A3 genes. Up to this time, only heterozygous mutations of COL9A3 gene have been reported in human and related to: (1) multiple epiphyseal dysplasia type 3, (2) susceptibility to an intervertebral disc disease, and (3) hearing loss. Here, we describe the first autosomal recessive Stickler family due to loss of function mutations (c.1176_1198del, p.Gln393Cysfs*25) of COL9A3 gene. These findings extend further the role of collagen genes family in the disease pathogenesis.
Keywords: Adolescent; Arthritis; Bone and Bones; Child; Child, Preschool; Collagen Diseases; Collagen Type IX; Connective Tissue Diseases; DNA Mutational Analysis; Facies; Female; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; Male; Mutation; Pedigree; Retinal Detachment

Breastfeeding and migraine drugs. - Davanzo, Riccardo; Bua, Jenny; Paloni, Giulia; Facchina, Giulia (Eur J Clin Pharmacol, 2014)
PURPOSE: Breastfeeding women may suffer from migraine. While we have many drugs for its treatment and prophylaxis, the majority are poorly studied in breastfeeding women. We conducted a review of the most common anti-migraine drugs (AMDs) and we determined their lactation risk. METHODS: For each AMD, we collected all retrievable data from Hale's Medications and Mother Milk (2012), from the LactMed database (2014) of the National Library of Medicine, and from a MedLine Search of relevant studies published in the last 10 years. RESULTS: According to our review, AMDs safe during breastfeeding are as follows: low-dose acetylsalicylic acid (ASA), ibuprofen, sumatriptan, metoprolol, propranolol, verapamil, amitriptyline, escitalopram, paroxetine, sertraline, acetaminophen, caffeine, and metoclopramide. AMDs compatible with breastfeeding but warranting caution are as follows: diclofenac, ketoprofen, naproxen, most new triptans, topiramate, valproate, venlafaxine, and cyproheptadine. Finally, high-dose ASA, atenolol, nadolol, cinnarizine, flunarizine, ergotamine, methysergide, and pizotifen are contraindicated. CONCLUSIONS: According to our review, the majority of the revised AMDs were assessed to be compatible with breastfeeding.
Keywords: Adrenergic beta-Antagonists; Analgesics, Non-Narcotic; Animals; Anti-Inflammatory Agents, Non-Steroidal; Anticonvulsants; Antidepressive Agents; Breast Feeding; Calcium Channel Blockers; Female; Humans; Migraine Disorders; Tryptamines

Breastfeeding during pregnancy: safety and socioeconomic status. - Monasta, Lorenzo; Cetin, Irene; Davanzo, Riccardo (Breastfeed Med, 2014)
Keywords: Breast Feeding; Female; Humans; Lactation; Male; Pregnancy; Pregnancy Complications; Weaning

Can body mass index accurately predict adiposity in newborns? - De Cunto, Angela; Paviotti, Giulia; Ronfani, Luca; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2014)
Body mass index (BMI) is correlated with body fatness and risk of related diseases in children and adults. Proportionality indexes such as BMI and ponderal index (PI) have been suggested as complementary measures in neonatal growth assessment. Yet, they are still not used in neonates and their correlation with fatness is unknown. The aim of the study was to test the hypothesis that BMI z-score would predict neonatal adiposity. Body composition measurements (ie, fat mass, fat-free mass) by air displacement plethysmography (PEA POD, LMI, Concord-USA), weight and length were obtained in 200 infants ≥36 weeks' gestational age (GA) at birth. Linear regression analysis showed a direct association between BMI z-score and %fat mass (r(2)=0.43, p<0.0001). This association was confirmed independently from sex, GA and maternal prepregnancy BMI. BMI z-score predicted adiposity better than PI. However, both BMI z-score and PI were poor predictors of adiposity at birth.
Keywords: Adiposity; Adult; Anthropometry; Body Composition; Body Mass Index; Cross-Sectional Studies; Female; Gestational Age; Humans; Infant, Newborn; Male; Mothers; Plethysmography; Predictive Value of Tests; Regression Analysis; Reproducibility of Results; Sex Factors

Can Lactobacillus fermentum LF10 and Lactobacillus acidophilus LA02 in a slow-release vaginal product be useful for prevention of recurrent vulvovaginal candidiasis?: A clinical study. - Murina, Filippo; Graziottin, Alessandra; Vicariotto, Franco; De Seta, Francesco (J Clin Gastroenterol, 2014)
OBJECTIVE: To assess the effectiveness of the association of 2 specific strains, Lactobacillus fermentum LF10 (DSM 19187) and Lactobacillus acidophilus LA02 (DSM 21717), specifically formulated in slow-release effervescent tablets, in patients with recurrent vulvovaginal candidiasis. STUDY DESIGN: The study was a clinical trial of 58 women diagnosed with recurrent VVC (≥4 culture-confirmed episodes in a 12-mo period). All patients were given 200 mg of fluconazole orally as an induction dose for 3 alternate days during the first treatment week. Afterward, the patients were given a new product formulated in slow-release vaginal tablets containing at least 0.4 billion live cells of each of lactobacillus L. fermentum LF10 and L. acidophilus LA02 (first phase of the prophylactic period), on alternate days for 10 consecutive nights. Patients who were still free of symptoms were given 1 vaginal tablet every week for the next 10 weeks (second phase of the prophylactic period). Patients asymptomatic after the total duration of the observation phase (7 mo) were considered as responders. RESULTS: During the second 10-week prophylactic phase, 49 of 57 (86.0%) patients remained free of clinical recurrence, whereas symptomatic VVC occurred in 8 patients (14.0%). During the 7-month follow-up, 42 patients of 49 (85.7%) were symptom free at the end of the protocol, whereas clinical recurrences occurred in 7 women (14.3%). Overall, 42 of 58 women enrolled in the study (72.4%) experienced no clinical recurrence throughout the 7-month observation phase (responders). CONCLUSIONS: This study strengthens the evidence supporting the use of specific lactobacilli with well-demonstrated activities associated with the creation and maintenance of a vaginal biofilm that hinders the persistence of an infection caused by Candida.
Keywords: Administration, Intravaginal; Adult; Biofilms; Candidiasis, Vulvovaginal; Delayed-Action Preparations; Female; Humans; Italy; Lactobacillus acidophilus; Lactobacillus fermentum; Middle Aged; Probiotics; Recurrence; Tablets; Time Factors; Treatment Outcome; Vagina; Vulva; Young Adult

Class IV laser therapy as treatment for chemotherapy-induced oral mucositis in onco-haematological paediatric patients: a prospective study. - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A; Verzegnassi, Federico; Treister, Nathaniel S; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena (Int J Paediatr Dent, 2014)
BACKGROUND: Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). AIM: This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. DESIGN: Eighteen onco-haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re-evaluated 11 days after the first day of laser therapy. RESULTS: All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11-day follow-up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1-2 days of laser therapy. CONCLUSIONS: Given class IV laser therapy appears to be safe, non-invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.

Clinical features and follow-up in patients with 22q11.2 deletion syndrome. - Cancrini, Caterina; Puliafito, Pamela; Digilio, Maria Cristina; Soresina, Annarosa; Martino, Silvana; Rondelli, Roberto; Consolini, Rita; Ruga, Ezia Maria; Cardinale, Fabio; Finocchi, Andrea; Romiti, Maria Luisa; Martire, Baldassarre; et al. (J Pediatr, 2014)
OBJECTIVE: To investigate the clinical manifestations at diagnosis and during follow-up in patients with 22q11.2 deletion syndrome to better define the natural history of the disease. STUDY DESIGN: A retrospective and prospective multicenter study was conducted with 228 patients in the context of the Italian Network for Primary Immunodeficiencies. Clinical diagnosis was confirmed by cytogenetic or molecular analysis. RESULTS: The cohort consisted of 112 males and 116 females; median age at diagnosis was 4 months (range 0 to 36 years 10 months). The diagnosis was made before 2 years of age in 71% of patients, predominantly related to the presence of heart anomalies and neonatal hypocalcemia. In patients diagnosed after 2 years of age, clinical features such as speech and language impairment, developmental delay, minor cardiac defects, recurrent infections, and facial features were the main elements leading to diagnosis. During follow-up (available for 172 patients), the frequency of autoimmune manifestations (P = .015) and speech disorders (P = .002) increased. After a median follow-up of 43 months, the survival probability was 0.92 at 15 years from diagnosis. CONCLUSIONS: Our data show a delay in the diagnosis of 22q11.2 deletion syndrome with noncardiac symptoms. This study provides guidelines for pediatricians and specialists for early identification of cases that can be confirmed by genetic testing, which would permit the provision of appropriate clinical management.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Age Factors; Child; Child, Preschool; Chromosomes, Human, Pair 22; Delayed Diagnosis; Developmental Disabilities; DiGeorge Syndrome; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; Genetic Testing; Humans; Infant; Infant, Newborn; Male; Monitoring, Physiologic; Prospective Studies; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Time Factors; Young Adult

Clinical significance of hyper-IgA in a paediatric laboratory series. - Copetti, Valentina; Pastore, Serena; De Pieri, Carlo; Radillo, Oriano; Taddio, Andrea; Ventura, Alessandro; Tommasini, Alberto (Arch Dis Child, 2014)
The causes of extremely elevated IgA, whether isolated or associated with an increase in other classes of immunoglobulin, are poorly defined in paediatrics. We reviewed the diagnostic significance of very high IgA levels (greater than 3 SD above the mean for age) in a cohort of patients referred to a tertiary care children's hospital. Hyper-IgA was found in 91 of 6364 subjects (1.4%) and in 68 cases was not associated with an increased IgG and/or IgM level. Most subjects with hyper-IgA (73.5%) had a severe immune defect, a chronic rheumatic disease or inflammatory bowel disease, while these conditions were very rare in a control group with normal IgA values (8%). Although our results may in part reflect the experience of a tertiary care centre, we suggest that hyper-IgA in children should always arouse suspicion of a serious disease.
Keywords: Adolescent; Child; Child, Preschool; Female; Hospitals, Pediatric; Humans; Hypergammaglobulinemia; Immunoglobulin A; Infant; Italy; Male; Tertiary Care Centers

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

A comparison of three scales for measuring pain in children with cognitive impairment. - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio (Acta Paediatr, 2014)
AIM: Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non-Communicating Children's Pain Checklist Postoperative Version (NCCPC-PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. METHODS: Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter-rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. RESULTS: The correlation between the NCCPC-PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter-rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC-PV was the easiest use and the most appropriate for rating the child's pain. CONCLUSION: The NCCPC-PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.

DC-SIGN polymorphisms are associated to type 1 diabetes mellitus. - da Silva, Ronaldo Celerino; Cunha Tavares, Nathália de Alencar; Moura, Ronald; Coelho, Antônio; Guimarães, Rafael Lima; Araújo, Jacqueline; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Silva, Jaqueline de Azevêdo (Immunobiology, 2014)
Type I diabetes mellitus (T1DM) is an autoimmune disorder featured by raised glucoses levels. It has been hypothesised that raised glucose levels in T1DM might be recognised as PAMPs, leading to immune response by overloading the cell receptors for pathogens recognition. DC-SIGN is a transmembrane protein, present in dendritic cells (DC) and macrophages: it has an important role in inflammatory response and T cells activation. Notably, DC-SIGN activation and triggering of the immune response depend on the type of ligand, which may lead to a pro or anti-inflammatory pathway. In our association study, we analysed the SNPs rs4804803 (-336 A>G) and rs735239 (-871 A>G), both at DC-SIGN promoter region, in 210 T1DM patients and 157 healthy controls, also looking for a correlation with the age of onset of the disease. We found that the allele G and genotypes G/G and A/G of SNP-871 (rs735239), as well as the alleles G-G (rs735239-rs4804803) and genotypes combined AA-GG (rs735239-rs4804803) were associated with protection of T1DM development. We did not find association between these variations with the age of onset of the disease and the presence of other autoimmune disorders. Our results suggest that SNPs in DC-SIGN promoter region can be associated to protection for T1DM in the Northeast Brazilian population.
Keywords: Adolescent; Alleles; Case-Control Studies; Cell Adhesion Molecules; Child; Child, Preschool; Diabetes Mellitus, Type 1; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Infant; Infant, Newborn; Lectins, C-Type; Male; Odds Ratio; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface

DEFB1 polymorphisms are involved in susceptibility to human papillomavirus infection in Brazilian gynaecological patients. - Segat, Ludovica; Zupin, Luisa; Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Chagas, Bárbara Simas; de Freitas, Antonio Carlos; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2014)
The human beta defensin 1 (hBD-1) antimicrobial peptide is a member of the innate immune system known to act in the first line of defence against microorganisms, including viruses such as human papillomavirus (HPV). In this study, five functional polymorphisms (namely g-52G>A, g-44C>G and g-20G>A in the 5'UTR and c.*5G>A and c.*87A>G in the 3'UTR) in the DEFB1 gene encoding for hBD-1 were analysed to investigate the possible involvement of these genetic variants in susceptibility to HPV infection and in the development of HPV-associated lesions in a population of Brazilian women. The DEFB1 g-52G>A and c.*5G>A single-nucleotide polymorphisms (SNPs) and the GCAAA haplotype showed associations with HPV-negative status; in particular, the c.*5G>A SNP was significantly associated after multiple test corrections. These findings suggest a possible role for the constitutively expressed beta defensin-1 peptide as a natural defence against HPV in the genital tract mucosa.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Middle Aged; Papillomavirus Infections; Polymorphism, Single Nucleotide; Reproductive Tract Infections; Young Adult

Development of an enzyme-linked immunosorbent assay for Bartonella henselae infection detection. - Ferrara, F; Di Niro, R; D'Angelo, S; Busetti, M; Marzari, R; Not, T; Sblattero, D (Lett Appl Microbiol, 2014)
UNLABELLED: Several serological diagnostics rely on enzyme-linked immunosorbent assay (ELISA) to detect bacterial infections. However, for some pathogens, including Bartonella henselae, diagnosis still depends on manually intensive, time-consuming assays including micro-immunofluorescence, Western blotting or indirect immunofluorescence. For such pathogens, there is obviously still a need to identify antigens to establish a reliable, fast and high-throughput assay (Dupon et al. ). We evaluated two B. henselae proteins to develop a novel serological ELISA: a well-known antigen, the 17-kDa protein, and GroEL, identified during this study by a proteomic approach. When serum IgG were tested, the specificity and sensitivity were 76 and 65·7% for 17-kDa, respectively, and 82 and 42·9% for GroEL, respectively. IgM were found to be more sensitive and specific for both proteins: 17-kDa protein, specificity 86·2% and sensitivity 75%; GroEL, specificity 97·7% and sensitivity 45·3%. IgM antibodies were also measured in lymphoma patients and patients with Mycobacterium tuberculosis infection to assess the usefulness of our ELISA to distinguish them from B. henselae infected patients. The resulting specificities were 89·1 and 93·5% for 17-kDa protein and GroEL, respectively. Combining the results from the two tests, we obtained a sensitivity of 82·8% and a specificity of 83·9%. Our work described and validated a proteomic approach suitable to identify immunogenic proteins useful for developing a serological test of B. henselae infection. SIGNIFICANCE AND IMPACT OF THE STUDY: A reliable serological assay for the diagnosis of Cat Scratch Disease (CSD) - a pathological condition caused by Bartonella henselae infection - has not yet been developed. Such an assay would be extremely useful to discriminate between CSD and other pathologies with similar symptoms but different aetiologies, for example lymphoma or tuberculosis. We investigate the use of two B. henselae proteins - GroEL and 17-kDa - to develop a serological-based ELISA, showing promising results with the potential for further development as an effective tool for the differential diagnosing of B. henselae infection.
Keywords: Adolescent; Adult; Amino Acid Sequence; Antibodies, Bacterial; Antigens, Bacterial; Bacterial Proteins; Bartonella henselae; Case-Control Studies; Cat-Scratch Disease; Chaperonin 60; Child; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin M; Lymphoma; Male; Molecular Sequence Data; ROC Curve; Tuberculosis, Pulmonary; Young Adult

Differences in time course activation of dorsolateral prefrontal cortex associated with low or high risk choices in a gambling task. - Bembich, Stefano; Clarici, Andrea; Vecchiet, Cristina; Baldassi, Giulio; Cont, Gabriele; Demarini, Sergio (Front Hum Neurosci, 2014)
Prefrontal cortex plays an important role in decision making (DM), supporting choices in the ordinary uncertainty of everyday life. To assess DM in an unpredictable situation, a playing card task, such as the Iowa Gambling Task (IGT), has been proposed. This task is supposed to specifically test emotion-based learning, linked to the integrity of the ventromedial prefrontal cortex (VMPFC). However, the dorsolateral prefrontal cortex (DLPFC) has demonstrated a role in IGT performance too. Our aim was to study, by multichannel near-infrared spectroscopy, the contribution of DLPFC to the IGT execution over time. We tested the hypothesis that low and high risk choices would differentially activate DLPFC, as IGT execution progressed. We enrolled 11 healthy adults. To identify DLPFC activation associated with IGT choices, we compared regional differences in oxy-hemoglobin variation, from baseline to the event. The time course of task execution was divided in four periods, each one consisting of 25 choices, and DLPFC activation was distinctly analyzed for low and high risk choices in each period. We found different time courses in DLPFC activation, associated with low or high risk choices. During the first period, a significant DLPFC activation emerged with low risk choices, whereas, during the second period, we found a cortical activation with high risk choices. Then, DLPFC activation decreased to non-significant levels during the third and fourth period. This study shows that DLPFC involvement in IGT execution is differentiated over time and according to choice risk level. DLPFC is activated only in the first half of the task, earlier by low risk and later by high risk choices. We speculate that DLPFC may sustain initial and more cognitive functions, such as attention shifting and response inhibition. The lack of DLPFC activation, as the task progresses, may be due to VMPFC activation, not detectable by fNIRS, which takes over the IGT execution in its second half.

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Effects of estroprogestins containing natural estrogen on vaginal flora. - De Seta, Francesco; Restaino, Stefano; Banco, Rubina; Conversano, Ester; De Leo, Rossella; Tonon, Maddalena; Maso, Gianpaolo; Barbati, Giulia; Lello, Stefano (Gynecol Endocrinol, 2014)
Estroprogestins with "natural oestrogen" has represented a new option in terms of combined hormonal contraception. So, the aim of this study is to investigate how estroprogestins with natural estrogen may modify the vaginal niche. In literature, very few studies focused on the interaction between hormonal contraception and vaginal milieu. This is a prospective comparative study. We enrolled 60 women from January 2013 to September 2013, 30 of them were administered estradiol valerate dienogest (E2V+DNG - Klaira®) in a quadriphasic regimen, while the other 30 women were administered 17-β estradiol with nomestrol acetate (EV+NOMAC - Zoely®) in a monophasic regimen. After a baseline study of vaginal milieu at recruitment of patients (Gram stain with Nugent score, vaginal pH, vaginal wet mount for the quantification of leukocytes, Lactobacilli and/or presence of Candida), we performed the same follow-up after six months of estroprogestin therapy. Our results showed that the women treated with E2V+DNG had a trend of an improvement of vaginal health in terms of increase of lactobacillar flora and reduction of vaginal pH in place of women treated with EV+NOMAC that showed a reduction of cervical mucus. Finally, our data about the effects on vaginal flora exerted by two estroprogestin pills (EPs) containing a natural estrogen suggest slight, but interesting differences in terms of vaginal ecology. These differences could be related to the type of estrogen, type of progestin, regimen of administration and, after all, to the net balance between estrogenic and progestin component of the EPs.
Keywords: Adolescent; Adult; Drug Combinations; Estradiol; Female; Humans; Megestrol; Middle Aged; Nandrolone; Norpregnadienes; Prospective Studies; Vagina; Young Adult

Exome analysis of HIV patients submitted to dendritic cells therapeutic vaccine reveals an association of CNOT1 gene with response to the treatment. - Moura, Ronald; Pontillo, Alessandra; d'Adamo, Pio; Pirastu, Nicola; Campos Coelho, Antonio; Crovella, Sergio (J Int AIDS Soc, 2014)
INTRODUCTION: With the aim of searching genetic factors associated with the response to an immune treatment based on autologous monocyte-derived dendritic cells pulsed with autologous inactivated HIV, we performed exome analysis by screening more than 240,000 putative functional exonic variants in 18 HIV-positive Brazilian patients that underwent the immune treatment. METHODS: Exome analysis has been performed using the ILLUMINA Infinium HumanExome BeadChip. zCall algorithm allowed us to recall rare variants. Quality control and SNP-centred analysis were done with GenABEL R package. An in-house implementation of the Wang method permitted gene-centred analysis. RESULTS: CCR4-NOT transcription complex, subunit 1 (CNOT1) gene (16q21), showed the strongest association with the modification of the response to the therapeutic vaccine (p=0.00075). CNOT1 SNP rs7188697 A/G was significantly associated with DC treatment response. The presence of a G allele indicated poor response to the therapeutic vaccine (p=0.0031; OR=33.00; CI=1.74-624.66), and the SNP behaved in a dominant model (A/A vs. A/G+G/G p=0.0009; OR=107.66; 95% CI=3.85-3013.31), being the A/G genotype present only in weak/transient responders, conferring susceptibility to poor response to the immune treatment. DISCUSSION: CNOT1 is known to be involved in the control of mRNA deadenylation and mRNA decay. Moreover, CNOT1 has been recently described as being involved in the regulation of inflammatory processes mediated by tristetraprolin (TTP). The TTP-CCR4-NOT complex (CNOT1 in the CCR4-NOT complex is the binding site for TTP) has been reported as interfering with HIV replication, through post-transcriptional control. Therefore, we can hypothesize that genetic variation occurring in the CNOT1 gene could impair the TTP-CCR4-NOT complex, thus interfering with HIV replication and/or host immune response. CONCLUSIONS: Being aware that our findings are exclusive to the 18 patients studied with a need for replication, and that the genetic variant of CNOT1 gene, localized at intron 3, has no known functional effect, we propose a novel potential candidate locus for the modulation of the response to the immune treatment, and open a discussion on the necessity to consider the host genome as another potential variant to be evaluated when designing an immune therapy study.
Keywords: AIDS Vaccines; Dendritic Cells; Exome; HIV Infections; Humans; Immunity, Humoral; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Transcription Factors; Treatment Outcome

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation

Fate of lymphocytes after withdrawal of tofacitinib treatment. - Piscianz, Elisa; Valencic, Erica; Cuzzoni, Eva; De Iudicibus, Sara; De Lorenzo, Elisa; Decorti, Giuliana; Tommasini, Alberto (PLoS One, 2014)
Tofacitinib (Tofa) is an inhibitor of Janus Kinase 3, developed for the treatment of autoimmune diseases and for the prevention of transplant rejection. Due to its selective action on proliferating cells, Tofa can offer a way to block T cell activation, without toxic effects on resting cells. However, few studies have investigated the effects of Tofa on lymphocyte activation in vitro. Our aim was to study the action of Tofa on different lymphocyte subsets after in vitro stimulation and to track the behaviour of treated cells after interruption of the treatment. Peripheral blood lymphocytes were stimulated in vitro with mitogen and treated with two concentrations of Tofa. After a first period in culture, cells were washed and further incubated for an additional time. Lymphocyte subsets, activation phenotype and proliferation were assessed at the different time frames. As expected, Tofa was able to reduce the activation and proliferation of lymphocytes in the first four days of treatment. In addition the drug led to a relative decrease of Natural Killer, B cells and CD8 T cells compared to CD4 T cells. However, treated cells were still viable after the first period in culture and begun to proliferate, strikingly, in a dose dependent manner when the drug was removed from the environment by replacing the culture medium. This novel data does not necessarily predict a similar behaviour in vivo, but can warn about the clinical use of this drug when a discontinuation of treatment with Tofa is considered for any reason.
Keywords: Antigens, CD; B-Lymphocytes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Drug Administration Schedule; Humans; Janus Kinase 3; Killer Cells, Natural; Lymphocyte Activation; Lymphocyte Count; Phytohemagglutinins; Piperidines; Primary Cell Culture; Protein Kinase Inhibitors; Pyrimidines; Pyrroles

From tube to breast: the bridging role of semi-demand breastfeeding. - Davanzo, Riccardo; Strajn, Tamara; Kennedy, Jacqueline; Crocetta, Anna; De Cunto, Angela (J Hum Lact, 2014)
Determination of the optimal timing of breastfeeding initiation for preterm infants is still a challenge for health professionals. Often unjustified delays and restrictions of breastfeeding occur due to non-evidence-based current opinions about preterm infants' feeding capacity. Semi-demand feeding has been proposed for preterm infants during the transition from scheduled to full demand feeding, to promote the establishment of self-regulated oral feeding. Although semi-demand feeding has been shown to be safe and effective in reducing time to reaching oral feeding, the implementation of this feeding pattern for preterm infants in the neonatal intensive care unit (NICU) is still limited. We developed a protocol for the application of semi-demand feeding in preterm infants based on the existing knowledge of preterm infant neurodevelopment and NICU organization and staff experience. The protocol's aim is to attain successful transition from tube feeding to breastfeeding. In this article, we describe the protocol used in the neonatal unit of the Maternal and Child Health Institute of Trieste, a third level care center in northeastern Italy.

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genetic landscape of populations along the Silk Road: admixture and migration patterns. - Mezzavilla, Massimo; Vozzi, Diego; Pirastu, Nicola; Girotto, Giorgia; d'Adamo, Pio; Gasparini, Paolo; Colonna, Vincenza (BMC Genet, 2014)
BACKGROUND: The ancient Silk Road has been a trading route between Europe and Central Asia from the 2(nd) century BCE to the 15(th) century CE. While most populations on this route have been characterized, the genetic background of others remains poorly understood, and little is known about past migration patterns. The scientific expedition "Marco Polo" has recently collected genetic and phenotypic data in six regions (Georgia, Armenia, Azerbaijan, Uzbekistan, Kazakhstan, Tajikistan) along the Silk Road to study the genetics of a number of phenotypes. RESULTS: We characterized the genetic structure of these populations within a worldwide context. We observed a West-East subdivision albeit the existence of a genetic component shared within Central Asia and nearby populations from Europe and Near East. We observed a contribution of up to 50% from Europe and Asia to most of the populations that have been analyzed. The contribution from Asia dates back to ~25 generations and is limited to the Eastern Silk Road. Time and direction of this contribution are consistent with the Mongolian expansion era. CONCLUSIONS: We clarified the genetic structure of six populations from Central Asia and suggested a complex pattern of gene flow among them. We provided a map of migration events in time and space and we quantified exchanges among populations. Altogether these novel findings will support the future studies aimed at understanding the genetics of the phenotypes that have been collected during the Marco Polo campaign, they will provide insights into the history of these populations, and they will be useful to reconstruct the developments and events that have shaped modern Eurasians genomes.
Keywords: Asian Continental Ancestry Group; Commonwealth of Independent States; European Continental Ancestry Group; Gene Flow; Homozygote; Human Migration; Humans; Phenotype; Polymorphism, Single Nucleotide; Principal Component Analysis; Sequence Analysis, DNA

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Hemophagocytic lymphohistiocytosis in total parenteral nutrition dependent children: description of 5 cases and practical tips for management. - Pastore, Serena; Barbieri, Francesca; Di Leo, Grazia; Valencic, Erica; Tommasini, Alberto; Ventura, Alessandro (J Pediatr Hematol Oncol, 2014)
Although total parenteral nutrition (TPN) is mandatory in children with intestinal failure, this treatment is not risk free. The main complications of TPN include catheter-related sepsis, thrombosis, hepatic cholestasis and cirrhosis, metabolic bone disease, and, rarely, reactive hemophagocytic lymphohistiocytosis (HLH). The pathogenesis of HLH in patients with TPN is not known, although some authors hypothesized that it can result from the activation of macrophages because of "fat overload." We reported 5 cases of HLH that occurred in patients with 4 different underlying disorders, all requiring TPN for a long term. In our series, an underlying immunological defect or a serious infection (sepsis) can have triggered HLH. Therefore, it could be reasonable to hypothesize that besides TPN in itself, minor immune defects and infections may act together by overcoming a threshold of immune stimulation, which ultimately leads to HLH.
Keywords: Child, Preschool; Fatty Acids; Female; Humans; Infant; Intestinal Diseases; Lymphohistiocytosis, Hemophagocytic; Male; Parenteral Nutrition, Total; Steroids; Treatment Outcome

Hereditary hearing loss: a 96 gene targeted sequencing protocol reveals novel alleles in a series of Italian and Qatari patients. - Vozzi, D; Morgan, A; Vuckovic, D; D'Eustacchio, A; Abdulhadi, K; Rubinato, E; Badii, R; Gasparini, P; Girotto, G (Gene, 2014)
Deafness is a really common disorder in humans. It can begin at any age with any degree of severity. Hereditary hearing loss is characterized by a vast genetic heterogeneity with more than 140 loci described in humans but only 65 genes so far identified. Families affected by hearing impairment would have real advantages from an early molecular diagnosis that is of primary relevance in genetic counseling. In this perspective, here we report a family-based approach employing Ion Torrent DNA sequencing technology to analyze coding and UTR regions of 96 genes related to hearing function and loss in a first series of 12 families coming from Italy and Qatar. Using this approach we were able to find the causative gene in 4 out of these 12 families (33%). In particular 5 novel alleles were identified in the following genes LOXHD1, TMPRSS3, TECTA and MYO15A already associated with hearing impairment. Our study confirms the usefulness of a targeted sequencing approach despite larger numbers are required for further validation and for defining a molecular epidemiology picture of hearing loss in these two countries.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Extracellular Matrix Proteins; Female; Genetic Testing; GPI-Linked Proteins; Hearing Loss; Humans; Italy; Male; Membrane Proteins; Molecular Sequence Data; Mutation; Myosins; Neoplasm Proteins; Pedigree; Qatar; Sequence Analysis, DNA; Serine Endopeptidases; Untranslated Regions

High-frequency percussive ventilation as rescue treatment in severe hypoxemic respiratory failure in term neonates. - Paviotti, Giulia; Bua, Jenny; De Cunto, Angela; Travan, Laura; Demarini, Sergio (J Crit Care, 2014)
Keywords: Female; High-Frequency Ventilation; Humans; Male; Oxygen; Pulmonary Gas Exchange; Respiratory Insufficiency

HLA-G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Domingues Barbosa, A; Tavares Dantas, A; de Ataíde Mariz, H; F da Rocha, L; Branco Pinto Duarte, A L; Monasta, L; Sandrin-Garcia, P; Crovella, S (Tissue Antigens, 2014)
We analyzed the possible association between human leukocyte antigen-G (HLA-G) genetic variants, supposed to regulate HLA-G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5'upstream regulatory region (5'URR) and 3'untranslated region (3'UTR) regions of the HLA-G gene were screened in 127 RA patients and 128 controls: 10 5'URR and 3 3'UTR HLA-G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5'URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P-values are modest, indicate a possible association between HLA-G gene polymorphisms and susceptibility to develop RA disease and its severity.
Keywords: 3' Untranslated Regions; 5' Flanking Region; Aged; Arthritis, Rheumatoid; Brazil; Disease Progression; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult

Immunomodulation mediated by a herbal syrup containing a standardized Echinacea root extract: a pilot study in healthy human subjects on cytokine gene expression. - Dapas, B; Dall'Acqua, S; Bulla, R; Agostinis, C; Perissutti, B; Invernizzi, S; Grassi, G; Voinovich, D (Phytomedicine, 2014)
In this study, the immunomodulatory effect of a triply standardized Echinacea angustifolia root extract (Polinacea(®)) was evaluated in 10 healthy subjects. Ten ml of syrup containing one hundred mg of extract (corresponding to 4.7 mg of Echinacoside and 8.0mg of a high molecular weight-20,000 Da- polysaccharide) were administered as a herbal syrup once a day for one month. The immunomodulatory effect was evaluated before and after herbal syrup administration evaluating the expression levels of the cytokines IL-2, IL-8, IL-6 and TNF-α. Cytokine expression was studied in lympho-monocytes and in plasma samples measuring the mRNA and protein levels, respectively. The results were analysed by ANOVA and non-parametric Friedman rank sum tests; when possible it was adopted a pair-wise comparisons at different post-treatment times, using the paired t-tests with Holm correction. The correlation between the variations of cytokine plasma levels and the respective mRNA was carried out using a linear regression model. In lympho-monocytes our data indicate the up-regulation of the mRNA levels of IL-2 and IL-8 and the down regulation of the mRNA levels of the pro-inflammatory cytokines TNF-α and IL6. The differential regulation was maximal after 14 days of treatment. IL-2 up-regulation and IL-6 down-regulation were also confirmed at the protein level in plasma. Finally, the up-regulation of the mRNA of IL-2/IL-8 and the down-regulation of IL-6 positively correlated with the protein levels detected in the plasma. In conclusion, this pilot study suggests a relevant role for the standardized Echinacea angustifolia root extract in the control of cytokine expression. This first demonstration of the immuno-modulating activity of Echinacea angustifolia root extract in the healthy subject, supports at least in part the common use of such products as health promoting supplement.
Keywords: Adult; Cytokines; Down-Regulation; Echinacea; Female; Glycosides; Healthy Volunteers; Humans; Immunomodulation; Interleukin-2; Interleukin-6; Interleukin-8; Lymphocytes; Male; Middle Aged; Monocytes; Pilot Projects; Plant Extracts; Plant Roots; Tumor Necrosis Factor-alpha

In vivo detection of polyomaviruses JCV and SV40 in mesenchymal stem cells from human umbilical cords. - Comar, Manola; Delbue, Serena; Zanotta, Nunzia; Valencic, Erica; Piscianz, Elisa; Del Savio, Rossella; Tesser, Alessandra; Tommasini, Alberto; Ferrante, Pasquale (Pediatr Blood Cancer, 2014)
BACKGROUND: Multipotent stromal cells are present in the Wharton's jelly matrix (WJSC) of the umbilical cord and can be used as an allogeneic source of cells to treat immunological disorders. Recently it was demonstrated that adult bone marrow (BM)-derived mesenchimal stromal cells (MSC) are susceptible to infection with viruses showing potential oncogenic properties, such as the polyomavirus JC (JCV). The aim of this study was to investigate the presence of human polyomaviruses (JCV, BK Virus-BKV, SV40, and Merkel cell polyomavirus-MCPyV) in WJSC, and explore the risk of infection. PROCEDURE: MSC samples from 35 umbilical cords were investigated by quantitative Real Time PCRs for the presence of DNA sequences of JCV, BKV, SV40, and MCPyV. RESULTS: JCV DNA was detected in 1/35 (2.8%) of MSC samples, while SV40 DNA was found in 3/35 (8.6%) of the examined samples. None of the samples showed sequences of BKV and MCPyV. CONCLUSIONS: The present study demonstrates the in vivo ability of polyomaviruses to infect WJSC. Since the therapeutic approach with the WJSC has high potentiality and a more intensive use can be easily hypothesized, the need to develop consensus guidelines to detect rare viral infections in MSC is pressing.
Keywords: DNA, Viral; Female; Fetal Blood; Humans; JC Virus; Male; Mesenchymal Stromal Cells; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Influence of HLA-G polymorphisms in human immunodeficiency virus infection and hepatitis C virus co-infection in Brazilian and Italian individuals. - da Silva, G K; Vianna, Priscila; Veit, Tiago Degani; Crovella, Sergio; Catamo, Eulalia; Cordero, Elvira Alicia Aparicio; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Chies, José Artur Bogo (Infect Genet Evol, 2014)
OBJECTIVE: This study aimed to investigate the role of Human Leukocyte Antigen (HLA)-G in the susceptibility to HIV-1 infection through the analysis of the HLA-G 3' untranslated region (UTR) polymorphisms 14 bp insertion/deletion (rs66554220) and +3142C>G (rs1063320). DESIGN: We analyzed 582 HIV-1 infected patients and 626 uninfected individuals from Brazil and Italy in a case-control study. METHODS: HLA-G polymorphisms were genotyped using PCR, PCR-RFLP assays or direct sequencing. All analyses were stratified by ethnicity. Genotypic, allelic and diplotypic frequencies were compared between HIV-1 infected subjects and controls using Chi-square or Fischer exact tests. Also, haplotypic frequencies were estimated using MLocus software. RESULTS: African-derived HIV-infected individuals presented a higher frequency of the 14 bp insertion allele as compared to non-infected individuals (0.468 versus 0.373, respectively; p(Bonf) = 0.010). A higher frequency of the 14 bp insertion +3142G (insG) haplotype (0.456 versus 0.346, p<0.001) and the insG/insG diplotype (OR=1.88, 95%CI = 1.08-3.23, p=0.021) was observed among African-derived patients as compared to uninfected controls. Also, we observed a higher frequency of the ins/ins genotype among African-derived HIV patients co-infected with HCV (OR=2.78, 95%CI = 1.20-6.49, p = 0.008). CONCLUSIONS: Our data point out to an increased frequency of alleles and genotypes associated with low HLA-G expression among African-derived patients, suggesting a potential role for HLA-G in the susceptibility to HIV-1 infection and HCV co-infection in those individuals.
Keywords: 3' Untranslated Regions; Adolescent; Adult; African Continental Ancestry Group; Aged; Brazil; Coinfection; Gene Frequency; Genetic Variation; Haplotypes; Hepatitis C; HIV Infections; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Influence of urine volume on the assessment of intestinal permeability in affected children by multiple sugar probes. - Addobbati, Riccardo; Pascolo, Lorella; Di Toro, Nicola; Sebastiani, Giulia B; Martellossi, Stefano; Not, Tarcisio (Clin Chem Lab Med, 2014)
BACKGROUND: In this study we have looked at the reliability of a multi-sugar test in a pediatric patient population and its accuracy at small urine volumes to evaluate intestinal permeability. METHODS: Out of 117 subjects enrolled, 31 were healthy and 86 were sick. A solution containing lactulose, rhamnose, sucrose, and sucralose was administered to subjects who were on fasting; the urine excreted during 5 h was collected and measured. Samples were analyzed by gas chromatography-tandem mass spectrometry and results were expressed as percentage of sugar recoveries and lactulose/rhamnose (L/R) ratio. RESULTS: The analyses showed a clear effect of low urinary volumes (≤240 mL) particularly affecting rhamnose excretion in healthy subjects and sucrose and sucralose recovery in diseased children. Despite the low rhamnose recovery, as lactulose is not similarly affected, the diagnostic reliability of L/R ratio is well preserved at low diuresis conditions. However, this ratio can be useful to discriminate acute conditions vs. clinical remissions only at high urine volumes. Data also suggest potential diagnostic applicability of sucrose and sucralose in children at high urine volumes. CONCLUSIONS: In conclusion, the multi-sugar test has a good predictivity in pediatric subjects but results must be carefully interpreted in the face of reduced diuresis.
Keywords: Carbohydrates; Child, Preschool; Diuresis; Female; Gas Chromatography-Mass Spectrometry; Gastrointestinal Diseases; Humans; Infant; Intestines; Lactulose; Male; Permeability; Rhamnose; Sucrose

Insight into genetic determinants of resting heart rate. - Mezzavilla, Massimo; Iorio, Annamaria; Bobbo, Marco; D'Eustacchio, Angela; Merlo, Marco; Gasparini, Paolo; Ulivi, Sheila; Sinagra, Gianfranco (Gene, 2014)
BACKGROUND: Recent studies suggested that resting heart rate (RHR) might be an independent predictor of cardiovascular mortality and morbidity. Nonetheless, the interrelation between RHR and cardiovascular diseases is not clear. In order to resolve this puzzle, the importance of genetic determinants of RHR has been recently suggested, but it needs to be further investigated. OBJECTIVE: The aim of this study was to estimate the contribution of common genetic variations on RHR using Genome Wide Association Study. METHODS: We performed a Genome Wide Association Study in an isolated population cohort of 1737 individuals, the Italian Network on Genetic Isolates - Friuli Venezia Giulia (INGI-FVG). Moreover, a haplotype analysis was performed. A regression tree analysis was run to highlight the effect of each haplotype combination on the phenotype. RESULTS: A significant level of association (p<5 × 10(-8)) was detected for Single Nucleotide Polymorphisms (SNPs) in two genes expressed in the heart: MAML1 and CANX. Founding that the three different variants of the haplotype, which encompass both genes, yielded a phenotypic correlation. Indeed, a haplotype in homozygosity is significantly associated with the lower quartile of RHR (RHR ≤ 58 bpm). Moreover no significant association was found between cardiovascular risk factors and the different haplotype combinations. CONCLUSION: Mastermind-like 1 and Calnexin were found to be associated with RHR. We demonstrated a relation between a haplotype and the lower quartile of RHR in our populations. Our findings highlight that genetic determinants of RHR may be implicated in determining cardiovascular diseases and could allow a better risk stratification.
Keywords: Calnexin; Cardiovascular Diseases; DNA-Binding Proteins; Female; Genome-Wide Association Study; Haplotypes; Heart Rate; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Transcription Factors

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Juvenile stroke in combined syndrome of hereditary hemorrhagic telangiectasia and juvenile polyposis. - Mazzucco, Sara; Benini, Luigi; Gallione, Carol; d'Adamo, Pio; Girelli, Domenico (Neurol Sci, 2014)
Keywords: Adult; Arteriovenous Malformations; Brain Ischemia; Chromosomes, Human, Pair 18; Echocardiography, Transesophageal; Embolism, Paradoxical; Embolization, Therapeutic; Epistaxis; Family Health; Humans; Intestinal Polyposis; Intracranial Embolism; Introns; Lod Score; Male; Pulmonary Artery; Smad4 Protein; Telangiectasia, Hereditary Hemorrhagic; Thalamus; Ultrasonography, Doppler, Transcranial

Lactobacillus plantarum P17630 for preventing Candida vaginitis recurrence: a retrospective comparative study. - De Seta, F; Parazzini, F; De Leo, R; Banco, R; Maso, G P; De Santo, D; Sartore, A; Stabile, G; Inglese, S; Tonon, M; Restaino, S (Eur J Obstet Gynecol Reprod Biol, 2014)
BACKGROUND: Recurrence is a frequent complaint of patients with vulvovaginal candidiasis (VVC). Although the pathogenesis of VVC remains a controversial issue, disruption of the balance between the vaginal microbiota may facilitate overgrowth by Candida. Some probiotic bacterial strains can suppress Candida albicans; Lactobacillus plantarum P17630 is able to attach to vaginal epithelial cells and significantly reduce the adhesion of C. albicans. OBJECTIVE: To evaluate the effect of the application of Lactobacillus plantarum P17630 in restoring the vaginal microbiota and prevention of relapses among women with acute VVC undergoing conventional (azole) local and main therapy. METHODS: Retrospective comparative study. We recruited 89 women with a diagnosis of VVC, who were placed into two groups on the basis of reported treatment. The control group was treated with a daily dose of 2% clotrimazole vaginal cream at bedtime for 3 days, followed by vaginal application of a capsule containing lubricant once a day for 6 days and then once a week for another 4 weeks. The probiotic group was treated with the same azole-based protocol but followed by vaginal application of a capsule containing Lactobacillus plantarum P17630 (>10₈ CFU) once a day for 6 days and then once a week for another 4 weeks beginning the day following clotrimazole discontinuation. Clinical and diagnostic patterns were monitored for three months of follow-up. RESULTS: At the end of study the probiotic-treated women showed a statistically significant increase in Lactobacillus values "+++" (80% versus 40%, p<0.001) and a better subjective resolution of symptoms such as vaginal discomfort described as burning or itching (90% versus 67.5%, p<0.03). Among controls there was a non-significant increase at 3 months of recurrence of infection, but a significant increase of women with value of pH=5 or >5. CONCLUSION: Although the results of different studies are controversial, most have suggested use of probiotics in the prevention or treatment of VVC, and no adverse effects have been reported. Our data with L. plantarum P17630 (Gyno-Canesflor - Bayer) confirm the role of this specific strain as a potential empirical preventive agent for reducing vaginal discomfort after conventional treatment of acute VVC and shifting the vaginal milieu toward a predominance of lactobacilli with an improvement of the vaginal pH value.
Keywords: Administration, Intravaginal; Adolescent; Adult; Antifungal Agents; Candidiasis, Vulvovaginal; Clotrimazole; Female; Humans; Lactobacillus plantarum; Microbiota; Middle Aged; Probiotics; Recurrence; Retrospective Studies; Secondary Prevention; Vagina; Vaginal Creams, Foams, and Jellies; Young Adult

LIG4 and RAD52 DNA repair genes polymorphisms and systemic lupus erythematosus. - De Azevêdo Silva, Jaqueline; Pancotto, João Alexandre Trés; Donadi, Eduardo Antônio; Crovella, Sergio; Sandrin-Garcia, Paula (Mol Biol Rep, 2014)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder with a strong genetic background. Nevertheless, SLE might also be triggered due to environmental factors, such as UV light exposure. DNA double strand breaks (DSBs) may be induced secondarily by UV radiation, increasing DNA immunogenicity and in SLE patients DNA repair is diminished, allowing the accumulation of DSBs and genomic instability. LIG4 and RAD52 genes play important roles in DNA repair mechanisms and a recent microarray analysis showed their differential expression in active SLE patients. In this study we investigated a potential association between LIG4 and RAD52 single nucleotide polymorphisms (SNPs) and SLE predisposition in a Southeast Brazilian population. We assessed four Tag SNPs in LIG4 and three in RAD52 gene region, encompassing most of the gene sequence, in 158 SLE patients and 212 healthy controls. We also performed SNPs analysis considering clinical manifestation, gender and ethnicity in SLE patients. Our data did not show association between LIG4 and RAD52 SNPs and SLE, its clinical manifestations or ethnicity in the tested population. The analysis regarding ethnicity and SLE clinical manifestations indicated Caucasian-derived patients as more susceptible to cutaneous and hematological alterations than the African-derived. To our knowledge, this is the first association study involving LIG4 and RAD52 genes and SLE predisposition.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; DNA Ligases; DNA Repair; Ethnic Groups; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Rad52 DNA Repair and Recombination Protein

Making the first days of life safer: time for a new protocol? - Paviotti, G; Demarini, S; Verardi, G; De Cunto, A; Davanzo, R (J Perinatol, 2014)
Keywords: Beds; Female; Humans; Infant Care; Male

Management of central venous catheters in pediatric onco-hematology using 0.9% sodium chloride and positive-pressure-valve needleless connector. - Buchini, Sara; Scarsini, Sara; Montico, Marcella; Buzzetti, Roberto; Ronfani, Luca; Decorti, Cinzia (Eur J Oncol Nurs, 2014)
PURPOSE: To describe, in a sample of pediatric onco-hematological patients, the rate of occlusions in unused central venous catheters (CVC) flushed once a week with a 0.9% sodium chloride solution through a positive-pressure-valve needleless connector. METHOD: Retrospective cohort study. Subjects aged 0-17 years were identified through a manual search in medical and nursing records and were observed for two years or until the occurrence of one of the following events: start or resume of continuous infusion; CVC removal; death. The primary study outcome was the frequency of CVC occlusion (partial or complete). RESULTS: Fifty-one patients were identified (median age 6 years). The median duration of follow-up was 169 days (IQR 111-305). During the follow up period, 14 patients (27%) had one CVC occlusion, in 2 cases (4%) the occlusion was complete, in 12 (23%) partial. All the occlusions were solved without the need for catheter removal. The lumen diameter ≤ 4.2 vs > 4.2 French showed a statistically significant association with occlusion at multivariate analysis (OR 4.0; 95% CI 1.1-14.7). CONCLUSIONS: Our findings are reassuring with respect to the management of the CVC using the adopted protocol. The study provides useful information for patient care, by verifying the performance of the adopted CVC management protocol and by identifying critical areas for nursing care.
Keywords: Adolescent; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Child, Preschool; Cohort Studies; Equipment Design; Female; Hematology; Humans; Infant; Infant, Newborn; Italy; Male; Oncology Nursing; Pediatric Nursing; Practice Guidelines as Topic; Retrospective Studies; Sodium Chloride

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Mutations of cytochrome c identified in patients with thrombocytopenia THC4 affect both apoptosis and cellular bioenergetics. - De Rocco, Daniela; Cerqua, Cristina; Goffrini, Paola; Russo, Giovanna; Pastore, Annalisa; Meloni, Francesca; Nicchia, Elena; Moraes, Carlos T; Pecci, Alessandro; Salviati, Leonardo; Savoia, Anna (Biochim Biophys Acta, 2014)
Inherited thrombocytopenias are heterogeneous diseases caused by at least 20 genes playing different role in the processes of megakaryopoiesis and platelet production. Some forms, such as thrombocytopenia 4 (THC4), are very rare and not well characterized. THC4 is an autosomal dominant mild thrombocytopenia described in only one large family from New Zealand and due to a mutation (G41S) of the somatic isoform of the cytochrome c (CYCS) gene. We report a novel CYCS mutation (Y48H) in patients from an Italian family. Similar to individuals carrying G41S, they have platelets of normal size and morphology, which are only partially reduced in number, but no prolonged bleeding episodes. In order to determine the pathogenetic consequences of Y48H, we studied the effects of the two CYCS mutations in yeast and mouse cellular models. In both cases, we found reduction of respiratory level and increased apoptotic rate, supporting the pathogenetic role of CYCS in thrombocytopenia.
Keywords: Amino Acid Sequence; Animals; Apoptosis; Base Sequence; Cells, Cultured; Child, Preschool; Cytochromes c; DNA Mutational Analysis; Embryo, Mammalian; Energy Metabolism; Family Health; Female; Fibroblasts; Humans; Lung; Male; Mice; Molecular Sequence Data; Mutation, Missense; Oxygen Consumption; Pedigree; Saccharomyces cerevisiae; Sequence Homology, Amino Acid; Thrombocytopenia

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

A neonate with a 'milky' blood. What can it be? - Bordugo, Andrea; Carlin, Eva; Demarini, Sergio; Faletra, Flavio; Colonna, Franco (Arch Dis Child Fetal Neonatal Ed, 2014)
Keywords: Female; Humans; Hyperlipoproteinemia Type IV; Infant, Newborn; Lipoprotein Lipase; Milk Proteins; Mutation

Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

No evidence of Polyomavirus and EBV infections in Italian patients with mixed cryoglobulinemia infected chronically with HCV. - Comar, Manola; Zanotta, Nunzia; Del Savio, Rossella; Vascotto, Fulvia; Calabrese, Nadia; Zorat, Francesca; Pozzato, Gabriele (J Med Virol, 2014)
Mixed cryoglobulinemia is a lymphoproliferative disorder associated with hepatitis C virus (HCV). In patients chronically affected by HCV the prevalence of mixed cryoglobulinemia is variable ranging from 0% to 56%. To verify whether polyomaviruses (PyV) play a role in this disorder a total of 222 blood samples from 63 HCV chronic patients, 43 with mixed cryoglobulinemia, 59 chronic lymphocytic leukemia, 50 polytransfused patients, and 50 blood donors were evaluated for Merkel (MCPyV), BKV, JCV, and SV40. EBV was additionally included in the analysis since association with this disorder has been reported. Mixed cryoglobulinemia patients infected chronically with HCV resulted negative for both PyV and EBV. MCPyV was found in 1 subject with Merkel Cell Carcinoma, in 10% of polytransfused and in 10% of blood donors while EBV was detected in 22% of polytransfused, 10% of B-cell lymphatic leukemia patients and 4% of blood donors (P < 0.01). Taken together, the absence of PyV and EBV in HCV-mixed cryoglobulinemia patients seems to exclude a direct involvement of these viruses in the pathogenesis of this disease while the presence of MCPyV in healthy individuals, at the same rate as in polytransfused patients, may reinforce data on a minimal role of this virus in other human pathologies.
Keywords: Adult; Base Sequence; Cryoglobulinemia; DNA, Viral; Epstein-Barr Virus Infections; Female; Hepacivirus; Hepatitis C, Chronic; Herpesvirus 4, Human; Humans; Italy; Leukemia, B-Cell; Male; Middle Aged; Polyomavirus; Polyomavirus Infections; Sequence Analysis, DNA; Vaginal Smears; Young Adult

A non-complement-fixing antibody to β2 glycoprotein I as a novel therapy for antiphospholipid syndrome. - Agostinis, Chiara; Durigutto, Paolo; Sblattero, Daniele; Borghi, Maria O; Grossi, Claudia; Guida, Filomena; Bulla, Roberta; Macor, Paolo; Pregnolato, Francesca; Meroni, Pier Luigi; Tedesco, Francesco (Blood, 2014)
A single-chain fragment variable (scFv) recognizing β2-glycoprotein 1 (β2GPI) from humans and other species was isolated from a human phage display library and engineered to contain an IgG1 hinge-CH2-CH3 domain. The scFv-Fc directed against β2GPI domain I-induced thrombosis and fetal loss, thus mimicking the effect of antibodies from patients with antiphospholipid syndrome (APS). Complement is involved in the biological effect of anti-β2GPI scFv-Fc, as demonstrated by its ability to promote in vitro and in vivo complement deposition and the failure to induce vascular thrombosis in C6-deficient rats and fetal loss in C5-depleted mice. A critical role for complement was also supported by the inability of the CH2-deleted scFv-Fc to cause vessel occlusion and pregnancy failure. This antibody prevented the pathological effects of anti-β2GPI antibodies from APS patients and displaced β2GPI-bound patient antibodies. The CH2-deleted antibody represents an innovative approach potentially useful to treat APS patients refractory to standard therapy.
Keywords: Abortion, Spontaneous; Animals; Antibodies, Monoclonal; Antiphospholipid Syndrome; Autoantigens; beta 2-Glycoprotein I; Complement Activation; Complement System Proteins; Human Umbilical Vein Endothelial Cells; Humans; Immunoglobulin G; Male; Mice; Protein Binding; Rats; Recombinant Proteins; Single-Chain Antibodies; Thrombosis; Trophoblasts

A novel deletion mutation involving TMEM38B in a patient with autosomal recessive osteogenesis imperfecta. - Rubinato, Elisa; Morgan, Anna; D'Eustacchio, Angela; Pecile, Vanna; Gortani, Giulia; Gasparini, Paolo; Faletra, Flavio (Gene, 2014)
Osteogenesis imperfecta (OI) is a hereditary bone disease characterized by decreased bone density and multiple fractures, usually inherited in an autosomal dominant manner. Several gene encoding proteins related to collagen metabolism have been described in some cases of autosomal recessive OI (including CRTAP, LEPRE1, PPIB, FKBP65, SERPINF1, BMP1, WNT1, FKBP10). Recently, TMEM38B, a gene that encodes TRIC-B, a monovalent cation-specific channel involved in calcium flux from intracellular stores and in cell differentiation, has been associated with autosomal recessive OI. Here, we describe the second deletion-mutation involving the TMEM38B gene in an 11 year-old Albanian female with a clinical phenotype of OI, born to parents with suspected consanguinity. SNP array analysis revealed a homozygous region larger than 2 Mb that overlapped with the TMEM38B locus and was characterized by a 35 kb homozygous deletion involving exons 1 and 2 of TMEM38B gene.
Keywords: Child; Chromosomes, Human, Pair 19; DNA Mutational Analysis; Exons; Female; Genes, Recessive; Homozygote; Humans; Ion Channels; Osteogenesis Imperfecta; Sequence Deletion

A novel P2RX2 mutation in an Italian family affected by autosomal dominant nonsyndromic hearing loss. - Faletra, Flavio; Girotto, Giorgia; d'Adamo, Adamo Pio; Vozzi, Diego; Morgan, Anna; Gasparini, Paolo (Gene, 2014)
Hereditary hearing loss (HHL) is a common disorder accounting for at least 60% of prelingual deafness. It is characterized by a large genetic heterogeneity, and despite the presence of a major gene, still there is a need to search for new causative mutations/genes. Very recently, a mutation within ATP-gated P2X(2) receptor (ligand-gated ion channel, purinergic receptor 2) gene (P2RX2) at DNFA41 locus has been reported leading to a bilateral and symmetrical sensorineural non-syndromic autosomal dominant HHL in two Chinese families. We performed a linkage analysis in a large Italian family with a dominant pattern of inheritance showing a significant 3.31 LOD score in a 2Mb region overlapping with the DNFA41 locus. Molecular analyses of P2RX2 identified a novel missense mutation (p.Gly353Arg) affecting a residue highly conserved across species. Visual inspection of the protein structure as obtained from comparative modeling suggests that substitution of the small glycine residue with a charged bulky residue such as an arginine that is close to the 'neck' of the region responsible for ion channel gating should have a high energetic cost and should lead to a severely destabilization of the fold. The identification of a second most likely causative mutation in P2RX2 gene further supports the possible role of this gene in causing autosomal dominant HHL.
Keywords: Amino Acid Sequence; Deafness; European Continental Ancestry Group; Female; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Receptors, Purinergic P2X2

The p53 transcriptional pathway is preserved in ATMmutated and NOTCH1mutated chronic lymphocytic leukemias. - Athanasakis, Emmanouil; Melloni, Elisabetta; Rigolin, Gian Matteo; Agnoletto, Chiara; Voltan, Rebecca; Vozzi, Diego; Piscianz, Elisa; Segat, Ludovica; dal Monego, Simeone; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
By using next generation sequencing, we have analyzed 108 B chronic lymphocytic leukemia (B-CLL) patients. Among genes involved in the TP53 pathway, we found frequent mutations in ATM (n=18), TP53 (n=10) and NOTCH1 (n=10) genes, rare mutations of NOTCH2 (n=2) and CDKN1A/p21 (n=1) and no mutations in BAX, MDM2, TNFRSF10A and TNFRSF10B genes. The in vitro treatment of primary B-CLL cells with the activator of p53 Nutlin-3 induced the transcription of p53 target genes, without significant differences between the B-CLL without mutations and those harboring either ATM or NOTCH1mutations. On the other hand, the subgroup of TP53mutated B-CLL exhibited a significantly lower induction of the p53 target genes in response to Nutlin-3 as compared to the other B-CLL samples. However, among the TP53mutated B-CLL, those showing mutations in the high hot spot region of the DNA binding domain [273-280 aa] maintained a significantly higher p53-dependent transcriptional activity as compared to the other TP53mutated B-CLL samples. Since the ability to elicit a p53-dependent transcriptional activity in vitro has a positive prognostic significance, our data suggest that ATMmutated, NOTCH1mutated and surprisingly, also a subset of TP53mutated B-CLL patients might benefit from therapeutic combinations including small molecule activator of the p53 pathway.
Keywords: Aged; Aged, 80 and over; Ataxia Telangiectasia Mutated Proteins; Base Sequence; Female; Genes, p53; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Models, Molecular; Molecular Sequence Data; Mutation; Receptor, Notch1; Signal Transduction; Tumor Suppressor Protein p53

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Pharmacogenetics of azathioprine in inflammatory bowel disease: a role for glutathione-S-transferase? - Stocco, Gabriele; Pelin, Marco; Franca, Raffaella; De Iudicibus, Sara; Cuzzoni, Eva; Favretto, Diego; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2014)
Azathioprine is a purine antimetabolite drug commonly used to treat inflammatory bowel disease (IBD). In vivo it is active after reaction with reduced glutathione (GSH) and conversion to mercaptopurine. Although this reaction may occur spontaneously, the presence of isoforms M and A of the enzyme glutathione-S-transferase (GST) may increase its speed. Indeed, in pediatric patients with IBD, deletion of GST-M1, which determines reduced enzymatic activity, was recently associated with reduced sensitivity to azathioprine and reduced production of azathioprine active metabolites. In addition to increase the activation of azathioprine to mercaptopurine, GSTs may contribute to azathioprine effects even by modulating GSH consumption, oxidative stress and apoptosis. Therefore, genetic polymorphisms in genes for GSTs may be useful to predict response to azathioprine even if more in vitro and clinical validation studies are needed.
Keywords: 6-Mercaptopurine; Animals; Apoptosis; Azathioprine; Glutathione; Glutathione Transferase; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Oxidative Stress; Pharmacogenetics; Polymorphism, Genetic

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

A population-based approach to study the impact of PROP perception on food liking in populations along the Silk Road. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; Dognini, Maddalena; Tepper, Beverly J; Gasparini, Paolo (PLoS One, 2014)
Taste is one of the main factors determining food choices. Differences in PROP bitter taste perception have been implicated in individual differences in food preferences and selection. The present study examined associations between, PROP phenotypes, self-reported food liking and TAS2R38 polymorphisms, the major gene implicated in PROP bitterness, in six different populations of the Caucasus and Central Asia, located along the ancient Silk Road. Differences in the distribution of PROP phenotypes across populations were detected, with a higher frequency of super tasters in Tajikistan (31.3%) and Armenia (39.0%) and a higher frequency of non tasters in Georgia (50.9%). While no relationships were observed between PROP phenotypes and food liking using standard statistical tests, we used an approach based on comparison of distance matrices derived from these data. The first matrix compared the food liking ratings of each population to all others pairwise using the Kruskal-Wallis test (at p<0.00063), and the second one compared the distribution of PROP phenotypes across all populations in a similar manner calculating the chi-square statistic as a distance measure. A strong correlation between the two matrices was found (Mantel test: r = 0.67, p-value = 0.03), suggesting that the pattern of food liking across populations was closely related to the distribution of PROP phenotypes. This same relationship was not observed when TAS2R38 genotypes were substituted for PROP phenotypes in this analysis. Our data suggest that a population-based approach utilizing distance matrices is a useful technique for detecting PROP-related differences in food liking and can be applied to other taste phenotypes.
Keywords: Armenia; Azerbaijan; Food; Genetic Association Studies; Genotype; Haplotypes; Humans; Polymorphism, Single Nucleotide; Propylthiouracil; Receptors, G-Protein-Coupled; Tajikistan; Taste; Taste Perception; Uzbekistan

Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Risk of Essure microinsert abdominal migration: case report and review of literature. - Ricci, Giuseppe; Restaino, Stefano; Di Lorenzo, Giovanni; Fanfani, Francesco; Scrimin, Federica; Mangino, Francesco P (Ther Clin Risk Manag, 2014)
PURPOSE: To report a case of Essure microinsert abdominal migration and literature review. METHODS: A 41-year-old woman was counseled to undergo Essure sterilization. The procedure was hampered by the presence of endometrial cavity adhesions, obscuring left tubal ostium. By using microscissors the adhesions were progressively lysed. Since the procedure had become very painful, the patient required general anesthesia. Once adhesion lysis was completed, the tubal ostium was well visible. Both devices were then easily introduced into the fallopian tubes. At the end of the procedure, five coils were visible on the right side and five coils on the left side, as recommended. RESULTS: The 3-month hysterosalpingogram follow-up suspected abdominal migration of the left device. Laparoscopy confirmed the device displacement in the left lower abdominal quadrant. Both fallopian tubes and the uterus appeared normal. No signs of perforation were detected. The device was embedded into the omentum, but it was easily removed. Bilateral tubal sterilization was performed by bipolar coagulation. CONCLUSION: There are only 13 cases, including the present, of Essure abdominal migration in the literature. In most cases, abdominal displacement of the microinsert is asymptomatic and does not induce tissue damage. However, in some cases, it may cause a severe adverse event, requiring major surgery. Therefore, removal of the migrated device should be performed as soon as possible. Moreover, during presterilization counseling, the patient should also be correctly informed about the risk of this rare but relevant complication, as well as about the surgical interventions that could be required to solve it.

The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection. - Calitri, Carmelina; Gabiano, Clara; Galli, Luisa; Chiappini, Elena; Giaquinto, Carlo; Buffolano, Wilma; Genovese, Orazio; Esposito, Susanna; Bernardi, Stefania; de Martino, Maurizio; Tovo, Pier-Angelo (BMC Infect Dis, 2014)
BACKGROUND: In the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing. METHODS: A description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children. RESULTS: Twenty-three women had 29 pregnancies. They had started an antiretroviral therapy at a median of 7.7 years (interquartile range, IQR 2.3 - 11.4), and had experienced a median of 4 therapeutic regimens (IQR 2-6). Twenty women (87%) had taken zidovudine (AZT) before pregnancy, in 14 cases as a starting monotherapy. In 21 pregnancies a protease inhibitor-based regimen was used. At delivery, the median of CD4+ T lymphocytes was 450/μL (IQR 275-522), and no viral load was detectable in 15 cases (reported in 21 pregnancies). Twenty-eight children were delivered through caesarean section (median gestational age: 38 weeks, IQR 36-38, median birth weight: 2550 grams, IQR 2270 - 3000). Intravenous AZT was administered during delivery in 26 cases. All children received oral AZT (median: 42 days, IQR 31 - 42), with no adverse events reported. No child acquired HIV-1 infection. CONCLUSIONS: Despite a long history of maternal infection, multiple antiretroviral regimens and, perhaps, the development of drug-resistant viruses, the risk of mother-to-child transmission does not seem to have increased among the second-generation of HIV-1 exposed infants.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Birth Weight; Cesarean Section; Child; Female; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Italy; Male; Pediatrics; Pregnancy; Pregnancy Complications, Infectious; Pregnancy Outcome; Prospective Studies; Viral Load; Young Adult; Zidovudine

Severe neonatal hyperbilirubinemia and UGT1A1 promoter polymorphism. - Travan, Laura; Lega, Sara; Crovella, Sergio; Montico, Marcella; Panontin, Elisa; Demarini, Sergio (J Pediatr, 2014)
OBJECTIVE: To assess whether UGT1A1 promoter polymorphisms associated with Gilbert Syndrome (GS) occur with a greater frequency in neonates with severe hyperbilirubinemia. STUDY DESIGN: In a case-control study performed at a single hospital center in Italy, 70 case subjects with severe hyperbilirubinemia (defined as bilirubin level ≥20 mg/dL or 340 μmol/L) and 70 controls (bilirubin level <12 mg/dL or 210 μmol/L) were enrolled. Both case and control subjects were full term newborns. Polymerase chain reaction analysis on blood spot was performed to determine the frequency of UGTA1A1 promoter polymorphisms in cases and controls. RESULTS: No statistical difference in the prevalence of UGTA1A1 gene variants was found between cases and controls (P = 1). Thirteen infants homozygous for (TA)7 polymorphism associated with GS were in the case group (18.6%) and 14 in the control group (20.0%). A heterozygous group was also equally distributed between cases (44.3%) and controls (42.9%). No (TA)8 repeat was found in the 2 groups. CONCLUSIONS: In our study population, GS polymorphism alone does not appear to play a major role in severe neonatal hyperbilirubinemia in neonates without signs of hemolysis.
Keywords: Case-Control Studies; Female; Genotype; Gilbert Disease; Glucuronosyltransferase; Humans; Hyperbilirubinemia, Neonatal; Infant, Newborn; Male; Polymerase Chain Reaction; Polymorphism, Genetic; Prevalence; Promoter Regions, Genetic

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Teleradiology for remote consultation using iPad improves the use of health system human resources for paediatric fractures: prospective controlled study in a tertiary care hospital in Italy. - Zennaro, Floriana; Grosso, Daniele; Fascetta, Riccardo; Marini, Marta; Odoni, Luca; Di Carlo, Valentina; Dibello, Daniela; Vittoria, Francesca; Lazzerini, Marzia (BMC Health Serv Res, 2014)
BACKGROUND: The growing cost of health care and lack of specialised staff have set e-Health high on the European political agenda. In a prospective study we evaluated the effect of providing images for remote consultation through an iPad on the number of in-hospital orthopaedic consultations for children with bone fractures. METHODS: Children from 0 to 18 years diagnosed with a bone fracture by the radiologist during the hours when an orthopaedic service is provided only on-call were eligible for enrollment. Cases were enrolled prospectively during September and October 2013. A standard approach (verbal information only, no X-Ray provided remotely) was compared to an experimental approach (standard approach plus the provision of X-ray for remote consultation through an iPad). The primary outcome was the number of orthopaedic in-hospital consultations that occurred. Other outcomes included: immediate activation of other services; time needed for decision-making; technical difficulties; quality of images and diagnostic confidence (on a likert scale of 1 to 10). RESULTS: Forty-two children were enrolled in the study. Number of in-hospital consultancies dropped from 32/42 (76.1%) when no X-ray was provided to 16/42 (38%) when the X-rays was provided (p < 0.001). With remote X-ray consultation in 14/42 (33.3%) cases services such as surgery and plaster room could be immediately activated, compared to no service activated without teleradiology (p < 0.001). Average time for decision making was 23.4 ± 21.8 minutes with remote X-ray consultation, compared to 56.2 ± 16.1 when the X-ray was not provided (p < 0.001). The comparison between images on the iPad and on the standard system for X- Ray visualisation resulted in a non statistically significant difference in the quality of images (average score 9.89 ± 0.37 vs 9.91 ± 0.30; p = 0.79), and in non statistically significant difference in diagnostic confidence (average score 9.91 ± 0.32 vs 9.92 ± 0.31; p = 0.88). CONCLUSIONS: Remote X-ray consultation through Aycan OsiriX PRO and iPad should be considered as a means for reducing the need of in-hospital orthopaedic consultation during on-call times, and potentially decrease the cost of care for the health system. In the future, alternative systems less expensive than Aycan OsiriX PRO should be further developed and tested.
Keywords: Adolescent; Child; Child, Preschool; Computers, Handheld; Decision Making; Fractures, Bone; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Remote Consultation; Teleradiology; Time Factors

TNF-α SNP rs1800629 and risk of relapse in childhood acute lymphoblastic leukemia: relation to immunophenotype. - Franca, Raffaella; Rebora, Paola; Athanasakis, Emmanouil; Favretto, Diego; Verzegnassi, Federico; Basso, Giuseppe; Tommasini, Alberto; Valsecchi, Maria Grazia; Decorti, Giuliana; Rabusin, Marco (Pharmacogenomics, 2014)
AIM: In the AIEOP-BFM ALL (Associazione Italiana Ematologia Oncologia Pediatrica-Berlin Frankfurt Münster acute lymphoblastic leukemia) 2000 protocol, 70% of relapsed patients had favorable prognostic features and fell within less intensive polychemotherapeutic regimens, suggesting the need for better assessing lower risk stratification. MATERIALS & METHODS: A novel two-phase study design selected 614 children to be genotyped for TNF-α SNP rs1800629 (-308G>A). A weighted Cox model was applied to evaluate the SNP effect on hazard of relapse, adjusting for immunophenotype, risk group, age and gender and including interaction terms. RESULTS: Significant interaction was found with immunophenotypes (p = 0.0007, with minor allele genotypes being adverse genetic markers in B-cell acute lymphoblastic leukemia and protective ones in T-cell acute lymphoblastic leukemia), and also with risk protocols (p = 0.0041, with minor allele genotypes as prognostic factor of relapse for standard risk patients [only one T-cell acute lymphoblastic leukemia in the subgroup analyzed]). CONCLUSION: The presence of at least one A allele in TNF-α SNP rs1800629 should suggest a closer monitoring in B-cell acute lymphoblastic leukemia standard risk patients.
Keywords: Adolescent; Antineoplastic Agents; Child; Child, Preschool; Drug Resistance, Neoplasm; Female; Genotype; Humans; Infant; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Phenotype; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Risk Assessment; Steroids; Tumor Necrosis Factor-alpha

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Unusual splice site mutations disrupt FANCA exon 8 definition. - Mattioli, Chiara; Pianigiani, Giulia; De Rocco, Daniela; Bianco, Anna Monica Rosaria; Cappelli, Enrico; Savoia, Anna; Pagani, Franco (Biochim Biophys Acta, 2014)
The pathological role of mutations that affect not conserved splicing regulatory sequences can be difficult to determine. In a patient with Fanconi anemia, we identified two unpredictable splicing mutations that act on either sides of FANCA exon 8. In patients-derived cells and in minigene splicing assay, we showed that both an apparently benign intronic c.710-5T>C transition and the nonsense c.790C>T substitution induce almost complete exon 8 skipping. Site-directed mutagenesis experiments indicated that the c.710-5T>C transition affects a polypyrimidine tract where most of the thymidines cannot be compensated by cytidines. The c.790C>T mutation located in position -3 relative to the donor site induce exon 8 skipping in an NMD-independent manner and complementation experiments with modified U1 snRNAs showed that U1 snRNP is only partially involved in the splicing defect. Our results highlight the importance of performing splicing functional assay for correct identification of disease-causing mechanism of genomic variants and provide mechanistic insights on how these two FANCA mutations affect exon 8 definition.
Keywords: Base Sequence; Cell Line, Tumor; Codon, Nonsense; Exons; Fanconi Anemia Complementation Group A Protein; HeLa Cells; Humans; Introns; Molecular Sequence Data; Mutagenesis, Site-Directed; Ribonucleoproteins, Small Nuclear; RNA Splice Sites; RNA Splicing

When does postnatal catch-up fat occur in late preterm infants? - De Cunto, Angela; Paviotti, Giulia; Demarini, Sergio (Acta Paediatr, 2014)
Keywords: Body Composition; Humans; Infant, Premature

Breastfeeding and neonatal weight loss in healthy term infants. - Davanzo, Riccardo; Cannioto, Zemira; Ronfani, Luca; Monasta, Lorenzo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Neonatal weight loss is universally recognized, yet poorly understood. Limited professional consensus exists on the definition of lower limit of safe weight loss. OBJECTIVE: Our aim was to assess the extent of neonatal weight loss and its association with selected clinical variables in a population of healthy term infants cared for using a specific protocol on weight loss. METHODS: We retrospectively considered 1003 infants consecutively admitted to the regular nursery of the Institute for Maternal and Child Health "Burlo Garofolo" (Trieste, Italy). We studied the relationship of selected variables with neonatal weight loss recorded during the hospital stay. We also analyzed all readmissions in the first month of life as a result of weight loss and its complications. RESULTS: We observed a mean absolute weight loss of 228 g ± 83g, and a mean percent weight loss of 6.7% ± 2.2%. Weight loss ≥ 10% and > 12% were 6% and 0.3%, respectively. In multivariate logistic regression, cesarean section, hot season, any formula feeding, and jaundice not requiring phototherapy were independently associated with neonatal weight loss ≥ 8%. Conversely, low gestational age status was associated with lower weight loss. Readmission within the first month of life because of dehydration occurred in 0.3% of infants. CONCLUSIONS: Breastfeeding, compared to formula feeding, may not be a risk factor for greater early neonatal weight loss, at least in contexts in which weight is routinely monitored, breastfeeding is repeatedly assessed and appropriately supported, and careful supplementation is prescribed to limit and promptly treat excess weight loss and its related complications.
Keywords: Apgar Score; Breast Feeding; Delivery, Obstetric; Gestational Age; Humans; Infant, Newborn; Length of Stay; Patient Readmission; Retrospective Studies; Seasons; Weight Loss

Breastfeeding at NICU discharge: a multicenter Italian study. - Davanzo, Riccardo; Monasta, Lorenzo; Ronfani, Luca; Brovedani, Pierpaolo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Human milk is the optimal form of nutrition for infants, especially sick or compromised infants, yet international data suggest that breastfeeding (feeding at the breast) and the use of expressed human milk (mother's and donor's milk) are limited in patients cared for in the neonatal intensive care unit (NICU). OBJECTIVE: The goal of this study was to examine feeding status at hospital discharge among high risk infants. METHODS: We used the 1991 World Health Organization infant feeding definitions, applied to the 72 hour period preceding discharge from the NICU. The study sample consisted of all high risk infants discharged from July 1, 2005, to June 30, 2006 from 13 Italian NICUs. Data on infant feeding in the last 72 hours were collected at discharge from the medical records. RESULTS: We recorded data from 2948 subjects with a median gestational age of 35 weeks (IQR, 32-38), a median birth weight of 2200 g (IQR, 1630-2920) and a median length of stay of 16 days (IQR, 8-33). At discharge, 28% of all infants were fed exclusively with human milk: 31%, 25%, 22% and 33% respectively in the <1500 g, 1500-2000 g, 2000-2499 g and ≥ 2500 g birth weight categories. The proportion of infants not fed with human milk varied from 6 to 82% across different centers. CONCLUSION: Our study found limited breastfeeding and use of human milk among the NICU infants at discharge. At discharge, infants with a birth weight 1500-2499 g were fed exclusively with human milk less than those in higher or lower birth weight categories.
Keywords: Breast Feeding; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Italy; Logistic Models; Multivariate Analysis; Patient Discharge

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

Infantile bilateral glaucoma in a child with ectodermal dysplasia. - Callea, Michele; Vinciguerra, Agatino; Willoughby, Colin E; Deroma, Laura; Clarich, Gabriella (Ophthalmic Genet, 2013)
Ectodermal dysplasia is a rare disease which affects at least two ectodermal-derived structures such as hair, nails, skin, sweat glands and teeth. Approximately 200 different conditions have been classified as an ectodermal dysplasia and X-linked hypohidrotic ectodermal dysplasia (XHED) represents the commonest form. Clinically, XHED is characterized by hypotrichosis, hypohidrosis and hypodontia. A variety of ocular manifestations have been reported in XHED, the most common being dryness of eyes due to tear deficiency and instability of the film secondary to the absence of meibomian gland function. Here we report a child with the distinctive clinical features of XHED confirmed with molecular diagnosis who presented with infantile bilateral glaucoma, in addition to the classical ocular involvement in XHED.
Keywords: Antihypertensive Agents; Child; Ectodermal Dysplasia; Ectodysplasins; Humans; Hydrophthalmos; Intraocular Pressure; Male; Mutation; Polymorphism, Single Nucleotide; Tonometry, Ocular

More on prolonged pacifier usage and risk of dental problems: an Italian survey of current clinical practice. - De Cunto, Angela; Minen, Federico; Ventura, Alessandro (J Pediatr Nurs, 2013)
Keywords: Female; Guidelines as Topic; Humans; Male; Pacifiers; Sudden Infant Death

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

The non-genotoxic activator of the p53 pathway Nutlin-3 shifts the balance between E2F7 and E2F1 transcription factors in leukemic cells. - di Iasio, Maria Grazia; Zauli, Giorgio (Invest New Drugs, 2013)
The effect of Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, was investigated on the steady-state mRNA levels of the transcription factors E2F1 and E2F7 in a cohort of primary B-chronic lymphocytic leukemia (B-CLL) patient samples (n = 15) and normal peripheral blood mononuclear cells (PBMC). A 24-h treatment with Nutlin-3 significantly down-regulated E2F1 and promoted the concomitant up-regulation of E2F7 in both leukemic and normal cells. Our data suggest that the ability of Nutlin-3 to up-regulate E2F7 likely represents an important molecular determinant in the anti-proliferative activity of Nutlin-3.
Keywords: Case-Control Studies; Cells, Cultured; E2F1 Transcription Factor; E2F7 Transcription Factor; Gene Expression Regulation, Leukemic; Humans; Imidazoles; In Situ Hybridization, Fluorescence; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; Piperazines; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Tumor Suppressor Protein p53

A novel CRYBB2 missense mutation causing congenital autosomal dominant cataract in an Italian family. - Faletra, Flavio; d'Adamo, Adamo Pio; Pensiero, Stefano; Athanasakis, Emmanouil; Catalano, Dario; Bruno, Irene; Gasparini, Paolo (Ophthalmic Genet, 2013)
Congenital cataract is a leading cause of visual impairment in children and brings approximately 10% of childhood blindness worldwide. Molecular analysis revealed ~60 loci to be associated with several phenotypes of childhood cataracts. Until now, more than 30 loci and 18 genes on different chromosomes have been associated with autosomal dominant congenital cataract (ADCC). Here, we present a three-generation Italian family with a non syndromic ADCC. A linkage analysis carried out using HumanCytoSNP-12 DNA Analysis BeadChip led us to identify ten genomic regions virtually involved in the disease. All the genes located in these regions were scored for possible relationship with ADCC and, according to a strict clinical and genetic selection, 4 genes have been analyzed. A novel sequence variant was found in the CRYBB2 gene (p.Ser143Phe). This variant affects a conserved aminoacid in the third Greek key motif of the protein, cosegregates with the disease phenotype in all affected individuals and is not present both in the unaffected family members and 100 healthy control subjects. Finally, we identified the first CRYBB2 mutation in an Italian family causing a clinical picture of ADCC.
Keywords: Amino Acid Sequence; beta-Crystallin B Chain; Cataract; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genotype; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Third trimester abdominal circumference, estimated fetal weight and uterine artery doppler for the identification of newborns small and large for gestational age. - Di Lorenzo, Giovanni; Monasta, Lorenzo; Ceccarello, Matteo; Cecotti, Vera; D'Ottavio, Giuseppina (Eur J Obstet Gynecol Reprod Biol, 2013)
OBJECTIVE: To understand if ultrasound biometric evaluation at 30-32 weeks of gestation is a valuable screening tool for the detection of small-for-gestational-age (SGA) and large-for-gestational-age (LGA) infants at birth in a low risk population. STUDY DESIGN: We enrolled 1848 pregnant women with singleton pregnancy undergoing routine fetal biometry. We divided the infants into four groups: moderate SGA, severe SGA, moderate LGA and severe LGA. We considered third-trimester estimated fetal weight (EFW), abdominal circumference (AC), EFW centile (EFWc), AC centile (ACc) and compared their prediction toward SGA and LGA to determine which of these parameters was the best estimator for fetal size. Then we took the strongest predictive value and added all history-related and ultrasound factors to run a stepdown multivariate logistic regression. All the variables were then dichotomized and sensitivity models only for statistically significant parameters were calculated. RESULTS: We identified the following predictive factors for each outcome: for severe SGA: EFWc with p<0.001, uterine artery pulsatility index (UtA PI) with p<0.002. For moderate SGA: EFWc with p<0.001, UtA PI with p<0.004, maternal preeclampsia p<0.002. For moderate and severe LGA: EFWc with p<0.001. CONCLUSION: We can detect in a low-risk population a group at risk of growth deviations. Adding Doppler velocimetry to 30-32 weeks EFWc improves the specificity (84%) regarding SGA newborns, maintaining a good sensitivity (71%), and reducing the population to be re-screened from 27 to 17%. An ultrasound examination at 34-36 weeks or the clinical assessment of maternal risk factors remain the best tools for LGA newborns.
Keywords: Adult; Anthropometry; Birth Weight; Diabetes, Gestational; Female; Fetal Growth Retardation; Fetal Weight; Gestational Age; Humans; Hypertension, Pregnancy-Induced; Infant, Newborn; Infant, Small for Gestational Age; Pregnancy; Pregnancy Trimester, Third; Prospective Studies; Sensitivity and Specificity; Ultrasonography, Prenatal; Uterine Artery

Under pressure. - De Cunto, Angela; Berti, Irene; Minute, Marta; Longo, Giorgio (Eur J Pediatr, 2013)
Physical urticaria is a rare but challenging subset of chronic urticaria. Wheals of pressure urticaria are typically delayed in appearance. A pressure test can easily be done to confirm the diagnosis.
Keywords: Child; Humans; Male; Pressure; Urticaria

Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53

Acute and recurrent pancreatitis in children: exploring etiological factors. - Minen, Federico; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro (Scand J Gastroenterol, 2012)
OBJECTIVE: Etiologies of acute pancreatitis (AP) in children are more variable than in adults, including drugs, traumas, infections and multisystem disorders as well as biliary anomalies. While causes of pancreatitis have been extensively analyzed, different series reported different causes. The aims of this study were: 1) to assess the etiological factors of acute and recurrent pancreatitis in a pediatric population from a tertiary care hospital; 2) to assess the usefulness of imaging studies in diagnosing etiologies of pancreatitis. MATERIAL AND METHODS: Thirty-four children (median age 11 years, 23 males) with AP and 11 with recurrent pancreatitis were retrospectively studied to assess etiology of pancreatitis in children. RESULTS: The most common etiologies of AP were medications (11/34) and biliary tract diseases (9/34), whereas systemic diseases accounted for a small percentage of case. Among patients with recurrent episodes, biliary anomalies were the most common cause (6/11), whereas only 2 out of 11 patients with recurrent pancreatitis presented a hereditary cause. CONCLUSIONS: This study highlights that etiologies of AP in children are variable. Epidemiology of AP could be influenced by single center's characteristics. Anatomic anomalies should be ruled out and genetic causes should be considered in recurrent cases.
Keywords: Adolescent; Azathioprine; Biliary Tract; Biliary Tract Diseases; Carrier Proteins; Child; Child, Preschool; Cholangiography; Cholangiopancreatography, Endoscopic Retrograde; Drug-Related Side Effects and Adverse Reactions; Female; Humans; Immunosuppressive Agents; Magnetic Resonance Imaging; Male; Pancreatitis; Recurrence; Retrospective Studies; Tomography, X-Ray Computed

Asbestos and SV40 in malignant pleural mesothelioma from a hyperendemic area of north-eastern Italy. - Comar, Manola; Zanotta, Nunzia; Pesel, Giuliano; Visconti, Patrizia; Maestri, Iva; Rinaldi, Rosa; Crovella, Sergio; Cortale, Maurizio; De Zotti, Renata; Bovenzi, Massimo (Tumori, 2012)
AIMS AND BACKGROUND: Malignant mesothelioma is a fatal cancer of increasing incidence in north-eastern Italy. Together with asbestos, the polyomavirus SV40 was hypothesized to contribute to the onset of malignant mesothelioma. To investigate the putative role of SV40 in the individual susceptibility to asbestos-induced malignant mesothelioma, we conducted a molecular epidemiological study on a series of malignant mesothelioma patients from an area in north-eastern Italy hyperendemic for malignant pleural mesothelioma. METHODS AND STUDY DESIGN: We collected 63 mesothelioma samples from incidence cases of patients diagnosed with malignant pleural mesothelioma in the period 2009-2010. DNA was extracted from patients' tissue biopsies using the BioRobot EZ1 Qiagen workstation. SV40 sequence detection and quantification was performed by specific real time PCR. The 74.6% of the 63 enrolled patients had a history of asbestos exposure. The epithelioid histotype was more prevalent in males (64.0%) and the mixed in females (61.5%) who showed significantly higher cancer co-morbidity (46.1% vs 12%, P = 0.005). SV40 was detected in 22% of MM tumors, with a low viral load. In SV40-positive patients, a threefold increased risk of asbestos exposure was observed, more evident in females (OR 4.32) than in males (OR 1.20). CONCLUSIONS: Our findings indicate that a high prevalence of SV40 was present in malignant mesothelioma incident cases from an area hyperendemic for malignant mesothelioma in north-eastern Italy. Although asbestos is considered the main risk factor in malignant mesothelioma onset, a role for SV40 could be hypothesized.
Keywords: Adult; Aged; Asbestos; Carcinogens; Disease Susceptibility; DNA, Viral; Endemic Diseases; Female; Humans; Italy; Male; Mesothelioma; Middle Aged; Pleural Neoplasms; Polyomavirus Infections; Real-Time Polymerase Chain Reaction; Risk Factors; Simian virus 40; Tumor Virus Infections; Viral Load

Association between BclI polymorphism in the NR3C1 gene and in vitro individual variations in lymphocyte responses to methylprednisolone. - Cuzzoni, Eva; De Iudicibus, Sara; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (Br J Clin Pharmacol, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT: In vitro lymphocyte steroid sensitivity has been suggested as a useful tool to predict in vivo response to glucocorticoid treatment in different inflammatory chronic diseases. A correlation between genetic polymorphisms and clinical response to glucocorticoids has been demonstrated in these patients. WHAT THIS STUDY ADDS: The BclI polymorphism in the glucocorticoid receptor (NR3C1) gene is associated with higher methylprednisolone potency in vitro. The combined evaluation of the in vitro sensitivity to methylprednisolone and BclI polymorphism could represent an aid for physicians to adjust therapy a priori. AIM To evaluate the association between the in vitro sensitivity of peripheral blood mononuclear cells (PBMCs) to methylprednisolone (MP) and the presence of genetic polymorphisms involved in glucocorticoid (GC) response. METHODS: In vitro MP inhibition of the proliferation of lymphocytes stimulated with concanavalin A was determined. Non linear regression of dose-response data was performed computing the MP concentration required to reduce proliferation to 50% (IC(50) ). The maximum inhibition achievable at the highest MP concentration (I(max) ) was also calculated. Moreover, the Taqman technique was used to analyze the BclI polymorphism in the NR3C1 gene and the Leu155His polymorphism in the NALP1 gene. RESULTS: A significant association between the BclI mutated genotype and an increased in vitro sensitivity to GCs was observed. CONCLUSIONS: The a priori evaluation of the BclI polymorphism, associated with a lymphocyte proliferation assay, could represent a useful diagnostic tool for the optimization of steroid treatment.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Apoptosis Regulatory Proteins; Cyclin D1; Dose-Response Relationship, Drug; Female; Genotype; Glucocorticoids; Humans; Lymphocytes; Male; Methylprednisolone; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Glucocorticoid; Young Adult

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

A case of familial hemiplegic migraine associated with a novel ATP1A2 gene mutation. - De Cunto, Angela; Bensa, Marco; Tonelli, Alessandra (Pediatr Neurol, 2012)
Hemiplegic migraine constitutes an unusual form, characterized by periodic attacks of migraine with a motor component (hemiplegia). Familial forms are dominantly inherited, and are attributable to mutations in genes encoding proteins involved in ion transportation, including ATP1A2, which codes for the α-2 isoform of the sodium-potassium adenosine triphosphatase, a P-type cation transport adenosine triphosphatase, and responsible for the so-called familial hemiplegic migraine type 2. We describe a 9-year-old boy affected by familial hemiplegic migraine, with a novel ATP1A2 gene mutation (c.1799T>C p.V600A) in exon 13. Long-term treatment with flunarizine resulted in a good clinical response and the prevention of further attacks.
Keywords: Amino Acid Sequence; Child, Preschool; Humans; Male; Migraine with Aura; Molecular Sequence Data; Mutation; Pedigree; Sodium-Potassium-Exchanging ATPase

Clinical and laboratory features of 103 patients from 42 Italian families with inherited thrombocytopenia derived from the monoallelic Ala156Val mutation of GPIbα (Bolzano mutation). - Noris, Patrizia; Perrotta, Silverio; Bottega, Roberta; Pecci, Alessandro; Melazzini, Federica; Civaschi, Elisa; Russo, Sabina; Magrin, Silvana; Loffredo, Giuseppe; Di Salvo, Veronica; Russo, Giovanna; Casale, Maddalena; et al. (Haematologica, 2012)
BACKGROUND: Bernard-Soulier syndrome is a very rare form of inherited thrombocytopenia that derives from mutations in GPIbα, GPIbβ, or GPIX and is typically inherited as a recessive disease. However, some years ago it was shown that the monoallelic c.515C>T transition in the GPIBA gene (Bolzano mutation) was responsible for macrothrombocytopenia in a few Italian patients. DESIGN AND METHODS: Over the past 10 years, we have searched for the Bolzano mutation in all subjects referred to our institutions because of an autosomal, dominant form of thrombocytopenia of unknown origin. RESULTS: We identified 42 new Italian families (103 cases) with a thrombocytopenia induced by monoallelic Bolzano mutation. Analyses of the geographic origin of affected pedigrees and haplotypes indicated that this mutation originated in southern Italy. Although the clinical expression was variable, patients with this mutation typically had a mild form of Bernard-Soulier syndrome with mild thrombocytopenia and bleeding tendency. The most indicative laboratory findings were enlarged platelets and reduced GPIb/IX/V platelet expression; in vitro platelet aggregation was normal in nearly all of the cases. CONCLUSIONS: Our study indicates that monoallelic Bolzano mutation is the most frequent cause of inherited thrombocytopenia in Italy, affecting 20% of patients recruited at our institutions during the last 10 years. Because many people from southern Italy have emigrated during the last century, this mutation may have spread to other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bernard-Soulier Syndrome; Child; Child, Preschool; Family Health; Female; Heterozygote; Humans; Infant; Italy; Male; Membrane Glycoproteins; Middle Aged; Mutation, Missense; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Genetic; Thrombocytopenia; Thrombopoietin; Tubulin; Young Adult

The clinical interpretation and significance of electronic fetal heart rate patterns 2 h before delivery: an institutional observational study. - Maso, Gianpaolo; Businelli, Caterina; Piccoli, Monica; Montico, Marcella; De Seta, Francesco; Sartore, Andrea; Alberico, Salvatore (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the clinical significance of intrapartum fetal heart rate (FHR) monitoring in low-risk pregnancies according to guidelines and specific patterns. METHODS: An obstetrician, blinded to neonatal outcome, retrospectively reviewed 198 low-risk cases that underwent continuous electronic fetal monitoring (EFM) during the last 2 h before delivery. The tracings were interpreted as normal, suspicious or pathological, according to specific guidelines of EFM and by grouping the different FHR patterns considering baseline, variability, presence of decelerations and bradycardia. The EFM groups and the different FHR-subgroups were associated with neonatal acid base status at birth, as well as the short-term neonatal composite outcome. Comparisons between groups were performed with Kruskal-Wallis test. Differences among categorical variables were evaluated using Fisher's exact test. Significance was set at p < 0.05 level. RESULTS: Significant differences were found for mean pH values in the three EFM groups, with a significant trend from "normal" [pH 7.25, 95 % confidence interval (CI) 7.28-7.32] to "pathological" tracings (pH 7.20, 95 % CI 7.17-7.13). Also the rates of adverse composite neonatal outcome were statistically different between the two groups (p < 0.005). Among the different FHR patterns, tracings with atypical variable decelerations and severe bradycardia were more frequently associated with adverse neonatal composite outcome (11.1 and 26.7 %, respectively). However, statistically significant differences were only observed between the subgroups with normal tracings and bradycardia. CONCLUSIONS: In low-risk pregnancies, there is a significant association between neonatal outcome and EFM classification. However, within abnormal tracings, neonatal outcome might differ according to specific FHR pattern.
Keywords: Acidosis; Bradycardia; Female; Fetal Blood; Fetal Monitoring; Heart Rate, Fetal; Humans; Hydrogen-Ion Concentration; Infant, Newborn; Labor, Obstetric; Predictive Value of Tests; Pregnancy; Pregnancy Outcome; Retrospective Studies; Single-Blind Method; Statistics, Nonparametric; Time Factors

Cognitive assessment of very preterm infants at 2-year corrected age: performance of the Italian version of the PARCA-R parent questionnaire. - Cuttini, Marina; Ferrante, Pierpaolo; Mirante, Nadia; Chiandotto, Valeria; Fertz, Mariacristina; Dall'Oglio, Anna Maria; Coletti, Maria Franca; Johnson, Samantha (Early Hum Dev, 2012)
BACKGROUND: Serial assessments of cognitive and language development are recommended for very preterm children, but standardized neuropsychological testing is time-consuming and expensive, as well as tiring for the child. AIMS: To validate the Italian version of the PARCA-R parent questionnaire and test its clinical effectiveness in assessing cognitive development of very preterm children at 2 years of corrected age. METHODS: 120 consecutive Italian very preterm children (mean gestational age 28.8 weeks, standard deviation 2.1) were assessed in four hospitals through the Mental Development Index (MDI) of the Bayley Scales of Infant Development (BSID-II). Parents completed the PARCA-R questionnaire, designed to measure children's non-verbal and verbal (vocabulary and sentence complexity) cognitive level. The correlation between the MDI and the PARCA-R Parent Report Composite (PRC) was tested through the Pearson correlation coefficient, and the receiver operating characteristic (ROC) curve was used to identify optimal PRC cut-offs. RESULTS: Significant correlation between the PRC score and MDI (r=0.60, p<0.001) indicated good concurrent validity. The area under the ROC curve was 0.83, and the cut-off of 46 lead to 72.7% sensitivity and 77.1% specificity in identifying children with moderate/severe cognitive delay (MDI<70). Negative predictive value was 96.6 (90.3-99.3). Screening through PARCA-R would reduce the number of children with MDI≥70 undergoing BSID-II or equivalent standardized tool from 109 to 25. CONCLUSIONS: The Italian version of PARCA-R retains good discriminative power for identifying cognitive delay in 2-year very preterm children. It is well accepted by parents, and represents a valid and efficient alternative for developmental screening and outcome measurement.
Keywords: Cognition; Female; Humans; Infant; Infant, Newborn; Infant, Premature; Italy; Male; Parents; Questionnaires; ROC Curve

Congenital hemangiopericytoma. - Travan, Laura; Demarini, Sergio; Del Frate, Giovanni; Zacchi, Alberto (J Pediatr, 2012)
Keywords: Biopsy, Needle; Female; Gestational Age; Hemangiopericytoma; Humans; Immunohistochemistry; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prognosis; Risk Assessment; Soft Tissue Neoplasms; Treatment Outcome; Ultrasonography, Prenatal

Delayed diagnosis of glycogen storage disease type III. - Minen, Federico; Cont, Gabriele; De Cunto, Angela; Martelossi, Stefano; Ventura, Alessandro; Maggiore, Giuseppe; Faletra, Flavio; Gasparini, Paolo; Cassandrini, Denise (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Delayed Diagnosis; Diagnostic Errors; Glycogen Storage Disease Type I; Glycogen Storage Disease Type III; Humans; Infant; Liver; Male

Does the 1.5 Mb microduplication in chromosome band Xp22.31 have a pathogenetic role? New contribution and a review of the literature. - Faletra, Flavio; d'Adamo, Adamo Pio; Santa Rocca, Maria; Carrozzi, Marco; Perrone, Maria Dolores; Pecile, Vanna; Gasparini, Paolo (Am J Med Genet A, 2012)
Keywords: Chromosome Breakpoints; Chromosome Duplication; Chromosomes, Human, X; Hand Deformities, Congenital; Humans; Intellectual Disability; Karyotyping; Muscle Hypotonia; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases

Does the LATCH score assessed in the first 24 hours after delivery predict non-exclusive breastfeeding at hospital discharge? - Tornese, Gianluca; Ronfani, Luca; Pavan, Carla; Demarini, Sergio; Monasta, Lorenzo; Davanzo, Riccardo (Breastfeed Med, 2012)
AIM: The aims of this study were to analyze the relationship between the LATCH score assessed in the first 24 hours after delivery and non-exclusive breastfeeding at discharge and to identify a cutoff for the LATCH score in order to identify women with higher risk of non-exclusive breastfeeding who may need additional breastfeeding support. SUBJECTS AND METHODS: We conducted a prospective observational study in the Maternity Ward of the Institute for Maternal and Child Health "Burlo Garofolo" (Trieste, Italy) and collected data from 299 mother-infant dyads. RESULTS: The rate of nonexclusive breastfeeding was inversely related to the LATCH score (p<0.001) with non-exclusive breastfeeding infants scoring less (6.9) than infants exclusively breastfed at discharge (7.6) (p=0.001). In multivariate analysis, non-exclusive breastfeeding was also associated with cesarean section, primiparity, and infant phototherapy. In order to support maternity staff in providing targeted interventions, we identified four LATCH score cutoffs associated with as many risk groups for non-exclusive breastfeeding at discharge. CONCLUSIONS: The LATCH score is a useful tool to identify mother-infant pairs who might benefit from additional skilled support in specific subgroups at risk of non-exclusive breastfeeding at discharge. Future research is needed to explore if the LATCH score assessed in the first days of life can also predict the duration of breastfeeding.
Keywords: Adult; Breast Feeding; Female; Health Promotion; Humans; Infant, Newborn; Italy; Logistic Models; Multivariate Analysis; Patient Care Planning; Patient Discharge; Prospective Studies; Risk Assessment; ROC Curve; Sensitivity and Specificity; Social Support

The effect of clodronate on a mevalonate kinase deficiency cellular model. - Zanin, Valentina; Marcuzzi, Annalisa; Piscianz, Elisa; Vuch, Josef; Bianco, Anna Monica; Monasta, Lorenzo; Decorti, Giuliana; Crovella, Sergio (Inflamm Res, 2012)
BACKGROUND: A potential anti-inflammatory effect of clodronate--an aminobisphosphonate--was described to antagonize the pro-inflammatory effects of the block in the mevalonate pathway, the main feature of a rare auto-inflammatory disease called mevalonate kinase deficiency (MKD). OBJECTIVE: In this study we evaluated the potential anti-inflammatory effect of clodronate in MKD--a still orphan drug pediatric disease. METHODS: We studied some biological parameters, nitric oxide production using Griess reagents and programmed cell death by flow cytometry, as common inflammatory parameters in MKD, in the presence of different doses of clodronate (1, 10 and 100 μM). RESULTS: In our cellular model and in monocytes from patients with MKD, clodronate induced an increase in programed cell death and nitric oxide production in comparison with non-treated cells. CONCLUSION: Our findings suggest that clodronate does not have an anti-inflammatory effect as previously reported but that it increases the epiphenomena of this pediatric disease.
Keywords: Adolescent; Adult; Alendronate; Animals; Anti-Inflammatory Agents; Apoptosis; Cell Line; Cells, Cultured; Child; Clodronic Acid; Female; Humans; Inflammation; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Models, Biological; Monocytes; Nitric Oxide; Young Adult

Effects of hormonal contraception on vaginal flora. - De Seta, Francesco; Restaino, Stefano; De Santo, Davide; Stabile, Guglielmo; Banco, Rubina; Busetti, Marina; Barbati, Giulia; Guaschino, Secondo (Contraception, 2012)
BACKGROUND: The sector of the market that deals with contraception offers a long list of different contraceptive methods. Within the estroprogestinic choice, the routes of administration are oral, transdermic and vaginal one. Even though efficacy is comparable with these methods, secondary and adverse effects are directly involved in the acceptability of the method. STUDY DESIGN: This was a prospective comparative study. During 1 year, we enrolled 60 asymptomatic women who voluntarily requested combined oral contraception (COC) or combined contraceptive vaginal ring (CCVR group). After a baseline study of vaginal milieu prior to starting hormonal contraception, we performed a follow-up. For each woman, we examined vaginal pH; quantification of leukocytes, lactobacilli, Candida and cocci on saline microscopy fluid; Gram stain with Nugent score and the presence of vaginal infection [culture for Trichomonas vaginalis, albicans and nonalbicans Candida, Group B Streptococcus (GBS)]. RESULTS: At the end of follow-up, there was a little change of vaginal milieu in both groups. We noted an increase of lactobacilli in the CCVR users and an increase of GBS in COC users. CONCLUSION: CCVR compared to COC users showed an increase of the number of lactobacilli in vaginal flora. It means that an increase of leukorrhea in that group could be protective in terms of prevention of vaginal imbalance/infection.
Keywords: Administration, Intravaginal; Adolescent; Adult; Bacterial Load; Candida; Candida albicans; Contraceptive Devices, Female; Contraceptives, Oral, Combined; Female; Humans; Hydrogen-Ion Concentration; Lactobacillus; Leukocyte Count; Middle Aged; Prospective Studies; Streptococcus agalactiae; Trichomonas vaginalis; Vagina

Effects of prone and supine position on cerebral blood flow in preterm infants. - Bembich, Stefano; Oretti, Chiara; Travan, Laura; Clarici, Andrea; Massaccesi, Stefano; Demarini, Sergio (J Pediatr, 2012)
We evaluated the effect of prone and supine position on cerebral blood flow (CBF) in stable preterm infants. CBF, PO(2), and PCO(2) were measured in the two positions. Peripheral oxygenation increased and CBF decreased in prone position. We speculate that CBF autoregulation may compensate for increased peripheral oxygenation, by decreasing CBF.
Keywords: Cerebrovascular Circulation; Female; Humans; Infant, Newborn; Infant, Premature; Male; Prone Position; Regional Blood Flow; Supine Position

The effects of uterine fundal pressure (Kristeller maneuver) on pelvic floor function after vaginal delivery. - Sartore, Andrea; De Seta, Francesco; Maso, Gianpaolo; Ricci, Giuseppe; Alberico, Salvatore; Borelli, Massimo; Guaschino, Secondo (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the role of uterine fundal pressure during the second stage of labor (Kristeller maneuver) on pelvic floor dysfunction (urinary and anal incontinence, genital prolapse, pelvic floor strength). METHODS: 522 primiparous women, enrolled 3 months after vaginal delivery, were divided in two groups: group A (297 women) identifies the women who received Kristeller maneuvers with different indications (e.g. fetal distress, failure to progress, mother exhaustion), group B (225 women) the women without maneuver. Participants were questioned about urogynecological symptoms and examined by Q-tip test, digital test, vaginal perineometry and uroflowmetric stop test score. RESULTS: Mediolateral episiotomies, dyspareunia and perineal pain were significantly higher in Kristeller group, whereas urinary and anal incontinence, genital prolapse and pelvic floor strength were not significantly different between the groups. CONCLUSIONS: Kristeller maneuver does not modify puerperal pelvic floor function but increases the rate of episiotomies.
Keywords: Delivery, Obstetric; Dyspareunia; Dystocia; Episiotomy; Fatigue; Fecal Incontinence; Female; Fetal Distress; Humans; Labor Stage, Second; Pain, Postoperative; Pelvic Floor; Pelvic Organ Prolapse; Perineum; Pregnancy; Pressure; Puerperal Disorders; Urinary Incontinence; Uterus

Efficacy of rifaximin vaginal tablets in treatment of bacterial vaginosis: a molecular characterization of the vaginal microbiota. - Cruciani, Federica; Brigidi, Patrizia; Calanni, Fiorella; Lauro, Vittoria; Tacchi, Raffaella; Donders, Gilbert; Peters, Klaus; Guaschino, Secondo; Vitali, Beatrice (Antimicrob Agents Chemother, 2012)
Bacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, double-blind, randomized, placebo-controlled study. An integrated molecular approach based on quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the effects of vaginal tablets containing the antibiotic. An increase in members of the genus Lactobacillus and a decrease in the BV-related bacterial groups after the antibiotic treatment were demonstrated by qPCR. PCR-DGGE profiles confirmed the capability of rifaximin to modulate the composition of the vaginal microbial communities and to reduce their complexity. This molecular analysis supported the clinical observation that rifaximin at 25 mg/day for 5 days represents an effective treatment to be used in future pivotal studies for the treatment of BV.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Double-Blind Method; Female; Humans; Lactobacillus; Metagenome; Middle Aged; Rifamycins; RNA, Ribosomal, 16S; Vagina; Vaginal Creams, Foams, and Jellies; Vaginosis, Bacterial; Young Adult

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

The energy balance positively regulates the levels of circulating TNF-related apoptosis inducing ligand in humans. - Biolo, Gianni; Secchiero, Paola; De Giorgi, Sara; Tisato, Veronica; Zauli, Giorgio (Clin Nutr, 2012)
BACKGROUND & AIMS: Although decreased levels of circulating TRAIL have been associated to cardiovascular risk and overall mortality, the mechanisms controlling TRAIL levels in physiopathological conditions are currently unknown. The aim of the present study was to investigate whether changes in the energy intake and insulin sensitivity may influence circulating TRAIL, and to analyze potential relationships between circulating TRAIL and changes in fat mass in healthy subjects receiving hypocaloric or hypercaloric diets. METHODS: Three distinct groups of participants were studied, at the end of a 14-day (n = 9), 35-day (n = 30) or 60-day (n = 16) period of experimental bed rest to induce insulin resistance and during controlled ambulation, after receiving eucaloric, hypocaloric or hypercaloric diets. RESULTS: After bed rest conditions, energy restriction significantly decreased circulating TRAIL, while overfeeding significantly increased TRAIL levels with respect to eucaloric control subjects. Moreover, a positive correlation was found between levels of circulating TRAIL and energy intake as well as between circulating TRAIL and energy balance, as determined by changes in fat mass in these subjects. CONCLUSIONS: Circulating levels of TRAIL exhibit a clear-cut positive correlation with the energy intake and balance in healthy subjects during experimental physical inactivity.
Keywords: Adult; Apoptosis; Bed Rest; Cross-Over Studies; Diet; Energy Intake; Energy Metabolism; Female; Humans; Insulin Resistance; Male; Motor Activity; Risk Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

First trimester maternal serum PIGF, free β-hCG, PAPP-A, PP-13, uterine artery Doppler and maternal history for the prediction of preeclampsia. - Di Lorenzo, G; Ceccarello, M; Cecotti, V; Ronfani, L; Monasta, L; Vecchi Brumatti, L; Montico, M; D'Ottavio, G (Placenta, 2012)
OBJECTIVE: To evaluate the detection of pregnancy hypertensive disorders by integrating maternal history, serum biomarkers and uterine artery Doppler in the first trimester. METHODS: We prospectively recruited 2118 women that underwent an 11-13 weeks aneuploidy screening. We gathered information on maternal history, uterine artery Doppler and serum biomarkers (PAPP-A, PlGF, PP-13 and free β-hCG). Models were developed for the prediction of overall preeclampsia (PE), early-onset PE, late-onset PE and gestational hypertension (GH). For each outcome, we performed a multivariate logistic regression starting from the saturated model: adopting a step-down procedure we excluded all factors not statistically significant (p > 0.05). Sensitivity models only for statistically significant parameters were calculated from the ROC curves for fixed false-positive rates (FPR). RESULTS: Among 2118 women, 46 (2.17%) developed GH and 25 (1.18%) were diagnosed with PE, including 12 (0.57%) early-onset PE and 13 (0.61%) late-onset PE. For a fixed FPR of 10 and 5%, serum PlGF, free β-hCG and chronic hypertension identified respectively 67 and 75% of women who developed early-onset PE. In the model for the prediction of overall PE the combination of the uterine artery Doppler pulsatility index (UtA PI) with PlGF and chronic hypertension reached a sensitivity of 60% for a 20% of FPR. CONCLUSION: An integration of maternal characteristics and first trimester maternal serum biomarkers (free β-hCG and PlGF) provided a possible screening for early-onset PE. In the overall PE model, UtA PI turned out to be statistically significant but did not improve the detection rate.
Keywords: Adult; Biological Markers; Chorionic Gonadotropin, beta Subunit, Human; Cohort Studies; Female; Galectins; Humans; Hypertension, Pregnancy-Induced; Pre-Eclampsia; Pregnancy; Pregnancy Complications; Pregnancy Proteins; Pregnancy Trimester, First; Pregnancy-Associated Plasma Protein-A; Prospective Studies; Ultrasonography, Prenatal; Uterine Artery; Uterus

Formation of membrane-defined compartments by tick-borne encephalitis virus contributes to the early delay in interferon signaling. - Miorin, Lisa; Albornoz, Amelina; Baba, Marycelin M; D'Agaro, Pierlanfranco; Marcello, Alessandro (Virus Res, 2012)
Interferons are key mediators of the innate antiviral response of the cell against viral infections. Viruses on the other hand have evolved various strategies to delay innate immunity in order to establish a productive infection. In this work we analyzed the pathway of interferon induction by the tick-borne encephalitis virus. We initially observed a consistent delay of interferon induction following virus replication. RIG-I, but not MDA5, and nuclear translocation of IRF3 were eventually required for interferon activation pointing to a defect in pattern recognition receptor's signaling. However, viral proteins could not directly inhibit the pathway suggesting an indirect mechanism. We found that dsRNA replication intermediates and replicated viral RNA localized to membrane-defined perinuclear compartments that resisted RNAse treatment. Thus, initial escape from innate immunity involved the formation of replication vesicles that may function as a barrier to pattern recognition receptors.
Keywords: Cell Membrane; Encephalitis Viruses, Tick-Borne; Humans; Immune Evasion; Interferons; Receptors, Pattern Recognition; RNA, Viral; Signal Transduction

Frequency of human papillomavirus types 16, 18, 31, and 33 and sites of cervical lesions in gynecological patients from Recife, Brazil. - Baldez da Silva, M F P T; Guimarães, V; Silva, M A R; Medeiros do Amaral, C M; Beçak, W; Stocco, R C; Freitas, A C; Crovella, S (Genet Mol Res, 2012)
Human papilloma virus (HPV) is a well-established cause of cervical cancer. While many studies have been performed so far on HPV viral biology, mode of infection and prevention measures, scanty information is available on lesion sites of infected women and the incidence of viral types at specific locations. We looked for a possible relationship between the most common viral types (HPVs 16, 18, 31, 33) found in Recife, PE, Brazil, and lesion sites. We examined 396 HPV-positive women at the Gynecological Unit of the IMIP at Recife; 288 women were positive for HPV 16, 18, 31, or 33, present as a single-virus type or as co-infection. HPV 16 was the most frequent virus type found in the vulva, vagina, uterine cervix-vagina, and uterine cervix. HPV 31 was the second prevalent virus type in vulva, vagina, uterine cervix-vagina, uterine cervix, and mole. HPVs 18 and 33 were present with similar frequencies in the mole-vulva region. Among the co-infections, HPV 16/18 and HPV16/31 were the most frequent in our study group, followed by HPV 16/33.
Keywords: Adolescent; Adult; Brazil; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; Papillomavirus Infections; Uterine Cervical Diseases; Young Adult

Functional single-nucleotide polymorphisms in the DEFB1 gene are associated with systemic lupus erythematosus in Southern Brazilians. - Sandrin-Garcia, P; Brandão, L A C; Guimarães, R L; Pancoto, J A T; Donadi, E A; Lima-Filho, J L de; Segat, L; Crovella, S (Lupus, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that results in inflammation and tissue damage. The etiology of SLE remains unknown, but recent studies have shown that the innate immune system may have a role in SLE pathogenesis through the secretion of small cationic peptides named defensins. The aim of the study was to determine the possible involvement in SLE of three functional single nucleotide polymorphisms (SNPs) (c.-52G>A, c.-44C>G and c.-20G>A) in the 5'UTR region of DEFB1 gene, by analyzing them in a population of 139 SLE patients and 288 healthy controls. The c.-52G>A SNP showed significant differences in allele and genotype frequency distribution between SLE patients and controls (p = 0.01 and p = 0.02 respectively) indicating protection against SLE (A allele, OR = 0.68, AA genotype OR = 0.51). Significant differences were also observed for c.-44C>G SNP, the C/G genotype being associated with susceptibility to SLE (OR = 1.60, p = 0.04). Moreover, statistically significant differences between patients and controls were found for two DEFB1 haplotypes (GCA and GGG, p = 0.01 and p = 0.02 respectively). When considering DEFB1 SNPs and SLE clinical and laboratory manifestations, significant association was found with neuropsychiatric disorders, immunological alterations and anti-DNA antibodies. In conclusion, our results evidence a possible role for the c.-52G>A and c.-44C>G DEFB1 polymorphisms in SLE pathogenesis, that can be considered as possible risk factors for development of disease and disease-related clinical manifestations. Additional studies are needed, to corroborate these results as well as functional studies to understand the biological role of these SNPs in the pathogenesis of SLE.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

Gluten-dependent intestinal autoimmune response. - Korponay-Szabó, Ilma Rita; Simon-Vecsei, Zsafia; De Leo, Luigina; Not, Tarcisio (Curr Pharm Des, 2012)
Celiac disease is a multi-systemic autoimmune disease of the small bowel induced by gluten in genetically predisposed subjects. Highly specific and gluten-dependent production of auto-antibodies targeting self-proteins of the transglutaminase family occurs in the intestinal mucosa. These anti-transglutaminase antibodies are found deposited in intestinal and extra-intestinal tissue where they might exert biological effects, together with the intestinal mucosal gliadin-specific T lymphocytes. We conducted a brief review on antitransglutaminase antibodies effects, discussing their roles in the pathogenesis of several clinical manifestations of celiac disease.
Keywords: Animals; Autoantibodies; Celiac Disease; Genetic Predisposition to Disease; Gliadin; Glutens; Humans; Intestinal Mucosa; T-Lymphocytes; Transglutaminases

Haematopoietic SCT in severe autoimmune diseases: updated guidelines of the European Group for Blood and Marrow Transplantation. - Snowden, J A; Saccardi, R; Allez, M; Ardizzone, S; Arnold, R; Cervera, R; Denton, C; Hawkey, C; Labopin, M; Mancardi, G; Martin, R; Moore, J J; et al. (Bone Marrow Transplant, 2012)
In 1997, the first consensus guidelines for haematopoietic SCT (HSCT) in autoimmune diseases (ADs) were published, while an international coordinated clinical programme was launched. These guidelines provided broad principles for the field over the following decade and were accompanied by comprehensive data collection in the European Group for Blood and Marrow Transplantation (EBMT) AD Registry. Subsequently, retrospective analyses and prospective phase I/II studies generated evidence to support the feasibility, safety and efficacy of HSCT in several types of severe, treatment-resistant ADs, which became the basis for larger-scale phase II and III studies. In parallel, there has also been an era of immense progress in biological therapy in ADs. The aim of this document is to provide revised and updated guidelines for both the current application and future development of HSCT in ADs in relation to the benefits, risks and health economic considerations of other modern treatments. Patient safety considerations are central to guidance on patient selection and HSCT procedural aspects within appropriately experienced and Joint Accreditation Committee of International Society for Cellular Therapy and EBMT accredited centres. A need for prospective interventional and non-interventional studies, where feasible, along with systematic data reporting, in accordance with EBMT policies and procedures, is emphasized.
Keywords: Autoimmune Diseases; Clinical Trials, Phase I as Topic; Clinical Trials, Phase II as Topic; European Union; Female; Hematopoietic Stem Cell Transplantation; Humans; Male; Risk Factors; Safety; Severity of Illness Index

HIV-1 induces NALP3-inflammasome expression and interleukin-1β secretion in dendritic cells from healthy individuals but not from HIV-positive patients. - Pontillo, Alessandra; Silva, Lais T; Oshiro, Telma M; Finazzo, Claudia; Crovella, Sergio; Duarte, Alberto J S (AIDS, 2012)
OBJECTIVE: NALP3-inflammasome is an innate mechanism, alternative to type-1 interferon, which is able to recognize nucleic acids and viruses in the cytoplasm and to induce pro-inflammatory response. Here, we hypothesized the involvement of inflammasome in the early defense against HIV-1 and in the full maturation of dendritic cells: for this, we evaluated the response of dendritic cells pulsed with HIV-1 in terms of inflammasome activation in healthy donors. Moreover, inflammasome response to HIV was evaluated in HIV-infected individuals. DESIGN AND METHODS: Monocyte-derived dendritic cells isolated from 20 healthy individuals (HC-DC) and 20 HIV-1-infected patients (HIV-DC) were pulsed with alditrithiol-2-inactivated HIV-1. We then analyzed inflammasome genes expression and interleukin-1β (IL-1β) secretion. RESULTS: In HC-DC, HIV-1 induced higher NLRP3/NALP3 mRNA expression compared with other inflammasome genes such as NALP1/NLRP1 or IPAF/NLRC4 (P < 0.001). This augmented expression was accompanied by CASP1-increased and IL1B-increased mRNA levels and by a significant increment of IL-1β secretion (P < 0.05). Otherwise, HIV-1 failed to activate inflammasome and cytokine production in HIV-DC. HIV-DC showed an increased NLRP3/NALP3 basal expression, suggesting a chronic inflammatory profile of patients' immune cells. CONCLUSION: HIV-1 was able to induce a NALP3-inflammasome response in healthy individuals, indicating that this inflammasome could play a role in the first steps of HIV-1 infection; the consequent inflammatory process may be important for directing host immune response against the virus and/or disease progression. HIV-DC seemed to be chronically activated, but unresponsive against pathogens. Our findings could be of interest considering the ongoing research about dendritic cell manipulation and therapeutic strategies for AIDS involving dendritic cell-based immune-vaccines.
Keywords: Acquired Immunodeficiency Syndrome; Adult; Brazil; Carrier Proteins; Caspase 1; Cells, Cultured; Dendritic Cells; DNA, Viral; Female; HIV-1; Humans; Immunity, Innate; Inflammasomes; Interleukin-1beta; Male; Tumor Necrosis Factor-alpha

Hydrogen sulfide down-regulates the expression and release of osteoprotegerin (OPG) by vascular endothelial cells. - Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Celeghini, Claudio; Secchiero, Paola; Zauli, Giorgio (Invest New Drugs, 2012)
Keywords: Cell Death; Cytostatic Agents; Down-Regulation; Human Umbilical Vein Endothelial Cells; Humans; Hydrogen Sulfide; Osteoprotegerin; Tumor Necrosis Factor-alpha

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

JCV+ Patients with Inflammatory bowel disease show elevated plasma levels of MIG and SCF. - Comar, Manola; Secchiero, Paola; De Lorenzo, Elisa; Martelossi, Stefano; Tommasini, Alberto; Zauli, Giorgio (Inflamm Bowel Dis, 2012)
Keywords: Adolescent; Adult; Chemokine CXCL9; Child; DNA, Viral; Female; Humans; Inflammatory Bowel Diseases; JC Virus; Leukoencephalopathy, Progressive Multifocal; Male; Stem Cell Factor; Young Adult

Letter: TPMT activity and age in IBD patients. - Stocco, G; De Iudicibus, S; Cuzzoni, E; Decorti, G; Martelossi, S; Ventura, A (Aliment Pharmacol Ther, 2012)
Keywords: Azathioprine; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Thioguanine

Lutein and zeaxanthin supplementation in preterm infants to prevent retinopathy of prematurity: a randomized controlled study. - Dani, Carlo; Lori, Ilaria; Favelli, Federica; Frosini, Saverio; Messner, Hubert; Wanker, Petra; De Marini, Sergio; Oretti, Chiara; Boldrini, Antonio; Massimiliano, Ciantelli; Bragetti, Patrizia; Germini, Cristiana (J Matern Fetal Neonatal Med, 2012)
OBJECTIVES: Lutein and its isomer zeaxanthin (L/Z) function in the eye as antioxidant agents and blue-light filters. Our aim was to evaluate whether their administration could help decrease the occurrence of retinopathy of prematurity (ROP) in preterm infants. METHODS: Infants with gestational age ≤32 weeks were randomly assigned to receive a daily dose of L/Z (0.14 + 0.006 mg) or placebo until discharge. RESULTS: ROP occurrence was similar in the L/Z (11/58; 19%) and placebo (15/56; 27%) groups, as the occurrence of ROP at each stage and the need of eye surgery. CONCLUSION: L/Z supplementation was ineffective in preventing ROP in preterm infants and did not affect the outcome at discharge of our patients.
Keywords: Antioxidants; Drug Administration Schedule; Drug Combinations; Female; Humans; Infant, Newborn; Infant, Premature; Logistic Models; Lutein; Male; Retinopathy of Prematurity; Risk Factors; Treatment Outcome; Xanthophylls; Zeaxanthins

Mannose-binding lectin and MBL-associated serine protease-2 gene polymorphisms in a Brazilian population from Rio de Janeiro. - Ferraroni, N R; Segat, L; Guimarães, R L; Brandão, L A C; Crovella, S; Constantino-Silva, R N; Loja, C; da Silva Duarte, A J; Grumach, A S (Int J Immunogenet, 2012)
Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encoding gene (MBL2) have been associated, depending upon ethnicity, with several diseases in different populations, little is known about the distribution of MASP2 gene polymorphisms in human populations. The aim of our study was thus to determine the frequencies of MBL2 (exon 1 and promoter) and MASP2 (p.D371Y) polymorphisms in a Brazilian population from Rio de Janeiro. A total of 294 blood donor samples were genotyped for 27 polymorphisms in the MBL2 gene by direct sequencing of a region spanning from the promoter polymorphism H/L rs11003125 to the rs1800451 polymorphism (at codon 57 in the first exon of the gene). Genotyping for MASP2 p.D371Y was carried out using fluorogenic probes. To our knowledge, this is the first study reporting the prevalence of the MASP2 p.D371Y polymorphism in a Brazilian population. The C allele frequency 39% is something intermediate between the reported 14% in Europeans and 90% in Sub-Saharan Africans. MBL2 polymorphisms frequencies were quite comparable to those previously reported for admixed Brazilians. Both MBL2 and MASP2 polymorphisms frequencies reported in our study for the admixed Brazilian population are somehow intermediate between those reported in Europeans and Africans, reflecting the ethnic composition of the southern Brazilian population, estimated to derive from an admixture of Caucasian (31%), African (34%) and Native American (33%) populations. In conclusion, our population genetic study describes the frequencies of MBL2 and MASP2 functional SNPs in a population from Rio de Janeiro, with the aim of adding new information concerning the distribution of these SNPs in a previously unanalysed Brazilian population, thus providing a new genetic tool for the evaluation of the association of MBL2 and MASP2 functional SNPs with diseases in Brazil, with particular emphasis on the state of Rio de Janeiro.
Keywords: Adolescent; Adult; Brazil; Ethnic Groups; Exons; Female; Fluorescent Dyes; Gene Frequency; Genetics, Population; Genome, Human; HapMap Project; Humans; Male; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases; Middle Aged; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Analysis, DNA; Young Adult

MBL interferes with endovascular trophoblast invasion in pre-eclampsia. - Agostinis, Chiara; Bossi, Fleur; Masat, Elisa; Radillo, Oriano; Tonon, Maddalena; De Seta, Francesco; Tedesco, Francesco; Bulla, Roberta (Clin Dev Immunol, 2012)
The spiral arteries undergo physiologic changes during pregnancy, and the failure of this process may lead to a spectrum of pregnancy disorders, including pre-eclampsia. Our recent data indicate that decidual endothelial cells (DECs), covering the inner side of the spiral arteries, acquire the ability to synthesize C1q, which acts as a link between endovascular trophoblast and DECs favouring the process of vascular remodelling. In this study, we have shown that sera obtained from pre-eclamptic patients strongly inhibit the interaction between extravillous trophoblast (EVT) and DECs, preventing endovascular invasion of trophoblast cells. We further demonstrated that mannose-binding lectin (MBL), one of the factor increased in pre-eclamptic patient sera, strongly inhibits the interaction of EVT with C1q interfering with the process of EVT adhesion to and migration through DECs. These data suggest that the increased level of MBL in pre-eclampsia may contribute to the failure of the endovascular invasion of trophoblast cells.
Keywords: Cell Communication; Decidua; Endothelial Cells; Female; Humans; Mannose-Binding Lectin; Pre-Eclampsia; Pregnancy; Transendothelial and Transepithelial Migration; Trophoblasts

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Molecular analysis of HEXA gene in Argentinean patients affected with Tay-Sachs disease: possible common origin of the prevalent c.459+5A>G mutation. - Zampieri, Stefania; Montalvo, Annalisa; Blanco, Mariana; Zanin, Irene; Amartino, Hernan; Vlahovicek, Kristian; Szlago, Marina; Schenone, Andrea; Pittis, Gabriela; Bembi, Bruno; Dardis, Andrea (Gene, 2012)
Tay-Sachs disease (TSD) is a recessively inherited disorder caused by the deficient activity of hexosaminidase A due to mutations in the HEXA gene. Up to date there is no information regarding the molecular genetics of TSD in Argentinean patients. In the present study we have studied 17 Argentinean families affected by TSD, including 20 patients with the acute infantile form and 3 with the sub-acute form. Overall, we identified 14 different mutations accounting for 100% of the studied alleles. Eight mutations were novel: 5 were single base changes leading to drastic residue changes or truncated proteins, 2 were small deletions and one was an intronic mutation that may cause a splicing defect. Although the spectrum of mutations was highly heterogeneous, a high frequency of the c.459+5G>A mutation, previously described in different populations was found among the studied cohort. Haplotype analysis suggested that in these families the c.459+5G>A mutation might have arisen by a single mutational event.
Keywords: Child; Cohort Studies; Female; Hexosaminidase A; Humans; Infant; Male; Mutation; Tay-Sachs Disease

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

More on professionals' attitudes on blood-tinged milk: a survey from Italy. - Bua, J; Travan, L; Davanzo, R; Demarini, S (J Perinatol, 2012)
Keywords: Attitude of Health Personnel; Breast Feeding; Clinical Protocols; Female; Humans; Intensive Care Units, Neonatal; Intensive Care, Neonatal; Male; Milk, Human; Professional Practice

Nutlin-3 differentially modulates miRNA34a and miRNA181 versus miR26a and miR155 in p53 proficient and p53 deficient B chronic lymphocytic leukemia (B-CLL) samples. - di Iasio, Maria Grazia; Addobbati, Riccardo; Radillo, Oriano; Voltan, Rebecca (Invest New Drugs, 2012)
Keywords: Down-Regulation; Gene Expression Profiling; Gene Expression Regulation, Leukemic; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; MicroRNAs; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Patient-centred screening for primary immunodeficiency, a multi-stage diagnostic protocol designed for non-immunologists: 2011 update. - de Vries, E (Clin Exp Immunol, 2012)
Members of the European Society for Immunodeficiencies (ESID) and other colleagues have updated the multi-stage expert-opinion-based diagnostic protocol for non-immunologists incorporating newly defined primary immunodeficiency diseases (PIDs). The protocol presented here aims to increase the awareness of PIDs among doctors working in different fields. Prompt identification of PID is important for prognosis, but this may not be an easy task. The protocol therefore starts from the clinical presentation of the patient. Because PIDs may present at all ages, this protocol is aimed at both adult and paediatric physicians. The multi-stage design allows cost-effective screening for PID of the large number of potential cases in the early phases, with more expensive tests reserved for definitive classification in collaboration with a specialist in the field of immunodeficiency at a later stage.
Keywords: Adult; Age of Onset; Child; Clinical Protocols; Cytotoxicity Tests, Immunologic; Early Diagnosis; General Practice; Granulocytes; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Incidence; Infection; Lymphocyte Subsets; Mass Screening; Medical History Taking; Patient-Centered Care; Pediatrics; Phenotype; Physical Examination; Recurrence

Pegylated TRAIL retains anti-leukemic cytotoxicity and exhibits improved signal transduction activity with respect to TRAIL. - Gonelli, Arianna; Radillo, Oriano; Drioli, Sara; Rimondi, Erika; Secchiero, Paola; Maria Bonora, Gian (Invest New Drugs, 2012)
To improve the pharmacokinetic profile of tumor necrosis factor-related apoptosis inducing ligand (TRAIL) an N-terminal specific pegylation was performed to generate pegylated TRAIL (PEG-TRAIL). In in vitro experiments, we found that although PEG-TRAIL was slightly less efficient than recombinant TRAIL in promoting leukemic cell apoptosis, it showed an improved ability to promote migration of bone-marrow mesenchymal stem cells and to elicit the ERK1/2 intracellular signal transduction pathway. Overall, these data suggest that TRAIL pegylation retains, or even enhances, the biological activities of TRAIL relevant for its therapeutic applications.
Keywords: Antineoplastic Agents; Apoptosis; Caspase 3; Cell Movement; Dose-Response Relationship, Drug; HL-60 Cells; Humans; Leukemia; Mesenchymal Stromal Cells; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Phosphorylation; Polyethylene Glycols; Recombinant Fusion Proteins; Signal Transduction; Time Factors; TNF-Related Apoptosis-Inducing Ligand

Pelvic inflammatory disease (PID) from Chlamydia trachomatis versus PID from Neisseria gonorrhea: from clinical suspicion to therapy. - De Seta, F; Banco, R; Turrisi, A; Airoud, M; De Leo, R; Stabile, G; Ceccarello, M; Restaino, S; De Santo, D (G Ital Dermatol Venereol, 2012)
Pelvic inflammatory disease (PID) is the most significant complication of sexually transmitted infections in childbearing-age women and it represents an important public health problem because of its long-term sequelae (chronic pelvic pain, tubal infertility, ectopic pregnancy). Prior to the mid 1970s PID was considered a monoetiologic infection, due primarily to Neisseria gonorrhea. Now it is well documented as a polymicrobial process, with a great number of microrganisms involved. In addition to Neisseria gonorrhea and Chlamydia trachomatis, other vaginal microrganisms (anaerobes, Gardnerella vaginalis, Haemophilus influenzae, enteric Gram negative rods, Streptococco agalactie, Mycoplasma genitalium) also have been associated with PID. There is a wide variation in PID clinical features; the type and severity of symptoms vary by microbiologic etiology. Women who have chlamydial PID seem more likely than women who have gonococcal PID to be asymptomatic. Since clinical diagnosis is imprecise, the suspicion of PID should be confirmed by genital assessment for signs of inflammation or infection, blood test and imaging evaluation. Laparoscopic approach is considered the gold standard. According to the polymicrobial etiology of PID, antibiotic treatment must provide broad spectrum coverage of likely pathogens. Early administration of antibiotics is necessary to reduce the risk of long-term sequelae.
Keywords: Chlamydia Infections; Chlamydia trachomatis; Female; Gonorrhea; Humans; Neisseria gonorrhoeae; Pelvic Inflammatory Disease

Personalized therapies in pediatric inflammatory and autoimmune diseases. - Stocco, Gabriele; De Iudicibus, Sara; Franca, Raffaella; Addobbati, Riccardo; Decorti, Giuliana (Curr Pharm Des, 2012)
Pediatric inflammatory and autoimmune diseases are a wide array of systemic or organ-specific conditions, characterized by an exaggerated immune reactivity, which generally occurs in immunogenetically predisposed children. Among the most important ones, in terms of their diffusion and morbidity in the population worldwide, pediatric inflammatory bowel disease (IBD) and juvenile rheumatoid arthritis (JRA) have to be considered. The aim of personalized therapy is to give to each patient the most appropriate drug and dose regimen, in order to maximize treatment response and reduce the risk of adverse events. In general, several therapeutic options exist for pediatric inflammatory and autoimmune conditions, therefore the perspective of pharmacological tools that allow identification of patients with increased risk of treatment issues related to a particular medication, in terms of lack of efficacy or increased probability of adverse events, is particularly desirable and promising. The present review will be focused on the personalized therapy approaches already available or in development for pediatric patients with IBD or JRA, comprising pharmacokinetic, pharmacodynamic and pharmacogenetic assays.
Keywords: Arthritis, Rheumatoid; Autoimmune Diseases; Child; Genetic Predisposition to Disease; Humans; Immunogenetic Phenomena; Individualized Medicine; Inflammation; Inflammatory Bowel Diseases; Pharmacogenetics

Polimorphisms in inflammasome genes are involved in the predisposition to systemic lupus erythematosus. - Pontillo, Alessandra; Girardelli, Martina; Kamada, Anselmo J; Pancotto, Joao A T; Donadi, Eduardo A; Crovella, Sergio; Sandrin-Garcia, Paula (Autoimmunity, 2012)
Recent findings provide evidence of inflammasome critical role in the predisposition to autoimmune disorders. The involvement of inflammasome in the pathogenesis of systemic lupus erythematosus (SLE) has been hypothesized even if no significant association within inflammasome genes mutations or polymorphisms and lupus has been reported yet. We analyzed 14 single nucleotide polymorphisms (SNPs) within 7 inflammasome genes (NLRP1, NLRP3, NLRC4, AIM2, CARD8, CASP1, IL1B) in 144 patients affected by systemic lupus erythematosus and in 158 healthy controls from Southern Brazilian (state of São Paulo) with the aim of disclosing the possible role of inflammasome genes in the susceptibility of SLE. Our results demonstrated that NLRP1 rs2670660 SNP and the NLRP1 rs12150220-rs2670660 A-G haplotype were associated with SLE in our study population, and in particular with the development of nephritis, rash and arthritis. These findings are concordant with previously reported association of NLRP1 with vitiligo and type-1 diabetes underlining once more the involvement of NALP1 inflammasome in the pathogenesis of autoimmune disorders.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Alleles; Apoptosis Regulatory Proteins; Brazil; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Inflammasomes; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide

Polymorphisms in DC-SIGN and L-SIGN genes are associated with HIV-1 vertical transmission in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; Zanin, Valentina; Arraes, Luiz Claudio; Crovella, Sergio (Hum Immunol, 2012)
DC-SIGN and L-SIGN are receptors expressed on specialized macrophages in decidua, (Hofbauer and placental capillary endothelial cells), known to interact with several pathogens, including HIV-1. To disclose the possible involvement of these molecules in the susceptibility to HIV vertical transmission, we analyzed DC-SIGN and L-SIGN gene single nucleotide polymorphisms (SNPs) in 192 HIV-1 positive children and 58 HIV-1 negative children all born to HIV-1 positive mothers, as well as 96 healthy uninfected children not exposed to HIV-1, all from Northeast Brazil. The frequency of three SNPs in the DC-SIGN promoter (-139G>A, -201G>T and -336A>G) were significantly different when comparing HIV positive children with HIV-1 exposed uninfected children, indicating an association with susceptibility to HIV-1 vertical transmission. This genetic association suggests that DC-SIGN molecule may play a role in susceptibility to HIV-1 infection through vertical transmission.
Keywords: Alleles; Brazil; Cell Adhesion Molecules; Child; Child, Preschool; Exons; Female; Gene Frequency; Genotype; HIV Infections; HIV-1; Humans; Infectious Disease Transmission, Vertical; Lectins, C-Type; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tandem Repeat Sequences

Polymorphisms in inflammasome' genes and susceptibility to HIV-1 infection. - Pontillo, Alessandra; Oshiro, Telma M; Girardelli, Martina; Kamada, Anselmo J; Crovella, Sergio; Duarte, Alberto J S (J Acquir Immune Defic Syndr, 2012)
The involvement of inflammasome genes in the susceptibility to HIV-1 infection was investigated. Twelve single nucleotide polymorphisms within NLRP1, NLRP3, NLRC4, CARD8, CASP1, and IL1B genes were analyzed in 150 HIV-1-infected Brazilian subjects and 158 healthy controls. The 2 polymorphisms rs10754558 in NLRP3 and rs1143634 in IL1B were significantly associated to the HIV-1 infection. These findings supported the previously hypothesized involvement of NALP3-inflammasome in HIV-1 pathogenesis, underlining once more the key role of inflammation and innate immunity in the susceptibility to HIV-1 infection.
Keywords: Adaptor Proteins, Signal Transducing; Adult; Apoptosis Regulatory Proteins; Brazil; Calcium-Binding Proteins; CARD Signaling Adaptor Proteins; Carrier Proteins; Caspase 1; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; HIV Infections; HIV-1; Humans; Inflammasomes; Interleukin-1beta; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; Neoplasm Proteins; Polymorphism, Single Nucleotide

A real-time polymerase chain reaction-based protocol for low/medium-throughput Y-chromosome microdeletions analysis. - Segat, Ludovica; Padovan, Lara; Doc, Darja; Petix, Vincenzo; Morgutti, Marcello; Crovella, Sergio; Ricci, Giuseppe (Genet Test Mol Biomarkers, 2012)
PURPOSE: We describe a real-time polymerase chain reaction (PCR) protocol based on the fluorescent molecule SYBR Green chemistry, for a low- to medium-throughput analysis of Y-chromosome microdeletions, optimized according to the European guidelines and aimed at making the protocol faster, avoiding post-PCR processing, and simplifying the results interpretation. METHODS: We screened 156 men from the Assisted Reproduction Unit, Department of Obstetrics and Gynecology, Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy), 150 not presenting Y-chromosome microdeletion, and 6 with microdeletions in different azoospermic factor (AZF) regions. For each sample, the Zinc finger Y-chromosomal protein (ZFY), sex-determining region Y (SRY), sY84, sY86, sY127, sY134, sY254, and sY255 loci were analyzed by performing one reaction for each locus. RESULTS: AZF microdeletions were successfully detected in six individuals, confirming the results obtained with commercial kits. CONCLUSION: Our real-time PCR protocol proved to be a rapid, safe, and relatively cheap method that was suitable for a low- to medium-throughput diagnosis of Y-chromosome microdeletion, which allows an analysis of approximately 10 samples (with the addition of positive and negative controls) in a 96-well plate format, or approximately 46 samples in a 384-well plate for all markers simultaneously, in less than 2 h without the need of post-PCR manipulation.
Keywords: Azoospermia; Chromosome Deletion; Chromosomes, Human, Y; Female; Humans; Kruppel-Like Transcription Factors; Male; Real-Time Polymerase Chain Reaction; Sex Chromosome Aberrations; Sex Chromosome Disorders of Sex Development

RICH (rapidly involuting congenital hemangioma): not only a definition of wealth. - Abate, Maria Valentina; Davanzo, Riccardo; Bibalo, Chiara; Zennaro, Floriana; Berti, Irene (J Pediatr, 2012)
Keywords: Female; Hemangioma; Humans; Infant, Newborn; Skin Neoplasms

Role of high molecular weight hyaluronic acid in postmenopausal vaginal discomfort. - Grimaldi, E F; Restaino, S; Inglese, S; Foltran, L; Sorz, A; Di Lorenzo, G; Guaschino, S (Minerva Ginecol, 2012)
AIM: Aim of the present study was to quantify the intensity of vulvovaginal symptoms before and after treatment with high molecular weight hyaluronic acid (HA), to test the tolerability and safety of the product, to evaluate the effect on the quality of life and the compliance to the treatment. METHODS: This was a double-blind randomized placebo-controlled study. In seven months we enrolled 36 post-menopausal women, equally distributed in placebo and active group. The evaluation was based on at least three atrophy-related signs and on the patient reported symptoms. After the written informed consent, the participants were instructed to apply the gel (drug or placebo) daily. Three days after the end of the treatment the patients received a final examination to evaluate the progress of symptoms, the presence of any adverse events and their correlation with the treatment. RESULTS: Self-evaluation scales and investigator evaluation showed that the vaginal dryness was significantly reduced both in placebo and in the active group; however, high molecular weight HA was the only active treatment in reducing significantly itching and burning (P<0.02 and <0.04 respectively). Both treatments significantly reduced vaginal atrophy (P<0.001), erythema (P<0.01 placebo and P<0.001 HA) and vaginal dryness (P<0.001), but HA treatment was significantly more effective on the first two symptoms. Both treatments were very well tolerated and compliance of the treatment was very high. CONCLUSION: High molecular weight HA could be effective in subjective and objective improvement of postmenopausal vaginal atrophy providing a good compliance. No adverse events occurred during the entire period of the study.
Keywords: Atrophy; Double-Blind Method; Female; Humans; Hyaluronic Acid; Middle Aged; Molecular Weight; Postmenopause; Vagina; Vaginal Diseases

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

SOCS1 is significantly up-regulated in Nutlin-3-treated p53wild-type B chronic lymphocytic leukemia (B-CLL) samples and shows an inverse correlation with miR-155. - di Iasio, Maria Grazia; Norcio, Alessia; Melloni, Elisabetta; Zauli, Giorgio (Invest New Drugs, 2012)
The basal SOCS1 mRNA levels were significantly lower in p53(mutated) BJAB and MAVER leukemic cell lines with respect to p53(wild-type) SKW6.4 and JVM-2 leukemic cell lines, p53(wild-type) primary B chronic lymphocytic leukemia (B-CLL) cells and primary normal peripheral blood mononuclear cells (PBMC). Moreover, the MDM2 small molecule inhibitor Nutlin-3 significantly increased the levels of SOCS1 mRNA in both primary p53(wild-type) B-CLL cells as well as in p53(wild-type) B leukemic cell lines, but not in p53(mutated) B leukemic cell lines nor in primary PBMC. Of note, a significant inverse correlation was observed between SOCS1 mRNA and miR-155 levels in Nutlin-3-treated primary B-CLL cells and PBMC, suggesting that the miRNA-155/SOCS1 axis represents a potentially important therapeutic target of Nutlin-3 in B-CLL.
Keywords: Cell Line, Tumor; Cells, Cultured; Down-Regulation; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; MicroRNAs; Piperazines; Suppressor of Cytokine Signaling Proteins; Tumor Suppressor Protein p53; Up-Regulation

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

Specific protein profile in cerebrospinal fluid from HIV-1-positive cART-treated patients affected by neurological disorders. - Zanin, Valentina; Delbue, Serena; Marcuzzi, Annalisa; Tavazzi, Eleonora; Del Savio, Rossella; Crovella, Sergio; Marchioni, Enrico; Ferrante, Pasquale; Comar, Manola (J Neurovirol, 2012)
Cytokines/chemokines are involved in the immune response of infections, including HIV-1. We defined the profile of 48 cytokines/chemokines in cerebrospinal fluid from 18 cART patients with chronic HIV-1 infection by Luminex technology. Nine patients were affected with leukoencephalopathies: five with John Cunningham virus (JCV) + progressive multifocal leukoencephalopathy (PML) and four with JCV-not determined leukoencephalopathy (NDLE). In addition, nine HIV-1-positive patients with no neurological signs (NND) and five HIV-1-negative patients affected with acute disseminated encephalomyelitis (ADEM) were enrolled. Ten cytokines (IL-15, IL-3, IL-16, IL-18, CTACK, GRO1, SCF, MCP-1, MIF, SDF) were highly expressed in HIV-1-positive patients while IL-1Ra and IL-17 were present at a lower level. In addition, the levels of IL-17, IL-9, FGF-basic, MIP-1β, and MCP-1 were significantly higher (p < 0.05) in patients with neurological diseases (PML, NDLE, ADEM) with respect to NND. Focusing the attention to the cytokine profile in JCV + PML patients with respect to JCV-NDLE patients, only TNF-β was significantly downregulated (p < 0.05) in JCV + PML patients. This pilot study emphasized the role of immunoregulation in HIV-1-related neurological disorders during cART treatment.
Keywords: Adult; Aged; Anti-HIV Agents; Cytokines; Encephalomyelitis, Acute Disseminated; Female; HIV Infections; HIV-1; Humans; Leukoencephalopathy, Progressive Multifocal; Male; Middle Aged; Pilot Projects

Stem cell ageing and apoptosis. - Fulle, Stefania; Centurione, Lucia; Mancinelli, Rosa; Sancilio, Silvia; Manzoli, Francesco Antonio; Di Pietro, Roberta (Curr Pharm Des, 2012)
Ageing has been defined as the process of deterioration of many body functions over the lifespan of an individual. In spite of the number of different theories about ageing, there is a general consensus in identifying ageing effects in a reduced capacity to regenerate injured tissues or organs and an increased propensity to infections and cancer. In recent years the stem cell theory of ageing has gained much attention. Adult stem cells residing in mammalian tissues are essential for tissue homeostasis and repair throughout adult life. With advancing age, the highly regulated molecular signalling necessary to ensure proper cellular, tissue, and organ homeostasis loses coordination and leads, as a consequence, to a compromised potential of regeneration and repair of damaged cells and tissues. Although a complete comprehension of the molecular mechanisms involved in stem cell ageing and apoptosis is far to be reached, recent studies are beginning to unravel the processes involved in stem cell ageing, particularly in adult skeletal muscle stem cells, namely satellite cells. Thus, the focus of this review is to analyse the relationship between stem cell ageing and apoptosis with a peculiar attention to human satellite cells as compared to haematopoietic stem cells. Undoubtedly, the knowledge of age-related changes of stem cells will help in understanding the ageing process itself and will provide novel therapeutic challenges for improved tissue regeneration.
Keywords: Adult; Apoptosis; Cell Aging; Humans; Stem Cells

Treatment with pamidronate for osteoporosis complicating long-term intestinal failure. - Pastore, S; Londero, M; Barbieri, F; Di Leo, G; Paparazzo, R; Ventura, A (J Pediatr Gastroenterol Nutr, 2012)
Long-term home parenteral nutrition (PN) is a potential risk for developing osteoporosis. Various attempts have been made to treat bone disease both by modifying the composition of PN and by administering hormones, such as calcitonin, parathyroid hormone, and sexual hormones. Bisphosphonates are recognized as a medication useful for the treatment of several bone disorders associated with excessive reabsorption. Nevertheless, there have been no paediatric studies on bisphosphonates use for intestinal failure-associated bone disease. Our study includes 6 paediatric patients receiving extremely long-term home PN (at least 3 years) who showed radiological and clinical signs of osteoporosis. Diagnosis of bone disease was made after a median period of 127.5 PN months. Treatment consisted in 2 cycles of intravenous pamidronate, 30 mg/m once per month for 6 months consecutively. They all showed a significant improvement in bone mineral density, evaluated after 6 and 12 months of pamidronate treatment. In our sample anthropometrical variables (weight, height, and body mass index) are not related with the z-score trend. Our patients had normal levels of calcium, phosphorus, and vitamin D, and proper nutrient intake. At the last follow-up, dual-energy x-ray absorptiometry scan showed that no patients had a z-score lower than -2.5; moreover, nobody developed bone fractures during the 108-month follow-up. The patients did not have any prominent adverse effect. Finally, in our experience, pamidronate is effective for improving bone mineral density and safe in patients with intestinal failure-associated bone disease.
Keywords: Absorptiometry, Photon; Adolescent; Bone Density; Bone Density Conservation Agents; Child; Child, Preschool; Diphosphonates; Female; Humans; Intestinal Diseases; Male; Osteoporosis; Parenteral Nutrition, Home

The active Zot domain (aa 288-293) increases ZO-1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO-1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation. - Goldblum, Simeon E; Rai, Usha; Tripathi, Amit; Thakar, Manjusha; De Leo, Luigina; Di Toro, Nicola; Not, Tarcisio; Ramachandran, Rithwik; Puche, Adam C; Hollenberg, Morley D; Fasano, Alessio (FASEB J, 2011)
Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activated receptor (PAR)(2)-expressing and PAR(2)-null cells established AT1002 activity to be PAR(2) dependent. Coincident with the increased intestinal permeability, confocal microscopy of AT1002-exposed rat intestinal IEC6 cells revealed displacement of ZO-1 and occludin from intercellular boundaries. In coimmunoprecipitation assays, AT1002 decreased ZO-1-occludin and ZO-1-claudin 1 interactions coincident with PKCα-dependent ZO-1 serine/threonine phosphorylation. Further, AT1002 increased serine phosphorylation of myosin 1C and, at the same time, transiently diminished its association with ZO-1. The COOH-terminal domain of ZO-1 was required for its association with myosin 1C. These data indicate that the NH(2)-terminal portion of active Zot contains a PAR(2)-activating motif, FCIGRL, that increases PKCα-dependent ZO-1 and myosin 1C serine/threonine phosphorylation. These modifications provoke selective disengagement of ZO-1 from its binding partners, occludin, claudin 1, and myosin 1C, coincident with opening of tjs.
Keywords: Amino Acid Sequence; Animals; Caco-2 Cells; Cell Line; Cells, Cultured; Cholera Toxin; Epithelial Cells; Humans; Immunoblotting; Male; Membrane Proteins; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Myosins; Oligopeptides; Phosphoproteins; Phosphorylation; Protein Binding; Protein Kinase C-alpha; Rats; Rats, Wistar; Receptor, PAR-2; RNA Interference; Serine; Threonine; Tight Junctions; Zonula Occludens-1 Protein

Antidepressant drugs and breastfeeding: a review of the literature. - Davanzo, Riccardo; Copertino, Marco; De Cunto, Angela; Minen, Federico; Amaddeo, Alessandro (Breastfeed Med, 2011)
The use of antidepressants in breastfeeding mothers is controversial: Manufacters often routinely discourage breastfeeding for the nursing mother despite the well-known positive impact that breastfeeding carries on the health of the nursing infant and on his or her family and society. We conducted a systematic review of drugs commonly used in the treatment of postpartum depression. For every single drug two sets of data were provided: (1) selected pharmacokinetic characteristics such as half-life, milk-to-plasma ratio, protein binding, and oral bioavailability and (2) information about lactational risk, according to some authoritative sources of the literature: Drugs in Pregnancy and Lactation edited by Briggs et al. (Lippincott Williams, Philadelphia, 2008), Medications and Mothers' Milk by Hale (Hale Publishing, Amarillo, TX, 2010), and the LactMed database of TOXNET ( www.pubmed.gov ; accessed June 2010). Notwithstanding a certain variability of advice, we found that (1) knowledge of pharmacokinetic characteristics are scarcely useful to assess safety and (2) the majority of antidepressants are not usually contraindicated: (a) Selective serotinin reuptake inhibitors and nortryptiline have a better safety profile during lactation, (b) fluoxetine must be used carefully, (c) the tricyclic doxepine and the atypical nefazodone should better be avoided, and (d) lithium, usually considered as contraindicated, has been recently rehabilitated.
Keywords: Adrenergic Uptake Inhibitors; Antidepressive Agents; Antidepressive Agents, Tricyclic; Biological Availability; Breast Feeding; Depression, Postpartum; Directive Counseling; Drug Monitoring; Female; Humans; Infant, Newborn; Lactation; Lithium Compounds; Maternal Exposure; Milk, Human; Monoamine Oxidase Inhibitors; Pregnancy; Serotonin Uptake Inhibitors

Anti-α-enolase Antibodies in Serum from Pediatric Patients Affected by Inflammatory Diseases: Diagnostic and Pathogenetic Insights. - Pontillo, Alessandra; Di Toro, Nicola; Edomi, Paolo; Shadlow, A; Ammadeo, A; Gattorno, M; Not, T; Lepore, L; Crovella, S (Int J Rheumatol, 2011)
Human glycolytic enzyme α-enolase was associated with human diseases and with inflammation. An ELISA test was developed to measure anti-α-enolase AAE IgG and AAE IgA in the serum from patients affected by inflammatory diseases with the purpose to evaluate it as a novel diagnostic marker. 80 healthy blood donors and 194 paediatric patients affected by Juvenile idiopathic arthritis (JIA), celiac disease (CD), Crohn's Disease (CrD), hereditary periodic fever (HPF), and PFAPA syndrome were included in the study. HPF patients showed high levels of AAE antibodies, whereas JIA, CD, and CrD presented only partial results. Benign fevers such as PFAPA were almost negative for AAE Abs. These findings suggested that the genetic dysfunction of inflammasome associated with HPF could lead to the formation of AAE Abs that could be used for an early and easy diagnosis.

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Childhood chronic anterior uveitis associated with vernal keratoconjunctivitis (VKC): successful treatment with topical tacrolimus. Case series. - Taddio, Andrea; Cimaz, Rolando; Caputo, Roberto; de Libero, Cinzia; Di Grande, Laura; Simonini, Gabriele; Mori, Francesca; Novembre, Elio; Pucci, Neri (Pediatr Rheumatol Online J, 2011)
Uveitis treatment involves topical corticosteroids along with cycloplegic-mydriatics. Particularly severe cases may require systemic corticosteroids and immunosuppressive drugs. Vernal keratoconjunctivitis (VKC) treatment consists of a brief period of topical corticosteroids and/or cyclosporine. In patients refractory to traditional treatment, the use of 0.1% topical ophtalmic FK- 506 (tacrolimus) ointment has been occasionally reported.This is the first report of the coexistence of uveitis and VKC. The documented response to topical tacrolimus eyedrop of uveitis and VKC is also of interest, in particular since to our knowledge there are no published reports on its clinical use in uveitis.

Circulating TRAIL shows a significant post-partum decline associated to stressful conditions. - Zauli, Giorgio; Monasta, Lorenzo; Rimondi, Erika; Vecchi Brumatti, Liza; Radillo, Oriano; Ronfani, Luca; Montico, Marcella; D'Ottavio, Giuseppina; Alberico, Salvatore; Secchiero, Paola (PLoS One, 2011)
BACKGROUND: Since circulating levels of TNF-related apoptosis inducing ligand (TRAIL) may be important in the physiopathology of pregnancy, we tested the hypothesis that TRAIL levels change at delivery in response to stressful conditions. METHODS/PRINCIPAL FINDINGS: We conducted a longitudinal study in a cohort of 73 women examined at week 12, week 16, delivery and in the corresponding cord blood (CB). Serum TRAIL was assessed in relationship with maternal characteristics and to biochemical parameters. TRAIL did not vary between 12 (67.6±27.6 pg/ml, means±SD) and 16 (64.0±16.2 pg/ml) weeks' gestation, while displaying a significant decline after partum (49.3±26.4 pg/ml). Using a cut-off decline >20 pg/ml between week 12 and delivery, the subset of women with the higher decline of circulating TRAIL (41.7%) showed the following characteristics: i) nullipara, ii) higher age, iii) operational vaginal delivery or urgent CS, iv) did not receive analgesia during labor, v) induced labor. CB TRAIL was significantly higher (131.6±52 pg/ml) with respect to the corresponding maternal TRAIL, and the variables significantly associated with the first quartile of CB TRAIL (<90 pg/ml) were higher pre-pregnancy BMI, induction of labor and fetal distress. With respect to the biochemical parameters, maternal TRAIL at delivery showed an inverse correlation with C-reactive protein (CRP), total cortisol, glycemia and insulin at bivariate analysis, but only with CRP at multivariate analysis. CONCLUSIONS: Stressful partum conditions and elevated CRP levels are associated with a decrease of circulating TRAIL.
Keywords: Adult; Biological Markers; C-Reactive Protein; Female; Fetal Blood; Fetal Distress; Humans; Labor, Obstetric; Logistic Models; Multivariate Analysis; Postpartum Period; Pregnancy; Pregnancy Outcome; Statistics, Nonparametric; Stress, Physiological; TNF-Related Apoptosis-Inducing Ligand

Clinical and genetic aspects of Bernard-Soulier syndrome: searching for genotype/phenotype correlations. - Savoia, Anna; Pastore, Annalisa; De Rocco, Daniela; Civaschi, Elisa; Di Stazio, Mariateresa; Bottega, Roberta; Melazzini, Federica; Bozzi, Valeria; Pecci, Alessandro; Magrin, Silvana; Balduini, Carlo L; Noris, Patrizia (Haematologica, 2011)
BACKGROUND: Bernard-Soulier syndrome is a severe bleeding disease due to a defect of GPIb/IX/V, a platelet complex that binds the von Willebrand factor. Due to the rarity of the disease, there are reports only on a few cases compromising any attempt to establish correlations between genotype and phenotype. In order to identify any associations, we describe the largest case series ever reported, which was evaluated systematically at the same center. DESIGN AND METHODS: Thirteen patients with the disease and seven obligate carriers were enrolled. We collected clinical aspects and determined platelet features, including number and size, expression of membrane glycoproteins, and ristocetin induced platelet aggregation. Mutations were identified by direct sequencing of the GP1BA, GP1BB, and GP9 genes and their effect was shown by molecular modeling analyses. RESULTS: Patients all had a moderate thrombocytopenia with giant platelets and a bleeding tendency whose severity varied among individuals. Consistent with expression levels of GPIbα always lower than 10% of control values, platelet aggregation was absent or severely reduced. Homozygous mutations were identified in the GP1BA, GP1BB and GP9 genes; six were novel alterations expected to destabilize the conformation of the respective protein. Except for obligate carriers of a GP9 mutation with a reduced GPIb/IX/V expression and defective aggregation, all the other carriers had no obvious anomalies. CONCLUSIONS: Regardless of mutations identified, the patients' bleeding diathesis did not correlate with thrombocytopenia, which was always moderate, and platelet GPIbα expression, which was always severely impaired. Obligate carriers had features similar to controls though their GPIb/IX/V expression showed discrepancies. Aware of the limitations of our cohort, we cannot define any correlations. However, further investigations should be encouraged to better understand the causes of this rare and underestimated disease.
Keywords: Adolescent; Adult; Amino Acid Sequence; Bernard-Soulier Syndrome; Blood Platelets; Cell Shape; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Markers; Hemorrhage; Homozygote; Humans; Italy; Male; Membrane Glycoproteins; Middle Aged; Molecular Sequence Data; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Point Mutation; Polymerase Chain Reaction; Ristocetin; Thrombocytopenia; von Willebrand Factor; Young Adult

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Compliance with the gluten-free diet: the role of locus of control in celiac disease. - Bellini, Anna; Zanchi, Chiara; Martelossi, Stefano; Di Leo, Grazia; Not, Tarcisio; Ventura, Alessandro (J Pediatr, 2011)
OBJECTIVES: To verify whether subjects with celiac disease (CD) have a different locus of control (LoC) compared with healthy subjects, and to evaluate the relationship between LoC and compliance with a prescribed gluten-free diet (GFD) and quality of life (QoL). STUDY DESIGN: We studied 156 subjects on a GFD (mean age, 10 years) and 353 healthy controls (mean age, 12 years). All subjects completed tests on the Nowicki-Strickland Locus of Control Scale; the subjects with CD also completed a questionnaire to measure compliance with dietary treatment and the disease's impact on QoL. RESULTS: There was no difference in LoC values between patients with CD and controls. Subjects with CD with good dietary compliance had a more internal LoC compared with those who were not compliant (P = .01). Patients who reported a satisfactory QoL had a more internal LoC compared with those who reported negative affects on QoL due to CD (P = .01). CONCLUSIONS: Our study confirms the usefulness of the LoC concept for identifying those patients who might be at risk for dietary transgression. Given the enhanced, psychological, and social well being that can result from adherence to a GFD, educational and psychological support can help internalize the LoC in those patients at risk for dietary transgression.
Keywords: Adolescent; Age Factors; Case-Control Studies; Celiac Disease; Child; Diet, Gluten-Free; Female; Humans; Internal-External Control; Italy; Male; Patient Compliance; Quality of Life

Concentrated midazolam for intranasal administration: a pilot study. - Calligaris, Lorenzo; Davide, Zanon; Alessandra, Maestro; De Bortoli, Romina; Chiaretti, Antonio; Barbi, Egidio (Pediatr Emerg Care, 2011)
Keywords: Administration, Intranasal; Child; Child, Preschool; Conscious Sedation; Dose-Response Relationship, Drug; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Pain; Pilot Projects; Preoperative Care

Corneal curvature and thickness development in premature infants. - De Silva, Silvana; Parentin, Fulvio; Michieletto, Paola; Pensiero, Stefano (J Pediatr Ophthalmol Strabismus, 2011)
PURPOSE: Analysis of postnatal changes in central corneal thickness (CCT) and corneal curvature (CC) in premature infants, their relation, and their possible influence on eye growth and intraocular pressure (IOP) evaluation. METHODS: CCT and CC were assessed in both eyes of 56 premature infants, born at 24 to 32 weeks of gestational age (GA), and then two or three times at post-conceptional ages (PCAs) of 28 to 42 weeks. RESULTS: CC changed from 65.83 diopters at 28 weeks of PCA to 49.38 diopters at 42 weeks of PCA. CCT decreased from 794 to 559 μm at the same ages. The reductions of these two corneal parameters seem to be related to each other and begin immediately after birth. CONCLUSION: In light of the few data available in the literature, these data provide more certainty about the CCT values of premature infants. The importance of CCT and CC fast variations after premature birth concerns both the knowledge of anterior segment development and the correct evaluation of IOP in immature eyes; the influence of these two parameters on the methods of IOP evaluation could be more remarkable at the lowest PCAs.
Keywords: Child Development; Cornea; Corneal Pachymetry; Eye; Female; Gestational Age; Humans; Infant, Newborn; Infant, Premature; Intraocular Pressure; Male; Premature Birth

Differential action of 3-hydroxyanthranilic acid on viability and activation of stimulated lymphocytes. - Piscianz, Elisa; Cuzzoni, Eva; De Iudicibus, Sara; Valencic, Erica; Decorti, Giuliana; Tommasini, Alberto (Int Immunopharmacol, 2011)
Lymphocytes proliferation after antigen-driven activation leads to an increase in cell count, which could last some week, until apoptosis mechanisms allow the homeostatic control of the system. During the first days of this stimulation, activated lymphocytes display high resistance to apoptosis and to most immunosuppressive drugs. According to the literature, few compounds have been described to kill recently activated cells, by inhibiting metabolic processes fundamental to proliferation. The aim of our work was to evaluate comparatively these different compounds, in order to identify the best strategy to kill cells that have undergone proliferation, while sparing the repertoire of resting cells. After preliminary experiments, 3-HAA and bortezomib were selected as the most suitable compounds for our purposes. The possible synergic effect of 3-HAA with bortezomib or with manganese ions was also assessed. 3-HAA was confirmed to be the most reliable pharmacologic approach to inhibit proliferation with acceptable toxicity on resting cells. While in the case of PHA stimulation 3-HAA led to death of most lymphocytes, only a minor percentage of cells were killed after allo-stimulation, suggesting that the effect is proportional to the percentage of stimulated lymphocytes. Manganese ions further enhanced this effect, while results with bortezomib seemed to be less consistent. These results deserve further investigations to develop new procedures for targeting activated cells with pharmacological approaches.
Keywords: 3-Hydroxyanthranilic Acid; Boronic Acids; Cell Survival; Cells, Cultured; Humans; Lymphocyte Activation; Lymphocytes; Manganese; Pyrazines

Epidemiological and molecular assessment of a measles outbreak in a highly vaccinated population of northeast Italy. - D'Agaro, P; Molin, G Dal; Gallo, T; Rossi, T; Santon, D; Busetti, M; Comar, M; Campello, C (Epidemiol Infect, 2011)
Two distinct measles outbreaks, unrelated from the epidemiological point of view but caused by genetically related strains, occurred in the Friuli Venezia Giulia region of northeastern Italy. Forty-two cases were reported during the period April-May 2008. In the first outbreak the index case was a teacher who introduced the virus into the Pordenone area, involving eight adolescents and young adults. The other concomitant outbreak occurred in the city of Trieste with 33 cases. The containment of the epidemics can be explained by the high MMR vaccine coverage in an area where the first dose was delivered to 93·4% and the second dose to 88·3% of the target children. Phylogenetic analysis of 14 measles virus strains showed that they belonged to a unique D4 genotype indistinguishable from the MVs/Enfield.GBR/14.07 strain, probably introduced from areas (i.e. Piedmont and Germany) where this genotype was present or had recently caused a large epidemic.
Keywords: Adolescent; Adult; Chi-Square Distribution; Child; Child, Preschool; Community-Acquired Infections; Disease Outbreaks; Female; Humans; Immunization Schedule; Infant; Italy; Male; Measles; Measles Vaccine; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny

The farnesyltransferase inhibitors tipifarnib and lonafarnib inhibit cytokines secretion in a cellular model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; De Leo, Luigina; Decorti, Giuliana; Crovella, Sergio; Tommasini, Alberto; Pontillo, Alessandra (Pediatr Res, 2011)
The shortage of geranylgeranyl-pyrophosphate (GGPP) was associated to an increased IL-1β release in the autoinflammatory syndrome mevalonate kinase deficiency (MKD), a rare inherited disease that has no specific therapy. Farnesyltransferase inhibitors (FTIs) act at the end of mevalonate pathway. Two FTIs, tipifarnib (Tip) and lonafarnib (Lon), were therefore evaluated as possible therapeutical choices for the treatment of MKD. FTIs could lead to a redirection of the limited available number of mevalonate intermediates preferentially to GGPP synthesis, eventually preventing the uncontrolled inflammatory response. The effect of Tip and Lon on intracellular cholesterol level (ICL) and on proinflammatory cytokines secretion was evaluated in a cellular model of MKD, chemically obtained treating RAW 264.7 cells with lovastatin (Lova) and alendronate (Ald). The combination of FTIs with the isoprenoid geraniol (GOH) was also tested both in this model and in monocytes isolated from MKD patients. Tip and Lon proved to revert the ICL lowering and to significantly reduce the lipopolysaccharide-induced cytokines secretion in Ald-Lova -RAW 264.7 cells. This anti-inflammatory effect was amplified combining the use of GOH with FTIs. The effect of GOH and Tip was successfully replicated in MKD patients' monocytes. Tip and Lon showed a dramatic anti-inflammatory effect in monocytes where mevalonate pathway was chemically or genetically impaired.
Keywords: Alendronate; Animals; Anti-Inflammatory Agents; Cell Line; Child; Child, Preschool; Cholesterol; Cytokines; Dose-Response Relationship, Drug; Enzyme Inhibitors; Farnesyltranstransferase; Humans; Inflammation Mediators; Lovastatin; Male; Mevalonate Kinase Deficiency; Mice; Monocytes; Phosphotransferases (Alcohol Group Acceptor); Piperidines; Polyenes; Polyisoprenyl Phosphates; Polyunsaturated Alkamides; Pyridines; Quinolones; Terpenes

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Frequency distribution of HLA DQ2 and DQ8 in celiac patients and first-degree relatives in Recife, northeastern Brazil. - Castro-Antunes, Margarida Maria; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Motta, Maria Eugênia Farias Almeida; Silva, Giselia Alves Pontes da (Clinics (Sao Paulo), 2011)
AIMS: The aim of this study was to evaluate the frequencies of the HLA genotypes DQ2 and DQ8 and the alleles A1*05, A1*0201, B1*0201 and B1*0302 in individuals with celiac disease in Recife, northeastern Brazil. METHODS: HLA DQ2 and DQ8 genotyping was performed for 73 individuals with celiac disease and 126 first-degree relatives with negative transglutaminase serology. The alleles DQA1*05, DQA1*0201, DQB1*02 and DQB1*0302 were identified by sequencing using specific primers and the EU-DQ kit from the Eurospital Laboratory, Trieste, Italy and double-checked by the All Set SPP kit (Dynal). RESULTS: Among the 73 cases, 50 (68.5%) had the genotype DQ2, 13 (17.8%) had DQ8, 5 (6.8%) had DQ2 and DQ8, and 5 did not have any of these genotypes. Among the 5 negative individuals, four had the B1*02 allele and one did not have any of the alleles studied. B1*02 was the most frequent allele in both groups (94% in the patients and 89% in the control relatives). CONCLUSIONS: In this study, celiac disease was associated with the genotypes DQ2 and DQ8. DQ2 predominated, but the distribution of the frequencies was different from what has been found in European populations and was closer to what has been found in the Americas. The high frequencies of the HLA genotypes DQ2 and DQ8 that were found in first-degree relatives would make it difficult to use these HLA genotypes for routine diagnosis of celiac disease in this group.
Keywords: Adolescent; Adult; Brazil; Celiac Disease; Chi-Square Distribution; Child; Child, Preschool; Cross-Sectional Studies; Europe; Family; Female; Gene Frequency; Genetic Predisposition to Disease; HLA-DQ Antigens; Humans; Infant; Male; Middle Aged; Young Adult

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High prevalence of BK polyomavirus sequences in human papillomavirus-16-positive precancerous cervical lesions. - Comar, Manola; Bonifacio, Daniela; Zanconati, Fabrizio; Di Napoli, Michela; Isidoro, Erica; Martini, Fernanda; Torelli, Lucio; Tognon, Mauro (J Med Virol, 2011)
High- and low-grade cervical lesions were analyzed for the presence of polyomavirus (PYV) and human papillomavirus (HPV) sequences. In precancerous cervical lesions, the overall prevalence of PYV sequences was 44% (41/93). Specifically, among the PYV-positive samples, 83% (34/41) tested positive for BK polyomavirus (BKV) sequences, whereas 17% (7/41) were positive for JC-virus. None of the samples were positive for simian virus 40. The presence of BKV DNA in high-grade squamous intraepithelial lesions was confirmed by in situ PCR. BKV sequences were detected more frequently in high-grade squamous intraepithelial lesions, together with the genotype HPV-16. The association of BKV with precancerous cervical lesions suggests that this polyomavirus participates with HPV-16 in the cell transformation process. Alternatively, BKV might multiply better in HPV-16-positive cells from precancerous cervical lesions than in HPV-16-negative cells.
Keywords: Adult; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; JC Virus; Middle Aged; Oncogene Proteins, Viral; Papillomavirus Infections; Precancerous Conditions; Simian virus 40; Uterine Cervical Diseases

In vivo distribution of β2 glycoprotein I under various pathophysiologic conditions. - Agostinis, Chiara; Biffi, Stefania; Garrovo, Chiara; Durigutto, Paolo; Lorenzon, Andrea; Bek, Alpan; Bulla, Roberta; Grossi, Claudia; Borghi, Maria O; Meroni, Pierluigi; Tedesco, Francesco (Blood, 2011)
In vitro studies have documented β2 glycoprotein I (β2GPI) binding to endothelial cells (ECs) and trophoblast using antiphospholipid antibodies. The in vivo binding of β2GPI to these cells and the conditions that favor their interaction have not been investigated. We analyzed the in vivo distribution of cyanine 5.5-labeled β2GPI in mice and evaluated the effect of pregnancy and circulating antibodies on its tissue localization. The signal was detected in the liver by whole body scan and ex vivo analysis. The β2GPI failed to bind to the vascular endothelium and reacted only with the ECs of uterine vessels. In pregnant mice the protein was localized on ECs and trophoblast at the embryo implantation sites. Immunized mice showed a similar β2GPI biodistribution to naive mice but the immunized pregnant animals exhibited a significant increase in fetal loss associated with C3 and C9 deposition at the implantation sites. Treatment of mice with LPS after β2GPI-Cy5.5 injection promoted protein localization on gut and brain ECs associated with IgG, C1q, and C9 deposition in immunized mice. These findings indicate that β2GPI binding to EC requires priming with pro-inflammatory factors which is not needed for uterine and placental localization probably dependent on hormonal changes.
Keywords: Animals; beta 2-Glycoprotein I; Complement C1q; Complement C3; Complement C9; Endothelial Cells; Endothelium, Vascular; Female; Fetal Death; Humans; Mice; Mice, Inbred BALB C; Pregnancy; Trophoblasts; Uterus

Mannose binding lectin gene (MBL2) functional polymorphisms are associated with systemic lupus erythematosus in southern Brazilians. - Sandrin-Garcia, Paula; Brandão, Lucas André Cavalcanti; Coelho, Antônio Victor Campos; Guimarães, Rafael Lima; Pancoto, João Alexandre Trés; Segat, Ludovica; Donadi, Eduardo Antônio; de Lima-Filho, José Luiz; Crovella, Sergio (Hum Immunol, 2011)
Susceptibility to systemic lupus erythematosus (SLE) has been associated with immunologic, environmental, and genetic factors. To uncover a possible association between MBL2 gene polymorphisms and SLE, we analyzed functional polymorphisms in the promoter and first exon of the MBL2 gene in 134 Brazilian SLE patients and 101 healthy controls. Genotype and allele frequencies of MBL2 A/O polymorphism were significantly different between patients and controls, and the O allele was associated with an increased risk of SLE. An association between low mannose binding lectin (MBL) producer combined genotypes and increased risk for SLE was also reported. Furthermore, when stratifying SLE patients according to clinical and laboratory data, an association between the A/O genotype and nephritic disorders and between the X/Y genotype and antiphospholipid syndrome was evident. Combined genotypes responsible for low MBL production were more frequently observed in SLE patients with nephritis. Our results indicate MBL2 polymorphisms as possible risk factors for SLE development and disease-related clinical manifestations.
Keywords: Adolescent; Adult; Aged; Brazil; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Lupus Erythematosus, Systemic; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Genetic; Population Groups; Promoter Regions, Genetic

Mannose-binding lectin gene (MBL-2) polymorphism in oral lichen planus. - Barkokebas, Andreza; de Albuquerque T Carvalho, Alessandra; de Souza, Paulo Roberto Eleutério; Gomez, Ricardo Santiago; Xavier, Guilherme Machado; Ribeiro, Camila Maria Beder; Crovella, Sergio; Porter, Stephen Ross; Leão, Jair Carneiro (Clin Oral Investig, 2011)
TNF-α may be associated with the etiopathogenesis of oral lichen planus (OLP), and it has been suggested that polymorphism of mannose-binding lectin (MBL) increases the in vitro production of TNF- α. The aim of the present study was to assess the relevance of genetic diversity of MBL in OLP. The study sample comprised 90 individuals, 45 OLP patients and 45 healthy volunteers. MBL-2 gene was amplified using real-time PCR. Frequency of A/A genotype was 55.6% in OLP and 53.3% in healthy volunteers. Likewise, A/0 heterozygote genotype was found in 42.2% and 35.6%; 2.2% and 11.1%, had the recessive 0/0 genotype respectively. Frequencies of the "A" and "0" alleles were 77% and 23% in the OLP group and 71.2% in control group. There were no statistically significant differences regarding genotype frequency (p = 0.546) or allele frequency (p = 0.497). In conclusion, no significant association was found between polymorphism of MBL-2 gene and OLP.
Keywords: Adolescent; Adult; Aged; Female; Gene Expression Regulation; Gene Frequency; Genes, Recessive; Genetic Variation; Genotype; Heterozygote; Homozygote; Humans; Lichen Planus, Oral; Male; Mannose-Binding Lectin; Middle Aged; Mutation; Polymorphism, Genetic; Real-Time Polymerase Chain Reaction; Tumor Necrosis Factor-alpha; Young Adult

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

miR-34a induces the downregulation of both E2F1 and B-Myb oncogenes in leukemic cells. - Zauli, Giorgio; Voltan, Rebecca; di Iasio, Maria Grazia; Bosco, Raffaella; Melloni, Elisabetta; Sana, Maria Elena; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To elucidate new molecular mechanisms able to downregulate the mRNA levels of key oncogenes, such as B-Myb and E2F1, in a therapeutic perspective. EXPERIMENTAL DESIGN: B-Myb and E2F1 mRNA levels were evaluated in primary B chronic lymphocytic leukemia (B-CLL, n = 10) and acute myeloid leukemia (AML, n = 5) patient cells, in a variety of p53(wild-type) and p53(mutated/deleted) leukemic cell lines, as well as in primary endothelial cells and fibroblasts. Knockdown experiments with siRNA for p53 and E2F1 and overexpression experiments with miR34a were conducted to elucidate the role of these pathways in promoting B-Myb downregulation. RESULTS: In vitro exposure to Nutlin-3, a nongenotoxic activator of p53, variably downregulated the expression of B-Myb in primary leukemic cells and in p53(wild-type) myeloid (OCI, MOLM) and lymphoblastoid (SKW6.4, EHEB) but not in p53(mutated) (NB4, BJAB, MAVER) or p53(deleted) (HL-60) leukemic cell lines. The transcriptional repression of B-Myb was also observed in primary normal endothelial cells and fibroblasts. B-Myb downregulation played a critical role in the cell-cycle block in G(1) phase induced by Nutlin-3, as shown by transfection experiments with specific siRNA. Moreover, we have provided experimental evidence suggesting that miR-34a is a central mediator in the repression of B-Myb both directly and through E2F1. CONCLUSIONS: Owing to the role of B-Myb and E2F1 transcription factors in controlling cell-cycle progression of leukemic cells, the downregulation of these oncogenes by miR-34a suggests the usefulness of therapeutic approaches aimed to modulate the levels of miR-34a.
Keywords: Base Sequence; Cell Cycle Proteins; Cell Line, Tumor; Cells, Cultured; Down-Regulation; E2F1 Transcription Factor; Gene Expression Regulation, Leukemic; HCT116 Cells; HL-60 Cells; Humans; Imidazoles; Leukemia; MicroRNAs; Models, Biological; Oncogenes; Piperazines; Sequence Homology, Nucleic Acid; Trans-Activators; Transfection

A molecular case-control study of the Merkel cell polyomavirus in colon cancer. - Campello, Cesare; Comar, Manola; D'Agaro, Pierlanfranco; Minicozzi, Anna; Rodella, Luca; Poli, Albino (J Med Virol, 2011)
To explore the putative role of the Merkel cell polyomavirus in human colon cancer, a prospective molecular case-control study was undertaken in patients and their relatives enrolled during a screening program. Fresh tissue samples from 64 cases of colon cancer (mean age 69.9 ± 11.0 years; 40 males) and fresh biopsies from 80 relatives (mean age 53.7 ± 8.6 years; 43 male; 55 son/daughter, 23 brother/sister, 2 parents) were analyzed by PCR and sequencing. Pre-cancerous lesions, namely adenomas and polyps, were detected in 15 (18.8%) and 9 (11.2%) of the controls, respectively. In addition, 144 blood samples were examined. Merkel cell polyomavirus DNA was detected in 6.3% of cases and 8.8% of controls. This difference was not statistically significant in the logistic regression analysis, after adjustment for age. Whereas blood samples from both cases and controls tested negative, the DNA Merkel cell polyomavirus was identified in 12.5% of adenoma/polyp tissues. No statistically significant difference was found when prevalence rates of Merkel cell polyomavirus in normal, pre-cancerous and cancer tissues were compared. Sequence analysis of the viral LT3 and VP1 regions showed high homology (>99%) with those of strains circulating worldwide, especially with genotypes detected in France. The findings of this survey are consistent with the hypothesis that the Merkel cell polyomavirus, in addition to other human polyomaviruses, can be recovered frequently from the gastrointestinal tract, because it is transmitted throughout the fecal-oral route. Moreover, the study does not indicate a role for Merkel cell polyomavirus in the genesis of colon cancer.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cluster Analysis; Colonic Neoplasms; DNA, Viral; Female; Genotype; Humans; Italy; Male; Merkel Cells; Middle Aged; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Sequence Analysis, DNA; Tumor Virus Infections

Molecular mechanism of glucocorticoid resistance in inflammatory bowel disease. - De Iudicibus, Sara; Franca, Raffaella; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (World J Gastroenterol, 2011)
Natural and synthetic glucocorticoids (GCs) are widely employed in a number of inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in moderate to severe active Crohn's disease and ulcerative colitis. Despite their extensive therapeutic use and the proven effectiveness, considerable clinical evidence of wide inter-individual differences in GC efficacy among patients has been reported, in particular when these agents are used in inflammatory diseases. In recent years, a detailed knowledge of the GC mechanism of action and of the genetic variants affecting GC activity at the molecular level has arisen from several studies. GCs interact with their cytoplasmic receptor, and are able to repress inflammatory gene expression through several distinct mechanisms. The glucocorticoid receptor (GR) is therefore crucial for the effects of these agents: mutations in the GR gene (NR3C1, nuclear receptor subfamily 3, group C, member 1) are the primary cause of a rare, inherited form of GC resistance; in addition, several polymorphisms of this gene have been described and associated with GC response and toxicity. However, the GR is not self-standing in the cell and the receptor-mediated functions are the result of a complex interplay of GR and many other cellular partners. The latter comprise several chaperonins of the large cooperative hetero-oligomeric complex that binds the hormone-free GR in the cytosol, and several factors involved in the transcriptional machinery and chromatin remodeling, that are critical for the hormonal control of target genes transcription in the nucleus. Furthermore, variants in the principal effectors of GCs (e.g. cytokines and their regulators) have also to be taken into account for a comprehensive evaluation of the variability in GC response. Polymorphisms in genes involved in the transport and/or metabolism of these hormones have also been suggested as other possible candidates of interest that could play a role in the observed inter-individual differences in efficacy and toxicity. The best-characterized example is the drug efflux pump P-glycoprotein, a membrane transporter that extrudes GCs from cells, thereby lowering their intracellular concentration. This protein is encoded by the ABCB1/MDR1 gene; this gene presents different known polymorphic sites that can influence its expression and function. This editorial reviews the current knowledge on this topic and underlines the role of genetics in predicting GC clinical response. The ambitious goal of pharmacogenomic studies is to adapt therapies to a patient's specific genetic background, thus improving on efficacy and safety rates.
Keywords: Drug Resistance; Glucocorticoids; Humans; Inflammatory Bowel Diseases; P-Glycoproteins; Polymorphism, Genetic; Receptors, Glucocorticoid; Signal Transduction; Transcription, Genetic

A multicenter, case-control study on risk factors for antepartum stillbirth. - Facchinetti, Fabio; Alberico, Salvatore; Benedetto, Chiara; Cetin, Irene; Cozzolino, Sabrina; Di Renzo, Gian Carlo; Del Giovane, Cinzia; Ferrari, Francesca; Mecacci, Federico; Menato, Guido; Tranquilli, Andrea L; Baronciani, Dante (J Matern Fetal Neonatal Med, 2011)
OBJECTIVE: As the influence of socio-demographic variables, lifestyle and medical conditions on the epidemiology of stillbirth (SB) is modified by population features, we aimed at investigating the role played by these factors on the incidence of SB in a developed country. STUDY DESIGN: Multivariate logistic regression analysis (OR with 95% CI) was utilized in a prospective multicentre nested case-control study to compare in a 1:2 ratio stillborn of >22 weeks gestation with matched for gestational age live-born (LB) infants. Intrapartum SB were excluded. RESULTS: Two hundred fifty-four consecutive SBs and 497 LBs were enrolled. Socio-demographic variables were equally distributed. Fetal malformations (7.96, 2.69-23.55), severe intrauterine growth restriction (IUGR) (birthweight ≤ 5(th) %ile) (4.32, 2.27?8.24), BMI > 25 (2.87, 1.90-4.33), and preeclampsia (PE, 0.40, 0.21-0.77) were recognized as independent predictors for SB. At term, only BMI > 25 was associated with SB (7.70, 2.9-20.5). CONCLUSION: Fetal malformations, severe IUGR and maternal BMI > 25 were associated with a significant increase in the risk of SB; PE presented instead a protective role. Maternal BMI > 25 was the only risk factor for SB identified in term pregnancies.
Keywords: Adult; Case-Control Studies; Cause of Death; Congenital Abnormalities; Female; Fetal Death; Fetal Growth Retardation; Humans; Infant, Newborn; Male; Obstetric Labor Complications; Pre-Eclampsia; Pregnancy; Risk Factors; Stillbirth; Young Adult

A multicenter, randomized, placebo-controlled trial of levetiracetam in children and adolescents with newly diagnosed absence epilepsy. - Fattore, Cinzia; Boniver, Clementina; Capovilla, Giuseppe; Cerminara, Caterina; Citterio, Antonietta; Coppola, Giangennaro; Costa, Paola; Darra, Francesca; Vecchi, Marilena; Perucca, Emilio (Epilepsia, 2011)
PURPOSE: To evaluate the potential efficacy of levetiracetam as an antiabsence agent in children and adolescents with newly diagnosed childhood or juvenile absence epilepsy. METHODS: Patients were randomized in a 2:1 ratio to receive de novo monotherapy with levetiracetam (up to 30 mg/kg/day) or placebo for 2 weeks under double-blind conditions. Responder status (primary end point) was defined as freedom from clinical seizures on days 13 and 14 and from electroencephalographic (EEG) seizures during a standard EEG recording with hyperventilation and intermittent photic stimulation on day 14. The double-blind phase was followed by an open-label follow-up. KEY FINDINGS: Nine of 38 patients (23.7%) were responders in the levetiracetam group, compared with one of 21 (4.8%) in the placebo group (p = 0.08). Seven of 38 patients (18.4%) were free from clinical and EEG seizures during the last 4 days of the trial (including 24-h EEG monitoring on day 14) compared with none of the patients treated with placebo (p = 0.04). Seventeen patients remained seizure-free on levetiracetam after 1 year follow-up. Of the 41 patients who discontinued levetiracetam due to lack of efficacy (n = 39) or adverse events (n = 2), 34 became seizure-free on other treatments. SIGNIFICANCE: Although superiority to placebo just failed to reach statistical significance for the primary end point, the overall findings are consistent with levetiracetam having modest efficacy against absence seizures. Further controlled trials exploring larger doses and an active comparator are required to determine the role of levetiracetam in the treatment of absence epilepsy.
Keywords: Adolescent; Age Factors; Anticonvulsants; Child; Child, Preschool; Double-Blind Method; Drug Resistance; Epilepsy, Absence; Female; Humans; Male; Outcome Assessment (Health Care); Piracetam

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, Daniele; Arzuffi, Paola; Zordan, Mauro; Da Re, Caterina; Lamperti, Costanza; Benna, Clara; d'Adamo, Pio; Diodato, Daria; Costa, Rodolfo; Mariotti, Caterina; Uziel, Graziella; Smiderle, Cristina; et al. (Nat Genet, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.
Keywords: Adult; Animals; Brain; Codon, Nonsense; Drosophila melanogaster; Electron Transport Complex III; Female; Gene Knockdown Techniques; Humans; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Nervous System Diseases

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

A new case of duplication of the MDS region identified by high-density SNP arrays and a review of the literature. - Faletra, Flavio; Devescovi, Raffaella; Pecile, Vanna; Fabretto, Antonella; Carrozzi, Marco; Gasparini, Paolo (J Appl Genet, 2011)
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Child; Female; Gene Duplication; Humans; Microtubule-Associated Proteins; Myelodysplastic Syndromes; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prognosis

Non-invasive assessment of hemispheric language dominance by optical topography during a brief passive listening test: a pilot study. - Bembich, Stefano; Demarini, Sergio; Clarici, Andrea; Massaccesi, Stefano; Grasso, Domenico Loenardo (Med Sci Monit, 2011)
BACKGROUND: The Wada test is usually used for pre-surgical assessment of language lateralization. Considering its invasiveness and risk of complications, alternative methods have been proposed but they are not always applicable to non-cooperative patients. In this study we explored the possibility of using optical topography (OT)--a multichannel near-infrared system--for non-invasive assessment of hemispheric language dominance during passive listening. MATERIAL/METHODS: Cortical activity was monitored in a sample of healthy, adult Italian native speakers, all right-handed. We assessed changes in oxy-haemoglobin concentration in temporal, parietal and posterior frontal lobes during a passive listening of bi-syllabic words and vowel-consonant-vowel syllables lasting less then 3 minutes. Activated channels were identified by t tests. RESULTS: Left hemisphere showed significant activity only during the passive listening of bi-syllabic words. Specifically, the superior temporal gyrus, the supramarginal gyrus and the posterior inferior parietal lobe were activated. CONCLUSIONS: During passive listening of bi-syllabic words, right handed healthy adults showed a significant activation in areas already known to be involved in speech comprehension. Although more research is needed, OT proved to be a promising alternative to the Wada test for non-invasive assessment of hemispheric language lateralization, even if using a particularly brief trial, which has been designed for future applications with non-cooperative subjects.
Keywords: Acoustic Stimulation; Adult; Cerebrum; Diagnostic Techniques and Procedures; Dominance, Cerebral; Female; Humans; Language; Male; Middle Aged; Oxyhemoglobins; Pilot Projects; Spectroscopy, Near-Infrared

Periodontal infection and preterm birth: successful periodontal therapy reduces the risk of preterm birth. - Di Mario, S; Spettoli, D; Alessandrini, C; Erenbourg, A; Ronfani, L; Basevi, V (BJOG, 2011)
Keywords: Female; Humans; Periodontal Diseases; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Randomized Controlled Trials as Topic; Risk Factors

A Phase II study on the safety and efficacy of a single dose of pegfilgrastim for mobilization and transplantation of autologous hematopoietic stem cells in pediatric oncohematology patients. - Cesaro, Simone; Zanazzo, Andrea Giulio; Frenos, Stefano; Luksch, Roberto; Pegoraro, Anna; Tridello, Gloria; Dallorso, Sandro (Transfusion, 2011)
BACKGROUND: Limited data are available on the use of pegfilgrastim in pediatric patients as a mobilizing agent in association with chemotherapy. STUDY DESIGN AND METHODS: This was a prospective, multicenter, Phase II study to evaluate the safety and efficacy of a single dose of 100 µg/kg pegfilgrastim in mobilizing peripheral blood stem cells (PBSCs) in pediatric patients. The primary endpoint of the study was the percentage of good mobilizers with pegfilgrastim (blood peak of CD34+ cells ≥ 20 × 10(6) /L). The results were compared with a historical control group. RESULTS: Thirty of 36 recruited patients were classified as good mobilizers (83%). The median value of circulating CD34+ at leukapheresis was 143 × 10(6) /L (range, 20 × 10(6) -1988 × 10(6) /L). No significant adverse effects were associated with the use of pegfilgrastim and no patient was withdrawn from using the drug. A blood peak of 20 × 10(6) /L or more CD34+ was observed in 33 of 36 control patients (92%) and the median CD34+ count at leukapheresis was 158 × 10(6) /kg (range, 28 × 10(6) -4529 × 10(6) /kg; p = 0.7). No significant differences were found between the two groups in terms of toxicity or other variables of mobilization. As at October 2008, 23 patients of the pegfilgrastim group and 32 patients of the filgrastim group underwent autologous transplant. No significant differences were found in terms of early toxicity, myeloid recovery, and Day 100 survival. CONCLUSION: A single dose of 100 µg/kg pegfilgrastim was safe and effective for PBSC collection in pediatric patients. We suggest that these results support the use of pegfilgrastim for pediatric patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Granulocyte Colony-Stimulating Factor; Hematopoietic Stem Cell Mobilization; Humans; Infant; Male; Neoplasms; Peripheral Blood Stem Cell Transplantation; Prospective Studies; Recombinant Proteins; Transplantation, Autologous

Phospholipase C-β3 is a key modulator of IL-8 expression in cystic fibrosis bronchial epithelial cells. - Bezzerri, Valentino; d'Adamo, Pio; Rimessi, Alessandro; Lanzara, Carmen; Crovella, Sergio; Nicolis, Elena; Tamanini, Anna; Athanasakis, Emmanouil; Tebon, Maela; Bisoffi, Giulia; Drumm, Mitchell L; Knowles, Michael R; et al. (J Immunol, 2011)
Respiratory insufficiency is the major cause of morbidity and mortality in patients affected by cystic fibrosis (CF). An excessive neutrophilic inflammation, mainly orchestrated by the release of IL-8 from bronchial epithelial cells and amplified by chronic bacterial infection with Pseudomonas aeruginosa, leads to progressive tissue destruction. The anti-inflammatory drugs presently used in CF patients have several limitations, indicating the need for identifying novel molecular targets. To address this issue, we preliminarily studied the association of 721 single nucleotide polymorphisms from 135 genes potentially involved in signal transduction implicated in neutrophil recruitment in a cohort of F508del homozygous CF patients with either severe or mild progression of lung disease. The top ranking association was found for a nonsynonymous polymorphism of the phospholipase C-β3 (PLCB3) gene. Studies in bronchial epithelial cells exposed to P. aeruginosa revealed that PLCB3 is implicated in extracellular nucleotide-dependent intracellular calcium signaling, leading to activation of the protein kinase Cα and Cβ and of the nuclear transcription factor NF-κB p65. The proinflammatory pathway regulated by PLCB3 acts by potentiating the Toll-like Receptors' signaling cascade and represents an interesting molecular target to attenuate the excessive recruitment of neutrophils without completely abolishing the inflammatory response.
Keywords: Adenosine Triphosphate; Calcium; Cell Line, Transformed; Cystic Fibrosis; Enzyme Activation; Epithelial Cells; Gene Expression; Gene Frequency; Genotype; Green Fluorescent Proteins; Host-Pathogen Interactions; Humans; Interleukin-8; Isoenzymes; Lung Diseases; Microscopy, Fluorescence; Phospholipase C beta; Polymorphism, Single Nucleotide; Protein Kinase C; Protein Kinase C beta; Pseudomonas aeruginosa; RNA Interference; Toll-Like Receptors; Transcription Factor RelA

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

Procalcitonin in detecting neonatal nosocomial sepsis. - Auriti, Cinzia; Fiscarelli, Ersilia; Ronchetti, Maria Paola; Argentieri, Marta; Marrocco, Gabriella; Quondamcarlo, Anna; Seganti, Giulio; Bagnoli, Francesco; Buonocore, Giuseppe; Serra, Giovanni; Bacolla, Gianfranco; Mastropasqua, Savino; et al. (Arch Dis Child Fetal Neonatal Ed, 2011)
OBJECTIVE: To investigate the accuracy of procalcitonin (PCT) as a diagnostic marker of nosocomial sepsis (NS) and define the most accurate cut-off to distinguish infected from uninfected neonates. SETTING: Six neonatal intensive care units (NICUs). PATIENTS: 762 neonates admitted to six NICUs during a 28-month observational study for whom at least one serum sample was taken on admission. MAIN OUTCOME MEASURES: Positive and negative predictive values at different PCT cut-off levels. RESULTS: The overall probability of an NS was doubled or more if PCT was >0.5 ng/ml. In very-low-birth-weight (VLBW) infants, a cut-off of >2.4 ng/ml gave a positive predictive value of NS near to 50% with a probability of a false-positive diagnosis of NS in about 10% of the patients. CONCLUSIONS: In VLBW neonates, a serum PCT value >2.4 ng/ml prompts early empirical antibiotic therapy, while in normal-birth-weight infants, a PCT value ≤2.4 ng/ml carries a low risk of missing an NS.

Promoting mother’s milk use in very low birth weight infants: when nutritional hierarchy deals with the professional value system. - Davanzo, Riccardo (J Hum Lact, 2011)
Keywords: Attitude of Health Personnel; Breast Feeding; Health Promotion; Humans; Infant, Newborn; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal

[Proteomic applications in gynecology-obstetrics]. - De Seta, F; Banco, R; Guaschino, S; De Santo, D; Turrisi, A; Piva, C (Minerva Ginecol, 2011)
Proteomics has recently emerged as a powerful approach both for discovering biomarkers as well as for understanding the physiopathology of unclear gynecological-obstetrical disorders. Currently, several biological fluids and fetal tissues were successfully tested, including maternal plasma, amniotic fluid, cervical-vaginal fluid, urine, saliva, placental trophoblast, amnio-chorionic membranes and cord blood. The potential of proteomics on the polycystic ovary syndrome (PCOS) involves biomarkers discovery for a more accurate diagnosis of the syndrome and identification, within the patients with PCOS, those who respond more easily to treatment and those who will be at increased risk for future metabolic complications. The proteomic approach applied to patients with endometriosis would allow not only a non-invasive early diagnosis, but also a staging of the disease and a prediction of infertility risk. Proteomics also involves oncological field, in order to discover biomarkers that allow early diagnosis and prognosis of female genital malignancies. In addition to this, proteomics could be used to understand and predict obstetrical complications such as recurrent spontaneous abortion, preterm birth and preeclampsia. However, further studies are needed on a larger cohort of patients to introduce these biomarkers in clinical practice.
Keywords: Endometriosis; Female; Genital Diseases, Female; Genital Neoplasms, Female; Humans; Polycystic Ovary Syndrome; Pregnancy; Pregnancy Complications; Proteomics

Refractory iron-deficiency anaemia in a child with portal cavernoma. - Pastore, Serena; Londero, Margherita; Cont, Gabriele; Di Leo, Grazia; Ventura, Alessandro (Gut, 2011)
Keywords: Anemia, Iron-Deficiency; Antihypertensive Agents; Child; Hemangioma, Cavernous; Humans; Hypertension, Portal; Ileal Diseases; Male; Propranolol; Vascular Neoplasms

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

Role of DC-SIGN and L-SIGN receptors in HIV-1 vertical transmission. - da Silva, Ronaldo Celerino; Segat, Ludovica; Crovella, Sergio (Hum Immunol, 2011)
The innate immune system acts in the first line of host defense against pathogens. One of the mechanisms used involves the early recognition and uptake of microbes by host professional phagocytes, through pattern recognition receptors (PRRs). These PRRs bind to conserved microbial ligands expressed by pathogens and initiate both innate and adaptative immune responses. Some PRRs located on the surface of dendritic cells (DCs) and other cells seem to play an important role in human immunodeficiency virus type 1 (HIV-1) transmission. Dendritic cell-specific intercellular adhesion molecule-3 grabbing non-integrin, CD209 (DC-SIGN) and its homolog, DC-SIGN-related (DC-SIGNR or L-SIGN) receptors are PPRs able to bind the HIV-1 gp120 envelope protein and, because alterations in their expression patterns also occur, they might play a role in both horizontal and vertical transmission as well as in disseminating the virus within the host. This review aims to explore the involvement of the DC-SIGN and L-SIGN receptors in HIV-1 transmission from mother to child.
Keywords: Cell Adhesion Molecules; HIV Infections; HIV-1; Humans; Immunity, Innate; Infectious Disease Transmission, Vertical; Lectins, C-Type; Polymorphism, Genetic; Receptors, Cell Surface

The role of mannose-binding lectin gene polymorphisms in susceptibility to HIV-1 infection in Southern Brazilian patients. - da Silva, Gabriela Kniphoff; Guimarães, Rafael; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Brandão, Lucas; Crovella, Sergio; Chies, José Artur Bogo (AIDS, 2011)
OBJECTIVE: This study investigates the role of mannose-binding lectin (MBL) in the susceptibility to HIV-1 infection analyzing polymorphisms located at the MBL2 promoter and exon 1 regions. MATERIALS AND METHODS: The prevalence of MBL2 variant alleles was investigated in 410 HIV-1-infected patients from the South Brazilian HIV cohort and in 345 unexposed uninfected healthy individuals. The promoter variants were genotyped using polymerase chain reaction with sequence-specific primers (PCR-SSP) and exon 1 variants were analyzed by real-time PCR using a melting temperature assay and were confirmed by PCR-restriction fragment length polymorphism (RFLP). MBL2 genotypic and allelic frequencies were compared between HIV-1-infected patients and controls using the chi-squared tests. RESULTS: The analyses were performed subdividing the individuals according to their ethnic origin. Among Euro-derived individuals a higher frequency of the LX/LX genotype was observed in patients when compared to controls (P < 0.001). The haplotypic analysis also showed a higher frequency of the haplotypes associated with lower MBL levels among HIV-1-infected patients (P = 0.0001). Among Afro-derived individuals the frequencies of LY/LY and HY/HY genotypes were higher in patients when compared to controls (P = 0.009 and P = 0.02). CONCLUSIONS: An increased frequency of MBL2 genotypes associated with low MBL levels was observed in Euro-derived patients, suggesting a potential role for MBL in the susceptibility to HIV-1 infection in Euro-derived individuals.
Keywords: Adult; Aged; Brazil; Female; Genetic Predisposition to Disease; HIV Infections; HIV-1; Humans; Lectins, C-Type; Male; Mannose-Binding Lectin; Mannose-Binding Lectins; Middle Aged; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Cell Surface; Young Adult

Rubella susceptibility profile in pregnant women with HIV. - Floridia, Marco; Pinnetti, Carmela; Ravizza, Marina; Tibaldi, Cecilia; Sansone, Matilde; Fiscon, Marta; Guaraldi, Giovanni; Guerra, Brunella; Alberico, Salvatore; Spinillo, Arsenio; Castelli, Paula; Dalzero, Serena; et al. (Clin Infect Dis, 2011)
Keywords: Female; HIV Infections; Humans; Pregnancy; Pregnancy Complications, Infectious; Rubella

Safety and efficacy of high-dose acarbose treatment for dumping syndrome. - De Cunto, Angela; Barbi, Egidio; Minen, Federico; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2011)
Dumping syndrome (DS) is a complication of Nissen fundoplication. Dietary strategies can ameliorate symptoms, but this approach is not always foolproof. Limited evidence reports the efficacy of acarbose for children who are unresponsive to feeding manipulations. We report 8 patients with DS aged between 7 and 24 months. In 4 of 8 nutritional strategies failed, and acarbose treatment was started. The initial dose was 25 mg for meals, and increased until postprandial glucose was stable. In 3 of 4 children the final dose was higher than previously reported, without adverse effects. Acarbose is useful to treat DS in cases of failure of dietary strategies.
Keywords: Acarbose; Child, Preschool; Dumping Syndrome; Female; Humans; Hyperglycemia; Hypoglycemic Agents; Infant; Male; Postprandial Period; Treatment Outcome

Secondary lymphoid tissue as an important site for WU polyomavirus infection in immunocompetent children. - Comar, Manola; Zanotta, Nunzia; Rossi, Tatiana; Pelos, Giorgio; D'Agaro, Pierlanfranco (J Med Virol, 2011)
The polyomaviruses KI and WU (KIPyV and WUPyV) have been identified in respiratory specimens from children with acute respiratory infections, which suggests the respiratory tract as a possible site of infection. However, the persistence of infection in the lymphoid system is unknown. Fresh samples (n = 211) of tonsils, adenoids, and peripheral blood mononuclear cells (PBMCs) from 83 immunocompetent children (mean age 4.8 years) were tested for amplification of the KIPyV VP1 and WUPyV VP2 genes. The known BK and JC polyomaviruses and the lymphotropic human herpesvirus (HHV)-6 were also investigated by quantitative real-time PCR and direct sequencing. In addition, 98 nasopharyngeal swabs collected from children (mean age 6.2 years) affected by seasonal influenza-like illness were tested. Of the lymphoid tissues, 34.9% were positive for WUPyV, 4.8% for BK virus, and 33.8% for HHV-6. KIPyV and JC virus were not detected in these specimens. None of the polyomaviruses were detected in PBMCs. Among the nasopharyngeal samples, the prevalence of WUPyV was 27.5%, although 70% of the positive samples were co-infected with at least one of the following respiratory viruses: influenza virus, adenovirus, and respiratory syncytial virus. Phylogenetic analysis revealed high sequence homology (99%) between lymphoid- and nasopharynx-derived WUPyV strains. These results suggest that the tonsils and adenoids of immunocompetent children are a reservoir for WUPyV infection; probably due to the respiratory route of transmission. In addition, the prevalence of WUPyV was high among the children, and the virus was identified more frequently in older children than during the first years of life.
Keywords: Adenoids; Child; Child, Preschool; DNA, Viral; Female; Humans; Infant; Leukocytes, Mononuclear; Male; Nasopharynx; Palatine Tonsil; Phylogeny; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Sequence Analysis, DNA; Sequence Homology

Setting research priorities to reduce global mortality from childhood pneumonia by 2015. - Rudan, Igor; El Arifeen, Shams; Bhutta, Zulfiqar A; Black, Robert E; Brooks, Abdullah; Chan, Kit Yee; Chopra, Mickey; Duke, Trevor; Marsh, David; Pio, Antonio; Simoes, Eric A F; Tamburlini, Giorgio; et al. (PLoS Med, 2011)
Keywords: Biomedical Research; Child, Preschool; Humans; Infant; Infant, Newborn; Pneumonia

Shwachman-Diamond syndrome and type 1 diabetes mellitus: more than a chance association? - Gana, S; Sainati, L; Frau, M R; Monciotti, C; Poli, F; Cannioto, Z; Comelli, M; Danesino, C; Minelli, A (Exp Clin Endocrinol Diabetes, 2011)
Shwachman-Diamond syndrome is a rare clinical condition consisting of exocrine pancreatic dysfunction, various degree of pancytopenia, and metaphyseal dysplasia. The majority of Shwachman-Diamond syndrome cases result from mutations in the Shwachman-Bodian-Diamond Syndrome gene. To date, type 1 diabetes mellitus has only been reported in 4 independent cases presenting with Shwachman-Diamond syndrome, 3 of them with molecular confirmation of the diagnosis. We describe 2 unrelated patients with clinical and molecular features typical of Shwachman-Diamond syndrome and type 1 diabetes mellitus. In addition, we report the occurrence rate of type 1 diabetes mellitus in the Italian registry for Shwachman-Diamond syndrome, which is low (3.23%) but increased at least 30-fold over the type 1 diabetes mellitus occurrence rate in the general population. No evidence of a direct correlation between Shwachman-Diamond syndrome and type 1 diabetes mellitus have been reported, therefore the presence of both diseases in the same patient might be a chance association, however we suggest that the defects in immune regulation of Shwachman-Diamond syndrome might play a role in the development of type 1 diabetes mellitus.
Keywords: Bone Marrow Diseases; CD4-CD8 Ratio; Diabetes Mellitus, Type 1; Exocrine Pancreatic Insufficiency; Female; Heterozygote; Humans; Immune System; Infant; Italy; Lipomatosis; Male; Mutation; Prevalence; Proteins; Registries

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Splicing mutations in glycogen-storage disease type II: evaluation of the full spectrum of mutations and their relation to patients' phenotypes. - Zampieri, Stefania; Buratti, Emanuele; Dominissini, Silvia; Montalvo, Anna Lisa; Pittis, Maria Gabriela; Bembi, Bruno; Dardis, Andrea (Eur J Hum Genet, 2011)
Glycogen-storage disease type II is an autosomal recessive-inherited disorder due to the deficiency of acid α-glucosidase. A large number of mutations in the acid α-glucosidase gene have been described to date. Among them, ~15% are variations that may affect mRNA splicing process. In this study, we have for the first time comprehensively reviewed the available information on splicing mutations of the acid α-glucosidase gene and we have evaluated their possible impact on the splicing process using different in silico approaches. Out of the 39 different GAA-sequence variations described, an in silico analysis using seven different programs showed that 97% of them are predicted to have an impact on the splicing process. Moreover, this analysis showed a quite good correlation between the impact of the mutation on the splicing process and the clinical phenotype. In addition, we have performed the functional characterization of three novel sequence variants found in Italian patients and still uncharacterized. Using a minigene system, we have confirmed their pathogenic nature. In conclusion, this study has shown that in silico analysis represents a useful tool to select mutations that affect the splicing process of the acid α-glucosidase gene and provides an updated picture of all this kind of mutations reported till now.
Keywords: alpha-Glucosidases; Cell Line; Computational Biology; DNA Mutational Analysis; Exons; Glycogen Storage Disease Type II; Humans; Introns; Mutagenesis, Site-Directed; Mutation; Phenotype; RNA Splicing

Therapeutic approaches in the treatment of juvenile dermatomyositis in patients with recent-onset disease and in those experiencing disease flare: an international multicenter PRINTO study. - Hasija, Rachana; Pistorio, Angela; Ravelli, Angelo; Demirkaya, Erkan; Khubchandani, Raju; Guseinova, Dinara; Malattia, Clara; Canhao, Helena; Harel, Liora; Foell, Dirk; Wouters, Carine; De Cunto, Carmen; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To evaluate response to therapy over a 24-month period in a large prospective international cohort of patients with juvenile dermatomyositis (DM). METHODS: The study included 145 patients with recent-onset juvenile DM and 130 juvenile DM patients experiencing disease flare, all of whom were <18 years old. Disease activity parameters and therapeutic approaches in 4 geographic areas were analyzed at baseline and at 6, 12, and 24 months. Response was assessed according to the Pediatric Rheumatology International Trials Organization (PRINTO) juvenile DM response criteria, and data were reported "as observed" and in the intent-to-treat (ITT) population. RESULTS: Patients with recent-onset juvenile DM at baseline had higher baseline disease activity and greater improvement over 24 months when compared to juvenile DM patients experiencing disease flare at baseline. Methotrexate (MTX) or high-dose corticosteroids were administered more frequently to patients with recent-onset juvenile DM, compared to juvenile DM patients experiencing disease flare, who were more likely to receive cyclosporine. Compared to patients from Western and Eastern Europe, a higher proportion of patients from South and Central America and North America received pulse steroids, and the average steroid dosage was higher in the North American and South and Central American patients. The use of MTX was similar in all 4 regions, while cyclosporin A was more frequently used in Western Europe. In the "as observed" analysis, 57.9% of the patients with recent-onset juvenile DM and 36.4% of the patients experiencing disease flare (P<0.001) reached at least a 70% response by PRINTO criteria at 6 months; these proportions had increased at month 24 to 78.4% and 51.2%, respectively (P<0.001). Corresponding results of the ITT analysis were much lower, with only one-third of the patients able to maintain the initial assigned therapy over 24 months. CONCLUSION: Patients with recent-onset juvenile DM are more likely to achieve significant clinical improvement over 24 months, when compared to patients experiencing flares of juvenile DM. Internationally, various therapeutic approaches are used to treat this disease.
Keywords: Adolescent; Adrenal Cortex Hormones; Child; Dermatologic Agents; Dermatomyositis; Female; Humans; Longitudinal Studies; Male; Methotrexate; Prospective Studies; Treatment Outcome

Trail down-regulates the release of osteoprotegerin (OPG) by primary stromal cells. - Corallini, Federica; Celeghini, Claudio; Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Secchiero, Paola; Zauli, Giorgio (J Cell Physiol, 2011)
The soluble member of the TNF-R superfamily osteoprotegerin (OPG) is abundantly released under basal conditions by both mesenchymal stem cells (MSC) and fibroblasts and by endothelial cells upon stimulation with inflammatory cytokines. Since MSC, fibroblasts and endothelial cells represent key elements of the normal and tumor microenvironment and express detectable levels of surface TRAIL receptors, we investigated the effect of TRAIL on OPG release. Unexpectedly, recombinant TRAIL decreased the spontaneous OPG release in all cell types examined. Moreover, TRAIL decreased OPG release also in stromal cells co-cultured with lymphoma cells and counteracted the OPG induction by TN-alpha in HUVEC and MSC. Such down-regulation was not due to a masking effect in the ELISA quantification of the OPG released in the culture supernatants due to binding of OPG to its ligands (TRAIL and RANKL), as demonstrated by competition experiments with recombinant TRAIL and by the lack of RANKL release/induction. In addition, OPG down-regulation was not due to induction of cytotoxic effects by TRAIL, since the degree of apoptosis in response to TRAIL was negligible in all primary cell types. With regards to the possible molecular mechanism accounting for the down-regulation of OPG release by TRAIL, we found that treatment of MSC with TRAIL significantly decreased the phosphorylation levels of p38/MAPK. There is a suggestion that this pathway is involved in the stabilization of OPG mRNA. In this respect, the ability of TRAIL to decrease the release of OPG, in the absence of cell cytotoxicity, was mimicked by the p38/MAPK inhibitor SB203580.
Keywords: Bone Marrow Cells; Cell Death; Cells, Cultured; Coculture Techniques; Down-Regulation; Endothelial Cells; Enzyme Activation; Enzyme-Linked Immunosorbent Assay; Fibroblasts; Humans; MAP Kinase Signaling System; Mesenchymal Stromal Cells; Osteoprotegerin; p38 Mitogen-Activated Protein Kinases; Protein Binding; Recombinant Proteins; Stromal Cells; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor-alpha

TRAIL promotes a pro-survival signal in erythropoietin-deprived human erythroblasts through the activation of an NF-kB/IkBalpha pathway. - Sancilio, S; Di Giacomo, V; Quaglietta, A M; Iacone, A; Angelucci, D; Tatasciore, U; Rana, R A; Cataldi, A; Zauli, G; Di Pietro, R (J Biol Regul Homeost Agents, 2011)
The biological activity of TNF-related apoptosis inducing ligand (TRAIL) was analyzed in primary human erythroblasts derived from mononuclear cells of blood donors, kept in culture in the presence of 20 percent foetal calf serum, growth factors (EPO, SCF, IL-3) and glucocorticoids (10-6 M dexamethasone, 10-6 M oestradiol) or under growth factor and serum starvation. In the presence of growth factors and serum, primary erythroblasts showed a differential expression of TRAIL-Receptors (Rs) at various degrees of maturation and responded to TRAIL treatment with a mild cytotoxicity. On the other hand, in the absence of serum and growth factors, TRAIL treatment unexpectedly up-regulated TRAIL-R4 decoy receptor and promoted erythroblast survival. The concomitant activation of NF-kB/IkB survival pathway was detected with Western blotting and immunofluorescence procedures and confirmed by experiments performed with SN50, a pharmacological inhibitor of the NF-kB/IkB pathway. Our study indicates that TRAIL has a twofold activity on erythroid lineages: it induces a mild erythroid cell cytotoxicity in the presence of serum and growth factors, while it promotes erythroid cell survival through the activation of the NF-kB/IkB pathway under starvation conditions.
Keywords: Cell Survival; Erythroblasts; Erythropoietin; Gene Expression Regulation; Humans; I-kappa B Kinase; Jurkat Cells; NF-kappa B; Peptides; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor Decoy Receptors

Two lumens, one diagnosis. - Pastore, Serena; Gortani, Giulia; Maschio, Massimo; Di Leo, Grazia; Ventura, Alessandro (J Pediatr, 2011)
Keywords: Capsule Endoscopy; Child, Preschool; Gastrointestinal Hemorrhage; Humans; Male; Meckel Diverticulum; Recurrence

An unusual case of buccal obstruction: the antrochoanal polyp. - De Cunto, Angela; Minen, Federico (Arch Dis Child, 2011)
Keywords: Adolescent; Cheek; Female; Humans; Mouth Diseases; Nasal Obstruction; Nasal Polyps; Oropharynx

Use of zidovudine-sparing HAART in pregnant HIV-infected women in Europe: 2000-2009. - Tariq, Shema; Townsend, Claire L; Cortina-Borja, Mario; Duong, Trinh; Elford, Jonathan; Thorne, Claire; Tookey, Pat A (J Acquir Immune Defic Syndr, 2011)
BACKGROUND: Increasing numbers of women in resource-rich settings are prescribed zidovudine (ZDV)-sparing highly active antiretroviral therapy (HAART) in pregnancy. We compare ZDV-sparing with ZDV-containing HAART in relation to maternal viral load at delivery, mother-to-child transmission (MTCT) of HIV, and congenital abnormality. METHODS: This is an analysis of data from the National Study of HIV in Pregnancy and Childhood and the European Collaborative Study. Data on 7573 singleton births to diagnosed HIV-infected women between January 2000 and June 2009 were analyzed. Logistic regression models were fitted to estimate adjusted odds ratios (AORs). RESULTS: Overall, 15.8% (1199 of 7573) of women received ZDV-sparing HAART, with increasing use between 2000 and 2009 (P < 0.001). Nearly a fifth (18.4%) of women receiving ZDV-sparing HAART in pregnancy had a detectable viral load at delivery compared with 28.6% of women on ZDV-containing HAART [AOR 0.90; 95% confidence interval (CI): 0.72 to 1.14, P = 0.4]. MTCT rates were 0.8% and 0.9% in the ZDV-sparing and ZDV-containing groups, respectively (AOR 1.81; 95% CI: 0.77 to 4.26, P = 0.2). The congenital abnormality rate was the same in both groups (2.7%, AOR 0.98; 95% CI: 0.66 to 1.45, P = 0.9), with no significant difference between the groups in a subanalysis of pregnancies with first trimester HAART exposure (AOR 0.79; 95% CI: 0.48 to 1.30, P = 0.4). CONCLUSIONS: We found no difference in risk of detectable viral load at delivery, MTCT, or congenital abnormality when comparing ZDV-sparing with ZDV-containing HAART. With increasing use of ZDV-sparing HAART, continued monitoring of pregnancy outcomes and long-term consequences of in utero exposure to these drugs is required.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Europe; Female; HIV Infections; Humans; Infant; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Retrospective Studies; Time Factors; Viral Load; Zidovudine

X-ray fluorescence elemental mapping and microscopy to follow hepatic disposition of a Gd-based magnetic resonance imaging contrast agent. - Delfino, Riccarda; Altissimo, Matteo; Menk, Ralf Hendrik; Alberti, Roberto; Klatka, Tomasz; Frizzi, Tommaso; Longoni, Antonio; Salomè, Murielle; Tromba, Giuliana; Arfelli, Fulvia; Clai, Milan; Vaccari, Lisa; et al. (Clin Exp Pharmacol Physiol, 2011)
1. Spatially resolved X-ray fluorescence (XRF) spectroscopy with synchrotron radiation is a technique that allows imaging and quantification of chemical elements in biological specimens with high sensitivity. In the present study, we applied XRF techniques at a macro and micro level to carry out drug distribution studies on ex vivo models to confirm the hepatobiliary disposition of the Gd-based magnetic resonance imaging contrast agent B22956/1. 2. Gd presence was selectively quantified allowing the determination of the time dependent disappearance of the drug from blood and its hepatic accumulation in mice after administration. Elemental mapping highlighted the drug distribution differences between healthy and diseased livers. XRF microanalyses showed that in CCl(4) -induced hepatitis, B22956/1 has greatly reduced hepatic accumulation, shown as a 20-fold reduction of Gd presence. Furthermore, a significant increase of Fe presence was found in steatotic compared with healthy livers, in line with the disease features. 3. The present results show that XRF might be useful in preclinical pharmacological studies with drugs containing exogenous elements. Furthermore, quantitative and high-sensitivity elemental mapping allows simultaneous detection of chemical variation, showing pathological conditions. This approach was useful in suggesting reduced B22956/1 accumulation in steatotic livers, thus opening possible new diagnostic perspectives for this drug.
Keywords: Animals; Contrast Media; Fatty Liver; Female; Gadolinium; Hepatitis; Iron; Liver; Magnetic Resonance Imaging; Mice; Mice, Inbred CBA; Organometallic Compounds; Spectrometry, X-Ray Emission

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts

Corticosteroids do not cause harmful increase of viral load in severe H1N1 virus infection. - Confalonieri, Marco; D'Agaro, Pierlanfranco; Campello, Cesare (Intensive Care Med, 2010)
Keywords: Adult; Antiviral Agents; Bronchoalveolar Lavage Fluid; Extracorporeal Membrane Oxygenation; Glucocorticoids; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Methylprednisolone; Oseltamivir; Respiration, Artificial; Severity of Illness Index; Viral Load; World Health Organization

Declining HCV seroprevalence in pregnant women with HIV. - Floridia, M; Tamburrini, E; Anzidei, G; Tibaldi, C; Muggiasca, M L; Guaraldi, G; Fiscon, M; Vimercati, A; Martinelli, P; Donisi, A; Dalzero, S; Ravizza, M (Epidemiol Infect, 2010)
We assessed recent trends in hepatitis C virus (HCV) prevalence in pregnant women with HIV using data from a large national study. Based on 1240 pregnancies, we observed a 3.4-fold decline in HCV seroprevalence in pregnant women with HIV between 2001 (29.3%) and 2008 (8.6%). This decline was the net result of two components: a progressively declining HCV seroprevalence in non-African women (from 35.7% in 2001 to 16.7% in 2008), sustained by a parallel reduction in history of injecting drug use (IDU) in this population, and a significantly growing presence (from 21.2% in 2001 to 48.6% in 2008) of women of African origin, at very low risk of being HCV-infected [average HCV prevalence 1%, adjusted odds ratio (aOR) for HCV 0.09, 95% CI 0.03-0.29]. Previous IDU was the stronger determinant of HCV co-infection in pregnant women with HIV (aOR 30.9, 95% CI 18.8-51.1). The observed trend is expected to translate into a reduced number of cases of vertical HCV transmission.
Keywords: Chi-Square Distribution; Female; Hepatitis C; HIV Infections; Humans; Italy; Logistic Models; Pregnancy; Risk Factors; Seroepidemiologic Studies

Decreased cholesterol levels reflect a consumption of anti-inflammatory isoprenoids associated with an impaired control of inflammation in a mouse model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; Decorti, Giuliana; Pontillo, Alessandra; Ventura, Alessandro; Tommasini, Alberto (Inflamm Res, 2010)
OBJECTIVE: The aim of this study was to evaluate, in a mouse model of mevalonate kinase deficiency (MKD), the possible link between inflammatory symptoms and serum cholesterol levels. MATERIALS AND METHODS: Balb/c mice were treated with alendronate and bacterial muramyl dipeptide. Body temperature, interleukin-1 beta (IL-1 beta) secretion and serum cholesterol levels were measured. RESULTS: An increased production of the pro-inflammatory cytokine IL-1 beta (p < 0.05) and a rise in body temperature (p < 0.05) was observed, while, in parallel, serum cholesterol concentration significantly decreased (p < 0.05). These effects were completely reversed when animals were treated with exogenous isoprenoids. CONCLUSIONS: In the mouse model of MKD, the inflammatory response is associated with a reduction in cholesterol levels, and hence this parameter could be used as an indicator of isoprenoid consumption. In addition, plant derived isoprenoids could represent candidate treatments for this disease.
Keywords: Animals; Anti-Inflammatory Agents; Cholesterol; Disease Models, Animal; Inflammation; Interleukin-1beta; Male; Mevalonate Kinase Deficiency; Mice; Mice, Inbred BALB C; Random Allocation; Terpenes

Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory

Design and development of a computer program for the evaluation of the healthcare executive - biomed 2010. - Zotti, Daniel; Bava, Michele; Delendi, Mauro (Biomed Sci Instrum, 2010)
According to the Italian law which regulates executive healthcare contracts, the professional evaluation is mandatory. The goal of the periodic evaluation is to enhance and motivate the professional involved. In addition this process should 1. increase the sense of duty towards the patients, 2. become aware of ones own professional growth and aspirations and 3. enhance the awareness of the healthcare executive regarding the companys strategies. To satisfy these requirements a data sheet has been modeled for every evaluated subject, divided in two sections. In the first part, the chief executive officer (CEO) scores: 1. behavioral characteristics, 2. multidisciplinary collaboration and involvement, 3. organizational skills, 4. professional quality and training, 5. relationships with the citizens. The scores for these fields are decided by the CEO. In the second part the CEO evaluates: 1. quantitative job dimension, 2.technology innovation, 3. scientific and educational activities. The value scores of these fields are decided by the CEO together with the professional under evaluation. A previously established correction coefficient can be used for all the scores. This evaluation system model has been constructed according to the enhancement quality approaches (Deming cycle) and a web-based software has been developed on a Linux platform using LAMP technology and php programming techniques. The program replicates all the evaluation process creating different profiles of authentications and authorizations which can then give to the evaluator the possibility to make lists of the professionals to evaluate, to upload documents regarding their activities and goals, to receive individual documents in automatically generated folders, to change the correction coefficients, to obtain year by year the individual scores. The advantages of using this web-based software include easy data consultation and update, the implementation of IT security issues, the easy portability and scalability of the system itself in different contexts even beyond healthcare.

Determinants of nosocomial infection in 6 neonatal intensive care units: an Italian multicenter prospective cohort study. - Auriti, Cinzia; Ronchetti, Maria Paola; Pezzotti, Patrizio; Marrocco, Gabriella; Quondamcarlo, Anna; Seganti, Giulio; Bagnoli, Francesco; De Felice, Claudio; Buonocore, Giuseppe; Arioni, Cesare; Serra, Giovanni; Bacolla, Gianfranco; et al. (Infect Control Hosp Epidemiol, 2010)
BACKGROUND: Nosocomial infections are still a major cause of morbidity and mortality among neonates admitted to neonatal intensive care units (NICUs). OBJECTIVE: To describe the epidemiology of nosocomial infections in NICUs and to assess the risk of nosocomial infection related to the therapeutic procedures performed and to the clinical characteristics of the neonates at birth and at admission to the NICU, taking into account the time between the exposure and the onset of infection. DESIGN: A multicenter, prospective cohort study. PATIENTS AND SETTING: A total of 1,692 neonates admitted to 6 NICUs in Italy were observed and monitored for the development of nosocomial infection during their hospital stay. METHODS: Data were collected on the clinical characteristics of the neonates admitted to the NICUs, their therapeutic interventions and treatments, their infections, and their mortality rate. The cumulative probability of having at least 1 infection and the cumulative probability of having at least 1 infection or dying were estimated. The hazard ratio (HR) for the first infection and the HR for the first infection or death were also estimated. RESULTS: A total of 255 episodes of nosocomial infection were diagnosed in 217 neonates, yielding an incidence density of 6.9 episodes per 1,000 patient-days. The risk factors related to nosocomial infection in very-low-birth-weight neonates were receipt of continuous positive airway pressure (HR, 3.8 [95% confidence interval CI, 1.7-8.1]), a Clinical Risk Index for Babies score of 4 or greater (HR, 2.2 [95% CI, 1.4-3.4]), and a gestational age of less than 28 weeks (HR, 2.1 [95% CI, 1.2-3.8]). Among heavier neonates, the risk factors for nosocomial infection were receipt of parenteral nutrition (HR, 8.1 [95% CI, 3.2-20.5]) and presence of malformations (HR, 2.3 [95% CI, 1.5-3.5]). CONCLUSIONS: Patterns of risk factors for nosocomial infection differ between very-low-birth-weight neonates and heavier neonates. Therapeutic procedures appear to be strong determinants of nosocomial infection in both groups of neonates, after controlling for clinical characteristics.
Keywords: Bacteremia; Birth Weight; Cross Infection; Gestational Age; Hospitals, University; Humans; Incidence; Infant, Newborn; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal; Italy; Length of Stay; Proportional Hazards Models; Prospective Studies; Risk Factors; Sepsis; Time Factors

Does infant gastro-oesophageal reflux really deserve medical attention? - Declich, V; Badina, L; Ventura, A (Arch Dis Child, 2010)
Keywords: Beds; Gastroesophageal Reflux; Humans; Infant; Infant Care; Posture; Prognosis

Epidemiological and molecular assessment of a rubella outbreak in North-Eastern Italy. - D'Agaro, Pierlanfranco; Dal Molin, Gianna; Zamparo, Emanuela; Rossi, Tatiana; Micuzzo, Michele; Busetti, Marina; Santon, Daniela; Campello, Cesare (J Med Virol, 2010)
From January to June 2008, a rubella outbreak involving 111 laboratory confirmed cases occurred in the Friuli Venezia Giulia (FVG) region of North-Eastern Italy. The outbreak occurred initially in two residential homes for young adults disabled mentally and physically. Subsequently, the epidemic spread to the general population. Young adult cohorts were mostly affected and the mean age of the patients was 26.8 years; the majority of cases were male (73.8%), with a mean age of 26.6 years in males and 27.4 in females. Three pregnant women had a primary infection and two had their pregnancies terminated. Genotyping of 16 isolates showed the circulation of RUBV 2B, a genotype originating from Asia and South Africa and now present in Europe. In addition, molecular analysis revealed a well defined space-temporal spread of two viruses showing distinct sequences. A seroepidemiological survey carried out in a city within the same geographical area showed that the proportion of women of childbearing age still susceptible to rubella virus was 5.5%, fairly close to the figure (<5%) expected by 2010.
Keywords: Adolescent; Adult; Antibodies, Viral; Disease Outbreaks; Epidemics; Female; Genotype; Humans; Immunoglobulin G; Italy; Male; Pregnancy; Pregnancy Complications, Infectious; Rubella; Rubella virus; Young Adult

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Fasting increases tobramycin oral absorption in mice. - De Leo, Luigina; Di Toro, Nicola; Decorti, Giuliana; Malusà, Noelia; Ventura, Alessandro; Not, Tarcisio (Antimicrob Agents Chemother, 2010)
The pharmacokinetics of the aminoglycoside tobramycin was evaluated after oral administration to fed or fasting (15 h) mice. As expected, under normal feeding conditions, oral absorption was negligible; however, fasting induced a dramatic increase in tobramycin bioavailability. The dual-sugar test with lactulose and l-rhamnose confirmed increased small bowel permeability via the paracellular route in fasting animals. When experiments aimed at increasing the oral bioavailability of hydrophilic compounds are performed, timing of fasting should be extremely accurate.
Keywords: Administration, Oral; Animals; Anti-Bacterial Agents; Biological Availability; Fasting; Injections, Intramuscular; Injections, Intravenous; Intestinal Absorption; Lactulose; Male; Mice; Mice, Inbred BALB C; Rhamnose; Tobramycin

First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment

A G to C transversion at the last nucleotide of exon 25 of the MYH9 gene results in a missense mutation rather than in a splicing defect. - Vettore, Silvia; De Rocco, Daniela; Gerber, Bernhard; Scandellari, Raffaella; Bianco, Anna Monica; Balduini, Carlo L; Pecci, Alessandro; Fabris, Fabrizio; Savoia, Anna (Eur J Med Genet, 2010)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephropathy leading to end-stage renal failure. In two families with macrothrombocytopenia we identified a novel c.3485G > C mutation in the last nucleotide of exon 25. Bioinformatic tools for splice site prediction and minigene functional test predicted splicing anomalies of exon 25. However, analysis of RNA purified from patient's peripheral blood did not allowed us to detect any anomalies, suggesting that RNA processing is correct at least in this tissue. Therefore, we concluded that c.3485G > C leads to a novel missense mutation (p.Arg1162Thr) of myosin-9, which resulted to be slightly degraded in patient platelets. A precise definition of the effect of mutations is fundamental to improve our knowledge into the pathogenetic mechanisms responsible for the disease.
Keywords: Adolescent; Adult; Blood Platelets; Computational Biology; Exons; Female; Humans; Inclusion Bodies; Kidney Failure, Chronic; Molecular Motor Proteins; Mutation, Missense; Myosin Heavy Chains; Neutrophils; Nonmuscle Myosin Type IIA; Nucleotides; RNA Splicing; Thrombocytopenia

High polymorphism of the MBL2 gene in patients with atopic dermatitis. - Carréra, Matilde Campos; Moura, Patrícia; Crovella, Sergio; de Souza, Paulo Roberto Eleutério; de Alencar, Luiz Cláudio Arraes; Sarinho, Emanuel (Ann Allergy Asthma Immunol, 2010)
BACKGROUND: Low serum levels of mannose-binding lectin (MBL) are determined mainly by variant alleles of the MBL2 gene and it has been suggested that MBL may play a role in the susceptibility to atopic dermatitis (AD). OBJECTIVE: The aim was to investigate the difference of the frequency of MBL2 variant alleles in AD patients and in a group of individuals without AD, and associate the MBL2 alleles with AD severity. METHODS: MBL2 variant allele's frequency was investigated in 131 children with AD and 165 healthy children/adolescents matched by convenience. The severity of disease was graded according to the SCORing Atopic Dermatitis (SCORAD) index. The first exon variants were called "O" and the wild type "A". The variants in the promoter were H/L at -550 and X/Y at -221, determined by Real Time PCR. RESULTS: Children with AD had higher frequency of allele O and the genotypes related to low or deficient levels of MBL, when compared to the healthy group (p = 0.0012 and p < 0.001, respectively), but not with AD severity. CONCLUSION: Low or deficient MBL serum levels determined genetically may contribute to the predisposition for AD, but not for disease severity.
Keywords: Adolescent; Alleles; Child; Child, Preschool; Dermatitis, Atopic; Disease Progression; Female; Genetic Predisposition to Disease; Genotype; Humans; Infant; Male; Mannose-Binding Lectin; Polymorphism, Genetic; Promoter Regions, Genetic

HLA-G*0105N allele is associated with augmented risk for HIV infection in white female patients. - Segat, Ludovica; Catamo, Eulalia; Fabris, Annalisa; Morgutti, Marcello; D'Agaro, Pierlanfranco; Campello, Cesare; Crovella, Sergio (AIDS, 2010)
We analyzed HLA-G 3777G > C, HLA-G 14 bp deletion/insertion and HLA-G*0105N polymorphisms in HIV-positive white adult participants, infected through horizontal heterosexual transmission, and unexposed uninfected individuals, all from north eastern Italy. We report a new association between the HLA-G*0105N allele and HIV infection in adult white female participants, being HLA-G*0105N null allele correlated with an augmented risk (odds ratio = 4.35, 95% confidence interval = 1.38-18.07, P = 0.005) for HIV infection.
Keywords: Adolescent; Adult; Aged; Female; Genetic Predisposition to Disease; Histocompatibility Antigens Class I; HIV Infections; HIV-1; Humans; Middle Aged; Polymorphism, Genetic; Young Adult

Hot water and preparation of infant formula: how hot does it have to be to be safe? - Davanzo, Riccardo; Giurici, Nagua; Demarini, Sergio (J Pediatr Gastroenterol Nutr, 2010)
Keywords: Guidelines as Topic; Hot Temperature; Humans; Infant; Infant Formula; Water; World Health Organization

[Human papillomavirus cervical infection: viral genotyping and risk factors for high-grade squamous intraepithelial lesion and cervix cancer]. - de Mendonça, Vilma Guimarães; Guimarães, Maria José Bezerra; de Lima Filho, José Luiz; de Mendonça, Carolina Guimarães; Martins, Danyelly Bruneska Gondim; Crovella, Sergio; de Alencar, Luiz Cláudio Arraes (Rev Bras Ginecol Obstet, 2010)
PURPOSE: to analyze the characteristics of viral infection and the risk factors for high-grade squamous intraepithelial lesion and cervical carcinoma in women with cervical HPV infection. METHODS: a case-control study was conducted on women with cervical HPV at a Gynecology reference service enrolled at the Public Health System, located in Recife, Northeastern Brazil. The groups of cases (72 women with high-grade squamous intraepithelial lesion or cervical cancer) and controls (176 women with normal Pap smear or benign alterations) were investigated for six viral genotypes (HPV 16, 18, 31, 33, 6, 11) in ecto- and endocervical material using MY09/MY11 primers. The independent variables were ranked in three levels of determination: distal (sociodemographic), intermediate (behavioral) and proximal (previous Pap smear). The homogeneity of proportions was tested (χ2), unadjusted Odds Ratios (OR) were obtained and hierarchical logistic regression was applied to the final model, with adjustment of the effect of each variable to the outcome based on the variables in the same and previous levels of causality. RESULTS: the viral genotype of cervical infection was identified in 76.6% of the 248 women participating in the study. High-risk HPV genotypes (83.4% of cases and 67.1% of controls) were predominant, especially HPV 16 and 31. The distal risk factors identified were: living in a rural area (OR=2.71, 95%CI: 1.18-6.23), less than three years of study (OR=3.97, 95%CI: 2.09-7.54) and family income below two minimum wages (OR=3.30, 95%CI: 1.04-10.51); intermediate: four or more pregnancies (OR=2.00, 95%CI: 1.06-3.76); and proximal: absence of a previous Pap smear (OR=9.74, 95%CI: 2.48-38.28). CONCLUSIONS: genotypes 16 and 31 of cervical HPV infection are predominant among women assisted by the Public Health System in Northeastern Brazil. Socioeconomic and reproductive factors, as well as the absence of cytological screening, represent risk factors for the progression of infection to high-grade squamous intraepithelial lesion and cervical cancer.
Keywords: Adult; Carcinoma in Situ; Case-Control Studies; Female; Genotype; Humans; Papillomaviridae; Papillomavirus Infections; Risk Factors; Socioeconomic Factors; Uterine Cervical Neoplasms

Individual differences in prefrontal cortex activity during perception of bitter taste using fNIRS methodology. - Bembich, Stefano; Lanzara, Carmela; Clarici, Andrea; Demarini, Sergio; Tepper, Beverly J; Gasparini, Paolo; Grasso, Domenico L (Chem Senses, 2010)
Although bitter taste has a crucial role in nutrition by preventing the ingestion of toxic foods, there are few studies on bitter taste neuroimaging. To identify cortical areas involved in bitter taste perception and to determine if individual differences in taste sensitivity to 6-n-propylthiouracil (PROP) are represented in the brain by different cortical activation patterns, we examined 48 healthy volunteers using functional near-infrared spectroscopy. Participants rated the perceived intensity of filter paper disks impregnated with PROP and NaCl during the imaging procedure and were then classified as PROP tasters and nontasters. We monitored cortical activity in both the anterior and posterior regions of the dorsolateral prefrontal cortex (DLPFC) and in the ventrolateral prefrontal cortex (VLPFC). No activity was detected in the anterior DLPFC in any of the participants. However, during the administration of PROP, significant cortical activation was detected in the more posterior regions of the left DLPFC and in the left and right VLPFC but only in PROP tasters. PROP nontasters showed no cortical activity in these areas. These data suggest that the prefrontal cortex is involved in the conscious perception of the bitter taste of PROP and that the pattern of activity is consistent with individual differences in the ability to taste this compound. Thus, the PROP phenotype is associated with fundamental differences in cortical taste processing.
Keywords: Adult; Eating; Female; Food Preferences; Humans; Individuality; Male; Perception; Phenotype; Prefrontal Cortex; Propylthiouracil; Sodium Chloride; Spectroscopy, Near-Infrared; Taste; Taste Threshold; Young Adult

Long-term observational, non-randomized study of enzyme replacement therapy in late-onset glycogenosis type II. - Bembi, Bruno; Pisa, Federica Edith; Confalonieri, Marco; Ciana, Giovanni; Fiumara, Agata; Parini, Rossella; Rigoldi, Miriam; Moglia, Arrigo; Costa, Alfredo; Carlucci, Annalisa; Danesino, Cesare; Pittis, Maria Gabriela; et al. (J Inherit Metab Dis, 2010)
OBJECTIVES: Type II glycogenosis (GSDII) is a lysosomal storage disorder due to acid alpha-glucosidase (GAA) deficiency. Enzyme replacement therapy (ERT) with human recombinant alpha-glucosidase (rhGAA) has been demonstrated to be effective in the treatment of infantile forms of GSDII, but little information is available concerning late-onset phenotypes. Long-term follow-up studies are not available at present. The aim of this study was to evaluate the ERT long-term effects in late-onset GSDII. METHODS: Twenty-four patients, including 7 juveniles and 17 adults, received bi-weekly infusion of rhGAA (20 mg/kg) for at least 36 months. Clinical conditions, muscular function (6-min walking test, 6MWT; Walton scale, WS), respiratory function (vital capacity, VC; forced expiratory volume, FEV1; arterial pCO(2)), and muscle enzymes were assessed every 6 months. RESULTS: The 6MWT improved in both juvenile and adult patients (p = 0.01, p = 0.0002, respectively), as well as in patients with moderate to severe muscle function impairment (WS >3.5; p = 0.002). An overall improvement in WS was also observed (p = 0.0003). VC and FEV1 remained unchanged, while pCO(2) decreased (p = 0.017). Muscle enzymes decreased significantly (p < 0.0001). Two patients (8%) showed transient secondary events during ERT. CONCLUSIONS: Long-term ERT with rhGAA was shown to be safe, well tolerated, and effective in improving motor function and in stabilizing respiratory function in late-onset GSDII. The response pattern showed a progressive clinical improvement during the follow-up period in juvenile patients, while in adults it reached and maintained a plateau after the first year of treatment.
Keywords: Adolescent; Adult; Age of Onset; Aged; alpha-Glucosidases; Child; Enzyme Replacement Therapy; Female; Follow-Up Studies; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Observation; Time Factors; Treatment Outcome; Young Adult

Mannose-binding lectin is produced by vaginal epithelial cells and its level in the vaginal fluid is influenced by progesterone. - Bulla, R; De Seta, F; Radillo, O; Agostinis, C; Durigutto, P; Pellis, V; De Santo, D; Crovella, S; Tedesco, F (Mol Immunol, 2010)
Mannose-binding lectin (MBL) is a recognition molecule of the complement (C) system and binds to carbohydrate ligands present on a wide range of pathogenic bacteria, viruses, fungi, and parasites. MBL has been detected in the cervico-vaginal cavity where it can provide a first-line defence against infectious agents colonizing the lower tract of the reproductive system. Analysis of the cervico-vaginal lavage (CVL) obtained from 11 normal cycling women at different phases of the menstrual cycle revealed increased levels of MBL in the secretive phase. Part of this MBL derives from the circulation as indicated by the presence of transferrin in CVL tested as a marker of vascular and tissue permeability. The local synthesis of MBL is suggested by the finding that its level is substantially higher than that of transferrin in the secretive phase. The contribution of endometrium is negligible since the MBL level did not change before and after hysterectomy. RT-PCR and in situ RT-PCR analysis showed that the vaginal tissue, and in particular the basal layer of the epithelium, is a source of MBL which binds to the basal membrane and to cells of the outer layers of the epithelium. In conclusion, we have shown that MBL detected in CVL derives both from plasma as result of transudation and from local synthesis and its level is progesterone dependent increasing in the secretive phase of the menstrual cycle.
Keywords: Adolescent; Adult; Body Fluids; Enzyme-Linked Immunosorbent Assay; Epithelial Cells; Female; Humans; Immunohistochemistry; Mannose-Binding Lectin; Menstrual Cycle; Progesterone; Reverse Transcriptase Polymerase Chain Reaction; Vagina; Young Adult

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Modeling the effect of 3 missense AGXT mutations on dimerization of the AGT enzyme in primary hyperoxaluria type 1. - Robbiano, Angela; Frecer, Vladimir; Miertus, Jan; Zadro, Cristina; Ulivi, Sheila; Bevilacqua, Elena; Mandrile, Giorgia; De Marchi, Mario; Miertus, Stanislav; Amoroso, Antonio (J Nephrol, 2010)
INTRODUCTION: Mutations of the AGXT gene encoding the alanine:glyoxylate aminotransferase liver enzyme (AGT) cause primary hyperoxaluria type 1 (PH1). Here we report a molecular modeling study of selected missense AGXT mutations: the common Gly170Arg and the recently described Gly47Arg and Ser81Leu variants, predicted to be pathogenic using standard criteria. METHODS: Taking advantage of the refined 3D structure of AGT, we computed the dimerization energy of the wild-type and mutated proteins. RESULTS: Molecular modeling predicted that Gly47Arg affects dimerization with a similar effect to that shown previously for Gly170Arg through classical biochemical approaches. In contrast, no effect on dimerization was predicted for Ser81Leu. Therefore, this probably demonstrates pathogenic properties via a different mechanism, similar to that described for the adjacent Gly82Glu mutation that affects pyridoxine binding. CONCLUSION: This study shows that the molecular modeling approach can contribute to evaluating the pathogenicity of some missense variants that affect dimerization. However, in silico studies--aimed to assess the relationship between structural change and biological effects--require the integrated use of more than 1 tool.
Keywords: Amino Acid Sequence; Female; Humans; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Protein Multimerization; Transaminases

Molecular surveillance of pandemic influenza A(H1N1) viruses circulating in Italy from May 2009 to February 2010: association between haemagglutinin mutations and clinical outcome. - Puzelli, S; Facchini, M; De Marco, M A; Palmieri, A; Spagnolo, D; Boros, S; Corcioli, F; Trotta, D; Bagnarelli, P; Azzi, A; Cassone, A; Rezza, G; et al. (Euro Surveill, 2010)
Haemagglutinin sequences of pandemic influenza A(H1N1) viruses circulating in Italy were examined, focusing on amino acid changes at position 222 because of its suggested pathogenic relevance. Among 169 patients, the D222G substitution was detected in three of 52 (5.8%) severe cases and in one of 117 (0.9%) mild cases, whereas the D222E mutation was more frequent and evenly distributed in mild (31.6%) and severe cases (38.4%). A cluster of D222E viruses among school children confirms reported human-to-human transmission of viruses mutated at amino acid position 222.
Keywords: Adolescent; Adult; Age Distribution; Aged; Amino Acid Substitution; Child; Child, Preschool; Female; Hemagglutinins; Humans; Infant; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Male; Middle Aged; Mutation; Pandemics; Population Surveillance; Reverse Transcriptase Polymerase Chain Reaction; Severity of Illness Index; Sex Distribution; Young Adult

Multiple segmental absence of intestinal musculature presenting as spontaneous isolated perforation in an extremely low-birth-weight infant. - Oretti, Chiara; Bussani, Rossana; Janes, Augusta; Demarini, Sergio (J Pediatr Surg, 2010)
Defect of the intestinal musculature is a rare condition. It may cause intestinal perforation or obstruction. It manifests itself mainly in the neonatal period and usually affects preterm infants. We describe one such case, which was first diagnosed as a spontaneous isolated intestinal perforation. Emergency laparotomy was performed and showed multiple perforations, with accompanying peritonitis and ascites. Pathologic examination showed partial or complete absence of the musculature, particularly of the inner circular layer, with fibrous tissue in the regions of missing muscle, and abnormal vasculature. The myenteric plexus was absent in areas of muscle loss but present in other sites. These findings suggest that the absence of muscle may not represent a congenital malformation but may be secondary to ischemic injury.
Keywords: Diseases in Twins; Female; Humans; Ileum; Infant, Extremely Low Birth Weight; Infant, Newborn; Infant, Premature; Intestinal Atresia; Intestinal Perforation; Laparotomy; Muscle, Smooth; Myenteric Plexus; Rare Diseases

MYH9-related disease: Report on five German families and description of a novel mutation. - Savoia, Anna; Germeshausen, Manuela; De Rocco, Daniela; Henschel, Bettina; Kratz, Christian P; Kuhlen, Michaela; Rath, Bettina; Steuhl, Klaus-Peter; Wermes, Cornelia; Ballmaier, Matthias (Ann Hematol, 2010)
Keywords: Adult; Aged; Child; Chromosome Disorders; DNA Mutational Analysis; Germany; Humans; Infant; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Young Adult

Neonatal jaundice and breastfeeding reputation. - Bramuzzo, Matteo; Davanzo, Riccardo (J Hum Lact, 2010)
Keywords: Bottle Feeding; Breast Feeding; Female; Humans; Infant, Newborn; Jaundice, Neonatal; Lactation Disorders; Milk, Human; Risk Factors

Oxidative stress-based cytotoxicity of delphinidin and cyanidin in colon cancer cells. - Cvorovic, Jovana; Tramer, Federica; Granzotto, Marilena; Candussio, Luigi; Decorti, Giuliana; Passamonti, Sabina (Arch Biochem Biophys, 2010)
Colorectal cancer is the second most frequent cause of cancer death in the western world. Although the prognosis has improved after the introduction of newer anticancer drugs, the treatment of metastatic colorectal cancer still remains a challenge due to a high percentage of drug-resistant tumor forms. We aimed at testing whether anthocyanidins exerted cytotoxicity in primary (Caco-2) and metastatic (LoVo and LoVo/ADR) colorectal cancer cell lines. Both cyanidin and delphinidin, though neither pelargonidin nor malvidin, were cytotoxic in metastatic cells only. The cell line most sensitive to anthocyanidins was the drug-resistant LoVo/ADR. There, cellular ROS accumulation, inhibition of glutathione reductase, and depletion of glutathione could be observed. This suggests that anthocyanidins may be used as sensitizing agents in metastatic colorectal cancer therapy.
Keywords: Anthocyanins; Antioxidants; Apoptosis; Caco-2 Cells; Camptothecin; Cell Line, Tumor; Colonic Neoplasms; Drug Resistance, Neoplasm; Glutathione; Glutathione Reductase; Humans; Oxidants; Oxidative Stress

Predictors of poor response to methotrexate in polyarticular-course juvenile idiopathic arthritis: analysis of the PRINTO methotrexate trial. - Vilca, Iris; Munitis, Pablo Garcia; Pistorio, Angela; Ravelli, Angelo; Buoncompagni, Antonella; Bica, Blanca; Campos, Lucia; Häfner, Renate; Hofer, Michael; Ozen, Seza; Huemer, Christian; Bae, Sang Cheol; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To determine whether baseline demographic, clinical, articular and laboratory variables predict methotrexate (MTX) poor response in polyarticular-course juvenile idiopathic arthritis. METHODS: Patients newly treated for 6 months with MTX enrolled in the Paediatric Rheumatology International Trials Organization (PRINTO) MTX trial. Bivariate and logistic regression analyses were used to identify baseline predictors of poor response according to the American College of Rheumatology pediatric (ACR-ped) 30 and 70 criteria. RESULTS: In all, 405/563 (71.9%) of patients were women; median age at onset and disease duration were 4.3 and 1.4 years, respectively, with anti-nuclear antibody (ANA) detected in 259/537 (48.2%) patients. With multivariate logistic regression analysis, the most important determinants of ACR-ped 70 non-responders were: disease duration > 1.3 years (OR 1.93), ANA negativity (OR 1.77), Childhood Health Assessment Questionnaire (CHAQ) disability index > 1.125 (OR 1.65) and the presence of right and left wrist activity (OR 1.55). Predictors of ACR-ped 30 non-responders were: ANA negativity (OR 1.92), CHAQ disability index > 1.14 (OR 2.18) and a parent's evaluation of child's overall well-being < or = 4.69 (OR 2.2). CONCLUSION: The subgroup of patients with longer disease duration, ANA negativity, higher disability and presence of wrist activity were significantly associated with a poorer response to a 6-month MTX course.
Keywords: Adolescent; Antibodies, Antinuclear; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Disability Evaluation; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Male; Methotrexate; Prognosis; Treatment Outcome

Prepregnancy BMI influences maternal and fetal outcomes in women with isolated gestational hyperglycaemia: a multicentre study. - Lapolla, A; Bonomo, M; Dalfrà, M G; Parretti, E; Mannino, D; Mello, G; Di Cianni, G (Diabetes Metab, 2010)
AIM: This multicentre study analyzed the maternal and fetal outcomes of women who had one elevated 3-h oral glucose tolerance test (isolated gestational hyperglycaemia [IGH]). METHODS: From 1999 to 2003, data were collected for 606 IGH women from 31 Italian obstetric or diabetic centres, including time and mode of delivery, gestational hypertension, preeclampsia, eclampsia, congenital malformations, and neonatal mortality and morbidity, to compare them with the general pregnant Italian population. A prognostic model for the outcome of pregnancy was constructed, and the concurrence of certain specified conditions was considered a positive outcome, whereas pregnancies that failed to meet one or more of the stated conditions were classified as "complicated". RESULTS: Macrosomia was significantly more frequent in women with IGH than in the normal pregnant population (10.7 vs 7.4%, respectively; P=0.003). Stillbirth and neonatal mortality rates did not differ from those in normal pregnancies, while a slight rise in the frequency of major malformations was not statistically significant (1.48 vs 0.89%, respectively; P<0.11). Multivariate logistic analyses confirmed that the prepregnancy body mass index (BMI) was an independent predictor of a complicated pregnancy. As for fetal growth, multivariate logistic analyses according to BMI showed that being overweight or obese were strong predictors of macrosomia. CONCLUSION: These findings in a large cohort of Italian women with IGH confirm the detrimental effect of even minimally altered glucose tolerance on fetal outcome. Also, prepregnancy obesity plays an important role in raising the risk of adverse perinatal outcomes in such patients.
Keywords: Adult; Blood Glucose; Body Mass Index; Female; Fetal Macrosomia; Glucose Tolerance Test; Humans; Hyperglycemia; Italy; Models, Statistical; Obesity; Pregnancy; Pregnancy Complications; Pregnancy Outcome; Prognosis; Retrospective Studies; Risk Factors; Time Factors

Screening for GJB2 and GJB6 gene mutations in patients from Campania region with sensorineural hearing loss. - Chinetti, Viviana; Iossa, Sandra; Auletta, Gennaro; Laria, Carla; De Luca, Maria; Di Leva, Francesca; Riccardi, Pasquale; Giannini, Pasquale; Gasparini, Paolo; Ciccodicola, Alfredo; Marciano, Elio; Franzè, Annamaria (Int J Audiol, 2010)
The aim of this study was to screen 349 patients affected by sensorineural hearing loss (SNHL), mostly from the Campania region (southern Italy), for GJB2 gene mutations and for two deletions of the GJB6 gene (del GJB6 -D13S1830 and del GJB6 -D13S1854). We identified pathogenetic GJB2 mutations in 51 cases (15% of patients). No GJB6 mutation was found. We also examined the audiologic features of the patients for whom we had an etiologic diagnosis, in order to identify correlations between the severity of hearing loss and the type of mutation.
Keywords: Acoustic Stimulation; Adolescent; Adult; Audiometry; Auditory Perception; Child; Child, Preschool; Connexins; Genetic Predisposition to Disease; Genetic Testing; Hearing Loss, Sensorineural; Heterozygote; Homozygote; Humans; Italy; Mass Screening; Middle Aged; Mutation; Phenotype; Risk Factors; Severity of Illness Index; Young Adult

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Breastfeed Rev, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low-income settings, the original KMC modelis implemented. This consists of continuous (24 h/day; 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding and, adequate follow up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC modelin all types of settings was discussed at the 7th International Workshop on KMC Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents'role, modification of the NICU environment, performance of care in KMC, and KMCin case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Acta Paediatr, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low income settings, the original KMC model is implemented. This consists of continuous (24 h/day, 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding; and, adequate follow-up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC model in all types of settings was discussed at the 7th International Workshop on KMC. Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents' role, modification of the NICU environment, performance of care in KMC, and KMC in case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.
Keywords: Attitude of Health Personnel; Female; Humans; Infant Care; Infant, Newborn; Intensive Care Units, Neonatal; Male; Parent-Child Relations; Practice Guidelines as Topic; Professional-Patient Relations; Role; Skin; Visitors to Patients

Storage of human milk: accepting certain uncertainties. - Davanzo, Riccardo; Travan, Laura; Demarini, Sergio (J Hum Lact, 2010)
Keywords: Food Handling; Humans; Milk, Human; Refrigeration

Targeting farnesyl-transferase as a novel therapeutic strategy for mevalonate kinase deficiency: in vitro and in vivo approaches. - De Leo, Luigina; Marcuzzi, Annalisa; Decorti, Giuliana; Tommasini, Alberto; Crovella, Sergio; Pontillo, Alessandra (Pharmacol Res, 2010)
Mevalonate kinase deficiency (MKD) is a rare inborn auto-inflammatory disease due to the impairment of the pathway for the biosynthesis of cholesterol and non-sterol isoprenoids. The shortage of isoprenoids compounds and in particular of geranylgeranylpyrophosphate (GGPP) was recently associated to the MKD characteristic inflammatory attacks. The aim of this study is to demonstrate that the normalization of the mevalonate pathway intermediates levels and in particular of GGPP, through the specific inhibition of farnesyl-transferase (FT) with Manumycin A could ameliorate the inflammatory phenotype of MKD patients. The effect of Manumycin A was first evaluated in MKD mouse and cellular models, chemically obtained using the aminobisphosphonate alendronate (ALD), and then in monocytes isolated from 2 MKD patients. Our findings were compared to those obtained by using natural exogenous isoprenoids (NEIs). Manumycin A was able to significantly reduce the inflammatory marker serum amyloid A in ALD-treated Balb/c mice, as well as IL-1 beta secretion in ALD-monocytes and in MKD patients. These results clearly showed that, through the inhibition of FT, an increased number of mevalonate pathway intermediates could be redirected towards the synthesis of GGPP diminishing the inflammatory response. The importance in limiting the shortage of GGPP was emphasized by the anti-inflammatory effect of NEIs that, due to their biochemical structure, can enter the MKD pathway. In conclusion, manumycin A, as well as NEIs, showed anti-inflammatory effect in MKD models and especially in MKD-monocytes, suggesting novel approaches in the treatment of MKD, an orphan disease without any efficacious treatment currently available.
Keywords: Adult; Animals; Anti-Inflammatory Agents; Cells, Cultured; Child, Preschool; Enzyme Inhibitors; Farnesyltranstransferase; Female; Humans; Male; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mice, Inbred BALB C; Monocytes; Polyenes; Polyisoprenyl Phosphates; Polyunsaturated Alkamides; Young Adult

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Ticks and Lyme borreliosis in an alpine area in northeast Italy. - Nazzi, F; Martinelli, E; Del Fabbro, S; Bernardinelli, I; Milani, N; Iob, A; Pischiutti, P; Campello, C; D'Agaro, P (Med Vet Entomol, 2010)
A 2-year study was conducted in a mountainous area of northeast Italy to evaluate the occurrence and distribution of ticks, as well as to assess the prevalence of the spirochaete Borrelia burgdorferi sensu lato. All ticks collected were Ixodes ricinus L. (Parasitiformes: Ixodidae). In general, most nymphs and adult ticks were collected from April to July. Tick density was highly variable among sites; however, two areas with different infestation levels were recognized. Prevalences of B. burgdorferi s.l. in nymphal stages were rather variable between sites; overall the prevalence of infected nymphs in the whole area was slightly higher than 20%. The prevalence of B. burgdorferi s.l. in nymphs does not seem to be correlated with nymph density. The correlation between the incidence of Lyme borreliosis (reported human cases/1000 inhabitants/year) and Borrelia prevalence in nymphs was not significant, although a significant correlation was found between borreliosis incidence and nymph density.
Keywords: Animals; Borrelia burgdorferi; Climate; Ecology; Humans; Incidence; Italy; Ixodes; Lyme Disease; Nymph; Population Density; Prevalence; Seasons; Ticks

Towards universal Kangaroo Mother Care: recommendations and report from the First European conference and Seventh International Workshop on Kangaroo Mother Care. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ibe, O; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Ruiz Peláez, J G; et al. (Acta Paediatr, 2010)
UNLABELLED: The hallmark of Kangaroo Mother Care (KMC) is the kangaroo position: the infant is cared for skin-to-skin vertically between the mother's breasts and below her clothes, 24 h/day, with father/substitute(s) participating as KMC providers. Intermittent KMC (for short periods once or a few times per day, for a variable number of days) is commonly employed in high-tech neonatal intensive care units. These two modalities should be regarded as a progressive adaptation of the mother-infant dyad, ideally towards continuous KMC, starting gradually and progressively with intermittent KMC. The other components in KMC are exclusive breastfeeding (ideally) and early discharge in kangaroo position with strict follow-up. Current evidence allows the following general statements about KMC in affluent and low-income settings: KMC enhances bonding and attachment; reduces maternal postpartum depression symptoms; enhances infant physiologic stability and reduces pain, increases parental sensitivity to infant cues; contributes to the establishment and longer duration of breastfeeding and has positive effects on infant development and infant/parent interaction. Therefore, intrapartum and postnatal care in all types of settings should adhere to a paradigm of nonseparation of infants and their mothers/families. Preterm/low-birth-weight infants should be regarded as extero-gestational foetuses needing skin-to-skin contact to promote maturation. CONCLUSION: Kangaroo Mother Care should begin as soon as possible after birth, be applied as continuous skin-to-skin contact to the extent that this is possible and appropriate and continue for as long as appropriate.
Keywords: Congresses as Topic; Female; Global Health; Humans; Infant Care; Infant, Newborn; Male; Parent-Child Relations; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Skin

Transmission of hemagglutinin D222G mutant strain of pandemic (H1N1) 2009 virus. - Puzelli, Simona; Facchini, Marzia; Spagnolo, Domenico; De Marco, Maria A; Calzoletti, Laura; Zanetti, Alessandro; Fumagalli, Roberto; Tanzi, Maria L; Cassone, Antonio; Rezza, Giovanni; Donatelli, Isabella (Emerg Infect Dis, 2010)
A pandemic (H1N1) 2009 virus strain carrying the D222G mutation was identified in a severely ill man and was transmitted to a household contact. Only mild illness developed in the contact, despite his obesity and diabetes. The isolated virus reacted fully with an antiserum against the pandemic vaccine strain.
Keywords: Adult; Amino Acid Substitution; Disease Outbreaks; Hemagglutinin Glycoproteins, Influenza Virus; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Middle Aged; Mutation, Missense; Phylogeny; Retrospective Studies; RNA, Viral; Sequence Analysis, RNA; Severity of Illness Index

Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand

Two cases of Noonan syndrome with severe respiratory and gastroenteral involvement and the SOS1 mutation F623I. - Fabretto, Antonella; Kutsche, Kerstin; Harmsen, May-Britt; Demarini, Sergio; Gasparini, Paolo; Fertz, Maria Cristina; Zenker, Martin (Eur J Med Genet, 2010)
Noonan syndrome (NS) is an autosomal dominant, inherited disorder characterized by facial dysmorphism, congenital heart defects, and reduced postnatal growth. Dysregulated RAS-MAPK signalling is the common molecular basis for NS, a genetically heterogeneous disease. Germline mutations in genes encoding small GTPases of the RAS family (KRAS and NRAS), modulators of RAS function (PTPN11, SOS1 and SHOC2) or downstream signal transducers (RAF1) are causative for NS. SOS1 is the second major gene for NS after PTPN11. Compared to patients with mutations in other genes, SOS1 mutation-positive individuals in general tend to have a more favorable outcome, with less short stature and cognitive impairment. We describe two unrelated patients with NS carrying the same heterozygous SOS1 missense mutation (c.1867T > A/p.F623I). The phenotype of both patients is remarkable as they show uncommon clinical features such as pulmonary lymphangiectasis, congenital pleural effusions, severe feeding problems, and laryngomalacia. These findings may be related to the specific mutation present in our two patients, or be part of the SOS1 phenotype. Detailed clinical assessment of large cohorts of patients with NS and SOS1 mutation is required to clarify this initial observation.
Keywords: Child, Preschool; Genes, ras; Germ-Line Mutation; Heterozygote; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Noonan Syndrome; Phenotype; SOS1 Protein

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal

Effect of chloroquine on cultured fibroblasts: release of lysosomal hydrolases and inhibition of their uptake. - Wiesmann, U N; DiDonato, S; Herschkowitz, N N (Biochem Biophys Res Commun, 1975)
Keywords: Biological Transport; Cells, Cultured; Cerebroside-Sulfatase; Chloroquine; Dextrans; Fibroblasts; Glucuronidase; Humans; Leukodystrophy, Metachromatic; Lysosomes; Pinocytosis; Skin; Sulfatases